3D mapping of the neutral X-ray absorption in the local interstellar medium: the Gaia and XMM-Newton synergy - Gatuzz, Efrain; Rezaei, S. Kh; Kallman, Timothy R.; Kreikenbohm, Annika; Oertel, Mirjam; Wilms, Jörn; Garcia, Javier (Monthly Notices of the Royal Astronomical Society, 2018)
We present a three-dimensional map of the hydrogen density distribution in the Galactic interstellar medium. The hydrogen-equivalent column densities were obtained from the Exploring the X-ray Transient and variable Sky project (EXTRAS) which provides equivalent NH values from X-ray spectral fits of observations within the XMM-Newton Data Release. EXTRAS include multiple fits for each source, allowing an accurate determination of the equivalent column densities, which depends on the continuum modelling of the spectra. A cross-correlation between the EXTRAS catalogue and the first Gaia Data Release was performed in order to obtain accurate parallax and distance measurements. We use a Bayesian method explained in Rezaei Kh. et al. (2017) in order to predict the most probable distribution of the density at any arbitrary point, even for lines of sight along which there are no initial observation. The resulting map shows small-scale density structures which could not have been modelled by using analytic density profiles. In this paper, we present a proof of concept of the kind of science possible with the synergy of these catalogues. However, given the systematic uncertainties connected to the source identification and to the dependence of NH on the spectral model, the present maps should be considered qualitatively at this point.
Keywords: ISM: atoms; ISM: structure; Galaxy: structure; X-rays: ISM

4U 1909+07: a well-hidden pearl - Fürst, Felix; Kreykenbohm, Ingo; Suchy, S.; Barragan, L.; Wilms, Jörn; Rothschild, R. E.; Pottschmidt, K. (Astronomy & Astrophysics, 2011)
We present the first detailed spectral and timing analysis of the high mass X-ray binary (HMXB) 4U1909+07 with INTEGRAL and RXTE. 4U1909+07 is detected in the ISGRI 20-40 keV energy band with an average countrate of 2.6 cts s(-1). The pulse period of similar to 604 s is not stable, but changing erratically on timescales of years. The pulse profile is strongly energy dependent: it shows a double peaked structure at low energies, the secondary pulse decreases rapidly with increasing energy and above 20 keV only the primary pulse is visible. This evolution is consistent between PCA, HEXTE, and ISGRI. The phase averaged spectrum can be well described by the sum of a photoabsorbed power law with a cutoff at high energies and a blackbody component. To investigate the pulse profile, we performed phase resolved spectral analysis. We find that the changing spectrum can be best described with a variation of the folding energy. We rule out a correlation between the black body component and the continuum variation and discuss possible accretion geometries.
Keywords: accretion; accretion disks; X-rays: binaries; stars: neutron

5.9-keV Mn K-shell X-ray luminosity from the decay of Fe-55 in Type Ia supernova models - Seitenzahl, I. R.; Summa, A.; Krauss, F.; Sim, S. A.; Diehl, R.; Elsaesser, D.; Fink, M.; Hillebrandt, W.; Kromer, M.; Maeda, K.; Mannheim, K.; Pakmor, R.; et al. (Monthly Notices of the Royal Astronomical Society, 2015)
We show that the X-ray line flux of the Mn Ka line at 5.9 keV from the decay of Fe-55 is a promising diagnostic to distinguish between Type Ia supernova (SN Ia) explosion models. Using radiation transport calculations, we compute the line flux for two three-dimensional explosion models: a near-Chandrasekhar mass delayed detonation and a violent merger of two (1.1 and 0.9 M-circle dot) white dwarfs. Both models are based on solar metallicity zero-age main-sequence progenitors. Due to explosive nuclear burning at higher density, the delayed-detonation model synthesizes similar to 3.5 times more radioactive Fe-55 than the merger model. As a result, we find that the peak Mn K alpha line flux of the delayed-detonation model exceeds that of the merger model by a factor of similar to 4.5. Since in both models the 5.9-keV X-ray flux peaks five to six years after the explosion, a single measurement of the X-ray line emission at this time can place a constraint on the explosion physics that is complementary to those derived from earlier phase optical spectra or light curves. We perform detector simulations of current and future X-ray telescopes to investigate the possibilities of detecting the X-ray line at 5.9 keV. Of the currently existing telescopes, XMM-Newton/pn is the best instrument for close (less than or similar to 1-2 Mpc), non-background limited SNe Ia because of its large effective area. Due to its low instrumental background, Chandra/ACIS is currently the best choice for SNe Ia at distances above similar to 2 Mpc. For the delayed-detonation scenario, a line detection is feasible with Chandra up to similar to 3 Mpc for an exposure time of 10(6) s. We find that it should be possible with currently existing X-ray instruments (with exposure times less than or similar to 5 x 10(5) s) to detect both of our models at sufficiently high S/N to distinguish between them for hypothetical events within the Local Group. The prospects for detection will be better with future missions. For example, the proposed Athena/X-IFU instrument could detect our delayed-detonation model out to a distance of similar to 5 Mpc. This would make it possible to study future events occurring during its operational life at distances comparable to those of the recent supernovae SN 2011 fe (similar to 6.4 Mpc) and SN 2014J (similar to 3.5 Mpc).
Keywords: line: formation; nuclear reactions; nucleosynthesis; abundances; radiative transfer; supernovae: general; white dwarfs; X-rays: general

A 33 hour period for the Wolf-Rayet/black hole X-ray binary candidate NGC 300 X-1 - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Context. NGC 300 X-1 is the second extragalactic candidate, after IC 10 X-1, in the rare class of Wolf-Rayet/compact object X-ray binary systems exemplified in the Galaxy by Cyg X-3. From a theoretical point of view, accretion onto a black hole in a detached system is possible for large orbital periods only if the mass of the relativistic object is high or the velocity of the accreted wind is low.Aims. We analysed a 2 week SWIFT XRT light curve of NGC 300 X-1 and searched for periodicities. Methods. Period searches were made using Lomb-Scargle periodogram analysis. We evaluated the confidence level using Monte Carlo simulations.Results. A period of 32.8 +/- 0.4 h (3 sigma error) was found for NGC 300 X-1 with a confidence level > 99%. Furthermore, we confirm the high irregular variability during the high flux level, as already observed in the XMM-Newton observations of the source. A folded XMM-Newton light curve is shown, with a profile that is in agreement with SWIFT. The mean absorbed X-ray luminosity in the SWIFT observations was 1.5 x 10(38) erg s(-1), close to the value derived from the XMM-Newton data.Conclusions. While Cyg X-3 has a short period of 4.8 h, the period of NGC 300 X-1 is very close to that of IC 10 X-1 (34.8 +/- 0.9 h). These are likely orbital periods. Possibility of formation of accretion disk for such high orbital periods strongly depends on the terminal velocity of the Wolf-Rayet star wind and black-hole mass. While low masses are possible for wind velocities <= 1000 km s(-1), these increase to several tens of solar masses for velocities > 1600 km s(-1) and no accretion disk may form for terminal velocities larger than 1900 km s(-1).
Keywords: X-rays : individuals : NGC 300 X-1; X-rays : binaries; stars : Wolf-Rayet

Accreting X-ray pulsars observed with integral - Wilms, Jörn; et al. (2007)
In this paper, we review the observational properties of two accreting X-ray pulsars, the persistent source 4U 1907+09 and the transient V 0332+53. Accreting X-ray pulsars are among the brightest sources in the Xray sky and are frequently observed by INTEGRAL and other X-ray missions. Nevertheless they are still very enigmatic sources as fundamental questions on the X-ray production mechanism still remain largely unanswered. These questions are addressed by performing detailed temporal and spectral studies on several objects over a long time range.Of vital importance is the study of cyclotron lines as they provide the only direct link to the magnetic field of the pulsar. While some objects show cyclotron lines which are extremely stable with time and with pulse phase, in other objects the lines strongly depend on the pulse phase, the luminosity of the source, or both.Of special interest in any case are transient sources where it is possible to study the evolution of the cyclotron line and the source in general from the onset until the end of the outburst through a wide range of different luminosity states.We present an observational review of a transient and a persistent accreting X-ray pulsar observed with Integral.
Keywords: X-rays : stars; stars : magnetic fields; stars : flare; stars : pulsars : individual : 4U 1907+09; stars : pulsars : individual : V0332+53

Accretion processes in astrophysics - Shakura, N.; Kolesnikov, D. A.; Postnov, K. A.; Volkov, I. M.; Bikmaev, I. F.; Irsmambetova, T. R.; Staubert, R.; Wilms, Jörn; Irtuganov, E.; Shurygin, P.; Golysheva, P. Yu; Shugarov, S. Yu; et al. (Physics-Uspekhi, 2019)
Accretion onto magnetized neutron stars is considered using as a case study long-term X-ray and optical observations of HZ Her/Her X-1, an X-ray binary system with a 1.7-day orbital period where disc accretion occurs from the optical donor star (HZ Her) onto a neutron star (Her X-1). On top of orbital variability and pulsating X-ray emission from the neutron star rotating with a period of about one second, a 35-day X-ray modulation of emission is observed. The 35-day variability is due to a tilted precessing accretion disc that periodically screens X-ray emission from the neutron star. The disc precession that occurs in the direction opposite to the orbital motion is determined by the joint action of the tidal torque from the donor and dynamical torque from the gas streams. Several dozen thousand broadband UBV photometric observations of HZ Her have been obtained since 1972. The shape of the orbital light curves of HZ Her also changes with the 35-day cycle phase. The orbital variability can be reproduced in a model that includes a precessing tilted and warped accretion disc around a freely precessing neutron star. The disc is warped near its inner edge due to interaction with the rotating neutron star magnetosphere. The magnetic torque depends on the precessional phase of the neutron star. The X-ray emission flux from the neutron star also depends on the free precession phase that modulates the heating of the optical-star atmosphere and the intensity of gas streams. We show that this model reproduces well both optical observations of HZ Her and the behavior of the 35-day X-ray cycle.
CRIS-Team WoS Importer:2020-03-24

Accurate Treatment of Comptonization in X-Ray Illuminated Accretion Disks - Garcia, Javier A.; Sokolova-Lapa, Ekaterina; Dauser, Thomas; Madej, Jerzy; Rozanska, Agata; Majczyna, Agnieszka; Harrison, Fiona A.; Wilms, Jörn (Astrophysical Journal, 2020)
A large fraction of accreting black hole and neutron star systems present clear evidence of the reprocessing of X-rays in the atmosphere of an optically thick accretion disk. The main hallmarks of X-ray reflection include fluorescent K-shell emission lines from iron (∼6.4-6.9 keV), the absorption iron K-edge (∼7-9 keV), and a broad featureless component known as the Compton hump (∼20-40 keV). This Compton hump is produced as the result of the scattering of high-energy photons (E ⪆ 10 keV) of the relatively colder electrons (T e ∼ 105-107 K) in the accretion disk, in combination with photoelectric absorption from iron. The treatment of this process in most current models of ionized X-ray reflection has been done using an approximated Gaussian redistribution kernel. This approach works sufficiently well up to ∼100 keV, but it becomes largely inaccurate at higher energies and at relativistic temperatures (T e ∼ 109 K). We present new calculations of X-ray reflection using a modified version of our code xillver, including an accurate solution for Compton scattering of the reflected unpolarized photons in the disk atmosphere. This solution takes into account quantum electrodynamic and relativistic effects allowing the correct treatment of high photon energies and electron temperatures. We show new reflection spectra computed with this model, and discuss the improvements achieved in reproducing the correct shape of the Compton hump, the discrepancies with previous calculations, and the expected impact of these new models in the interpretation of observational data.
CRIS-Team Scopus Importer:2021-04-19

A CHANDRA OBSERVATION OF THE BURSTING MILLISECOND X-RAY PULSAR IGR J17511-3057 - Paizis, Adamantia; Nowak, M. A.; Rodriguez, Jerome; Wilms, Jörn; Chaty, Sylvain; Del Santo, Melania; Ubertini, P. (Astrophysical Journal, 2012)
IGR J17511-3057 is a low-mass X-ray binary hosting a neutron star and is one of the few accreting millisecond X-ray pulsars with X-ray bursts. We report on a 20 ks Chandra grating observation of IGR J17511-3057, performed on 2009 September 22. We determine the most accurate X-ray position of IGRJ17511-3057, alpha(J2000) = 17(h)51(m)08(s).66, delta(J2000) = -30 degrees.57'41 ''.0 (90% uncertainty of 0 ''.6). During the observation, a similar to 54 s long type-I X-ray burst is detected. The persistent (non-burst) emission has an absorbed 0.5-8 keV luminosity of 1.7 x 10(36) erg s(-1) (at 6.9 kpc) and can be well described by a thermal Comptonization model of soft, similar to 0.6 keV, seed photons upscattered by a hot corona. The type-I X-ray burst spectrum, with average luminosity over the 54 s duration L0.5-8 (keV) = 1.6 x 10(37) erg s(-1), can be well described by a blackbody with kT(bb) similar to 1.6 keV and R-bb similar to 5 km. While an evolution in temperature of the blackbody can be appreciated throughout the burst (average peak kT(bb) = 2.5(-0.4)(+0.8) keV to tail kT(bb) = 1.3(-0.1)(+0.2) keV), the relative emitting surface shows no evolution. The overall persistent and type-I burst properties observed during the Chandra observation are consistent with what was previously reported during the 2009 outburst of IGR J17511-3057.
Keywords: accretion; accretion disks; pulsars: individual (IGR J17511-3057); stars: neutron; X-rays: binaries; X-rays: bursts

A CLUMPY STELLAR WIND AND LUMINOSITY-DEPENDENT CYCLOTRON LINE REVEALED BY THE FIRST SUZAKU OBSERVATION OF THE HIGH-MASS X-RAY BINARY 4U 1538-522 - Hemphill, Paul B.; Rothschild, Richard E.; Markowitz, Alex; Fuerst, Felix; Pottschmidt, Katja; Wilms, Jörn (Astrophysical Journal, 2014)
We present results from the first Suzaku observation of the high-mass X-ray binary 4U 1538-522. The broadband spectral coverage of Suzaku allows for a detailed spectral analysis, characterizing the cyclotron resonance scattering feature at 23.0 +/- 0.4 keV and the iron K alpha line at 6.426 +/- 0.008 keV, as well as placing limits on the strengths of the iron K beta line and the iron K edge. We track the evolution of the spectral parameters both in time and in luminosity, notably finding a significant positive correlation between cyclotron line energy and luminosity. A dip and spike in the light curve is shown to be associated with an order-of-magnitude increase in column density along the line of sight, as well as significant variation in the underlying continuum, implying the accretion of a overdense region of a clumpy stellar wind. We also present a phase-resolved analysis, with most spectral parameters of interest showing significant variation with phase. Notably, both the cyclotron line energy and the iron K alpha line intensity vary significantly with phase, with the iron line intensity significantly out of phase with the pulse profile. We discuss the implications of these findings in the context of recent work in the areas of accretion column physics and cyclotron resonance scattering feature formation.
Keywords: pulsars: individual (4U 1538-522); stars: magnetic field; stars: oscillations; X-rays: binaries; X-rays: stars

A COMPREHENSIVE SPECTRAL ANALYSIS OF THE X-RAY PULSAR 4U 1907+09 FROM TWO OBSERVATIONS WITH THE SUZAKU X-RAY OBSERVATORY - Rivers, Elizabeth; Markowitz, Alex; Pottschmidt, Katja; Roth, Stefanie; Barragan, Laura; Fürst, Felix; Suchy, Slawomir; Kreykenbohm, Ingo; Wilms, Jörn; Rothschild, Richard (Astrophysical Journal, 2010)
We present results from two observations of the wind-accreting X-ray pulsar 4U 1907+09 using the Suzaku Observatory. The broadband time-averaged spectrum allows us to examine the continuum emission of the source and the cyclotron resonance scattering feature at similar to 19 keV. Additionally, using the narrow CCD response of Suzaku near 6 keV allows us to study in detail the Fe K bandpass and to quantify the Fe K beta line for this source for the first time. The source is absorbed by fully covering material along the line of sight with a column density of N-II similar to 2 x 10(22) cm(-2), consistent with a wind-accreting geometry, and a high Fe abundance (similar to 3-4 times solar). Time-and phase-resolved analyses allow us to study variations in the source spectrum. In particular, dips found in the 2006 observation which are consistent with earlier observations occur in the hard X-ray bandpass, implying a variation of the whole continuum rather than occultation by intervening material, while a dip near the end of the 2007 observation occurs mainly in the lower energies implying an increase in N-H along the line of sight, perhaps indicating clumpiness in the stellar wind.
Keywords: pulsars: individual (4U 1907+09); stars: magnetic field; X-rays: binaries; X-rays: stars

A DOUBLE-PEAKED OUTBURST OF A 0535+26 OBSERVED WITH INTEGRAL, RXTE, AND SUZAKU - Caballero, I.; Pottschmidt, K.; Marcu, D. M.; Barragan, L.; Ferrigno, C.; Klochkov, D.; Heras, J. A. Zurita; Suchy, S.; Wilms, Jörn; Kretschmar, Peter; Santangelo, A.; Kreykenbohm, Ingo; et al. (Astrophysical Journal Letters, 2013)
The Be/X-ray binary A 0535+26 showed a normal (type I) outburst in 2009 August. It is the fourth in a series of normal outbursts associated with the periastron, but is unusual because it presented a double-peaked light curve. The two peaks reached a flux of similar to 450 mCrab in the 15-50 keV range. We present results of the timing and spectral analysis of INTEGRAL, RXTE, and Suzaku observations of the outburst. The energy-dependent pulse profiles and their evolution during the outburst are studied. No significant differences with respect to other normal outbursts are observed. The centroid energy of the fundamental cyclotron line shows no significant variation during the outburst. A spectral hardening with increasing luminosity is observed. We conclude that the source is accreting in the sub-critical regime. We discuss possible explanations for the double-peaked outburst.
Keywords: pulsars: individual (A 0535+26); stars: magnetic field; X-rays: binaries; X-rays: stars

Advances in Understanding High-Mass X-ray Binaries with INTEGRALand Future Directions - Kretschmar, Peter; Furst, Felix; Sidoli, Lara; Bozzo, Enrico; Alfonso-Garzon, Julia; Bodaghee, Arash; Chaty, Sylvain; Chernyakova, Masha; Ferrigno, Carlo; Manousakis, Antonios; Negueruela, Ignacio; Postnov, Konstantin; et al. (New Astronomy Reviews, 2019)
High mass X-ray binaries are among the brightest X-ray sources in the Milky Way, as well as in nearby Galaxies. Thanks to their highly variable emissions and complex phenomenology, they have attracted the interest of the high energy astrophysical community since the dawn of X-ray Astronomy. In more recent years, they have challenged our comprehension of physical processes in many more energy bands, ranging from the infrared to very high energies. In this review, we provide a broad but concise summary of the physical processes dominating the emission from high mass X-ray binaries across virtually the whole electromagnetic spectrum. These comprise the interaction of stellar winds with the high gravitational and magnetic fields of compact objects, the behaviour of matter under extreme magnetic and gravity conditions, and the perturbation of the massive star evolutionary processes by presence in a binary system. We highlight the role of the INTEGRAL mission in the discovery of many of the most interesting objects in the high mass X-ray binary class and its contribution in reviving the interest for these sources over the past two decades. We show how the INTEGRAL discoveries have not only contributed to significantly increase the number of high mass X-ray binaries known, thus advancing our understanding of the population as a whole, but also have opened new windows of investigation that stimulated the multi-wavelength approach nowadays common in most astrophysical research fields. We conclude the review by providing an overview of future facilities being planned from the X-ray to the very high energy domain that will hopefully help us in finding an answer to the many questions left open after more than 18 years of INTEGRAL scientific observations.
CRIS-Team Scopus Importer:2021-04-20
Keywords: accretion; gamma rays: observations; INTEGRAL observatory; pulsars: general; stars: neutron; X-rays: binaries

A first search for coincident gravitational waves and high energy neutrinos using LIGO, Virgo and ANTARES data from 2007 - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
We present the results of the first search for gravitational wave bursts associated with high energy neutrinos. Together, these messengers could reveal new, hidden sources that are not observed by conventional photon astronomy, particularly at high energy. Our search uses neutrinos detected by the underwater neutrino telescope ANTARES in its 5 line configuration during the period January - September 2007, which coincided with the fifth and first science runs of LIGO and Virgo, respectively. The LIGO-Virgo data were analysed for candidate gravitational-wave signals coincident in time and direction with the neutrino events. No significant coincident events were observed. We place limits on the density of joint high energy neutrino - gravitational wave emission events in the local universe, and compare them with densities of merger and core-collapse events.
Keywords: gravitational waves / experiments; neutrino astronomy

A giant radio flare from Cygnus X-3 with associated ?-ray emission - Corbel, S.; Dubus, G.; Tomsick, J. A.; Szostek, A.; Corbet, R. H. D.; Miller-Jones, J. C. A.; Richards, J. L.; Pooley, G.; Trushkin, S.; Dubois, R.; Hill, A. B.; Kerr, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2012)
With frequent flaring activity of its relativistic jets, Cygnus X-3 (Cyg X-3) is one of the most active microquasars and is the only Galactic black hole candidate with confirmed high-energy ?-ray emission, thanks to detections by Fermi Large Area Telescope (Fermi/LAT) and AGILE. In 2011, Cyg X-3 was observed to transit to a soft X-ray state, which is known to be associated with high-energy ?-ray emission. We present the results of a multiwavelength campaign covering a quenched state, when radio emission from Cyg X-3 is at its weakest and the X-ray spectrum is very soft. A giant (similar to 20 Jy) optically thin radio flare marks the end of the quenched state, accompanied by rising non-thermal hard X-rays. Fermi/LAT observations (E= 100 MeV) reveal renewed ?-ray activity associated with this giant radio flare, suggesting a common origin for all non-thermal components. In addition, current observations unambiguously show that the ?-ray emission is not exclusively related to the rare giant radio flares. A three-week period of ?-ray emission is also detected when Cyg X-3 was weakly flaring in radio, right before transition to the radio quenched state. No ?-rays are observed during the similar to 1-month long quenched state, when the radio flux is weakest. Our results suggest transitions into and out of the ultrasoft X-ray (radio-quenched) state trigger ?-ray emission, implying a connection to the accretion process, and also that the ?-ray activity is related to the level of radio flux (and possibly shock formation), strengthening the connection to the relativistic jets.
Keywords: black hole physics; stars: individual: Cyg X-3; ISM: jets and outflows; gamma-rays: stars; radio continuum: stars; X-rays: binaries

A giant X-ray dust scattering ring discovered with SRG/eROSITA around the black hole transient MAXI J1348-630 - Lamer, G.; Schwope, A. D.; Predehl, P.; Traulsen, I.; Wilms, Jörn; Freyberg, M. (Astronomy & Astrophysics, 2021)
We report the discovery of a giant dust scattering ring around the Black Hole transient MAXI J1348-630 with SRG/eROSITA during its first X-ray all-sky survey. During the discovery observation in February 2020, the ring had an outer diameter of 1.3 deg, growing to 1.6 deg by the time of the second all-sky survey scan in August 2020. This makes the new dust ring by far the largest X-ray scattering ring observed so far. Dust scattering halos, in particular the rings found around transient sources, provide an opportunity to make precise distance measurements towards the original X-ray sources. We combine data from SRG/eROSITA, XMM-Newton, MAXI, and Gaia to measure the geometrical distance of MAXI J1348-630. The Gaia data place the scattering dust at a distance of 2050 pc. Based on the measured time lags and the geometry of the ring we find MAXI J1348-630 at a distance of 3390 pc with a statistical uncertainty of only 1.1% and a systematic uncertainty of 10% caused mainly by the parallax offset of Gaia. This result makes MAXI J1348-630 one of the black hole transients with the most accurately determined distances. The new distance leads to a revised mass estimate for the black hole of 11 ± 2 MâŠ . The transition to the soft state during the outburst occurred when the bolometric luminosity of MAXI J1348-630 reached 1.7% of its Eddington luminosity.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Dust; extinction; Stars: black holes; Stars: distances; Stars: individual: MAXI J1648-630; X-rays: binaries; X-rays: ISM

A HARD X-RAY POWER-LAW SPECTRAL CUTOFF IN CENTAURUS X-4 - Chakrabarty, Deepto; Tomsick, John A.; Grefenstette, Brian W.; Psaltis, Dimitrios; Bachetti, Matteo; Barret, Didier; Boggs, Steven E.; Christensen, Finn E.; Craig, William W.; Fuerst, Felix; Hailey, Charles J.; Harrison, Fiona A.; et al. (Astrophysical Journal, 2014)
The low-mass X-ray binary (LMXB) Cen X-4 is the brightest and closest (<1.2 kpc) quiescent neutron star transient. Previous 0.5-10 keV X-ray observations of Cen X-4 in quiescence identified two spectral components: soft thermal emission from the neutron star atmosphere and a hard power-law tail of unknown origin. We report here on a simultaneous observation of Cen X-4 with NuSTAR (3-79 keV) and XMM-Newton (0.3-10 keV) in 2013 January, providing the first sensitive hard X-ray spectrum of a quiescent neutron star transient. The 0.3-79 keV luminosity was 1.1 x 10(33) D-kpc(2) erg s(-1), with similar or equal to 60% in the thermal component. We clearly detect a cutoff of the hard spectral tail above 10 keV, the first time such a feature has been detected in this source class. We show that thermal Comptonization and synchrotron shock origins for the hard X-ray emission are ruled out on physical grounds. However, the hard X-ray spectrum is well fit by a thermal bremsstrahlung model with kT(e) = 18 keV, which can be understood as arising either in a hot layer above the neutron star atmosphere or in a radiatively inefficient accretion flow. The power-law cutoff energy may be set by the degree of Compton cooling of the bremsstrahlung electrons by thermal seed photons from the neutron star surface. Lower thermal luminosities should lead to higher (possibly undetectable) cutoff energies. We compare Cen X-4's behavior with PSR J1023+0038, IGR J18245-2452, and XSS J12270-4859, which have shown transitions between LMXB and radio pulsar modes at a similar X-ray luminosity.
Keywords: accretion; accretion disks; binaries: close; stars: individual (Cen X-4); stars: neutron; X-rays: binaries

A highly magnetized twin-jet base pinpoints a supermassive black hole - Baczko, Anne-Kathrin; Schulz, Robert; Kadler, Matthias; Ros, Eduardo; Perucho, Manel; Krichbaum, T. P.; Boeck, M.; Bremer, M.; Großberger, Christoph; Lindqvist, M.; Lobanov, A. P.; Mannheim, K.; et al. (Astronomy & Astrophysics, 2016)
Supermassive black holes (SMBH) are essential for the production of jets in radio-loud active galactic nuclei (AGN). Theoretical models based on (Blandford & Znajek 1977, MNRAS, 179, 433) extract the rotational energy from a Kerr black hole, which could be the case for NGC 1052, to launch these jets. This requires magnetic fields on the order of 10G to 10G. We imaged the vicinity of the SMBH of the AGN NGC 1052 with the Global Millimetre VLBI Array and found a bright and compact central feature that is smaller than 1.9 light days (100 Schwarzschild radii) in radius. Interpreting this as a blend of the unresolved jet bases, we derive the magnetic field at 1 Schwarzschild radius to lie between 200 G and 8.3 × 10 G consistent with Blandford & Znajek models.
Keywords: Galaxies: active; Galaxies: jets; Galaxies: magnetic fields; Galaxies: nuclei; Magnetic fields

All-flavor Search for a Diffuse Flux of Cosmic Neutrinos with Nine Years of ANTARES Data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The ANTARES detector is at present the most sensitive neutrino telescope in the northern hemisphere. The highly significant cosmic neutrino excess observed by the Antarctic IceCube detector can be studied with ANTARES, exploiting its complementing field of view, exposure, and lower energy threshold. Searches for an all-flavor diffuse neutrino signal, covering nine years of ANTARES data taking, are presented in this Letter. Upward-going events are used to reduce the atmospheric muon background. This work includes for the first time in ANTARES both track-like (mainly nu mu) and shower-like (mainly nu(e)) events in this kind of analysis. Track-like events allow for an increase of the effective volume of the detector thanks to the long path traveled by muons in rock and/ or sea water. Shower-like events are well reconstructed only when the neutrino interaction vertex is close to, or inside, the instrumented volume. A mild excess of high-energy events over the expected background is observed in nine years of ANTARES data in both samples. The best fit for a single power-law cosmic neutrino spectrum, in terms of perflavor flux at 100 TeV, is Phi(1f)(0) (100 TeV) = (1.7 +/- 1.0) x 10(-18) GeV-1 cm(-2) s(-1) sr(-1) with spectral index Gamma = 2.4(-0.4)(+0.5) .The null cosmic flux assumption is rejected with a significance of 1.6 sigma .
Keywords: astroparticle physics; neutrinos

All-sky search for high-energy neutrinos from gravitational wave event GW170104 with the Antares neutrino telescope: The ANTARES Collaboration - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (European Physical Journal C, 2017)
Advanced LIGO detected a significant gravitational wave signal (GW170104) originating from the coalescence of two black holes during the second observation run on January 4th, 2017. Anall-sky high-energy neutrino follow-up search has been made using data from the Antares neutrino telescope, including both upgoing and downgoing events in two separate analyses. No neutrino candidates were found within +/- 500 s around the GW event time nor any time clustering of events over an extended time window of +/- 3 months. The non-detection is used to constrain isotropic-equivalent high-energy neutrino emission from GW170104 to less than similar to 1.2 x 10(55) erg for a E-2 spectrum. This constraint is valid in the energy range corresponding to the 5-95% quantiles of the neutrino flux [3.2 TeV; 3.6 PeV], if the GW emitter was below the Antares horizon at the alert time.

A method for detection of muon induced electromagnetic showers with the ANTARES detector - Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Auberth, J. J.; Baret, B.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2012)
The primary aim of ANTARES is neutrino astronomy with upward going muons created in charged current muon neutrino interactions in the detector and its surroundings. Downward going muons are background for neutrino searches. These muons are the decay products of cosmic-ray collisions in the Earth's atmosphere far above the detector. This paper presents a method to identify and count electromagnetic showers induced along atmospheric muon tracks with the ANTARES detector. The method is applied to both cosmic muon data and simulations and its applicability to the reconstruction of muon event energies is demonstrated. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino telescope; Electromagnetic shower identification; High energy muons; Energy reconstruction

A method to stabilise the performance of negatively fed KM3NeT photomultipliers - Adrián-Martínez, S.; Ageron, M.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Avgitas, T.; et al. (Journal of Instrumentation, 2016)
The KM3NeT research infrastructure, currently under construction in the Mediterranean Sea, will host neutrino telescopes for the identification of neutrino sources in the Universe and for studies of the neutrino mass hierarchy. These telescopes will house hundreds of thousands of photomultiplier tubes that will have to be operated in a stable and reliable fashion. In this context, the stability of the dark counts has been investigated for photomultiplier tubes with negative high voltage on the photocathode and held in insulating support structures made of 3D printed nylon material. Small gaps between the rigid support structure and the photomultiplier tubes in the presence of electric fields can lead to discharges that produce dark count rates that are highly variable. A solution was found by applying the same insulating varnish as used for the high voltage bases directly to the outside of the photomultiplier tubes. This transparent conformal coating provides a convenient and inexpensive method of insulation.
Keywords: Instrument optimization; Large detector systems for particle and astroparticle physics; Neutrino detectors; Photon detectors for UV; visible and IR photons (gas) (gas-photocathodes; solid-photocathodes)

A model for cyclotron resonance scattering features - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Aims. We study the physics of cyclotron line formation in the high-energy spectra of accreting X-ray pulsars. In particular, we link numerical predictions for the line profiles to results from observational data analysis. Therefore, first we investigate the theoretical predictions and the significance of our model parameters, and second we aim at the development of a model to fit cyclotron lines in observational data.Methods. Simulations were performed using Monte Carlo methods. The data were extracted with HEADAS 6.1.1 and INTEGRAL OSA 5.1. A convolution model for the cyclotron line shapes was implemented for the XSPEC spectral analysis software package and for data packages compatible with XSPEC local models.Results. We predict the shapes of cyclotron lines for different prescribed physical settings. The calculations assume that the line-forming region is a low-density electron plasma, which is of cylindrical or slab geometry and which is exposed to a uniform, sub-critical magnetic field. We investigate the dependence of the shape of the fundamental line on angle, geometry, optical depth and temperature. We also discuss variations of the line ratios for non-uniform magnetic fields. We have developed a new convolution and interpolation model to simulate line features regardless of any a priori assumed shape of the neutron star continuum. Fitting RXTE and INTEGRAL data of the accreting X-ray pulsar V0332+ 53 with this model gives a qualitative description of the data. Strong emission wings of the fundamental cyclotron feature as predicted by internally irradiated plasma geometries are in principle observable by todays instruments but are not formed in V0332+ 53, hinting at a bottom illuminated slab geometry for line formation.
Keywords: X-rays : binaries; stars : neutron; accretion; accretion disks; magnetic fields; line : formation; methods : numerical

A MULTIWAVELENGTH STUDY OF CYGNUS X-1: THE FIRST MID-INFRARED SPECTROSCOPIC DETECTION OF COMPACT JETS - Rahoui, Farid; Lee, Julia C.; Heinz, Sebastian; Hines, Dean C.; Pottschmidt, Katja; Wilms, Jörn; Grinberg, Victoria (Astrophysical Journal, 2011)
We report on a Spitzer/InfraRed Spectrograph (mid-infrared), RXTE/PCA+HEXTE (X-ray), and Ryle (radio) simultaneous multiwavelength study of the microquasar Cygnus X-1, which aimed at an investigation of the origin of its mid-infrared emission. Compact jets were present in two out of three observations, and we show that they strongly contribute to the mid-infrared continuum. During the first observation, we detect the spectral break-where the transition from the optically thick to the optically thin regime takes place-at about 2.9x10(13) Hz. We then show that the jet's optically thin synchrotron emission accounts for Cygnus X-1's emission beyond 400 keV, although it cannot alone explain its 3-200 keV continuum. A compact jet was also present during the second observation, but we do not detect the break, since it has likely shifted to higher frequencies. In contrast, the compact jet was absent during the last observation, and we show that the 5-30 mu m mid-infrared continuum of Cygnus X-1 stems from the blue supergiant companion star HD 226868. Indeed, the emission can then be understood as the combination of the photospheric Rayleigh-Jeans tail and the bremsstrahlung from the expanding stellar wind. Moreover, the stellar wind is found to be clumpy, with a filling factor f(infinity) approximate to 0.09-0.10. Its bremsstrahlung emission is likely anti-correlated to the soft X-ray emission, suggesting an anti-correlation between the mass-loss and mass-accretion rates. Nevertheless, we do not detect any mid-infrared spectroscopic evidence of interaction between the jets and Cygnus X-1's environment and/or the companion star's stellar wind.
Keywords: binaries: close; dust; extinction; infrared: stars; stars: individual (Cygnus X-1); X-rays: binaries

An accreting pulsar with extreme properties drives an ultraluminous x-ray source in NGC 5907 - Israel, Gian Luca; Belfiore, Andrea; Stella, Luigi; Esposito, Paolo; Casella, Piergiorgio; De Luca, Andrea; Marelli, Martino; Papitto, Alessandro; Perri, Matteo; Puccetti, Simonetta; Rodriguez Castillo, Guillermo A.; Salvetti, David; et al. (Science, 2017)
Ultraluminous x-ray sources (ULXs) in nearby galaxies shine brighter than any x-ray source in our Galaxy. ULXs are usually modeled as stellar-mass black holes (BHs) accreting at very high rates or intermediate-mass BHs. We present observations showing that NGC 5907 ULX is instead an x-ray accreting neutron star (NS) with a spin period evolving from 1.43 seconds in 2003 to 1.13 seconds in 2014. It has an isotropic peak luminosity of similar to 1000 times the Eddington limit for a NS at 17.1 megaparsec. Standard accretion models fail to explain its luminosity, even assuming beamed emission, but a strong multipolar magnetic field can describe its properties. These findings suggest that other extreme ULXs (x-ray luminosity >= 1041 erg second(-1)) might harbor NSs.

An algorithm for the reconstruction of high-energy neutrino-induced particle showers and its application to the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (European Physical Journal C, 2017)
A novel algorithm to reconstruct neutrino-induced particle showers within the ANTARES neutrino telescope is presented. The method achieves a median angular resolution of 6. for shower energies below 100TeV. Applying this algorithm to 6 years of data taken with theANTARES detector, 8 events with reconstructed shower energies above 10TeV are observed. This is consistent with the expectation of about 5 events from atmospheric backgrounds, but also compatible with diffuse astrophysical flux measurements by the IceCube collaboration, from which 2-4 additional events are expected. A 90% C.L. upper limit on the diffuse astrophysical neutrino flux with a value per neutrino flavour of E-2.Phi(90%) = 4.9 . 10(-8) GeV.cm(-2).s(-1).sr(-1) is set, applicable to the energy range from 23TeV to 7.8PeV, assuming an unbroken E-2 spectrum and neutrino flavour equipartition at Earth.

An Algorithm for the Reconstruction of Neutrino-induced Showers in the ANTARES Neutrino Telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astronomical Journal, 2017)
Muons created by nu(mu) charged current (CC) interactions in the water surrounding the ANTARES neutrino telescope have been almost exclusively used so far in searches for cosmic neutrino sources. Due to their long range, highly energetic muons inducing Cherenkov radiation in the water are reconstructed with dedicated algorithms that allow for the determination of the parent neutrino direction with a median angular resolution of about 0 degrees.4 for an E-2 neutrino spectrum. In this paper, an algorithm optimized for accurate reconstruction of energy and direction of shower events in the ANTARES detector is presented. Hadronic showers of electrically charged particles are produced by the disintegration of the nucleus both in CC and neutral current interactions of neutrinos in water. In addition, electromagnetic showers result from the CC interactions of electron neutrinos while the decay of a tau lepton produced in nu(tau) CC interactions will, in most cases, lead to either a hadronic or an electromagnetic shower. A shower can be approximated as a point source of photons. With the presented method, the shower position is reconstructed with a precision of about 1 m; the neutrino direction is reconstructed with a median angular resolution between 2 degrees and 3 degrees in the energy range of 1-1000 TeV. In this energy interval, the uncertainty on the reconstructed neutrino energy is about 5%-10%. The increase in the detector sensitivity due to the use of additional information from shower events in the searches for a cosmic neutrino flux is also presented.
Keywords: neutrinos; telescopes

An evaluation of the exposure in nadir observation of the JEM-EUSO mission - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Ambrosio, M.; Anchordoqui, L.; Anzalone, Anna; Arai, Y.; Aramo, Carla; Asano, K.; Ave, M.; Barrillon, P.; et al. (Astroparticle Physics, 2013)
We evaluate the exposure during nadir observations with JEM-EUSO, the Extreme Universe Space Observatory, on-board the Japanese Experiment Module of the International Space Station. Designed as a mission to explore the extreme energy Universe from space, JEM-EUSO will monitor the Earth's nighttime atmosphere to record the ultraviolet light from tracks generated by extensive air showers initiated by ultra-high energy cosmic rays. In the present work, we discuss the particularities of space-based observation and we compute the annual exposure in nadir observation. The results are based on studies of the expected trigger aperture and observational duty cycle, as well as, on the investigations of the effects of clouds and different types of background light. We show that the annual exposure is about one order of magnitude higher than those of the presently operating ground-based observatories. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Ultra High Energy Cosmic Rays; Space-based experiment; Extensive air showers; JEM-EUSO mission

ANTARES constrains a blazar origin of two IceCube PeV neutrino events - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Astronomy & Astrophysics, 2015)
Results. Both blazars predicted to be the most neutrino-bright in the TANAMI sample (1653-329 and 1714-336) have a signal flux fitted by the likelihood analysis corresponding to approximately one event. This observation is consistent with the blazar-origin hypothesis of the IceCube event IC 14 for a broad range of blazar spectra, although an atmospheric origin cannot be excluded. No ANTARES events are observed from any of the other four blazars, including the three associated with IceCube event IC20. This excludes at a 90% confidence level the possibility that this event was produced by these blazars unless the neutrino spectrum is flatter than -2.4.
Keywords: neutrinos; galaxies: active; quasars: general

ANTARES Neutrino Search for Time and Space Correlations with IceCube High-energy Neutrino Events - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astrophysical Journal, 2019)
In past years the IceCube Collaboration has reported the observation of astrophysical high-energy neutrino events in several analyses. Despite compelling evidence for the first identification of a neutrino source, TXS 0506+056, the origin of the majority of these events is still unknown. In this paper, we search for a possible transient origin of the IceCube astrophysical events using neutrino events detected by the ANTARES telescope. The arrival time and direction of 6894 track-like and 160 shower-like events detected over 2346 days of livetime are examined to search for coincidences with 54 IceCube high-energy track-like neutrino events, by means of a maximum likelihood method. No significant correlation is observed and upper limits on the one-flavor neutrino fluence from the direction of the IceCube candidates are derived. The nonobservation of time and space correlation within the time window of 0.1 days with the two most energetic IceCube events constrains the spectral index of a possible point-like transient neutrino source to be harder than -2.3 and -2.4 for each event, respectively.
CRIS-Team WoS Importer:2019-07-26

ANTARES Search for Point Sources of Neutrinos Using Astrophysical Catalogs: A Likelihood Analysis - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, Simone; et al. (Astrophysical Journal, 2021)
A search for astrophysical pointlike neutrino sources using the data collected by the ANTARES detector between 2007 January 29 and 2017 December 31 is presented. A likelihood method is used to assess the significance of an excess of muon neutrinos inducing track-like events in correlation with the location of a list of possible sources. Different sets of objects are tested in the analysis: (a) a subsample of the Fermi 3LAC catalog of blazars, (b) a jet-obscured population of active galactic nuclei, (c) a sample of hard X-ray selected radio galaxies, (d) a star-forming galaxy catalog, and (e) a public sample of 56 very-high-energy track events from the IceCube experiment. None of the tested sources shows a significant association with the sample of neutrinos detected by ANTARES. The smallest p-value is obtained for the catalog of radio galaxies with an equal-weights hypothesis, with a pre-trial p-value equivalent to a 2.8 sigma excess, which is equivalent to 1.6 sigma post-trial. In addition, the results of a dedicated analysis for the blazar MG3 J225517+2409 are also reported: this source is found to be the most significant within the Fermi 3LAC sample, with five ANTARES events located less than one degree from the source. This blazar showed evidence of flaring activity in Fermi data, in spacetime coincidence with a high-energy track detected by IceCube. An a posteriori significance of 2.6 sigma for the combination of ANTARES and IceCube data is reported.
CRIS-Team WoS Importer:2021-04-30

ANTARES upper limits on the multi-TeV neutrino emission from the GRBs detected by IACTs - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
The first gamma-ray burst detections by Imaging Atmospheric Cherenkov Telescopes have been recently announced: GRB 190114C, detected by MAGIC, GRB 180720B and GRB 190829A, observed by H.E.S.S. A dedicated search for neutrinos in space and time coincidence with the gamma-ray emission observed by IACTs has been performed using ANTARES data. The search covers both the prompt and afterglow phases, yielding no neutrinos in coincidence with the three GRBs studied. Upper limits on the energetics of the neutrino emission are inferred. The resulting upper limits are several orders of magnitude above the observed gamma-ray emission, and they do not allow to constrain the available models.
CRIS-Team Scopus Importer:2021-04-16

An ultraluminous supersoft source with a 4 hour modulation in NGC 4631 - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Context. Supersoft X- ray sources (SSSs) are characterised by very low temperatures (< 100 eV). Classical SSSs have bolometric luminosities in the range of 10(36)-10(38) erg s(-1) and are modelled with steady nuclear burning of hydrogen on the surfaces of white dwarfs. However, several SSSs have been discovered with much higher luminosities. Their nature is still unclear. Aims. We report the discovery of a 4 h modulation for an ultraluminous SSS in the nearby edge-on spiral galaxy NGC 4631, observed with XMM-Newton in 2002 June. Temporal and spectral analysis of the source is performed. Methods. We use a Lomb-Scargle periodogram analysis for the period search and evaluate the confidence level using Monte-Carlo simulations. We measure the source temperature, flux and luminosity through spectral fitting. Results. A modulation of 4.2 +/- 0.4 h (3 sigma error) was found for the SSS with a confidence level > 99%. Besides dips observed in the light curve, the flux decreased by a factor of 3 within similar to 10 h. The spectrum can be described with an absorbed blackbody model with kT similar to 67 eV. The absorbed luminosity in the 0.2-2 keV energy band was 2.7 x 1038 erg s-1 while the bolometric luminosity was a hundred time higher (3.2 x 1040 erg s(-1)), making the source one of the most luminous of its class, assuming the best fit model is correct. Conclusions. This source is another very luminous SSS for which the standard white dwarf interpretation cannot be applied, unless a strong beaming factor is considered. A stellar-mass black hole accreting at a super Eddington rate is a more likely interpretation, where the excess of accreted matter is ejected through a strong optically-thick outflow. The 4 h modulation could either be an eclipse from the companion star or the consequence of a warped accretion disk.
Keywords: galaxies : individual : NGC 4631; X-rays : galaxies; X-rays : binaries

An X-ray spectral analysis of the central regions of NGC 4593 - Wilms, Jörn; et al. (Astrophysical Journal, 2007)
We present a detailed analysis of XMM-Newton EPIC-pn data for the Seyfert 1 galaxy NGC 4593. We discuss the X-ray spectral properties of this source, as well as its variations with time. The 0.5-10 keV spectrum shows significant complexity beyond a simple power-law form, with clear evidence existing for a "soft excess,'' as well as absorption by highly ionized plasma ( a warm absorber) within the central engine of this active galactic nucleus. We show that the soft excess is best described as originating from thermal Comptonization by plasma that is appreciably cooler than the primary X-ray-emitting plasma; we find that the form of the soft excess cannot be reproduced adequately by reflection from an ionized accretion disk. The only measurable deviation from the power-law continuum in the hard spectrum comes from the presence of cold and ionized fluorescent iron K alpha emission lines at 6.4 and 6.97 keV, respectively. While constraints on the ionized iron line are weak, the cold line is found to be narrow at CCD resolution with a flux that does not track the temporal changes in the underlying continuum, implying an origin in the outer radii of the accretion disk or the putative molecular torus of Seyfert unification schemes. The X-ray continuum itself varies on all accessible timescales. We detect a similar to 230 s time lag between soft and hard EPIC-pn bands that, if interpreted as scattering timescales within a Comptonizing disk corona, can be used to constrain the physical size of the primary X-ray source to a characteristic length scale of similar to 2r(g). Taken together, the small implied coronal size and the large implied iron-line emitting region indicate a departure from the current picture of a "typical'' AGN geometry.
Keywords: accretion; accretion disks; black hole physics; galaxies : nuclei

An X-ray variable absorber within the broad line region in Fairall 51 - Svoboda, J.; Beuchert, Tobias; Guainazzi, M.; Longinotti, A. L.; Piconcelli, E.; Wilms, Jörn (Astronomy & Astrophysics, 2015)
Conclusions. A week-long scale of the variability indicates that the absorber is located at the distance approximate to 0.05 pc from the centre, i.e., in the broad line region.
Keywords: galaxies: active; galaxies: Seyfert; galaxies: individual: Fairall 51

A polarized fast radio burst at low Galactic latitude - Petroff, E.; Burke-Spolaor, S.; Keane, E. F.; Mclaughlin, M. A.; Miller, R.; Andreoni, I.; Bailes, Matthew; Barr, E. D.; Bernard, S. R.; Bhandari, S.; Bhat, N. D. R.; Burgay, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We report on the discovery of a new fast radio burst (FRB), FRB 150215, with the Parkes radio telescope on 2015 February 15. The burst was detected in real time with a dispersion measure (DM) of 1105.6 +/- 0.8 pc cm(-3), a pulse duration of 2.8(-0.5)(+1.2) ms, and a measured peak flux density assuming that the burst was at beam centre of 0.7(-0.1)(+0.2) Jy. The FRB originated at a Galactic longitude and latitude of 24.66 degrees, 5.28 degrees and 25 degrees away from the Galactic Center. The burst was found to be 43 +/- 5 per cent linearly polarized with a rotation measure (RM) in the range -9 < RM < 12 rad m(-2) (95 per cent confidence level), consistent with zero. The burst was followed up with 11 telescopes to search for radio, optical, X-ray, gamma-ray and neutrino emission. Neither transient nor variable emission was found to be associated with the burst and no repeat pulses have been observed in 17.25 h of observing. The sightline to the burst is close to the Galactic plane and the observed physical properties of FRB 150215 demonstrate the existence of sight lines of anomalously low RM for a given electron column density. The Galactic RM foreground may approach a null value due to magnetic field reversals along the line of sight, a decreased total electron column density from the Milky Way, or some combination of these effects. A lower Galactic DM contribution might explain why this burst was detectable whereas previous searches at low latitude have had lower detection rates than those out of the plane.
Keywords: polarization; methods: data analysis; surveys; ISM: structure

A Possible Phase-dependent Absorption Feature in the Transient X-Ray Pulsar SAX J2103.5+4545 - Brumback, M. C.; Hickox, R. C.; Furst, F. S.; Pottschmidt, K.; Hemphill, P.; Tomsick, J. A.; Wilms, Jörn; Ballhausen, Ralf (Astrophysical Journal, 2018)
We present an X-ray spectral and timing analysis of two Nuclear Spectroscopic Telescope Array (NuSTAR) observations of the transient Be X-ray binary SAX J2103.5+4545 during its 2016 April outburst, which was characterized by the highest flux since NuSTAR's launch. These observations provide detailed hard X-ray spectra of this source during its bright precursor flare and subsequent fainter regular outburst for the first time. In this work, we model the phase-averaged spectra for these observations with a negative and positive power law with an exponential cutoff (NPEX) model and compare the pulse profiles at different flux states. We found that the broadband pulse profile changes from a three-peaked pulse in the first observation to a two-peaked pulse in the second observation, and that each of the pulse peaks has some energy dependence. We also perform pulse-phase spectroscopy and fit phase-resolved spectra with NPEX to evaluate how spectral parameters change with pulse phase. We find that while the continuum parameters are mostly constant with pulse phase, a weak absorption feature at similar to 12 keV might, with further study, be classified as a cyclotron line, does show strong pulse-phase dependence.
Keywords: pulsars: individual (SAX J2103.5+4545); stars: neutron; X-rays: binaries

A precessing Be disc as a possible model for occultation events in GX 304-1 - Kühnel, Matthias; Rothschild, R. E.; Okazaki, A. T.; Müller, Sebastian; Pottschmidt, K.; Ballhausen, Ralf; Choi, J.; Kreykenbohm, Ingo; Fuerst, F.; Marcu-Cheatham, D. M.; Hemphill, P.; Sagredo, Macarena; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We report on the RXTE detection of a sudden increase in the absorption column density, N-H, during the 2011 May outburst of GX 304-1. The NH increased up to similar to 16 x 10(22) atoms cm(-2), which is a factor of 3-4 larger than what is usually measured during the outbursts of GX 304-1 as covered by RXTE. Additionally, an increase in the variability of the hardness ratio as calculated from the energy resolved RXTE-Proportional Counter Array light curves is measured during this time range. We interpret these facts as an occultation event of the neutron star by material in the line of sight. Using a simple 3D model of an inclined and precessing Be disc around the Be-type companion, we are able to qualitatively explain the NH evolution over time. We are able to constrain the Be disc density to be of the order of 10(-11) g cm(-3). Our model strengthens the idea of inclined Be discs as origin of double-peaked outbursts as the derived geometry allows accretion twice per orbit under certain conditions.
Keywords: occultations; stars: neutron; pulsars: individual: GX 304-1; X-rays: binaries

Arcus: The X-ray grating spectrometer explorer - Smith, R. K.; Abraham, M. H.; Allured, R.; Bautz, M.; Bookbinder, J.; Bregman, J. N.; Brenneman, L.; Brickhouse, N. S.; Burrows, D. N.; Burwitz, V.; Carvalho, R.; Cheimets, P. N.; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
Arcus will be proposed to the NASA Explorer program as a free-flying satellite mission that will enable high-resolution soft X-ray spectroscopy (8-50Å) with unprecedented sensitivity - effective areas of >500 sq cm and spectral resolution >2500. The Arcus key science goals are (1) to determine how baryons cycle in and out of galaxies by measuring the effects of structure formation imprinted upon the hot gas that is predicted to lie in extended halos around galaxies, groups, and clusters, (2) to determine how black holes influence their surroundings by tracing the propagation of out-flowing mass, energy and momentum from the vicinity of the black hole out to large scales and (3) to understand how accretion forms and evolves stars and circumstellar disks by observing hot infalling and outflowing gas in these systems. Arcus relies upon grazing-incidence silicon pore X-ray optics with the same 12m focal length (achieved using an extendable optical bench) that will be used for the ESA Athena mission. The focused X-rays from these optics will then be diffracted by high-efficiency off-plane reflection gratings that have already been demonstrated on sub-orbital rocket flights, imaging the results with flight-proven CCD detectors and electronics. The power and telemetry requirements on the spacecraft are modest. The majority of mission operations will not be complex, as most observations will be long (∼100 ksec), uninterrupted, and pre-planned, although there will be limited capabilities to observe targets of opportunity, such as tidal disruption events or supernovae with a 3-5 day turnaround. After the end of prime science, we plan to allow guest observations to maximize the science return of Arcus to the community.
Keywords: Gratings; Instrumentation; X-rays: spectroscopy

AS ABOVE, SO BELOW: EXPLOITING MASS SCALING IN BLACK HOLE ACCRETION TO BREAK DEGENERACIES IN SPECTRAL INTERPRETATION - Markoff, Sera; Nowak, Michael A.; Gallo, Elena; Hynes, Robert; Wilms, Jörn; Plotkin, Richard M.; Maitra, Dipankar; Silva, Catia V.; Drappeau, Samia (Astrophysical Journal Letters, 2015)
Over the past decade, evidence has mounted that several aspects of black hole (BH) accretion physics proceed in a mass-invariant way. One of the best examples of this scaling is the empirical "fundamental plane of BH accretion" relation linking mass, radio, and X-ray luminosity over eight orders of magnitude in BH mass. The currently favored theoretical interpretation of this relation is that the physics governing power output in weakly accreting BHs depends more on relative accretion rate than on mass. In order to test this theory, we explore whether a mass-invariant approach can simultaneously explain the broadband spectral energy distributions from two BHs at opposite ends of the mass scale but that are at similar Eddington accretion fractions. We find that the same model, with the same value of several fitted physical parameters expressed in mass-scaling units to enforce self-similarity, can provide a good description of two data sets from V404 Cyg and M81*, a stellar and supermassive BH, respectively. Furthermore, only one of several potential emission scenarios for the X-ray band is successful, suggesting it is the dominant process driving the fundamental plane relation at this accretion rate. This approach thus holds promise for breaking current degeneracies in the interpretation of BH high-energy spectra and for constructing better prescriptions of BH accretion for use in various local and cosmological feedback applications.
Keywords: accretion; accretion disks; black hole physics; galaxies: active; galaxies: jets; radiation mechanisms: non-thermal; X-rays: binaries

A Search for Cosmic Neutrino and Gamma-Ray Emitting Transients in 7.3 yr of ANTARES and Fermi LAT Data - Solares, H. A. Ayala; Cowen, D. F.; Delaunay, J. J.; Fox, D. B.; Keivani, A.; Mostafa, M.; Murase, K.; Turley, C. F.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; et al. (Astrophysical Journal, 2019)
We analyze 7.3 yr of ANTARES high-energy neutrino and Fermi Large Area Telescope (LAT) gamma-ray data in search of cosmic neutrino + gamma-ray (nu + gamma) transient sources or source populations. Our analysis has the potential to detect either individual nu + gamma transient sources (durations delta t less than or similar to 1000 s), if they exhibit sufficient gamma-ray or neutrino multiplicity, or a statistical excess of nu + gamma transients of individually lower multiplicities. Individual high gamma-ray multiplicity events could be produced, for example, by a single ANTARES neutrino in coincidence with a LAT-detected gamma-ray burst. Treating ANTARES track and cascade event types separately, we establish detection thresholds by Monte Carlo scrambling of the neutrino data, and determine our analysis sensitivity by signal injection against these scrambled data sets. We find our analysis is sensitive to nu + gamma transient populations responsible for >5% of the observed gamma-coincident neutrinos in the track data at 90% confidence. Applying our analysis to the unscrambled data reveals no individual nu + gamma events of high significance; two ANTARES track + Fermi gamma-ray events are identified that exceed a once per decade false alarm rate threshold (p = 17%). No evidence for subthreshold nu + gamma source populations is found among the track (p = 39%) or cascade (p = 60%) events. Exploring a possible correlation of high-energy neutrino directions with Fermi gamma-ray sky brightness identified in previous work yields no added support for this correlation. While TXS.0506+056, a blazar and variable (nontransient) Fermi gamma-ray source, has recently been identified as the first source of high-energy neutrinos, the challenges in reconciling observations of the Fermi gamma-ray sky, the IceCube high-energy cosmic neutrinos, and ultrahigh-energy cosmic rays using only blazars suggest a significant contribution by other source populations. Searches for transient sources of high-energy neutrinos thus remain interesting, with the potential for either neutrino clustering or multimessenger coincidence searches to lead to discovery of the first nu + gamma transients.
CRIS-Team WoS Importer:2020-01-03

A search for neutrino emission from the Fermi bubbles with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J; Baret, B.; Barrios-Marti, J.; Basa, S.; et al. (European Physical Journal C, 2014)
Analysis of the Fermi-LAT data has revealed two extended structures above and below the Galactic Centre emitting gamma rays with a hard spectrum, the so-called Fermi bubbles. Hadronic models attempting to explain the origin of the Fermi bubbles predict the emission of high-energy neutrinos and gamma rays with similar fluxes. The ANTARES detector, a neutrino telescope located in the Mediterranean Sea, has a good visibility to the Fermi bubble regions. Using data collected from 2008 to 2011 no statistically significant excess of events is observed and therefore upper limits on the neutrino flux in TeV range from the Fermi bubbles are derived for various assumed energy cutoffs of the source.

A search for Secluded Dark Matter in the Sun with the ANTARES neutrino telescope - Adrián-Martínez, S.; Albert, A.; André, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2016)
A search for Secluded Dark Matter annihilation in the Sun using 2007-2012 data of the ANTARES neutrino telescope is presented. Three different cases are considered: a) detection of dimuons that result from the decay of the mediator, or neutrino detection from: b) mediator that decays into a dimuon and, in turn, into neutrinos, and c) mediator that decays directly into neutrinos. As no significant excess over background is observed, constraints are derived on the dark matter mass and the lifetime of the mediator.
Keywords: dark matter detectors; dark matter experiments; neutrino astronomy; neutrino detectors

A Suzaku, NuSTAR, and XMM-Newton view on variable absorption and relativistic reflection in NGC 4151 - Beuchert, Tobias; Markowitz, A. G.; Dauser, Thomas; Garcia, Javier; Keck, M. L.; Wilms, Jörn; Kadler, M.; Brenneman, L. W.; Zdziarski, A. A. (Astronomy & Astrophysics, 2017)
We disentangle X-ray disk reflection from complex line-of-sight absorption in the nearby Seyfert NGC 4151, using a suite of Suzaku, NuSTAR, and XMM-Newton observations. Extending upon earlier published work, we pursue a physically motivated model using the latest angle-resolved version of the lamp-post geometry reflection model RELXILLCP_LP together with a Comptonization continuum. We use the long-look simultaneous Suzaku/NuSTAR observation to develop a baseline model wherein we model reflected emission as a combination of lamp-post components at the heights of 1.2 and 15.0 gravitational radii. We argue for a vertically extended corona as opposed to two compact and distinct primary sources. We find two neutral absorbers (one full-covering and one partial-covering), an ionized absorber (log xi = 2 : 8), and a highly-ionized ultra-fast outflow, which have all been reported previously. All analyzed spectra are well described by this baseline model. The bulk of the spectral variability between similar to 1 keV and similar to 6 keV can be accounted for by changes in the column density of both neutral absorbers, which appear to be degenerate and inversely correlated with the variable hard continuum component flux. We track variability in absorption on both short (2 d) and long (similar to 1 yr) timescales; the observed evolution is either consistent with changes in the absorber structure (clumpy absorber at distances ranging from the broad line region to the inner torus or a dusty radiatively driven wind) or a geometrically stable neutral absorber that becomes increasingly ionized at a rising flux level. The soft X-rays below 1 keV are dominated by photoionized emission from extended gas that may act as a warm mirror for the nuclear radiation.
Keywords: galaxies: active; galaxies: nuclei; galaxies: individual: NGC4151; galaxies: Seyfert; X-rays: galaxies

A Suzaku X-ray observation of one orbit of the supergiant fast X-ray transient IGR J16479-4514 - Sidoli, Lara; Esposito, Paolo; Sguera, Vito; Bodaghee, A.; Tomsick, J. A.; Pottschmidt, K.; Rodriguez, Jerome; Romano, Patrizia; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2013)
We report on a 250 ks long X-ray observation of the supergiant fast X-ray transient IGR J16479-4514 performed with Suzaku in 2012 February. During this observation, about 80 per cent of the short orbital period (P-orb similar to 3.32 d) was covered as continuously as possible for the first time. The source light curve displays variability of more than two orders of magnitude, starting with a very low emission state (10(-13) erg cm(-2) s(-1); 1-10 keV) lasting the first 46 ks, consistent with being due to the X-ray eclipse by the supergiant companion. The transition to the uneclipsed X-ray emission is energy dependent. Outside the eclipse, the source spends most of the time at a level of 6-7 x 10(-12) erg cm(-2) s(-1) punctuated by two structured faint flares with a duration of about 10 and 15 ks, respectively, reaching a peak flux of 3-4 x 10(-11) erg cm(-2) s(-1), separated by about 0.2 in orbital phase. Remarkably, the first faint flare occurs at a similar orbital phase of the bright flares previously observed in the system. This indicates the presence of a phase-locked large-scale structure in the supergiant wind, driving a higher accretion rate on to the compact object. The average X-ray spectrum is hard and highly absorbed, with a column density, N-H, of 1023 cm-2, clearly in excess of the interstellar absorption. There is no evidence for variability of the absorbing column density, except that during the eclipse, where a less absorbed X-ray spectrum is observed. A narrow Fe K alpha emission line at 6.4 keV is viewed along the whole orbit, with an intensity which correlates with the continuum emission above 7 keV. The scattered component visible during the X-ray eclipse allowed us to directly probe the wind density at the orbital separation, resulting in rho(w) = 7 x 10(-14) g cm(-3). Assuming a spherical geometry for the supergiant wind, the derived wind density translates into a ratio. M-w/v(infinity) = 7 x 10(-17) M-circle dot km(-1) which, assuming terminal velocities in a large range 500-3000 km s(-1), implies an accretion luminosity two orders of magnitude higher than that observed. As a consequence, a mechanism should be at work reducing the mass accretion rate. Different possibilities are discussed.
Keywords: accretion; accretion discs; X-rays: binaries; supergiants; X-rays: individual: IGR J16479-4514

Asymmetric jet production in the active galactic nucleus of NGC 1052 - Baczko, A-K; Schulz, R.; Kadler, M.; Ros, Eduardo; Perucho, M.; Fromm, C. M.; Wilms, Jörn (Astronomy & Astrophysics, 2019)
Context. Few active galactic nuclei (AGN) reveal double-sided jet systems. However, these systems are crucial to understand basic physical properties of extragalactic jets.
CRIS-Team WoS Importer:2019-03-08

Athena Wide Field Imager key science drivers - Rau, Arne; Nandra, Kirpal; Aird, James; Comastri, Andrea; Dauser, Thomas; Merloni, Andrea; Pratt, Gabriel W.; Reiprich, Thomas H.; Fabian, Andy C.; Georgakakis, Antonis; Güdel, Manuel; Rózańska, Agata; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
The Wide Field Imager (WFI) is one of two instruments for the Advanced Telescope for High-ENergy Astrophysics (Athena). In this paper we summarise three of the many key science objectives for the WFI - the formation and growth of supermassive black holes, non-gravitational heating in clusters of galaxies, and spin measurements of stellar mass black holes - and describe their translation into the science requirements and ultimately instrument requirements. The WFI will be designed to provide excellent point source sensitivity and grasp for performing wide area surveys, surface brightness sensitivity, survey power, and absolute temperature and density calibration for in-depth studies of the outskirts of nearby clusters of galaxies and very good high-count rate capability, throughput, and low pile-up, paired with very good spectral resolution, for detailed explorations of bright Galactic compact objects.
Keywords: ATHENA; Wide Field Imager

Athena X-IFU synthetic observations of galaxy clusters to probe the chemical enrichment of the Universe - Cucchetti, E.; Pointecouteau, E.; Peille, P.; Clerc, N.; Rasia, Elena; Biffi, V.; Borgani, S.; Tornatore, L.; Dolag, K.; Roncarelli, M.; Gaspari, M.; Ettori, S.; et al. (Astronomy & Astrophysics, 2018)
Answers to the metal production of the Universe can be found in galaxy clusters, notably within their intra-cluster medium (ICM). The X-ray Integral Field Unit (X-IFU) on board the next-generation European X-ray observatory Athena (2030s) will provide the necessary leap forward in spatially-resolved spectroscopy required to disentangle the intricate mechanisms responsible for this chemical enrichment. In this paper, we investigate the future capabilities of the X-IFU in probing the hot gas within galaxy clusters. From a test sample of four clusters extracted from cosmological hydrodynamical simulations, we present comprehensive synthetic observations of these clusters at different redshifts (up to z <= 2) and within the scaled radius R-500 performed using the instrument simulator SIXTE. Through 100 ks exposures, we demonstrate that the X-IFU will provide spatially resolved mapping of the ICM physical properties with little to no biases ((sic)5%) and well within statistical uncertainties. The detailed study of abundance profiles and abundance ratios within R-500 also highlights the power of the X-IFU in providing constraints on the various enrichment models. From synthetic observations out to z = 2, we have also quantified its ability to track the chemical elements across cosmic time with excellent accuracy, and thereby to investigate the evolution of metal production mechanisms as well as the link to the stellar initial mass-function. Our study demonstrates the unprecedented capabilities of the X-IFU of unveiling the properties of the ICM but also stresses the data analysis challenges faced by future high-resolution X-ray missions such as Athena.
Keywords: galaxies: clusters: intracluster medium; galaxies: abundances; galaxies: fundamental parameters; techniques: imaging spectroscopy; methods: numerical; X-rays: galaxies: clusters

Athena X-ray Integral Field Unit on-board Event Processor: Analysis of performance of two triggering algorithms - Cobo, Beatriz; Teresa Ceballos, Mara; Peille, Philippe; Mesnager, Jean-Michel; Wilms, Jörn; Dauser, Thomas; Kirsch, Christian; Pinsard, Frederic; Cara, Christophe; Gros, Michel; Ravera, Laurent; Bandler, Simon; et al. (2018)
In the framework of the ESA Athena mission, the X-ray Integral Field Unit (X-IFU) micro-calorimeter will provide unprecedented spatially resolved high-resolution X-ray spectroscopy. For this purpose, the on-board Event Processor (EP) must initially trigger the current pulses induced by the X-ray photons hitting the detector to proceed with a reconstruction which provides the arrival time, spatial location and energy of each event. The current event triggering design is implemented in two stages: one initial trigger of the low-pass filtered derivative of the raw data to extract records containing pulses and a second stage performing a fine detection to look for all the pulses in the record. In order to establish the current baseline detection technique of the EP in the X-IFU instrument, an assessment of the capabilities of different triggering algorithms is required, both in terms of performance (detection efficiency) and computational load, as processing will take place on-board. We present a comparison of two detection algorithms, the Simplest Threshold Crossing (STC) and the model-dependent Adjusted Derivative (AD). The analysis also evaluates the (possible) negative effect of different instrumental scenarios as a reduced sampling rate. The evaluations point out that the simplest algorithm STC shows worse performance than AD for the smallest pulses separations and the lowest secondary energies. Nevertheless, checking the expected number of such pulses combinations in a typical bright source observation, we conclude that it does not have impact in the science. Moreover, the savings in the computational resources and calibration needs make STC a valuable option.
Keywords: Athena; X-ray Integral Field Unit; X-ray spectroscopy; space telescopes; instrumentation; Event Processor; pulse detection; performance analysis

A variable-density absorption event in NGC 3227 mapped with Suzaku and Swift - Beuchert, Tobias; Markowitz, Alex; Krauß, Felicia; Miniutti, Giovanni; Longinotti, A. L.; Guainazzi, M.; De La Calle Perez, Ignacio; Malkan, M.; Elvis, M.; Miyaji, Takamitsu; Hiriart, David; Lopez, J. M.; et al. (Astronomy & Astrophysics, 2015)
Context. The morphology of the circumnuclear gas accreting onto supermassive black holes in Seyfert galaxies remains a topic of much debate. As the innermost regions of active galactic nuclei (AGN) are spatially unresolved, X-ray spectroscopy, and in particular line-of-sight absorption variability, is a key diagnostic to map out the distribution of gas.Aims. Observations of variable X-ray absorption in multiple Seyferts and over a wide range of timescales indicate the presence of clumps/clouds of gas within the circumnuclear material. Eclipse events by clumps transiting the line of sight allow us to explore the properties of the clumps over a wide range of radial distances from the optical/UV broad line region (BLR) to beyond the dust sublimation radius. Time-resolved absorption events have been extremely rare so far, but suggest a range of density profiles across Seyferts. We resolve a weeks-long absorption event in the Seyfert NGC 3227.Methods. We examine six Suzaku and 12 Swift observations from a 2008 campaign spanning five weeks. We use a model accounting for the complex spectral interplay of three absorbers with different levels of ionization. We perform time-resolved spectroscopy to discern the absorption variability behavior. We also examine the IR to X-ray spectral energy distribution (SED) to test for reddening by dust.Results. The 2008 absorption event is due to moderately-ionized (log xi similar to 1.2-1.4) gas covering 90% of the line of sight. We resolve the density profile to be highly irregular, in contrast to a previous symmetric and centrally-peaked event mapped with RXTE in the same object. The UV data do not show significant reddening, suggesting that the cloud is dust-free.Conclusions. The 2008 campaign has revealed a transit by a filamentary, moderately-ionized cloud of variable density that is likely located in the BLR, and possibly part of a disk wind.
Keywords: galaxies: active; galaxies: Seyfert; galaxies: nuclei

A Wolf-Rayet/black-hole X-ray binary candidate in NGC 300 - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Context. Wolf Rayet/black hole binaries are believed to exist as a later evolutionary product of high-mass X-ray binaries. Hundreds of such binaries may exist in galaxies, but only a few of them are close enough to be observed as X-ray binaries. Only a couple of candidates have been reported so far.Aims. Based on XMM-Newton observations, we report the positional coincidence of the brightest X-ray source in NGC 300 (NGC 300 X-1) with a Wolf-Rayet candidate. Temporal and spectral analysis of the X-ray source is performed.Methods. We determine an accurate X-ray position of the object, and derive light curves, spectra and flux in four XMM-Newton observations.Results. The positions of the X-ray source and the helium star candidate coincide within 0".11 +/- 0".45. The X-ray light curves show irregular variability. During one XMM-Newton observation, the flux increased by about a factor of ten in 10 h. The spectrum can be modelled by a power-law with Gamma similar to 2.45 with additional relatively weak line emission, notably around 0.95 keV. The mean observed (absorbed) luminosity in the 0.2-10 keV band is similar to 2 x 10(38) erg s(-1).Conclusions. NGC 300 X-1 is a good candidate for a Wolf-Rayet/black-hole X-ray binary: its position coincides with a Wolf-Rayet candidate and the unabsorbed X-ray luminosity reached L0.2-10 keV similar to 1 x 10(39) erg s(-1), suggesting the presence of a black hole.
Keywords: galaxies : individual : NGC 300; X-rays : binaries; stars : Wolf-Rayet

Black hole lightning due to particle acceleration at subhorizon scales - Aleksic, J.; Ansoldi, S.; Antonelli, L. A.; Antoranz, Pedro; Babic, A.; Bangale, P.; Barrio, J. A.; Becerra Gonzalez, Josefa; Bednarek, Wlodek; Bernardini, E.; Biasuzzi, B.; Biland, A.; et al. (Science, 2014)
Supermassive black holes with masses of millions to billions of solar masses are commonly found in the centers of galaxies. Astronomers seek to image jet formation using radio interferometry but still suffer from insufficient angular resolution. An alternative method to resolve small structures is to measure the time variability of their emission. Here we report on gamma-ray observations of the radio galaxy IC 310 obtained with the MAGIC (Major Atmospheric Gamma-ray Imaging Cherenkov) telescopes, revealing variability with doubling time scales faster than 4.8 min. Causality constrains the size of the emission region to be smaller than 20% of the gravitational radius of its central black hole. We suggest that the emission is associated with pulsar-like particle acceleration by the electric field across a magnetospheric gap at the base of the radio jet.

BROADBAND SPECTROSCOPY USING TWO SUZAKU OBSERVATIONS OF THE HMXB GX 301-2 - Suchy, Slawomir; Fürst, Felix; Pottschmidt, Katja; Caballero, Isabel; Kreykenbohm, Ingo; Wilms, Jörn; Markowitz, Alex; Rothschild, Richard E. (Astrophysical Journal, 2012)
We present the analysis of two Suzaku observations of GX 301-2 at two orbital phases after the periastron passage. Variations in the column density of the line-of-sight absorber are observed, consistent with accretion from a clumpy wind. In addition to a cyclotron resonance scattering feature (CRSF), multiple fluorescence emission lines were detected in both observations. The variations in the pulse profiles and the CRSF throughout the pulse phase have a signature of a magnetic dipole field. Using a simple dipole model we calculated the expected magnetic field values for different pulse phases and were able to extract a set of geometrical angles, loosely constraining the dipole geometry in the neutron star. From the variation of the CRSF width and energy, we found a geometrical solution for the dipole, making the inclination consistent with previously published values.
Keywords: pulsars: individual (GX 301-2); stars: magnetic field; X-rays: binaries; X-rays: stars

Broad emission lines for a negatively spinning black hole - Dauser, Thomas; Wilms, Jörn; Reynolds, C. S.; Brenneman, L. W. (Monthly Notices of the Royal Astronomical Society, 2010)
We present an extended scheme for the calculation of the profiles of emission lines from accretion discs around rotating black holes. The scheme includes discs with angular momenta which are parallel and antiparallel with respect to the black hole's angular momentum, as both configurations are assumed to be stable. We discuss line shapes for such discs and present a code for modelling observational data with this scheme in X-ray data analysis programs. Based on a Green's function approach, an arbitrary radius dependence of the disc emissivity and arbitrary limb-darkening laws can be easily taken into account, while the amount of pre-computed data is significantly reduced with respect to other available models.
Keywords: accretion; accretion discs; black hole physics; line: profiles; galaxies: active; galaxies: nuclei

Calibration aspects of the JEM-EUSO mission - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, Anna; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The JEM-EUSO telescope will be, after calibration, a very accurate instrument which yields the number of received photons from the number of measured photo-electrons. The project is in phase A (demonstration of the concept) including already operating prototype instruments, i.e. many parts of the instrument have been constructed and tested. Calibration is a crucial part of the instrument and its use. The focal surface (FS) of the JEM-EUSO telescope will consist of about 5000 photo-multiplier tubes (PMTs), which have to be well calibrated to reach the required accuracy in reconstructing the air-shower parameters. The optics system consists of 3 plastic Fresnel (double-sided) lenses of 2.5 m diameter. The aim of the calibration system is to measure the efficiencies (transmittances) of the optics and absolute efficiencies of the entire focal surface detector. The system consists of 3 main components: (i) Pre-flight calibration devices on ground, where the efficiency and gain of the PMTs will be measured absolutely and also the transmittance of the optics will be. (ii) On-board relative calibration system applying two methods: a) operating during the day when the JEM-EUSO lid will be closed with small light sources on board. b) operating during the night, together with data taking: the monitoring of the background rate over identical sites. (iii) Absolute in-flight calibration, again, applying two methods: a) measurement of the moon light, reflected on high altitude, high albedo clouds. b) measurements of calibrated flashes and tracks produced by the Global Light System (GLS). Some details of each calibration method will be described in this paper.
Keywords: Air-Shower fluorescence telescope; JEM-EUSO; Calibration; Space-Based experiment

Calorimetric neutrino expectations from bright blazar flares - Kreter, Michael; Kadler, Matthias; Krauß, Felicia; Buson, Sara; Ojha, Roopesh; Mannheim, Karl; Wilms, Jörn; Böttcher, Markus (Proceedings of Science, 2019)
Blazar jets are extreme environments, in which relativistic proton interactions with an ultraviolet photon field could give rise to photopion production. High-confidence associations of individual high-energy neutrinos with blazar flares could be achieved via spatially and temporally coincident detections. In 2017, the track-like, extremely high-energy neutrino event IC 170922A was found to coincide with increased γ-ray emission from the blazar TXS 0506+056, leading to the identification of the most promising neutrino source candidate so far. We test the chance coincidence of such events by calculating the expected number of neutrinos that can be detected by IceCube, based on a broadband parametrization of bright short-term blazar flares that were observed in the past 8 years by Fermi/LAT. We find that the integrated keV-to-GeV fluence of most individual blazar flares is far too small to yield a substantial Poisson probability for the detection of one or more neutrinos with IceCube. In contrast to such short-term flares that usually last only a few days or less, TXS0506+056 did show a major outburst that lasted several months, giving rise to a much higher fluence than most short blazar flares. We show, based on the calorimetric argumentation presented in this work, that the association of the IC 170922A neutrino with TXS 0506+056 is energetically plausible at a significance level of about 3.5 sigma. We further discuss strategies to search for more significant associations in future data unblindings of IceCube and KM3NeT.
CRIS-Team Scopus Importer:2021-04-20

Chandra-HETGS Characterization of an Outflowing Wind in the Accreting Millisecond Pulsar IGR J17591-2342 - Nowak, Michael A.; Paizis, Adamantia; Jaisawal, Gaurava Kumar; Chenevez, Jerome; Chaty, Sylvain; Fortin, Francis; Rodriguez, Jerome; Wilms, Jörn (Astrophysical Journal, 2019)
An accreting millisecond X-ray pulsar, IGR J17591-2342 was discovered in 2018 August in scans of the Galactic bulge and center by the International Gamma-Ray Astrophysics Laboratory X-ray and gamma-ray observatory. It exhibited an unusual outburst profile with multiple peaks in the X-ray, as observed by several X-ray satellites over 3 months. Here we present observations of this source performed in the X-ray / gamma-ray and near-infrared domains and focus on a simultaneous observation performed with the Chandra High Energy Transmission Gratings Spectrometer (HETGS) and the Neutron Star Interior Composition Explorer (NICER). The HETGS provides high-resolution spectra of the Si edge region that yield clues as to the source's distance and reveal evidence (at 99.999% significance) of an outflow with a velocity of 2800 km s(-1). We demonstrate good agreement between the NICER and HETGS continua, provided that one properly accounts for the differing manners in which these instruments view the dust-scattering halo in the source's foreground. Unusually, we find a possible set of Ca lines in the HETGS spectra (with significances ranging from 97.0% to 99.7%). We hypothesize that IGR. J17591-2342 is a neutron star low-mass X-ray binary at the distance of the Galactic bulge or beyond that may have formed from the collapse of a white dwarf system in a rare, calcium-rich Type Ib supernova explosion.
CRIS-Team WoS Importer:2019-04-09

Chandra Spectral and Timing Analysis of Sgr A∗'s Brightest X-Ray Flares - Haggard, Daryl; Nynka, Melania; Mon, Brayden; Hernandez, Noelia De La Cruz; Nowak, Michael; Heinke, Craig; Neilsen, Joseph; Dexter, Jason; Fragile, P. Chris; Baganoff, Fred; Bower, Geoffrey C.; Corrales, Lia R.; et al. (Astrophysical Journal, 2019)
We analyze the two brightest Chandra X-ray flares detected from Sagittarius A∗, with peak luminosities more than 600 and 245 greater than the quiescent X-ray emission. The brightest flare has a distinctive double-peaked morphology - it lasts 5.7 ks (∼2 hr), with a rapid rise time of 1500 s and a decay time of 2500 s. The second flare lasts 3.4 ks, with rise and decay times of 1700 and 1400 s. These luminous flares are significantly harder than quiescence: the first has a power-law spectral index Γ = 2.06 0.14 and the second has Γ = 2.03 0.27, compared to Γ = 3.0 0.2 for the quiescent accretion flow. These spectral indices (as well as the flare hardness ratios) are consistent with previously detected Sgr A∗ flares, suggesting that bright and faint flares arise from similar physical processes. Leveraging the brightest flare's long duration and high signal-to-noise, we search for intraflare variability and detect excess X-ray power at a frequency of ν ≈ 3 mHz, but show that it is an instrumental artifact and not of astrophysical origin. We find no other evidence (at the 95% confidence level) for periodic or quasi-periodic variability in either flares' time series. We also search for nonperiodic excess power but do not find compelling evidence in the power spectrum. Bright flares like these remain our most promising avenue for identifying Sgr A∗'s short timescale variability in the X-ray, which may probe the characteristic size scale for the X-ray emission region.
CRIS-Team Scopus Importer:2021-04-20

Chandra X-ray spectroscopy of focused wind in the Cygnus X-1 system. II. The non-dip spectrum in the low/hard state - modulations with orbital phase - Miskovicova, Ivica; Hell, Natalie; Hanke, Manfred; Nowak, Michael A.; Pottschmidt, Katja; Schulz, Norbert S.; Grinberg, Victoria; Duro, Refiz; Madej, Oliwia K.; Lohfink, Anne M.; Rodriguez, Jerome; Bel, Marion Cadolle; et al. (Astronomy & Astrophysics, 2016)
Accretion onto the black hole in the system HDE 226868/Cygnus X-1 is powered by the strong line-driven stellar wind of the O-type donor star. We study the X-ray properties of the stellar wind in the hard state of Cyg X-1, as determined using data from the Chandra High Energy Transmission Gratings. Large density and temperature inhomogeneities are present in the wind, with a fraction of the wind consisting of clumps of matter with higher density and lower temperature embedded in a photoionized gas. Absorption dips observed in the light curve are believed to be caused by these clumps. This work concentrates on the non-dip spectra as a function of orbital phase. The spectra show lines of H-like and He-like ions of S, Si, Na, Mg, Al, and highly ionized Fe (Fe xvii-Fe xxiv). We measure velocity shifts, column densities, and thermal broadening of the line series. The excellent quality of these five observations allows us to investigate the orbital phase-dependence of these parameters. We show that the absorber is located close to the black hole. Doppler shifted lines point at a complex wind structure in this region, while emission lines seen in some observations are from a denser medium than the absorber. The observed line profiles are phase-dependent. Their shapes vary from pure, symmetric absorption at the superior conjunction to P Cygni profiles at the inferior conjunction of the black hole.
Keywords: Accretion; accretion disks; Stars: individual: Cyg X-1; Stars: individual: HDE 226868; Stars: winds; outflows; X-rays: binaries

Chandra X-ray spectroscopy of the focused wind in the Cygnus X-1 system III. Dipping in the low/hard state - Hirsch, Maria; Hell, Natalie; Grinberg, Victoria; Ballhausen, Ralf; Nowak, Michael A.; Pottschmidt, Katja; Schulz, Norbert S.; Dauser, Thomas; Hanke, Manfred; Kallman, Timothy R.; Brown, Gregory; Wilms, Jörn (Astronomy & Astrophysics, 2019)
We present an analysis of three Chandra High Energy Transmission Gratings observations of the black hole binary Cyg X-1/HDE 226868 at different orbital phases. The stellar wind that is powering the accretion in this system is characterized by temperature and density inhomogeneities including structures, or "clumps", of colder, more dense material embedded in the photoionized gas. As these clumps pass our line of sight, absorption dips appear in the light curve. We characterize the properties of the clumps through spectral changes during various dip stages. Comparing the silicon and sulfur absorption line regions (1.6-2.7 keV 7.7-4.6 angstrom) in four levels of varying column depth reveals the presence of lower ionization stages, i.e., colder or denser material, in the deeper dip phases. The Doppler velocities of the lines are roughly consistent within each observation, varying with the respective orbital phase. This is consistent with the picture of a structure that consists of differently ionized material, in which shells of material facing the black hole shield the inner and back shells from the ionizing radiation. The variation of the Doppler velocities compared to a toy model of the stellar wind, however, does not allow us to pin down an exact location of the clump region in the system. This result, as well as the asymmetric shape of the observed lines, point at a picture of a complex wind structure.
CRIS-Team WoS Importer:2019-06-28

CHANDRA X-RAY SPECTROSCOPY OF THE FOCUSED WIND IN THE CYGNUS X-1 SYSTEM. I. THE NONDIP SPECTRUM IN THE LOW/HARD STATE - Hanke, Manfred; Wilms, Jörn; Nowak, Michael A.; Pottschmidt, Katja; Schulz, Norbert S.; Lee, Julia C. (Astrophysical Journal, 2009)
We present analyses of a 50 ks observation of the supergiant X-ray binary system Cygnus X-1 (Cyg X-1)/HDE226868 taken with the Chandra High Energy Transmission Grating Spectrometer (HETGS). Cyg X-1 was in its spectrally hard state and the observation was performed during superior conjunction of the black hole, allowing for the spectroscopic analysis of the accreted stellar wind along the line of sight. A significant part of the observation covers X-ray dips as commonly observed for Cyg X-1 at this orbital phase, however, here we analyze only the high count rate nondip spectrum. The full 0.5-10 keV continuum can be described by a single model consisting of a disk, a narrow and a relativistically broadened Fe K alpha line, and a power-law component, which is consistent with simultaneous Rossi X-Ray Timing Explorer broadband data. We detect absorption edges from overabundant neutral O, Ne, and Fe, and absorption line series from highly ionized ions and infer column densities and Doppler shifts. With emission lines of He-like Mg XI, we detect two plasma components with velocities and densities consistent with the base of the spherical wind and a focused wind. A simple simulation of the photoionization zone suggests that large parts of the spherical wind outside of the focused stream are completely ionized, which is consistent with the low velocities (<200 km s(-1)) observed in the absorption lines, as the position of absorbers in a spherical wind at low projected velocity is well constrained. Our observations provide input for models that couple the wind activity of HDE 226868 to the properties of the accretion flow onto the black hole.
Keywords: accretion; accretion disks; stars: individual (HDE 226868; Cyg X-1); stars: winds; outflows; techniques: spectroscopic; X-rays: binaries

Characterisation of the Hamamatsu photomultipliers for the KM3NeT Neutrino Telescope - Aiello, S.; Akrame, S. E.; Ameli, F.; Anassontzis, E. G.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Avgitas, T.; Baars, M.; et al. (Journal of Instrumentation, 2018)
The Hamamatsu R12199-023-inch photomultiplier tube is the photodetector chosen for the first phase of the KM3NeT neutrino telescope. About 7000 photomultipliers have been characterised for dark count rate, timing spread and spurious pulses. The quantum efficiency, the gain and the peak-to-valley ratio have also been measured for a sub-sample in order to determine parameter values needed as input to numerical simulations of the detector.
Keywords: Cherenkov detectors; Large detector systems for particle and astroparticle physics; Neutrino detectors; Photon detectors for UV; visible and IR photons (vacuum)

Characterization of the Particle-induced Background of XMM-Newton EPIC-pn: Short- and Long-term Variability - Bulbul, Esra; Kraft, Ralph; Nulsen, Paul; Freyberg, Michael; Miller, Eric D.; Grant, Catherine; Bautz, Mark W.; Burrows, David N.; Allen, Steven; Eraerds, Tanja; Fioretti, Valentina; Gasteldello, Fabio; et al. (Astrophysical Journal, 2020)
The particle-induced background of X-ray observatories is produced by galactic cosmic ray (GCR) primary protons, electrons, and He ions. Events due to direct interaction with the detector are usually removed by onboard processing. The interactions of these primary particles with the detector environment produce secondary particles that mimic X-ray events from celestial sources, and are much more difficult to identify. The filter-wheel closed data from the XMM-Newton EPIC-pn camera in small window mode (SWM) contains both the X-ray-like background events, and the events due to direct interactions with the primary particles. From this data, we demonstrate that X-ray-like background events are spatially correlated with the primary particle interaction. This result can be used to further characterize and reduce the non-X-ray background in silicon-based X-ray detectors in current and future missions. We also show that spectrum and pattern fractions of secondary particle events are different from those produced by cosmic X-rays.
CRIS-Team WoS Importer:2020-06-19

Coincidence of a high-fluence blazar outburst with a PeV-energy neutrino event - Kadler, Matthias; Krauss, Felicia; Mannheim, K.; Ojha, R.; Mueller, C.; Schulz, R.; Anton, Gisela; Baumgartner, W.; Beuchert, T.; Buson, S.; Carpenter, B.; Eberl, Thomas; et al. (Nature Physics, 2016)
The astrophysical sources of the extraterrestrial, very high-energy neutrinos detected by the IceCube collaboration remain to be identified. Gamma-ray (3-ray) blazars have been predicted to yield a cumulative neutrino signal exceeding the atmospheric background above energies of 100 TeV, assuming that both the neutrinos and the 3-ray photons are produced by accelerated protons in relativistic jets. As the background spectrum falls steeply with increasing energy, the individual events with the clearest signature of being of extraterrestrial origin are those at petaelectronvolt energies. Inside the large positional-uncertainty fields of the first two petaelectronvolt neutrinos detected by IceCube, the integrated emission of the blazar population has a sufficiently high electromagnetic flux to explain the detected IceCube events, but fluences of individual objects are too low to make an unambiguous source association. Here, we report that a major outburst of the blazar PKS B1424-418 occurred in temporal and positional coincidence with a third petaelectronvolt-energy neutrino event (HESE-35) detected by IceCube. On the basis of an analysis of the full sample of 3-ray blazars in the HESE-35 field, we show that the long-term average 3-ray emission of blazars as a class is in agreement with both the measured all-sky flux of petaelectronvolt neutrinos and the spectral slope of the IceCube signal. The outburst of PKS B1424-418 provides an energy output high enough to explain the observed petaelectronvolt event, suggestive of a direct physical association.

Combined search for neutrinos from dark matter self-annihilation in the Galactic Center with ANTARES and IceCube - Albert, A.; Andre, M.; Domi, Alba; Anghinolfi, M.; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, Simone; et al. (Physical Review D, 2020)
We present the results of the first combined dark matter search targeting the Galactic Center using the ANTARES and IceCube neutrino telescopes. For dark matter particles with masses from 50 to 1000 GeV, the sensitivities on the self-annihilation cross section set by ANTARES and IceCube are comparable, making this mass range particularly interesting for a joint analysis. Dark matter self-annihilation through the tau(+)tau(-) , mu(+)mu(-) , b (b) over bar, and W+W- channels is considered for both the Navarro-Frenk-White and Burkert halo profiles. In the combination of 2101.6 days of ANTARES data and 1007 days of IceCube data, no excess over the expected background is observed. Limits on the thermally averaged dark matter annihilation cross section are set. These limits present an improvement of up to a factor of 2 in the studied dark matter mass range with respect to the individual limits published by both collaborations. When considering dark matter particles with a mass of 200 GeV annihilating through the tau(+)tau(-)channel, the value obtained for the limit is 7.44 x 10(-24) cm(3) s(-1 )for the Navarro-Frenk-White halo profile. For the purpose of this joint analysis, the model parameters and the likelihood are unified, providing a benchmark for forthcoming dark matter searches performed by neutrino telescopes.
CRIS-Team WoS Importer:2020-11-13

Confirming the thermal Comptonization model for black hole X-ray emission in the low-hard state - Castro, M.; D'Amico, F.; Braga, J.; Maiolino, T.; Pottschmidt, K.; Wilms, Jörn (Astronomy & Astrophysics, 2014)
Hard X-ray spectra of black hole binaries in the low/hard state are well modeled by thermal Comptonization of soft seed photons by a corona-type region with kT similar to 50 keV and optical depth around 1. Previous spectral studies of 1E 1740.7-2942, including both the soft and the hard X-ray bands, were always limited by gaps in the spectra or by a combination of observations with imaging and non-imaging instruments. In this study, we have used three rare nearly-simultaneous observations of 1E 1740.7-1942 by both XMM-Newton and INTEGRAL satellites to combine spectra from four different imaging instruments with no data gaps, and we successfully applied the Comptonization scenario to explain the broadband X-ray spectra of this source in the low/hard state. For two of the three observations, our analysis also shows that, models including Compton reflection can adequately fit the data, in agreement with previous reports. We show that the observations can also be modeled by a more detailed Comptonization scheme. Furthermore, we find the presence of an iron K-edge absorption feature in one occasion, which confirms what had been previously observed by Suzaku. Our broadband analysis of this limited sample shows a rich spectral variability in 1E 1740.7 2942 at the low/hard state, and we address the possible causes of these variations. More simultaneous soft/hard X-ray observations of this system and other black-hole binaries would be very helpful in constraining the Comptonization scenario and shedding more light on the physics of these systems.
Keywords: radiation mechanisms: non-thermal; radiation mechanisms: thermal; X-rays: stars

Constraining jet/disc geometry and radiative processes in stellar black holes XTE J1118+480 and GX 339-4 - Maitra, Dipankar; Markoff, Sera; Brocksopp, Catherine; Noble, Michael; Nowak, Michael; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2009)
We present results from modelling of quasi-simultaneous broad-band (radio through X-ray) observations of the Galactic stellar black hole (BH) transient X-ray binary (XRB) systems XTE J1118+480 and GX 339-4 using an irradiated disc + compact jet model. In addition to quantifying the physical properties of the jet, we have developed a new irradiated disc model which also constrains the geometry and temperature of the outer accretion disc by assuming a disc heated by viscous energy release and X-ray irradiation from the inner regions. For the source XTE J1118+480, which has better spectral coverage of the two in optical and near-infrared (OIR) wavelengths, we show that the entire broad-band continuum can be well described by an outflow-dominated model + an irradiated disc. The best-fitting radius of the outer edge of the disc is consistent with the Roche lobe geometry of the system, and the temperature of the outer edge of the accretion disc is similar to those found for other XRBs. Irradiation of the disc by the jet is found to be negligible for this source. For GX 339-4, the entire continuum is well described by the jet-dominated model only, with no disc component required. For the two XRBs, which have very different physical and orbital parameters and were in different accretion states during the observations, the sizes of the jet base are similar and both seem to prefer a high fraction of non-thermal electrons in the acceleration/shock region and a magnetically dominated plasma in the jet. These results, along with recent similar results from modelling other galactic XRBs and AGNs, may suggest an inherent unity in diversity in the geometric and radiative properties of compact jets from accreting black holes.
Keywords: accretion; accretion discs; black hole physics; radiation mechanisms: general; stars: winds; outflows; X-rays: individual: GX 339-4; X-rays: individual: J1118+480

Constraining the contribution of Gamma-Ray Bursts to the high-energy diffuse neutrino flux with 10 yr of ANTARES data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, S.; et al. (Monthly Notices of the Royal Astronomical Society, 2021)
Addressing the origin of the astrophysical neutrino flux observed by IceCube is of paramount importance. Gamma-Ray Bursts (GRBs) are among the few astrophysical sources capable of achieving the required energy to contribute to such neutrino flux through p gamma interactions. In this work, ANTARFS data have been used to search for upward going muon neutrinos in spatial and temporal coincidence with 784 GRBs occurred from 2007 to 2017. For each GRB, the expected neutrino flux has been calculated in the framework of the internal shock model and the impact of the lack of knowledge on the majority of source redshifts and on other intrinsic parameters of the emission mechanism has been quantified. It is found that the model parameters that set the radial distance where shock collisions occur have the largest impact on neutrino flux expectations. In particular, the bulk Lorentz factor of the source ejecta and the minimum variability time-scale are found to contribute significantly to the GRB-neutrino flux uncertainty. For the selected sources, ANTARES data have been analysed by maximizing the discovery probability of the stacking sample through an extended maximum-likelihood strategy. Since no neutrino event passed the quality cuts set by the optimization procedure, 90 per cent confidence level upper limits (with their uncertainty) on the total expected diffuse neutrino flux have been derived, according to the model. The GRB contribution to the observed diffuse astrophysical neutrino flux around 100 TeV is constrained to be less than 10 percent.
CRIS-Team WoS Importer:2021-01-29

Constraining the neutrino emission of gravitationally lensed Flat-Spectrum Radio Quasars with ANTARES data - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagii, S.; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2014)
This paper proposes to exploit gravitational lensing effects to improve the sensitivity of neutrino telescopes to the intrinsic neutrino emission of distant blazar populations. This strategy is illustrated with a search for cosmic neutrinos in the direction of four distant and gravitationally lensed Flat-Spectrum Radio Quasars. The magnification factor is estimated for each system assuming a singular isothermal profile for the lens. Based on data collected from 2007 to 2012 by the ANTARES neutrino telescope, the strongest constraint is obtained from the lensed quasar B0218+357, providing a limit on the total neutrino luminosity of this source of 1.08 x 10(46) erg s(-1) This limit is about one order of magnitude lower than those previously obtained in the ANTARES standard point source searches with non-lensed Flat-Spectrum Radio Quasars.
Keywords: gravitational lensing; neutrino astronomy

Constraining the origin and models of chemical enrichment in galaxy clusters using the Athena X-IFU - Mernier, F.; Cucchetti, E.; Tornatore, L.; Biffi, V.; Pointecouteau, E.; Clerc, N.; Peille, P.; Rasia, Elena; Barret, Didier; Borgani, Stefano; Bulbul, E.; Dauser, Thomas; et al. (Astronomy & Astrophysics, 2020)
Chemical enrichment of the Universe at all scales is related to stellar winds and explosive supernovae phenomena. Metals produced by stars and later spread throughout the intracluster medium (ICM) at the megaparsec scale become a fossil record of the chemical enrichment of the Universe and of the dynamical and feedback mechanisms determining their circulation. As demonstrated by the results of the soft X-ray spectrometer onboard Hitomi, high-resolution X-ray spectroscopy is the path to differentiating among the models that consider different metal-production mechanisms, predict the outcoming yields, and are a function of the nature, mass, and/or initial metallicity of their stellar progenitor. Transformational results shall be achieved through improvements in the energy resolution and effective area of X-ray observatories, allowing them to detect rarer metals (e.g. Na, Al) and constrain yet-uncertain abundances (e.g. C, Ne, Ca, Ni). The X-ray Integral Field Unit (X-IFU) instrument onboard the next-generation European X-ray observatory Athena is expected to deliver such breakthroughs. Starting from 100 ks of synthetic observations of 12 abundance ratios in the ICM of four simulated clusters, we demonstrate that the X-IFU will be capable of recovering the input chemical enrichment models at both low (z = 0.1) and high (z = 1) redshifts, while statistically excluding more than 99.5% of all the other tested combinations of models. By fixing the enrichment models which provide the best fit to the simulated data, we also show that the X-IFU will constrain the slope of the stellar initial mass function within ∼12%. These constraints will be key ingredients in our understanding of the chemical enrichment of the Universe and its evolution.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Galaxies: abundances; Galaxies: clusters: intracluster medium; Galaxies: fundamental parameters; Methods: numerical; Supernovae: general; X-rays: galaxies: clusters

Constraints on the neutrino emission from the Galactic Ridge with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Physics Letters B, 2016)
A highly significant excess of high-energy astrophysical neutrinos has been reported by the IceCube Collaboration. Some features of the energy and declination distributions of IceCube events hint at a North/South asymmetry of the neutrino flux. This could be due to the presence of the bulk of our Galaxy in the Southern hemisphere. The ANTARES neutrino telescope, located in the Mediterranean Sea, has been taking data since 2007. It offers the best sensitivity to muon neutrinos produced by galactic cosmic ray interactions in this region of the sky. In this letter a search for an extended neutrino flux from the Galactic Ridge region is presented. Different models of neutrino production by cosmic ray propagation are tested. No excess of events is observed and upper limits for different neutrino flux spectral indices Γ are set. For Γ=2.4 the 90% confidence level flux upper limit at 100 TeV for one neutrino flavour corresponds to Φ (100 TeV)=2.0⋅10 GeVcmssr. Under this assumption, at most two events of the IceCube cosmic candidates can originate from the Galactic Ridge. A simple power-law extrapolation of the Fermi-LAT flux to account for IceCube High Energy Starting Events is excluded at 90% confidence level.
Keywords: ANTARES; Diffuse muon neutrino flux; Neutrino telescope

Constraints on the winds of hot subdwarf stars from X-ray observations of two sdB binaries with compact companions: CD-30 degrees 11223 and PG 1232-136 - Mereghetti, Sandro; La Palombara, Nicola; Esposito, Paolo; Gastaldello, Fabio; Tiengo, A.; Heber, Ulrich; Geier, Stephan; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2014)
Little observational data are available on the weak stellar winds of hot subdwarf stars of B spectral type (sdB). Close binary systems composed of an sdB star and a compact object (white dwarf, neutron star or black hole) could be detected as accretion-powered X-ray sources. The study of their X-ray emission can probe the properties of line-driven winds of sdB stars that cannot be derived directly from spectroscopy because of the low luminosity of these stars. Here we report on the first sensitive X-ray observations of two sdB binaries with compact companions. CD -30A degrees A 11223 is the sdB binary with the shortest known orbital period (1.2 h) and its companion is certainly a white dwarf. PG 1232-136 is an sdB binary considered the best candidate to host a black hole companion. We observed these stars with XMM-Newton in 2013 August for 50 ks and in 2009 July for 36 ks, respectively. None of them was detected and we derived luminosity upper limits of similar to 1.5 x 10(29) erg s(-1) for CD -30A degrees A 11223 and similar to 5 x 10(29) erg s(-1) for PG 1232-136. The corresponding mass-loss rate for PG 1232-136 is poorly constrained, owing to the unknown efficiency for black hole accretion. On the other hand, in the case of CD -30A degrees A 11223 we could derive, under reasonable assumptions, an upper limit of similar to 3 x 10(-13) M-aS (TM) yr(-1) on the wind mass-loss rate from the sdB star. This is one of the few observational constraints on the weak winds expected in this class of low-mass hot stars. We also report the results on the X-ray emission from a cluster of galaxies serendipitously discovered in the field of CD -30 degrees 11223.
Keywords: stars: individual: CD-30 11223; PG 1232-136; subdwarfs; stars: winds; outflows; X-rays: binaries; X-rays: galaxies: clusters; X-rays: individual: XMMU J141057.7-305132

Continued decay in the cyclotron line energy in Hercules X-1 - Staubert, R.; Klochkov, D.; Vybornov, V.; Wilms, Jörn; Harrison, F. A. (Astronomy & Astrophysics, 2016)
The centroid energy E of the cyclotron line in the spectrum of the binary X-ray pulsar Her X-1 has been found to decrease with time on a time scale of a few tens of years - surprisingly short in astrophysical terms. This was found for the pulse phase-averaged line centroid energy using observational data from various X-ray satellites over the time period 1996 to 2012, establishing a reduction of ∼4 keV. Here we report on the result of a new observation by NuSTAR performed in August 2015. The earlier results are confirmed and strengthened with respect to both the dependence of E on flux (it is still present after 2006) and the dependence on time: the long-term decay continued with the same rate, corresponding to a reduction of ∼5 keV in 20 yr.
Keywords: Accretion; accretion disks; Magnetic fields; Radiation mechanisms: general; Radiation mechanisms: non-thermal; Stars: neutron; X-rays: binaries

CORONA, JET, AND RELATIVISTIC LINE MODELS FOR SUZAKU/RXTE/CHANDRA-HETG OBSERVATIONS OF THE CYGNUS X-1 HARD STATE - Nowak, Michael A.; Hanke, Manfred; Trowbridge, Sarah N.; Markoff, Sera B.; Wilms, Jörn; Pottschmidt, Katja; Coppi, Paolo; Maitra, Dipankar; Davis, John E.; Tramper, Frank (Astrophysical Journal, 2011)
Using Suzaku and the Rossi X-ray Timing Explorer (RXTE), we have conducted a series of four simultaneous observations of the galactic black hole candidate Cyg X-1 in what were historically faint and spectrally hard "low states." Additionally, all of these observations occurred near superior conjunction with our line of sight to the X-ray source passing through the dense phases of the "focused wind" from the mass donating secondary. One of our observations was also simultaneous with observations by the Chandra-High Energy Transmission Grating (HETG). These latter spectra are crucial for revealing the ionized absorption due to the secondary's focused wind. Such absorption is present and must be accounted for in all four spectra. These simultaneous data give an unprecedented view of the 0.8-300 keV spectrum of Cyg X-1, and hence bear upon both corona and X-ray emitting jet models of black hole hard states. Three models fit the spectra well: coronae with thermal or mixed thermal/non-thermal electron populations and jets. All three models require a soft component that we fit with a low temperature disk spectrum with an inner radius of only a few tens of GM/c(2). All three models also agree that the known spectral break at 10 keV is not solely due to the presence of reflection, but each gives a different underlying explanation for the augmentation of this break. Thus, whereas all three models require that there is a relativistically broadened Fe line, the strength and inner radius of such a line is dependent upon the specific model, thus making premature line-based estimates of the black hole spin in the Cyg X-1 system. We look at the relativistic line in detail, accounting for the narrow Fe emission and ionized absorption detected by HETG. Although the specific relativistic parameters of the line are continuum dependent, none of the broad line fits allow for an inner disk radius that is >40 GM/c(2).
Keywords: accretion; accretion disks; black hole physics; radiation mechanisms: non-thermal; X-rays: binaries

Correlated optical, X- ray, and gamma- ray flaring activity seen with INTEGRAL during the 2015 outburst of V404 Cygni - Rodriguez, J.; Bel, M. Cadolle; Alfonso-Garzon, J.; Siegert, T.; Zhang, X. -L.; Grinberg, V.; Savchenko, V.; Tomsick, J. A.; Chenevez, J.; Clavel, M.; Corbel, S.; Diehl, R.; et al. (Astronomy & Astrophysics, 2015)
After 25 years of quiescence, the microquasar V404 Cyg entered a new period of activity in June 2015. This X-ray source is known to undergo extremely bright and variable outbursts seen at all wavelengths. It is therefore an object of prime interest to understand the accretion-ejection connections. These can, however, only be probed through simultaneous observations at several wavelengths. We made use of the INTEGRAL instruments to obtain long, almost uninterrupted observations from 2015 June 20, 15: 50 UTC to June 25, 4: 05 UTC, from the optical V band up to the soft gamma-rays. V404 Cyg was extremely variable in all bands, with the detection of 18 flares with fluxes exceeding 6 Crab (20-40 keV) within three days. The flare recurrence can be as short as similar to 20 min from peak to peak. A model-independent analysis shows that the >6 Crab flares have a hard spectrum. A simple 10-400 keV spectral analysis of the off-flare and flare periods shows that the variation in intensity is likely to be only due to variations of a cut-off power-law component. The optical flares seem to be at least of two different types: one occurring in simultaneity with the X-ray flares, the other showing a delay greater than 10 min. The former could be associated with X-ray reprocessing by either an accretion disk or the companion star. We suggest that the latter are associated with plasma ejections that have also been seen in radio.
Keywords: accretion; accretion disks; X-rays: binaries; radio continuum: stars; stars: black holes; stars: individual: V404 Cygni

Correlated radio-X-ray variability of galactic black holes: A radio-X-ray flare in cygnus X-1 - Wilms, Jörn; et al. (Astrophysical Journal, 2007)
We report on the first detection of a quasi-simultaneous radio-X-ray flare of Cygnus X-1. The detection was made on 2005 April 16 with pointed observations by the RXTE and the Ryle telescope, during a phase where the black hole candidate was close to a transition from its soft state to its hard state. The radio flare lagged the X-rays by similar to 7 minutes, peaking at 3:20 hr barycentric time (TDB 2,453,476.63864). We discuss this lag in the context of models explaining such flaring events as the ejection of electron bubbles emitting synchrotron radiation.
Keywords: accretion; ccretion disks; black hole physics; X-rays : binaries; X-rays : stars

Cosmic ray oriented performance studies for the JEM-EUSO first level trigger - Abdellaoui, Ghouti; Abe, S.; Acheli, A.; Adams, J. H.; Ahmad, S.; Ahriche, A.; Albert, J. -N.; Allard, D.; Alonso, Gustavo; Anchordoqui, L.; Andreev, V.; Anzalone, A.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2017)
JEM-EUSO is a space mission designed to investigate Ultra-High Energy Cosmic Rays and Neutrinos (E > 5.10(19) eV) from the International Space Station (ISS). Looking down from above its wide angle telescope is able to observe their air showers and collect such data from a very wide area. Highly specific trigger algorithms are needed to drastically reduce the data load in the presence of both atmospheric and human activity related background light, yet retain the rare cosmic ray events recorded in the telescope. We report the performance in offline testing of the first level trigger algorithm on data from JEM-EUSO prototypes and laboratory measurements observing different light sources: data taken during a high altitude balloon flight over Canada, laser pulses observed from the ground traversing the real atmosphere, and model landscapes reproducing realistic aspect ratios and light conditions as would be seen from the ISS itself. The first level trigger logic successfully kept the trigger rate within the permissible bounds when challenged with artificially produced as well as naturally encountered night sky background fluctuations and while retaining events with general air-shower characteristics. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: JEM-EUSO; Trigger system; FPGA; Nightglow background

Crosstalk in an FDM Laboratory Setup and the Athena X-IFU End-to-End Simulator - Den Hartog, Roland; Kirsch, Christian; De Vries, C.; Akamatsu, H.; Dauser, Thomas; Peille, P.; Cucchetti, E.; Jackson, B.; Bandler, S.; Smith, Stephen; Wilms, Jörn (SPRINGER/PLENUM PUBLISHERS, 2018)
The impact of various crosstalk mechanisms on the performance of the Athena X-IFU instrument has been assessed with detailed end-to-end simulations. For the crosstalk in the electrical circuit, a detailed model has been developed. In this contribution, we test this model against measurements made with an FDM laboratory setup and discuss the assumption of deterministic crosstalk in the context of the weak link effect in the detectors. We conclude that crosstalk levels predicted by the model are conservative with respect to the observed levels.
Keywords: Athena; X-IFU; TES; FDM; Crosstalk

Cyclotron line energy in Hercules X-1: Stable after the decay - Staubert, R.; Ducci, L.; Ji, L.; Fürst, F.; Wilms, Jörn; Rothschild, R. E.; Pottschmidt, K.; Brumback, M.; Harrison, F. (Astronomy & Astrophysics, 2020)
We summarize the results of a dedicated effort made between 2012 and 2019 to follow the evolution of the cyclotron line in Her X-1 through repeated NuSTAR observations. The previously observed nearly 20-year-long decay of the cyclotron line energy has ended in 2012: from then on, the pulse-phase-averaged flux-corrected cyclotron line energy has remained stable and constant at an average value of Ecyc = (37.44 ± 0.07) keV (normalized to a flux level of 6.8 RXTE/ASM-cts s-1). The flux dependence of Ecyc discovered in 2007 is now measured with high precision, giving a slope of (0.675 ± 0.075) keV/(ASM-cts s-1), corresponding to an increase of 6.5% of Ecyc for an increase in flux by a factor of two. We also find that all line parameters as well as the continuum parameters show a correlation with X-ray flux. While a correlation between Ecyc and X-ray flux (both positive and negative) is now known for several accreting binaries with various suggestions for the underlying physics, the phenomenon of a long-term decay has so far only been seen in Her X-1 and Vela X-1, with far less convincing explanations.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Pulsars: individual: Her X-1; Radiation mechanisms: general; Scattering; Stars: magnetic field; Stars: neutron; X-rays: stars

Cyclotron line features of magnetized accreting neutron stars - Wilms, Jörn; et al. (2007)
Providing the only known direct estimate of the magnetic field strength of an accreting neutron star, the study of 'Cyclotron Resonance Scattering Features' (often abbreviated CRSFs or cyclotron lines) is fundamental to a better understanding of the physics of those powerful X-ray sources. During the last three decades cyclotron lines have been detected as absorption features in many accreting neutron star binaries [1, 2, 3, 4]. The excellent energy resolution of todays' instruments on satellites such as INTEGRAL allows not only for the detection of cyclotron lines but also for a good resolution of their complex line shapes. Using a revised version of the Monte Carlo code by R. Araya [5, 6], we set up a preliminary model for cyclotron line formation and compare its predictions to observational data.
Keywords: X-rays : stars; stars : neutron; magnetic fields; line : formation

Cyclotron lines in highly magnetized neutron stars - Staubert, R.; Truemper, J.; Kendziorra, E.; Klochkov, D.; Postnov, K.; Kretschmar, P.; Pottschmidt, K.; Haberl, F.; Rothschild, R. E.; Santangelo, A.; Wilms, Jörn; Kreykenbohm, Ingo; et al. (Astronomy & Astrophysics, 2019)
Cyclotron lines, also called cyclotron resonant scattering features are spectral features, generally appearing in absorption, in the X-ray spectra of objects containing highly magnetized neutron stars, allowing the direct measurement of the magnetic field strength in these objects. Cyclotron features are thought to be due to resonant scattering of photons by electrons in the strong magnetic fields. The main content of this contribution focusses on electron cyclotron lines as found in accreting X-ray binary pulsars (XRBP) with magnetic fields on the order of several 10(12) Gauss. Also, possible proton cyclotron lines from single neutron stars with even stronger magnetic fields are briefly discussed. With regard to electron cyclotron lines, we present an updated list of XRBPs that show evidence of such absorption lines. The first such line was discovered in a 1976 balloon observation of the accreting binary pulsar Hercules X-1, it is considered to be the first direct measurement of the magnetic field of a neutron star. As of today (end 2018), we list 35 XRBPs showing evidence of one ore more electron cyclotron absorption line(s). A few have been measured only once and must be confirmed (several more objects are listed as candidates). In addition to the Tables of objects, we summarize the evidence of variability of the cyclotron line as a function of various parameters (especially pulse phase, luminosity and time), and add a discussion of the di ff erent observed phenomena and associated attempts of theoretical modeling. We also discuss our understanding of the underlying physics of accretion onto highly magnetized neutron stars. For proton cyclotron lines, we present tables with seven neutron stars and discuss their nature and the physics in these objects.
Keywords: accretion; accretion disks; magnetic fields; radiation mechanisms: non-thermal; binaries: general; X-rays: binaries; stars: neutron

Cyclotron resonant scattering feature simulations II. Description of the CRSF simulation process - Schwarm, Fritz-Walter; Ballhausen, Ralf; Falkner, Sebastian; Schoenherr, G.; Pottschmidt, K.; Wolff, M. T.; Becker, P. A.; Furst, F.; Marcu-Cheatham, D. M.; Hemphill, P. B.; Sokolova-Lapa, E.; Dauser, Thomas; et al. (Astronomy & Astrophysics, 2017)
Context. Cyclotron resonant scattering features (CRSFs) are formed by scattering of X-ray photons off quantized plasma electrons in the strong magnetic field (of the order 10(12) G) close to the surface of an accreting X-ray pulsar. Due to the complex scattering cross-sections, the line profiles of CRSFs cannot be described by an analytic expression. Numerical methods, such as Monte Carlo (MC) simulations of the scattering processes, are required in order to predict precise line shapes for a given physical setup, which can be compared to observations to gain information about the underlying physics in these systems.Aims. A versatile simulation code is needed for the generation of synthetic cyclotron lines. Sophisticated geometries should be investigatable by making their simulation possible for the first time.Methods. The simulation utilizes the mean free path tables described in the first paper of this series for the fast interpolation of propagation lengths. The code is parallelized to make the very time-consuming simulations possible on convenient time scales. Furthermore, it can generate responses to monoenergetic photon injections, producing Green's functions, which can be used later to generate spectra for arbitrary continua.Results. We develop a new simulation code to generate synthetic cyclotron lines for complex scenarios, allowing for unprecedented physical interpretation of the observed data. An associated XSPEC model implementation is used to fit synthetic line profiles to NuSTAR data of Cep X-4. The code has been developed with the main goal of overcoming previous geometrical constraints in MC simulations of CRSFs. By applying this code also to more simple, classic geometries used in previous works, we furthermore address issues of code verification and cross-comparison of various models. The XSPEC model and the Green's function tables are available online (see link in footnote, page 1).
Keywords: X-rays: binaries; stars: neutron; methods: numerical

Cyclotron resonant scattering feature simulations: I. Thermally averaged cyclotron scattering cross sections, mean free photon-path tables, and electron momentum sampling - Schwarm, Fritz-Walter; Schönherr, Gabriele; Falkner, Sebastian; Pottschmidt, Katja; Wolff, Michael; Becker, Peter A.; Sokolova-Lapa, Ekaterina; Klochkov, Dmitry; Ferrigno, Carlo; Fuerst, Felix; Hemphill, Paul F.; Marcu-Cheatham, Diana M.; et al. (Astronomy & Astrophysics, 2017)
Context. Electron cyclotron resonant scattering features (CRSFs) are observed as absorption-like lines in the spectra of X-ray pulsars. A significant fraction of the computing time for Monte Carlo simulations of these quantum mechanical features is spent on the calculation of the mean free path for each individual photon before scattering, since it involves a complex numerical integration over the scattering cross section and the (thermal) velocity distribution of the scattering electrons. Aims. We aim to numerically calculate interpolation tables which can be used in CRSF simulations to sample the mean free path of the scattering photon and the momentum of the scattering electron. The tables also contain all the information required for sampling the scattering electron's final spin. Methods. The tables were calculated using an adaptive Simpson integration scheme. The energy and angle grids were refined until a prescribed accuracy is reached. The tables are used by our simulation code to produce artificial CRSF spectra. The electron momenta sampled during these simulations were analyzed and justified using theoretically determined boundaries. Results. We present a complete set of tables suited for mean free path calculations of Monte Carlo simulations of the cyclotron scattering process for conditions expected in typical X-ray pulsar accretion columns (0:01 ≤ B/B ≤ 0.12, where B = 4.413 × 10 G, and 3 keV ≤ kT ≤ 15 keV). The sampling of the tables is chosen such that the results have an estimated relative error of at most 1=15 for all points in the grid. The tables are available online (see link in footnote, page 1
Keywords: Methods: numerical; Stars: neutron; X-rays: binaries

Cygnus X-1 contains a 21-solar mass black hole-Implications for massive star winds - Miller-Jones, James C.A.; Bahramian, Arash; Orosz, Jerome A.; Mande, Ilya; Gou, Lijun; Maccarone, Thomas J.; Neijsse, Coenraad J.; Zhao, Xueshan; Ziółkowski, Janusz; Reid, Mark J.; Uttley, Phil; Zheng, Xueying; et al. (Science, 2021)
The evolution of massive stars is influenced by the mass lost to stellar winds over their lifetimes. These winds limit the masses of the stellar remnants (such as black holes) that the stars ultimately produce. We used radio astrometry to refine the distance to the black hole X-ray binary Cygnus X-1, which we found to be 2:220:180:17 kiloparsecs. When combined with archival optical data, this implies a black hole mass of 21.2 ± 2.2 solar masses, which is higher than previous measurements. The formation of such a high-mass black hole in a high-metallicity system (within the Milky Way) constrains wind mass loss from massive stars.
CRIS-Team Scopus Importer:2021-03-19

Decomposing blazar spectra into lepto-hadronic emission components - Gokus, A.; Richter, S.; Spanier, Felix; Kreter, M.; Kadler, M.; Mannheim, K.; Wilms, Jörn (Astronomische Nachrichten, 2018)
The recently reported coincidences between high-energy neutrino events and major blazar outbursts reinforce the relevance of lepto-hadronic emission models for blazars. We study the influence of physical parameters on the neutrino output by modeling blazar spectral energy distributions self-consistently assuming a relativistically propagating acceleration zone surrounded by a larger cooling zone. We find that the gross features of the spectral energy distribution can readily be explained with the model. A rigorous test requires time-resolved measurements of blazar spectral energy distributions during an outburst and high-statistics neutrino measurements to discriminate the leptonic and hadronic emission components.
Keywords: acceleration of particles; galaxies: Active; galaxies: Individual (TXS 0506+056)

Deep-Sea Bioluminescence Blooms after Dense Water Formation at the Ocean Surface - Tamburini, Christian; Canals, Miquel; Houpert, Loic; Lefevre, Dominique; Martini, Verine; D'Ortenzio, Fabrizio; Robert, Anne; Testor, Pierre; Aguilar, Juan Antonio; Al Samarai, Imen; Albert, Arnaud; Andre, Michel; et al. (PLoS ONE, 2013)
The deep ocean is the largest and least known ecosystem on Earth. It hosts numerous pelagic organisms, most of which are able to emit light. Here we present a unique data set consisting of a 2.5-year long record of light emission by deep-sea pelagic organisms, measured from December 2007 to June 2010 at the ANTARES underwater neutrino telescope in the deep NW Mediterranean Sea, jointly with synchronous hydrological records. This is the longest continuous time-series of deep-sea bioluminescence ever recorded. Our record reveals several weeks long, seasonal bioluminescence blooms with light intensity up to two orders of magnitude higher than background values, which correlate to changes in the properties of deep waters. Such changes are triggered by the winter cooling and evaporation experienced by the upper ocean layer in the Gulf of Lion that leads to the formation and subsequent sinking of dense water through a process known as "open-sea convection". It episodically renews the deep water of the study area and conveys fresh organic matter that fuels the deep ecosystems. Luminous bacteria most likely are the main contributors to the observed deep-sea bioluminescence blooms. Our observations demonstrate a consistent and rapid connection between deep open-sea convection and bathypelagic biological activity, as expressed by bioluminescence. In a setting where dense water formation events are likely to decline under global warming scenarios enhancing ocean stratification, in situ observatories become essential as environmental sentinels for the monitoring and understanding of deep-sea ecosystem shifts.

Deep-sea deployment of the KM3NeT neutrino telescope detection units by self-unrolling - Aiello, S.; Domi, Alba; Albert, A.; Garre, S. Alves; Aly, Z.; Ameli, F.; Anassontzis, E.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; et al. (Journal of Instrumentation, 2020)
KM3NeT is a research infrastructure being installed in the deep Mediterranean Sea. It will house a neutrino telescope comprising hundreds of networked moorings - detection units or strings - equipped with optical instrumentation to detect the Cherenkov radiation generated by charged particles from neutrino-induced collisions in its vicinity. In comparison to moorings typically used for oceanography, several key features of the KM3NeT string are different: the instrumentation is contained in transparent and thus unprotected glass spheres; two thin Dyneema (R) ropes are used as strength members; and a thin delicate backbone tube with fibre-optics and copper wires for data and power transmission, respectively, runs along the full length of the mooring. Also, compared to other neutrino telescopes such as ANTARES in the Mediterranean Sea and GVD in Lake Baikal, the KM3NeT strings are more slender to minimise the amount of material used for support of the optical sensors. Moreover, the rate of deploying a large number of strings in a period of a few years is unprecedented. For all these reasons, for the installation of the KM3NeT strings, a custom-made, fast deployment method was designed. Despite the length of several hundreds of metres, the slim design of the string allows it to be compacted into a small, re-usable spherical launching vehicle instead of deploying the mooring weight down from a surface vessel. After being lowered to the seafloor, the string unfurls to its full length with the buoyant launching vehicle rolling along the two ropes. The design of the vehicle, the loading with a string, and its underwater self-unrolling are detailed in this paper.
CRIS-Team WoS Importer:2020-12-18

Deep sea tests of a prototype of the KM3NeT digital optical module - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; De Asmundis, R.; et al. (European Physical Journal C, 2014)
The first prototype of a photo-detection unit of the future KM3NeT neutrino telescope has been deployed in the deepwaters of the Mediterranean Sea. This digital optical module has a novel design with a very large photocathode area segmented by the use of 31 three inch photomultiplier tubes. It has been integrated in the ANTARES detector for in-situ testing and validation. This paper reports on the first months of data taking and rate measurements. The analysis results highlight the capabilities of the new module design in terms of background suppression and signal recognition. The directionality of the optical module enables the recognition of multiple Cherenkov photons from the same (40)Kdecay and the localisation of bioluminescent activity in the neighbourhood. The single unit can cleanly identify atmospheric muons and provide sensitivity to the muon arrival directions.

Dependence of atmospheric muon flux on seawater depth measured with the first KM3NeT detection units: The KM3NeT Collaboration - Ageron, M.; Aiello, S.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Bagatelas, C.; Barbarino, G.; Baret, B.; et al. (European Physical Journal C: Particles and Fields, 2020)
KM3NeT is a research infrastructure located in the Mediterranean Sea, that will consist of two deep-sea Cherenkov neutrino detectors. With one detector (ARCA), the KM3NeT Collaboration aims at identifying and studying TeV–PeV astrophysical neutrino sources. With the other detector (ORCA), the neutrino mass ordering will be determined by studying GeV-scale atmospheric neutrino oscillations. The first KM3NeT detection units were deployed at the Italian and French sites between 2015 and 2017. In this paper, a description of the detector is presented, together with a summary of the procedures used to calibrate the detector in-situ. Finally, the measurement of the atmospheric muon flux between 2232–3386 m seawater depth is obtained.
CRIS-Team Scopus Importer:2020-02-18

Detection capabilities of the Athena X-IFU for the warm-hot intergalactic medium using gamma-ray burst X-ray afterglows - Walsh, Sarah; Mcbreen, Sheila; Martin-Carrillo, Antonio; Dauser, Thomas; Wijers, Nastasha; Wilms, Jörn; Schaye, Joop; Barret, Didier (Astronomy & Astrophysics, 2020)
At low redshifts, the observed baryonic density falls far short of the total number of baryons predicted. Cosmological simulations suggest that these baryons reside in filamentary gas structures, known as the warm-hot intergalactic medium (WHIM). As a result of the high temperatures of these filaments, the matter is highly ionised such that it absorbs and emits far-UV and soft X-ray photons. Athena, the proposed European Space Agency X-ray observatory, aims to detect the "missing"baryons in the WHIM up to redshifts of z = 1 through absorption in active galactic nuclei and gamma-ray burst (GRB) afterglow spectra, allowing for the study of the evolution of these large-scale structures of the Universe. This work simulates WHIM filaments in the spectra of GRB X-ray afterglows with Athena using the SImulation of X-ray TElescopes framework. We investigate the feasibility of their detection with the X-IFU instrument, through Oâ€» VII (E = 573 eV) and O VIII (E = 674 eV) absorption features, for a range of equivalent widths imprinted onto GRB afterglow spectra of observed starting fluxes ranging between 10-12 and 10-10 erg cm-2 s-1, in the 0.3-10 keV energy band. The analyses of X-IFU spectra by blind line search show that Athena will be able to detect O VII-O VIII absorption pairs with EWO VII > 0.13 eV and EWO VIII > 0.09 eV for afterglows with F > 2 × 10-11 erg cm-2 s-1. This allows for the detection of ≈ 45-137 O VII-O VIII absorbers during the four-year mission lifetime. The work shows that to obtain an O VII-O VIII detection of high statistical significance, the local hydrogen column density should be limited at NH < 8 × 1020 cm-2.
CRIS-Team Scopus Importer:2020-10-30
Keywords: Gamma-ray burst: general; Instrumentation: detectors; Intergalactic medium; Large-scale structure of Universe; X-rays: general

Detection of large-scale X-ray bubbles in the Milky Way halo - Predehl, P.; Sunyaev, R. A.; Becker, W.; Brunner, H.; Burenin, R.; Bykov, A.; Cherepashchuk, A.; Chugai, N.; Churazov, E.; Doroshenko, V.; Eismont, N.; Freyberg, M.; et al. (Nature, 2020)
The halo of the Milky Way provides a laboratory to study the properties of the shocked hot gas that is predicted by models of galaxy formation. There is observational evidence of energy injection into the halo from past activity in the nucleus of the Milky Way1–4; however, the origin of this energy (star formation or supermassive-black-hole activity) is uncertain, and the causal connection between nuclear structures and large-scale features has not been established unequivocally. Here we report soft-X-ray-emitting bubbles that extend approximately 14 kiloparsecs above and below the Galactic centre and include a structure in the southern sky analogous to the North Polar Spur. The sharp boundaries of these bubbles trace collisionless and non-radiative shocks, and corroborate the idea that the bubbles are not a remnant of a local supernova5 but part of a vast Galaxy-scale structure closely related to features seen in γ-rays6. Large energy injections from the Galactic centre7 are the most likely cause of both the γ-ray and X-ray bubbles. The latter have an estimated energy of around 1056 erg, which is sufficient to perturb the structure, energy content and chemical enrichment of the circumgalactic medium of the Milky Way.
CRIS-Team Scopus Importer:2020-12-25

Detection potential of the KM3NeT detector for high-energy neutrinos from the Fermi bubbles - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Aharonian, F.; Aiello, S.; Albert, A.; Alexandri, M.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; et al. (Astroparticle Physics, 2013)
A recent analysis of the Fermi Large Area Telescope data provided evidence for a high-intensity emission of high-energy gamma rays with a E-2 spectrum from two large areas, spanning 50 above and below the Galactic centre (the "Fermi bubbles"). A hadronic mechanism was proposed for this gamma-ray emission making the Fermi bubbles promising source candidates of high-energy neutrino emission. In this work Monte Carlo simulations regarding the detectability of high-energy neutrinos from the Fermi bubbles with the future multi-km(3) neutrino telescope KM3NeT in the Mediterranean Sea are presented. Under the hypothesis that the gamma-ray emission is completely due to hadronic processes, the results indicate that neutrinos from the bubbles could be discovered in about one year of operation, for a neutrino spectrum with a cutoff at 100 TeV and a detector with about 6 km(3) of instrumented volume. The effect of a possible lower cutoff is also considered. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino telescope; Fermi Bubbles; KM3NeT

Development of the Wide Field Imager for Athena - Meidinger, Norbert; Eder, Josef; Fuermetz, Maria; Nandra, Kirpal; Pietschner, Daniel; Plattner, Markus; Rau, Arne; Reiffers, Jonas; Strecker, Rafael; Barbera, Marco; Brand, Thorsten; Wilms, Jörn (2015)
The WFI (Wide Field Imager) instrument is planned to be one of two complementary focal plane cameras on ESA's next X-ray observatory Athena. It combines unprecedented survey power through its large field of view of 40 arcmin x 40 arcmin together with excellent count-rate capability (>= 1 Crab). The energy resolution of the silicon sensor is state-of-the-art in the energy band of interest from 0.2 keV to 15 keV, e.g. the full width at half maximum of a line at 6 keV will be <= 150 eV until the end of the nominal mission phase. This performance is accomplished by using DEPFET active pixel sensors with a pixel size of 130 mu m x 130 mu m well suited to the on-axis angular resolution of 5 arcsec of the mirror system. Each DEPFET pixel is a combined detector-amplifier structure with a MOSFET integrated onto a fully depleted 450 mu m thick silicon bulk. Two different types of DEPFET sensors are planned for the WFI instrument: A set of four large-area sensors to cover the physical size of 14 cm x 14 cm in the focal plane and a single smaller gateable DEPFET sensor matrix optimized for high count-rate observations. Here we present the conceptual design of the instrument with focus on the critical subsystems and describe the instrument performance expectations. An outline of the model philosophy and the project organization completes the presentation.
Keywords: Active pixel sensor; Athena; DEPFET; focal plane camera; Hot and Energetic Universe; WFI; X-ray astronomy; X-ray detector

Developments and results in the context of the JEM-EUSO program obtained with the ESAF simulation and analysis framework - Abe, S.; Adams, J. H.; Allard, D.; Alldredge, P.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Baret, B.; Barghini, D.; Battisti, M.; Bayer, J.; Bellotti, R.; et al. (European Physical Journal C: Particles and Fields, 2023)
JEM-EUSO is an international program for the development of space-based Ultra-High Energy Cosmic Ray observatories. The program consists of a series of missions which are either under development or in the data analysis phase. All instruments are based on a wide-field-of-view telescope, which operates in the near-UV range, designed to detect the fluorescence light emitted by extensive air showers in the atmosphere. We describe the simulation software ESAF in the framework of the JEM-EUSO program and explain the physical assumptions used. We present here the implementation of the JEM-EUSO, POEMMA, K-EUSO, TUS, Mini-EUSO, EUSO-SPB1 and EUSO-TA configurations in ESAF. For the first time ESAF simulation outputs are compared with experimental data.
CRIS-Team Scopus Importer:2023-11-24

Dipping in Cygnus X-2 in a multi-wavelength campaign due to absorption of extended ADC emission - Balucinska-Church, M.; Schulz, N. S.; Wilms, Jörn; Gibiec, A.; Hanke, Manfred; Spencer, R. E.; Rushton, A.; Church, M. J. (Astronomy & Astrophysics, 2011)
We report results of one-day simultaneous multiwavelength observations of Cygnus X-2 using XMM, Chandra, the European VLBI Network and the XMM Optical Monitor. During the observations, the source did not exhibit Z-track movement, but remained in the vicinity of the soft apex. It was in a radio quiescent/quiet state of <150 mu Jy. Strong dip events were seen as 25% reductions in X-ray intensity. The use of broadband CCD spectra in combination with narrow-band grating spectra has now demonstrated for the first time that these dipping events in Cygnus X-2 are caused by absorption in cool material in quite a unique way. In the band 0.2-10 keV, dipping appears to be due to progressive covering of the Comptonized emission of an extended accretion disk corona, the covering factor rising to 40% in deep dipping with an associated column density of 3 x 10(23) atom cm(-2). Remarkably, the blackbody emission of the neutron star is not affected by these dips, in strong contrast with observations of typical low mass X-ray binary dipping sources. The Chandra and XMM gratings directly measure the optical depths in absorption edges such as Ne K, Fe L, and O K and a comparison of the optical depths in the edges of non-dip and dip data reveals no increase of optical depth during dipping even though the continuum emission sharply decreases. Based on these findings, at orbital phase 0.35, we propose that dipping in this observation is caused by absorption in the outer disk by structures located opposite to the impact bulge of the accretion stream. With an inclination angle >60 degrees these structures can still cover large parts of the extended ADC, without absorbing emission from the central neutral star.
Keywords: accretion; accretion disks; acceleration of particles; stars: neutron; X-rays: binaries; X-rays: individuals: Cyg X-2; radio continuum: general

Discovery of a flux-related change of the cyclotron line energy in Hercules X-1 - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Aims. We present the results of ten years of repeated measurements of the Cyclotron Resonance Scattering Feature (CRSF) in the spectrum of the binary X-ray pulsar Her X-1 and report the discovery of a positive correlation of the centroid energy of this absorption feature in pulse phase averaged spectra with source luminosity.Methods. Our results are based on a uniform analysis of observations by the RXTE satellite from 1996 to 2005, using suffciently long observations of 12 individual 35-day Main-On states of the source.Results. The mean centroid energy E-c of the CRSF in pulse phase averaged spectra of Her X-1 during this time is around 40 keV, with significant variations from one Main-On state to the next. We find that the centroid energy of the CRSF in Her X-1 changes by similar to 5% in energy for a factor of 2 in luminosity. The correlation is positive, contrary to what is observed in some high luminosity transient pulsars.Conclusions. Our finding is the first significant measurement of a positive correlation between Ec and luminosity in any X-ray pulsar. We suggest that this behaviour is expected in the case of sub-Eddington accretion and present a calculation of a quantitative estimate, which is very consistent with the effect observed in Her X-1. We urge that Her X-1 is regularly monitored further and that other X-ray pulsars are investigated for a similar behaviour.
Keywords: accretion; accretion disks; binaries : eclipsing; stars : neutron; X-rays : binaries; X-rays : stars

Discovery of Pulsation Dropout and Turn-on during the High State of the Accreting X-Ray Pulsar LMC X-4 - Brumback, Mckinley C.; Hickox, Ryan C.; Bachetti, Matteo; Ballhausen, Ralf; Furst, Felix S.; Pike, Sean; Pottschmidt, Katja; Tomsick, John A.; Wilms, Jörn (Astrophysical Journal Letters, 2018)
Two Nuclear Spectroscopic Telescope Array (NuSTAR) observations of the luminous X-ray pulsar LMC X-4 in 2015 October and November captured several bright accretion flares from this source, which has a long history of stable pulse and superorbital behavior. We present a timing analysis of these data in which we detect a rapid pulse "turn-on" in association with the accretion flares, during which the source reaches super-Eddington luminosities. Pulsations, which are normally seen from this source, are found to only occur for approximately one hour before and during the bright flares. Beyond one hour before and after the flares, we find pulsations to be weak or nonexistent, with fractional rms amplitudes of less than 0.05. At the onset of the flare, the pulse profiles exhibit a phase shift of 0.25 cycles that could be associated with a change in the emission geometry. This increase in pulse strength occurring well before the flare cannot be explained by the propeller effect, and potentially offers a connection between the magnetic properties of pulsars that accrete close to their Eddington limits and ultraluminous X-ray pulsars.
Keywords: pulsars: individual (LMC X-4); stars: neutron; X-rays: binaries

Discovery of slow X-ray pulsations in the high-mass X-ray binary 4U 2206+54 - Reig, Pablo; Torrejon, J. M.; Negueruela, Ignacio; Blay, P.; Ribo, Marc; Wilms, Jörn (Astronomy & Astrophysics, 2009)
Context. The source 4U 2206+54 is one of the most enigmatic high-mass X-ray binaries. In spite of intensive searches, X-ray pulsations have not been detected in the time range 10(-3)-10(3) s. A cyclotron line at similar to 30 keV has been suggested by various authors but never detected with significance. The stellar wind of the optical companion is abnormally slow. The orbital period, initially reported to be 9.6 days, disappeared and a new periodicity of 19.25 days emerged.Aims. The main objective of our RXTE monitoring of 4U 2206+54 is to study the X-ray orbital variability of the spectral and timing parameters. The new long and uninterrupted RXTE observations allow us to search for long (similar to 1 h) pulsations for the first time.Methods. We divided the similar to 7-day observation into five intervals and obtained time-averaged energy spectra and power spectral density for each observation interval. We also searched for pulsations using various algorithms.Results. We have discovered 5560-s pulsations in the light curve of 4U2206+54. Initially detected in RXTE data, these pulsations are also present in INTEGRAL and EXOSAT observations. The average X-ray luminosity in the energy range 2-10 keV is 1.5 x 10(35) erg s(-1) with a ratio F-max/F-min similar to 5. This ratio implies an eccentricity of similar to 0.4, somewhat higher than previously suggested. The power spectrum is dominated by red noise that can be fitted with a single power law whose index and strength decrease with X-ray flux. The source also shows a soft excess at low energies. If the soft excess is modelled with a blackbody component, then the size and temperature of the emitting region agrees with its interpretation in terms of a hot spot on the neutron star surface.Conclusions. The discovery of X-ray pulsations in 4U 2206+54 confirms the neutron star nature of the compact companion and definitively rules out the presence of a black hole. The source displays variability on time scales of days, presumably due to changes in the mass accretion rate as the neutron star moves around the optical companion in a moderately eccentric orbit. If current models for the spin evolution in X-ray pulsars are correct, then the magnetic field of 4U 2206+54 at birth must have been B >= 10(14) G.
Keywords: stars: early-type; stars: emission-line; Be; stars: binaries: close; X-rays: binaries; stars: pulsars: general

DISK-DOMINATED STATES OF 4U 1957+11: CHANDRA, XMM-NEWTON, AND RXTE OBSERVATIONS OF OSTENSIBLY THE MOST RAPIDLY SPINNING GALACTIC BLACK HOLE - Nowak, Michael A.; Juett, Adrienne; Homan, Jeroen; Yao, Yangsen; Wilms, Jörn; Schulz, Norbert S.; Canizares, Claude R. (Astrophysical Journal, 2008)
We present simultaneous Chandra High-Energy Transmission Gratings (HETG) and Rossi X-ray Timing Explorer (RXTE) observations of a "soft state'' of the black hole candidate 4U 1957+11. These spectra, having limited hard X-ray excess, are an excellent test of disk atmosphere models that include effects of black hole spin. The HETG data show, by modeling the broadband continuum and direct fitting of absorption edges, that the disk spectrum is only very mildly absorbed, with N-H = (1-2) x 10(21) cm(-2). These data additionally reveal lambda lambda 13.449 Ne IX absorption consistent with the warm/ hot phase of the interstellar medium. The fitted disk model implies an inclined disk around a low-mass black hole rotating with normalized spin a* approximate to 1. We show, however, that pure Schwarzschild models describe the data extremely well, albeit with large disk atmosphere "color-correction'' factors. Standard correction factors can be attained if one incorporates mild Comptonization. We find that the Chandra observations do not uniquely determine spin, even with this otherwise extremely well-measured, nearly pure disk spectrum. XMM-Newton RXTE observations, taken only six weeks later, are equally unconstraining. This lack of constraint is partly driven by the unknown mass and distance of 4U 1957+ 11; however, it is also driven by the limited Chandra and XMM-Newton bandpasses. We therefore present a series of 48 RXTE observations taken at different brightness/ hardness levels. These data prefer a spin of a* approximate to 1, even when including a mild Comptonization component; however, they also show evolution of the color-correction factors. If the rapid-spin models with standard correction factors are to be believed, then the RXTE observations predict that 4U 1957+ 11 can range from a 3 M-circle dot black hole at 10 kpc with a* approximate to 0: 83 to a 16 M-circle dot black hole at 22 kpc with
Keywords: accretion; accretion disks; black hole physics; radiation mechanisms: thermal; X-rays: binaries

DISTORTED CYCLOTRON LINE PROFILE IN CEP X-4 AS OBSERVED BY NuSTAR - Fuerst, F.; Pottschmidt, K.; Miyasaka, H.; Bhalerao, V.; Bachetti, M.; Boggs, S. E.; Christensen, F. E.; Craig, W. W.; Grinberg, V.; Hailey, C. J.; Harrison, F. A.; Kennea, J. A.; et al. (Astrophysical Journal Letters, 2015)
We present spectral analysis of Nuclear Spectroscopic Telescope Array and Swift observations of Cep X-4 during its outburst in 2014. We observed the source once during the peak of the outburst and once during the decay, finding good agreement in the spectral shape between the observations. We describe the continuum using a power law with a Fermi-Dirac cutoff at high energies. Cep X-4 has a very strong cyclotron resonant scattering feature (CRSF) around 30 keV. A simple absorption-like line with a Gaussian optical depth or a pseudo-Lorentzian profile both fail to describe the shape of the CRSF accurately, leaving significant deviations at the red side of the line. We characterize this asymmetry with a second absorption feature around 19 keV. The line energy of the CRSF, which is not influenced by the addition of this feature, shows a small but significant positive luminosity dependence. With luminosities between (1-6) x 10(36) erg s(-1), Cep X-4 is below the theoretical limit where such a correlation is expected. This behavior is similar to Vela X-1 and we discuss parallels between the two systems.
Keywords: accretion; accretion disks; radiation: dynamics; stars: neutron; X-rays: binaries; X-rays: individual (Cep X-4)

Dual-frequency VLBI study of Centaurus A on sub-parsec scales The highest-resolution view of an extragalactic jet - Müller, Cornelia; Kadler, Matthias; Roopesh, Ojha; Wilms, Jörn; Böck, Moritz; Edwards, P. G.; Fromm, C. M.; Hase, H.; Horiuchi, S.; Katz, Uli; Lovell, J. E. J.; Ploetz, C.; et al. (Astronomy & Astrophysics, 2011)
Context. Centaurus A is the closest active galactic nucleus. High resolution imaging using Very Long Baseline Interferometry (VLBI) enables us to study the spectral and kinematic behavior of the radio jet-counterjet system on sub-parsec scales, providing essential information for jet emission and formation models.Aims. Our aim is to study the structure and spectral shape of the emission from the central-parsec region of Cen A.Methods. As a target of the Southern Hemisphere VLBI monitoring program TANAMI (Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry), VLBI observations of Cen A are made regularly at 8.4 and 22.3 GHz with the Australian Long Baseline Array (LBA) and associated telescopes in Antarctica, Chile, and South Africa.Results. The first dual-frequency images of this source are presented along with the resulting spectral index map. An angular resolution of 0.4 mas x 0.7 mas is achieved at 8.4 GHz, corresponding to a linear scale of less than 0.013 pc. Hence, we obtain the highest resolution VLBI image of CenA, comparable to previous space-VLBI observations. By combining with the 22.3 GHz image, which has been taken without contributing transoceanic baselines at somewhat lower resolution, we present the corresponding dual-frequency spectral index distribution along the sub-parsec scale jet revealing the putative emission regions for recently detected gamma-rays from the core region by Fermi/LAT.Conclusions. We resolve the innermost structure of the milliarcsecond scale jet and counterjet system of CenA into discrete components. The simultaneous observations at two frequencies provide the highest resolved spectral index map of an AGN jet allowing us to identify multiple possible sites as the origin of the high energy emission.
Keywords: techniques: high angular resolution; galaxies: individual: Centaurus A; black hole physics; galaxies: active; galaxies: individual: NGC 5128; galaxies: jets

Dust and gas absorption in the high mass X-ray binary IGR J16318-4848 - Ballhausen, Ralf; Lorenz, Maximilian; Fuerst, Felix; Pottschmidt, Katja; Corrales, Lia; Tomsick, John A.; Kühnel, Matthias; Kretschmar, Peter; Kallman, Timothy R.; Grinberg, Victoria; Hell, Natalie; Psadaraki, Ioanna; et al. (Astronomy & Astrophysics, 2020)
Context. With an absorption column density on the order of 1024 cm-2, IGR J16318-4848 is one of the most extreme cases of a highly obscured high mass X-ray binary. In addition to the overall continuum absorption, the source spectrum exhibits a strong iron and nickel fluorescence line complex at 6.4 keV. Previous empirical modeling of these features and comparison with radiative transfer simulations raised questions about the structure and covering fraction of the absorber and the profile of the fluorescence lines. Aims. We aim at a self-consistent description of the continuum absorption, the absorption edges, and the fluorescence lines to constrain the properties of the absorbing material, such as ionization structure and geometry. We further investigate the effects of dust absorption on the observed spectra and the possibility of fluorescence emission from dust grains. Methods. We used XMM-Newton and NuSTAR spectra to first empirically constrain the incident continuum and fluorescence lines. Next we used XSTAR to construct a customized photoionization model where we vary the ionization parameter, column density, and covering fraction. In the third step we modeled the absorption and fluorescence in a dusty olivine absorber and employed both a simple analytical model for the fluorescence line emission and a Monte Carlo simulation of radiative transfer that generates line fluxes, which are very close to the observational data. Results. Our empirical spectral modeling is in agreement with previous works. Our second model, the single gas absorber does not describe the observational data. In particular, irrespective of the ionization state or column density of the absorber, a much higher covering fraction than previously estimated is needed to produce the strong fluorescence lines and the large continuum absorption. A dusty, spherical absorber (modeled as consisting of olivine dust, although the nature of dust cannot be constrained) is able to produce the observed continuum absorption and edges. Conclusions. A dense, dusty absorber in the direct vicinity of the source consisting of dust offers a consistent description of both the strong continuum absorption and the strong emission features in the X-ray spectrum of IGR J16318-4848. In particular, for low optical depth of individual grains, which is the case for typical volume densities and grain size distribution models, the dust will contribute significantly to the fluorescence emission.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Circumstellar matter; Dust; extinction; X-rays: binaries; X-rays: individuals: IGR J16318-4848

Einleitung: Unendlichkeit: Versuch einer asymptotischen Annäherung - Freiburg, Rudolf; Lubkoll, Christine; Schoberth, Wolfgang; Weth, Thomas; Wilms, Jörn; Leven, Karl-Heinz (Unendlichkeit: Erlanger Universitätstage Ansbach 2015, 2016)
Keywords: Unendlichkeit; Literatur; Alexander Pope; Edward Young; Thodizee; Gott; Ewigkeit; Zeit; Raum

eROSITA ground operations - Brunner, H.; Boller, T.; Coutinho, D.; Dauser, Thomas; Dennerl, K.; Dwelly, T.; Freyberg, M.; Fuermetz, M.; Georgakakis, A.; Grossberger, C.; Kreykenbohm, Ingo; Lamer, G.; et al. (2018)
eROSITA (extended ROentgen Survey with an Imaging Telescope Array) is the primary instrument on-board the Russian/German "Spectrum-Roentgen-Gamma"(SRG) mission. It will perform the first all-sky imaging X-ray survey in the medium X-ray energy band. eROSITA is currently awaiting its launch from Baikonur in early 2019 into an L2 halo orbit. Preparations for eROSITA ground operations have been under way in parallel with the hardware development of the eROSITA telescope, comprising the areas mission planning, telescope operation and data reception, the operation of a data processing pipeline, and the creation of tools for data access and interactive data analysis. eROSITA mission: After a brief calibration and performance verification phase eROSITA will perform a four-year all-sky survey fully covering the sky eight times, which will be followed by several years of dedicated observations of interesting objects. Two ground antennas in Russia (near Moscow and in Siberia) will be available to provide several hours of daily ground contact for commanding and for data reception. eROSITA data rights will be equally divided between the Russian and German partners. Operation and data centers will exist at Max-Planck-Institut fur extraterrestrische Physics (MPE) in Garching, Germany and at the Russian Space Research Institute (IKI) in Moscow. Interfaces and procedures for mission planning, telescope operation and data exchange are closely coordinated between both sites. Mission planning and operation: Based on orbit simulations provided by the Russian side, a software environment for optimizing the desired sky coverage and observing efficiency while fulfilling visibility and solar constraints was set up. Agreed upon observing timelines will be converted to eROSITA and SRG command sequences fed to the Russian ground station for up-linking. MPE personnel will be on site either in Moscow or at MPE in Garching during each ground contact to conduct on-demand commanding and to assess instrument health and data quality. Data analysis pipeline and interactive data analysis: The eROSITA data processing pipeline consists of modules for data ingestion, event calibration, exposure calculation, source detection, and the creation of high-level source specific data products. It will be operated at MPE on a daily basis after each ground contact. A subset of the software tasks comprising the data analysis pipeline also functions as interactive data analysis tools. These can be grouped into tasks for X-ray event calibration, selection and binning, exposure, background and sensitivity map creation and for source detection. Data products are provided in a standards compliant FITS format for use with well-known high-level X-ray data analysis tools. A Web based graphical source catalog and data products viewer will allow easy data browsing. Since mid-2014 the interactive eROSITA data analysis package is available to the eROSITA user community, permitting the analysis of simulated eROSITA datasets, created by a sophisticated X-ray modeling and simulation tool.
Keywords: eROSITA; SRG; Spectrum-Roentgen-Gamma; X-ray telescope; space telescope; all-sky survey; astrophysics; ground segment

EROSITA on SRG - Predehl, Peter; Andritschke, Robert; Babyshkin, Vladimir; Becker, Werner; Bornemann, Walter; Bräuninger, Heinrich; Brunner, Hermann; Boller, Thomas; Burwitz, Vadim; Burkert, Wolfgang; Clerc, Nicolas; Churazov, Eugene; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
eROSITA (extended ROentgen Survey with an Imaging Telescope Array) is the core instrument on the Russian/German Spektrum-Roentgen-Gamma (SRG) mission which is now officially scheduled for launch on September 2017, eROSITA will perform a deep survey of the entire X-ray sky. Within the first 4 years of the mission the sky will be scanned 8 times. In the soft band (0.5-2 keV), it will be about 30 times more sensitive than ROSAT, while in the hard band (2-8 keV) it will provide the first ever true imaging survey of the sky. eROSITA is currently (June 2016) in its final integration and test phase. All seven FM Mirror Assemblies and Camera Assemblies (+ 1 spare) have been tested and calibrated. All subsystems and components are well within their expected performances.
Keywords: eROSITA; X-ray astronomy; X-ray optics; X-ray telescopes; X-ray testing

Erratum: The impact of precession on the observed population of ULXs (MNRAS (2023) 522 (5654) DOI: 10.1093/mnras/stab3049) - Khan, Norman; Middleton, Matthew J.; Wiktorowicz, Grzegorz; Dauser, Thomas; Roberts, Timothy P.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2023)
This is a correction to the paper 'The impact of precession on the observed population of ULXs', published in MNRAS, 509 (2), 2493-2506 (2022). In our paper, we incorrectly reported the neutron star spin to have a value of a∗ = 0.01 when in fact we used a value of a∗ = 0.0005, in accordance with the known spin period of ULX pulsars (P = 1 s) and canonical values for the NS systems (M = 1.4 × 2 × 1033 g and I = 1045 g cm−2). This does not affect any results in the paper.
CRIS-Team Scopus Importer:2023-06-23

Erratum to “Results from the search for dark matter in the Milky Way with 9 years of data of the ANTARES neutrino telescope” [Phys. Lett. B 769 (2017)249–254](S037026931730254X)(10.1016/j.physletb.2017.03.063) - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Physics Letters B, 2019)
Limits on the neutrino flux for a given mass [Formula presented] and annihilation channel are calculated as in Eq. (7)(page 252), with the integrated acceptances defined in Eq. (8)(page 252)as the effective area averaged over the neutrino energy. A numerical approximation of WIMP annihilation spectra, adapted from [1]with a too coarse binning, led to an overestimation of the integrated acceptances for dark-matter induced neutrino events. The spectra were replaced with a fine-binned version both in the likelihood and in the acceptances. The main change is a weaker limit for WIMP masses larger than 1 TeV/ [Formula presented]. Updated versions of Figs. 3–6 are provided.
CRIS-Team Scopus Importer:2019-06-04

EUSO-SPB1 mission and science - Abdellaoui, G.; Abe, S.; Adams, J. H.; Allard, D.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arnone, E.; Asano, K.; Attallah, R.; Attoui, H.; Pernas, M. Ave; et al. (Astroparticle Physics, 2024)
The Extreme Universe Space Observatory on a Super Pressure Balloon 1 (EUSO-SPB1) was launched in 2017 April from Wanaka, New Zealand. The plan of this mission of opportunity on a NASA super pressure balloon test flight was to circle the southern hemisphere. The primary scientific goal was to make the first observations of ultra-high-energy cosmic-ray extensive air showers (EASs) by looking down on the atmosphere with an ultraviolet (UV) fluorescence telescope from suborbital altitude (33 km). After 12 days and 4 h aloft, the flight was terminated prematurely in the Pacific Ocean. Before the flight, the instrument was tested extensively in the West Desert of Utah, USA, with UV point sources and lasers. The test results indicated that the instrument had sensitivity to EASs of ⪆3 EeV. Simulations of the telescope system, telescope on time, and realized flight trajectory predicted an observation of about 1 event assuming clear sky conditions. The effects of high clouds were estimated to reduce this value by approximately a factor of 2. A manual search and a machine-learning-based search did not find any EAS signals in these data. Here we review the EUSO-SPB1 instrument and flight and the EAS search.
CRIS-Team Scopus Importer:2023-09-22
Keywords: Air fluorescence; Cosmic rays (329); Extensive air showers; High-altitude balloons (738); JEM-EUSO

EUSO-TA - First results from a ground-based EUSO telescope - Abdellaoui, G.; Abe, S.; Adams, J. H.; Ahriche, A.; Allard, D.; Allen, L.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arai, Y.; Asano, K.; Attallah, R.; et al. (Astroparticle Physics, 2018)
EUSO-TA is a ground-based telescope, installed at the Telescope Array (TA) site in Black Rock Mesa, Utah, USA. This is the first detector to successfully use a Fresnel lens based optical system and multi-anode photomultipliers (64 channels per tube, 2304 channels encompassing a 10.6 degrees x 10.6 degrees field of view) for detection of Ultra High Energy Cosmic Rays (UHECR). The telescope is located in front of one of the fluorescence detectors of the TA experiment. Since its installation in 2013, the detector has observed several ultra-high energy cosmic ray events and, in addition, meteors. The limiting magnitude of 5.5 on summed frames (similar to 3 ms) has been established. Measurements of the UV night sky emission in different conditions and moon phases and positions have been completed. The performed observations serve as a proof of concept for the future application of this detector technology. (C) 2018 Elsevier B.V. All rights reserved.
Keywords: UHECR; EAS; JEM-EUSO; cosmic rays; Fresnel lens

Event reconstruction for KM3NeT/ORCA using convolutional neural networks - Aiello, S.; Albert, A.; Garre, S. Alves; Aly, Z.; Ameli, F.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anguita, M.; Anton, Gisela; Ardid, M.; Aublin, J.; et al. (Journal of Instrumentation, 2020)
The KM3NeT research infrastructure is currently under construction at two locations in the Mediterranean Sea. The KM3NeT/ORCA water-Cherenkov neutrino detector off the French coast will instrument several megatons of seawater with photosensors. Its main objective is the determination of the neutrino mass ordering. This work aims at demonstrating the general applicability of deep convolutional neural networks to neutrino telescopes, using simulated datasets for the KM3NeT/ORCA detector as an example. To this end, the networks are employed to achieve reconstruction and classification tasks that constitute an alternative to the analysis pipeline presented for KM3NeT/ORCA in the KM3NeT Letter of Intent. They are used to infer event reconstruction estimates for the energy, the direction, and the interaction point of incident neutrinos. The spatial distribution of Cherenkov light generated by charged particles induced in neutrino interactions is classified as shower- or track-like, and the main background processes associated with the detection of atmospheric neutrinos are recognized. Performance comparisons to machine-learning classification and maximum-likelihood reconstruction algorithms previously developed for KM3NeT/ORCA are provided. It is shown that this application of deep convolutional neural networks to simulated datasets for a large-volume neutrino telescope yields competitive reconstruction results and performance improvements with respect to classical approaches.
CRIS-Team WoS Importer:2020-10-30

Evidence for an evolving cyclotron line energy in 4U 1538-522 - Hemphill, Paul B.; Rothschild, Richard E.; Furst, Felix; Grinberg, Victoria; Klochkov, Dmitry; Kretschmar, Peter; Pottschmidt, Katja; Staubert, Ruediger; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2016)
We have performed a full time and luminosity-resolved spectral analysis of the high-mass X-ray binary 4U 1538-522 using the available RXTE, INTEGRAL, and Suzaku data, examining both phase-averaged and pulse-phase-constrained data sets and focusing on the behaviour of the cyclotron resonance scattering feature (CRSF). No statistically significant trend between the energy of the CRSF and luminosity is observed in the combined data set. However, the CRSF energy appears to have increased by 1.5 keV in the 8.5 yr between the RXTE and Suzaku measurements, with Monte Carlo simulations finding the Suzaku measurement 4.6σ above the RXTE points. Interestingly, the increased Suzaku CRSF energy is much more significant and robust in the pulse-phase-constrained spectra from the peak of the main pulse, suggesting a change that is limited to a single magnetic pole. The seven years of RXTE measurements do not show any strongly significant evolution with time on their own. We discuss the significance of the CRSF's behaviour with respect to luminosity and time in the context of historical observations of this source as well as recent observational and theoretical work concerning the neutron star accretion column, and suggest some mechanisms by which the observed change over time could occur.
Keywords: Accretion; accretion discs; Pulsars: Individual: 4U 1538-522; Stars: Magnetic field; X-rays: Binaries; X-rays: Stars

Evidence for different accretion regimes in GRO J1008-57 - Kühnel, Matthias; Furst, Felix; Pottschmidt, Katja; Kreykenbohm, Ingo; Ballhausen, Ralf; Falkner, Sebastian; Rothschild, Richard E.; Klochkov, Dmitry; Wilms, Jörn (Astronomy & Astrophysics, 2017)
We present a comprehensive spectral analysis of the BeXRB GRO J1008-57 over a luminosity range of three orders of magnitude using NuSTAR, Suzaku, and RXTE data. We find significant evolution of the spectral parameters with luminosity. In particular, the photon index hardens with increasing luminosity at intermediate luminosities in the range 10(36)-10(37) erg s(-1). This evolution is stable and repeatedly observed over different outbursts. However, at the extreme ends of the observed luminosity range, we find that the correlation breaks down, with a significance level of at least 3.7 sigma. We conclude that these changes indicate transitions to different accretion regimes, which are characterized by different deceleration processes, such as Coulomb or radiation breaking. We compare our observed luminosity levels of these transitions to theoretical predications and discuss the variation of those theoretical luminosity values with fundamental neutron star parameters. Finally, we present detailed spectroscopy of the unique "triple peaked" outburst in 2014/15 which does not fit in the general parameter evolution with luminosity. The pulse profile on the other hand is consistent with what is expected at this luminosity level, arguing against a change in accretion geometry. In summary, GRO J1008-57 is an ideal target to study different accretion regimes due to the well-constrained evolution of its broad-band spectral continuum over several orders of magnitude in luminosity.
Keywords: X-rays: binaries; stars: neutron; stars: emission-line; Be; pulsars: individual: GRO J1008-57

Expansion cone for the 3-inch PMTs of the KM3NeT optical modules - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Aharonian, F.; Aiello, S.; Albert, A.; Alexandri, M.; Ameli, F.; Anassontzis, E. G.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; et al. (Journal of Instrumentation, 2013)
Detection of high-energy neutrinos from distant astrophysical sources will open a new window on the Universe. The detection principle exploits the measurement of Cherenkov light emitted by charged particles resulting from neutrino interactions in the matter containing the telescope. A novel multi-PMT digital optical module (DOM) was developed to contain 31 3-inch photomultiplier tubes (PMTs). In order to maximize the detector sensitivity, each PMT will be surrounded by an expansion cone which collects photons that would otherwise miss the photocathode. Results for various angles of incidence with respect to the PMT surface indicate an increase in collection efficiency by 30% on average for angles up to 45 degrees with respect to the perpendicular. Ray-tracing calculations could reproduce the measurements, allowing to estimate an increase in the overall photocathode sensitivity, integrated over all angles of incidence, by 27% (for a single PMT). Prototype DOMs, being built by the KM3NeT consortium, will be equipped with these expansion cones.
Keywords: Optical detector readout concepts; Instrument optimisation; Cherenkov detectors; Large detector systems for particle and astroparticle physics

Explaining the asymmetric line profile in Cepheus X-4 with spectral variation across pulse phase - Bhargava, Yash; Bhalerao, Varun; Ballhausen, Ralf; Furst, Felix; Pottschmidt, Katja; Tomsick, John A.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2019)
The high mass X-ray binary Cepheus X-4, during its 2014 outburst, showed evidence for an asymmetric cyclotron line in its hard X-ray spectrum. The 2014 spectrum provides one of the clearest cases of an asymmetric line profile among all studied sources with Cyclotron Resonance Scattering Features (CRSF). We present a phase-resolved analysis of NuSTAR and Suzaku data taken at the peak and during the decline phases of this outburst. We find that the pulse-phased resolved spectra are well-fit by a single, symmetric cyclotron feature. The fit parameters vary strongly with pulse phase: most notably the central energy and depth of the cyclotron feature, the slope of the power-law component, and the absorbing column density. We synthesise a 'phase averaged' spectrum using the best-fitting parameters for these individual pulse phases, and find that this combined model spectrum has a similar asymmetry in the cyclotron features as discovered in phase-averaged data. We conclude that the pulse phase resolved analysis with simple symmetric line profiles when combined can explain the asymmetry detected in the phase-averaged data.
Keywords: accretion; accretion discs; stars: neutron; X-rays: binaries; X-rays: individual (Cep X-4)

Extended X-ray emission in PKS 1718-649 - Beuchert, T.; Rodriguez-Ardila, A.; Moss, V. A.; Schulz, R.; Kadler, M.; Wilms, Jörn; Angioni, Roberto; Callingham, J. R.; Gräfe, Christina; Krauss, F.; Kreikenbohm, A.; Langejahn, M.; et al. (Astronomy & Astrophysics, 2018)
PKS 1718 649 is one of the closest and most comprehensively studied candidates of a young active galactic nucleus (AGN) that is still embedded in its optical host galaxy. The compact radio structure, with a maximal extent of a few parsecs, makes it a member of the group of compact symmetric objects (CSO). Its environment imposes a turnover of the radio synchrotron spectrum towards lower frequencies, also classifying PKS 1718-649 as gigahertz-peaked radio spectrum (GPS) source. Its close proximity has allowed the first detection of extended X-ray emission in a GPS/CSO source with Chandra that is for the most part unrelated to nuclear feedback. However, not much is known about the nature of this emission. By co-adding all archival Chandra data and complementing these datasets with the large effective area of XMM-Newton, we are able to study the detailed physics of the environment of PKS 1718-649. Not only can we confirm that the bulk of the less than or similar to kiloparsec-scale environment emits in the soft X-rays, but we also identify the emitting gas to form a hot, collisionally ionized medium. While the feedback of the central AGN still seems to be constrained to the inner few parsecs, we argue that supernovae are capable of producing the observed large-scale X-ray emission at a rate inferred from its estimated star formation rate.
Keywords: galaxies: active; galaxies: nuclei; galaxies: individual: PKS 1718-649; galaxies: ISM; galaxies: star formation; X-rays: galaxies

EXTP: Enhanced X-ray Timing and Polarization mission - Zhang, S. N.; Feroci, M.; Santangelo, A.; Dong, Y. W.; Feng, H.; Lu, F. J.; Nandra, K.; Wang, Z. S.; Zhang, S.; Bozzo, E.; Brandt, S.; De Rosa, A.; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
EXTP is a science mission designed to study the state of matter under extreme conditions of density, gravity and magnetism. Primary goals are the determination of the equation of state of matter at supra-nuclear density, the measurement of QED effects in highly magnetized star, and the study of accretion in the strong-field regime of gravity. Primary targets include isolated and binary neutron stars, strong magnetic field systems like magnetars, and stellar-mass and supermassive black holes. The mission carries a unique and unprecedented suite of state-of-the-art scientific instruments enabling for the first time ever the simultaneous spectral-timing-polarimetry studies of cosmic sources in the energy range from 0.5-30 keV (and beyond). Key elements of the payload are: the Spectroscopic Focusing Array (SFA) - a set of 11 X-ray optics for a total effective area of ∼0.9 m and 0.6 m at 2 keV and 6 keV respectively, equipped with Silicon Drift Detectors offering <180 eV spectral resolution; the Large Area Detector (LAD) - a deployable set of 640 Silicon Drift Detectors, for a total effective area of ∼3.4 m, between 6 and 10 keV, and spectral resolution better than 250 eV; the Polarimetry Focusing Array (PFA) - a set of 2 X-ray telescope, for a total effective area of 250 cm at 2 keV, equipped with imaging gas pixel photoelectric polarimeters; the Wide Field Monitor (WFM) - a set of 3 coded mask wide field units, equipped with position-sensitive Silicon Drift Detectors, each covering a 90 degrees × 90 degrees field of view. The eXTP international consortium includes major institutions of the Chinese Academy of Sciences and Universities in China, as well as major institutions in several European countries and the United States. The predecessor of eXTP, the XTP mission concept, has been selected and funded as one of the so-called background missions in the Strategic Priority Space Science Program of the Chinese Academy of Sciences since 2011. The strong European participation has significantly enhanced the scientific capabilities of eXTP. The planned launch date of the mission is earlier than 2025.
Keywords: Neutron Star EOS; spectroscopy; Strong Gravity; Strong Magnetism; X-ray astronomy; X-ray timing

Extragalactic Wolf-Rayet/black-hole X-ray binary candidates NGC 300 X-1 and IC 10 X-1 - Carpano, S.; Pollock, A. M. T.; Prestwich, A.; Kilgard, R.; Crowther, P.; Wilms, Jörn; Yungelson, L.; Ehle, Matthias (2008)
NGC 300 X-1 and IC 10 X-1 have recently been identified in nearby galaxies as extragalactic examples of the rare class of Wolf-Rayet/compact object X-ray binary system uniquely exemplified in the Galaxy by Cyg X-3. Using Swift TOO observations of NGC 300 X-1 and IC 10 X-1, we recently discovered very similar periods of 32.8 +/- 0.4 and 34.8 +/- 0.9 hours, respectively. We believe that these are likely to be orbital periods. It seems surprising that these are so similar and large compared to the short 4.8 hour period of Cyg X-3, suggesting different evolutionary paths. For both extragalactic candidates we show the allowed ranges of component masses and Wolf-Rayet star wind velocities for which accretion disks could form around the black holes.

EXTraS discovery of an 1.2-s X-ray pulsar in M 31 - Esposito, Paolo; Israel, G. L.; Belfiore, Andrea; Novara, G.; Sidoli, Lara; Castillo, G. A. Rodriguez; De Luca, Andrea; Tiengo, A.; Haberl, Frank; Salvaterra, Ruben; Read, A. M.; Salvetti, D.; et al. (Monthly Notices of the Royal Astronomical Society: Letters, 2016)
During a search for coherent signals in the X-ray archival data of XMM-Newton, we discovered a modulation at 1.2 s in 3XMMJ004301.4+413017 (3X J0043), a source lying in the direction of an external arm ofM31. This short period indicates a neutron star (NS). Between 2000 and 2013, the position of 3X J0043 was imaged by public XMM-Newton observations 35 times. The analysis of these data allowed us to detect an orbital modulation at 1.27 d and study the long-term properties of the source. The emission of the pulsar was rather hard (most spectra are described by a power law withΓ <1) and, assuming the distance to M 31, the 0.3-10 keV luminosity was variable, from 3 × 10 to 2 × 10 erg s. The analysis of optical data shows that, while 3X J0043 is likely associated to a globular cluster in M 31, a counterpart with V ≥ 22 outside the cluster cannot be excluded. Considering our findings, there are two main viable scenarios for 3X J0043: a peculiar low-mass X-ray binary, similar to 4U 1822-37 or 4U 1626-67, or an intermediate-mass X-ray binary resembling Her X-1. Regardless of the exact nature of the system, 3X J0043 is the first accreting NS in M 31 in which the spin period has been detected.
Keywords: Galaxies: individual: M 31; X-rays: binaries; X-rays: individual: 3XMM J004301.4+413017

Extreme ultra-soft X-ray variability in an eROSITA observation of the narrow-line Seyfert 1 galaxy 1H 0707-495 - Boller, Th; Liu, T.; Weber, Philipp; Arcodia, R.; Dauser, Thomas; Wilms, Jörn; Nandra, K.; Buchner, J.; Merloni, A.; Freyberg, M. J.; Krumpe, M.; Waddell, S. G.H. (Astronomy & Astrophysics, 2021)
The ultra-soft narrow-line Seyfert 1 galaxy 1H 0707-495 is a well-known and highly variable active galactic nucleus (AGN), with a complex, steep X-ray spectrum, and has been studied extensively with XMM-Newton. 1H 0707-495 was observed with the extended ROentgen Survey with an Imaging Telescope Array (eROSITA) aboard the Spectrum-Roentgen-Gamma (SRG) mission on October 11, 2019, for about 60 000 s as one of the first calibration and pointed verification phase (CalPV) observations. The eROSITA light curves show significant variability in the form of a flux decrease by a factor of 58 with a 1 σ error confidence interval between 31 and 235. This variability is primarily in the soft band, and is much less extreme in the hard band. No strong ultraviolet variability has been detected in simultaneous XMM-Newton Optical Monitor observations. The UV emission is LUV ≈ 1044 erg s-1, close to the Eddington limit. 1H 0707-495 entered the lowest hard flux state seen in 20 yr of XMM-Newton observations. In the eROSITA All-Sky Survey (eRASS) observations taken in April 2020, the X-ray light curve is still more variable in the ultra-soft band, but with increased soft and hard band count rates more similar to previously observed flux states. A model including relativistic reflection and a variable partial covering absorber is able to fit the spectra and provides a possible explanation for the extreme light-curve behaviour. The absorber is probably ionised and therefore more transparent to soft X-rays. This leaks soft X-rays in varying amounts, leading to large-Amplitude soft-X-ray variability.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Accretion; accretion disks; Galaxies: Seyfert; X-rays: general

Fermi/LAT counterparts of IceCube neutrinos above 100 TeV - Krauss, F.; Deoskar, K.; Baxter, Claire; Kadler, M.; Kreter, M.; Langejahn, M.; Mannheim, K.; Polko, P.; Wang, B.; Wilms, Jörn (Astronomy & Astrophysics, 2018)
The IceCube Collaboration has published four years of data and the observed neutrino flux is significantly in excess of the expected atmospheric background. Due to the steeply falling atmospheric background spectrum, events at the highest energies are most likely extraterrestrial. In our previous approach we have studied blazars as the possible origin of the High-Energy Starting Events (HESE) neutrino events at PeV energies. In this work we extend our study to include all HESE neutrinos (which does not include IC 170922A) at or above a reconstructed energy of 100 TeV, but below 1 PeV. We study the X-ray and gamma-ray data of all (similar to 200) 3LAC blazars that are positionally consistent with the neutrino events above 100 TeV to determine the maximum neutrino flux from these sources. This larger sample allows us to better constrain the scaling factor between the observed and maximum number of neutrino events. We find that when we consider a realistic neutrino spectrum and other factors, the number of neutrinos is in good agreement with the detected number of IceCube HESE events. We also show that there is no direct correlation between Fermi/LAT gamma-ray flux and the IceCube neutrino flux and that the expected number of neutrinos is consistent with the non-detection of individual bright blazars.
Keywords: neutrinos; galaxies: active; quasars: general; BL Lacertae objects: general

Finding a 24-day orbital period for the X-ray binary 1A 1118-616 - Staubert, R.; Pottschmidt, K.; Doroshenko, Victor; Wilms, Jörn; Suchy, S.; Rothschild, R.; Santangelo, A. (Astronomy & Astrophysics, 2011)
We report the first determination of the binary period and orbital ephemeris of the Be X-ray binary containing the pulsar 1A 1118-616 (35 years after the discovery of the source). The orbital period is found to be P(orb) = 24.0 +/- 0.4 days. The source was observed by RXTE during its last large X-ray outburst in January 2009, which peaked at MJD 54845.4, by taking short observations every few days, covering an elapsed time comparable to the orbital period. Using the phase connection technique, pulse arrival time delays could be measured and an orbital solution determined. The data are consistent with a circular orbit and the time of 90 degrees longitude was found to be T(pi/2) = MJD 54845.37(10), which is coincident with that of the peak X-ray flux.
Keywords: binaries: general; stars: neutron; X-rays: general; X-rays: binaries; X-rays: individuals: 1A 1118-616; ephemerides

First all-flavor neutrino pointlike source search with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
A search for cosmic neutrino sources using the data collected with the ANTARES neutrino telescope between early 2007 and the end of 2015 is performed. For the first time, all neutrino interactions-charged and neutral-current interactions of all flavors-are considered in a search for point-like sources with the ANTARES detector. In previous analyses, only muon neutrino charged-current interactions were used. This is achieved by using a novel reconstruction algorithm for shower-like events in addition to the standard muon track reconstruction. The shower channel contributes about 23% of all signal events for an E-2 energy spectrum. No significant excess over background is found. The most signal-like cluster of events is located at (alpha, delta) = (343.8 degrees, 23.5 degrees) with a significance of 1.9 sigma. The neutrino flux sensitivity of the search is about E(2)d Phi/dE = 6 x 10(-9) GeV cm(-2) s(-1) for declinations from -90 degrees up to -42 degrees, and below 10(-8) GeV cm(-2) s(-1) for declinations up to 5 degrees. The directions of 106 source candidates and 13 muon track events from the IceCube high-energy sample events are investigated for a possible neutrino signal and upper limits on the signal flux are determined.

First multi-wavelength campaign on the gamma-ray-loud active galaxy IC 310 - Ahnen, M. L.; Ansoldi, S.; Antonelli, L. A.; Arcaro, C.; Babic, A.; Banerjee, B.; Bangale, P.; De Almeida, U. Barres; Barrio, J. A.; Becerra Gonzalez, Josefa; Bednarek, Wlodek; Bernardini, E.; et al. (Astronomy & Astrophysics, 2017)
Context. The extragalactic very-high-energy gamma-ray sky is rich in blazars. These are jetted active galactic nuclei that are viewed at a small angle to the line-of-sight. Only a handful of objects viewed at a larger angle are so far known to emit above 100 GeV. Multi-wavelength studies of such objects up to the highest energies provide new insights into the particle and radiation processes of active galactic nuclei.Aims. We aim to report the results from the first multi-wavelength campaign observing the TeV detected nucleus of the active galaxy IC 310, whose jet is observed at a moderate viewing angle of 10 degrees-20 degrees.Methods. The multi-instrument campaign was conducted between 2012 November and 2013 January, and involved observations with MAGIC, Fermi, INTEGRAL, Swift, OVRO, MOJAVE and EVN. These observations were complemented with archival data from the AllWISE and 2MASS catalogs. A one-zone synchrotron self-Compton model was applied to describe the broadband spectral energy distribution.Results. IC 310 showed an extraordinary TeV flare at the beginning of the campaign, followed by a low, but still detectable TeV flux. Compared to previous measurements in this energy range, the spectral shape was found to be steeper during the low emission state. Simultaneous observations in the soft X-ray band showed an enhanced energy flux state and a harder-when-brighter spectral shape behavior. No strong correlated flux variability was found in other frequency regimes. The broadband spectral energy distribution obtained from these observations supports the hypothesis of a double-hump structure.Conclusions. The harder-when-brighter trend in the X-ray and VHE emission, observed for the first time during this campaign, is consistent with the behavior expected from a synchrotron self-Compton scenario. The contemporaneous broadband spectral energy distribution is well described with a one-zone synchrotron self-Compton model using parameters that are comparable to those found for other gamma-ray-emitting misaligned blazars.
Keywords: galaxies: active; galaxies: individual: IC 310; gamma rays: galaxies

First observations of speed of light tracks by a fluorescence detector looking down on the atmosphere - Abdellaoui, G.; Abe, S.; Adams, J. H.; Ahriche, A.; Allard, D.; Allen, L.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arai, Y.; Asano, K.; Attallah, R.; et al. (Journal of Instrumentation, 2018)
EUSO-Balloon is a pathfinder mission for the Extreme Universe Space Observatory onboard the Japanese Experiment Module (JEM-EUSO). It was launched on the moonless night of the 25(th) of August 2014 from Timmins, Canada. The flight ended successfully after maintaining the target altitude of 38 km for five hours. One part of the mission was a 2.5 hour underflight using a helicopter equipped with three UV light sources (LED, xenon flasher and laser) to perform an inflight calibration and examine the detectors capability to measure tracks moving at the speed of light. We describe the helicopter laser system and details of the underflight as well as how the laser tracks were recorded and found in the data. These are the first recorded laser tracks measured from a fluorescence detector looking down on the atmosphere. Finally, we present a first reconstruction of the direction of the laser tracks relative to the detector.
Keywords: Detectors for UV; visible and IR photons; Lasers; Balloon instrumentation; Space instrumentation

First results on dark matter annihilation in the Sun using the ANTARES neutrino telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anton, L.; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
A search for high-energy neutrinos coming from the direction of the Sun has been performed using the data recorded by the ANTARES neutrino telescope during 2007 and 2008. The neutrino selection criteria have been chosen to maximize the selection of possible signals produced by the self-annihilation of weakly interacting massive particles accumulated in the centre of the Sun with respect to the atmospheric background. After data unblinding, the number of neutrinos observed towards the Sun was found to be compatible with background expectations. The 90% CL upper limits in terms of spin-dependent and spin-independent WIMP-proton cross-sections are derived and compared to predictions of two supersymmetric models, CMSSM and MSSM-7. The ANTARES limits are comparable with those obtained by other neutrino observatories and are more stringent than those obtained by direct search experiments for the spin-dependent WIMP-proton cross-section in the case of hard self-annihilation channels (W+W-, tau(+)tau(-)).
Keywords: neutrino experiments; dark matter detectors; supersymmetry and cosmology; particle physics - cosmology connection

First search for neutrinos in correlation with gamma-ray bursts with the ANTARES neutrino telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Journal of Cosmology and Astroparticle Physics, 2013)
A search for neutrino-induced muons in correlation with a selection of 40 gamma-ray bursts that occurred in 2007 has been performed with the ANTARES neutrino telescope. During that period, the detector consisted of 5 detection lines. The ANTARES neutrino telescope is sensitive to TeV-PeV neutrinos that are predicted from gamma-ray bursts. No events were found in correlation with the prompt photon emission of the gamma-ray bursts and upper limits have been placed on the flux and fluence of neutrinos for different models.
Keywords: neutrino experiments; neutrino astronomy; gamma ray bursts theory

FIRST SEARCH FOR POINT SOURCES OF HIGH-ENERGY COSMIC NEUTRINOS WITH THE ANTARES NEUTRINO TELESCOPE - Adrian-Martinez, S.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J. -J.; et al. (Astrophysical Journal Letters, 2011)
Results are presented of a search for cosmic sources of high-energy neutrinos with the ANTARES neutrino telescope. The data were collected during 2007 and 2008 using detector configurations containing between 5 and 12 detection lines. The integrated live time of the analyzed data is 304 days. Muon tracks are reconstructed using a likelihood-based algorithm. Studies of the detector timing indicate a median angular resolution of 0.5 +/- 0.1 deg. The neutrino flux sensitivity is 7.5 x 10(-8)(E(v)/GeV)(-2) GeV(-1) s(-1) cm(-2) for the part of the sky that is always visible (delta < -48 deg), which is better than limits obtained by previous experiments. No cosmic neutrino sources have been observed.
Keywords: astroparticle physics; cosmic rays; neutrinos

gamma-ray emission from the Perseus cluster of galaxies observed with the MAGIC telescopes - Colin, P.; Eisenacher, D.; Hildebrand, D.; Lombardi, S.; Lindorfs, E.; Paneque, D.; Partini, S.; Prada, F.; Sitarek, Julian; Zandanel, F.; Dauser, Thomas; Kadler, M.; et al. (2012)
The Perseus cluster of galaxies is a nearby cool-core cluster with an intra-cluster medium (ICM) characterized by very high central densities. The observation of the Perseus cluster with the MAGIC telescopes, during 85 h from 2009 to 2011, resulted in the discovery of 2 point-like sources at very high energy (>100GeV, VHE) coinciding with the central radio galaxy NGC1275 and the radio galaxy IC 310. The gamma-ray properties of these 2 sources are presented, taking into account contemporaneous Fermi-LAT as well as multi-wavelength data. Flux variability and spectral energy distribution shapes indicate that the VHE gamma-rays do not originate from large-scale interaction of the radio galaxies with ICM but more likely from the active nuclei of these two galaxies. They could be both misaligned version of BL Lac objects, the most common TeV AGN. Our results provide vital clues to understand emission mechanisms of such misaligned objects, and how they may be related to the beamed emission seen in BL Lacs. No evidence of large-scale VHE gamma-ray emission from hadronic cosmic ray (CR) interactions with the ICM has been found. The flux upper limit above 1 TeV reaches the signal expected by some theoretical models, constraining the cluster CR physics. In the framework of the hadronic model of the radiomini-halos, this limit implies a minimal magnetic field ranging from 4-9 mu G for the central cluster region.
Keywords: gamma-ray astronomy; Galaxy Cluster; Radio galaxy; NGC 1275; IC 310; Cosmic rays

Gamma-ray emission in radio galaxies under the VLBI scope: I. Parsec-scale jet kinematics and high-energy properties of γ -ray-detected TANAMI radio galaxies - Angioni, Roberto; Ros, E.; Kadler, M.; Ojha, R.; Mueller, C.; Edwards, P. G.; Burd, P. R.; Carpenter, B.; Dutka, M. S.; Gulyaev, S.; Hase, H.; Horiuchi, S.; et al. (Astronomy & Astrophysics, 2019)
Aims. In the framework of the multi-wavelength and very long baseline interferometry (VLBI) monitoring program TANAMI (Tracking Active Nuclei with Austral Milliarcsecond Interferometry), we study the evolution of the parsec-scale radio emission in radio galaxies in the southern hemisphere and their relationship to the γ-ray properties of the sources. Our study investigates systematically, for the first time, the relationship between the two energy regimes in radio galaxies. In this first paper, we focus on Fermi-LAT-detected sources. Methods. The TANAMI program monitors a large sample of radio-loud AGN at 8.4 GHz and 22.3 GHz with the Australian long baseline array (LBA) and associated telescopes in Antarctica, Chile, New Zealand and South Africa. We performed a kinematic analysis for five γ-ray detected radio galaxies using multi-epoch 8.4 GHz VLBI images, deriving limits on intrinsic jet parameters such as speed and viewing angle. We analyzed 103 months of Fermi-LAT data in order to study possible connections between the γ-ray properties and the pc-scale jets of Fermi-LAT-detected radio galaxies, both in terms of variability and average properties. We discuss the individual source results and draw preliminary conclusions on sample properties including published VLBI results from the MOJAVE (Monitoring Of Jets in Active galactic nuclei with VLBA Experiments) survey, with a total of fifteen sources. Results. We find that the first γ-ray detection of Pictor A might be associated with the passage of a new VLBI component through the radio core, which appears to be a defining feature of high-energy emitting Fanaroff-Riley type II radio galaxies. We detect subluminal parsec-scale jet motions in the peculiar AGN PKS 0521-36, and we confirm the presence of fast γ-ray variability in the source down to timescales of six hours, which is not accompanied by variations in the VLBI jet. We robustly confirm the presence of significant superluminal motion, up to βapp ∼ 3, in the jet of the TeV radio galaxy PKS 0625-35. Our VLBI results constrain the jet viewing angle to be θ < 53°, allowing for the possibility of a closely aligned jet. Finally, by analyzing the first pc-scale multi-epoch images of the prototypical compact symmetric object (CSO) PKS 1718-649, we place an upper limit on the separation speed between the two mini-lobes. This in turn allows us to derive a lower limit on the age of the source. Conclusions. We can draw some preliminary conclusions on the relationship between pc-scale jets and γ-ray emission in radio galaxies, based on Fermi-LAT-detected sources with available multi-epoch VLBI measurements. We find that the VLBI core flux density correlates with the γ-ray flux, as seen in blazars. On the other hand, the γ-ray luminosity does not show any dependence on the core brightness temperature and core dominance, which are two common indicators of jet Doppler boosting. This seems to indicate that γ-ray emission in radio galaxies is not driven by orientation-dependent effects, as in blazars, in accordance with the unified model of jetted AGN.
CRIS-Team Scopus Importer:2019-08-02
Keywords: Galaxies: active; Galaxies: jets; Galaxies: nuclei; γrays: galaxies

GAMMA-RAY OBSERVATIONS OF THE MICROQUASARS CYGNUS X-1, CYGNUS X-3, GRS 1915+105, AND GX 339-4 WITH THE FERMI LARGE AREA TELESCOPE - Bodaghee, Arash; Tomsick, John A.; Pottschmidt, Katja; Rodriguez, Jerome; Wilms, Jörn; Pooley, Guy G. (Astrophysical Journal, 2013)
Detecting gamma-rays from microquasars is a challenging but worthwhile endeavor for understanding particle acceleration and the jet mechanism and for constraining leptonic/hadronic emission models. We present results from a likelihood analysis on timescales of 1 day and 10 days of similar to 4 yr worth of gamma-ray observations (0.1-10 GeV) by Fermi-LAT of Cyg X-1, Cyg X-3, GRS 1915 + 105, and GX 339-4. Our analysis reproduced all but one of the previous gamma-ray outbursts of Cyg X-3 as reported with Fermi or AGILE, plus five new days on which Cyg X-3 is detected at a significance of similar to 5 sigma that are not reported in the literature. In addition, Cyg X-3 is significantly detected on 10 day timescales outside of known gamma-ray flaring epochs, which suggests that persistent gamma-ray emission from Cyg X-3 has been detected for the first time. For Cyg X-1 we find three low-significance excesses (similar to 3-4 sigma) on daily timescales that are contemporaneous with gamma-ray flares reported (also at low significance) by AGILE. Two other microquasars, GRS 1915+105 and GX 339-4, are not detected, and we derive 3 sigma upper limits of 2.3 x 10(-8) photons cm(-2) s(-1) and 1.6 x 10-8 photons cm(-2) s(-1), respectively, on the persistent flux in the 0.1-10 GeV range. These results enable us to define a list of the general conditions that are necessary for the detection of gamma-rays from microquasars.
Keywords: black hole physics; gamma rays: stars; stars: neutron; X-rays: binaries; X-rays: individual (Cygnus X-3; Cygnus X-1; GRS 1915+105; GX 339-4)

Geant4 simulation for the responses to X-rays and charged particles through the eXTP focusing mirrors - Qi, L. Q.; Li, G.; Xu, Y. P.; Zhang, J.; Yang, Y. J.; Sheng, L. Z.; Basso, S.; Campana, R.; Chen, Y.; De Rosa, A.; Pareschi, G.; Qiang, P. F.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2020)
A geometrical and physical model of Wolter-I type mirrors has been implemented in Geant4 for the design of the enhanced X-ray Timing and Polarimetry observatory (eXTP). It can simultaneously simulate the mirror responses to X-rays and charged particles. A new geometry class G4Hyperboloid is created and verified, which allows an exact surface profile description of Wolter-I optics. A physics model for the interaction of X-rays and matter is implemented to effectively estimate the focusing performances with reasonable accuracy, including the effective area and the point spread function. Scattering models of charged particles at grazing incidence are discussed. The multiple scattering model provided by the latest Geant4 release can be used instead of the single scattering model with reasonable accuracy and CPU cost when the step size is properly constrained.
CRIS-Team Scopus Importer:2020-03-17
Keywords: eXTP; Geant4; X-ray telescope

GPU Supported Simulation of Transition-Edge Sensor Arrays - Lorenz, Maximilian; Kirsch, Christian; Merino-Alonso, P. E.; Peille, P.; Dauser, Thomas; Cucchetti, E.; Smith, S. J.; Wilms, Jörn (Journal of Low Temperature Physics, 2020)
We present numerical simulations of full transition-edge sensor (TES) arrays utilizing graphical processing units (GPUs). With the support of GPUs, it is possible to perform simulations of large pixel arrays to assist detector development. Comparisons with TES small-signal and noise theory confirm the representativity of the simulated data. In order to demonstrate the capabilities of this approach, we present its implementation in xifusim, a simulator for the X-ray Integral Field Unit, a cryogenic X-ray spectrometer on board the future Athena X-ray observatory.
CRIS-Team WoS Importer:2020-04-24

GRO J1008-57: an (almost) predictable transient X-ray binary - Kühnel, Matthias; Müller, Sebastian; Kreykenbohm, Ingo; Fuerst, F.; Pottschmidt, K.; Rothschild, R. E.; Caballero, I.; Grinberg, Victoria; Schoenherr, G.; Shrader, C.; Klochkov, D.; Staubert, R.; et al. (Astronomy & Astrophysics, 2013)
A study of archival RXTE, Swift, and Suzaku pointed observations of the transient high-mass X-ray binary GRO J1008-57 is presented. A new orbital ephemeris based on pulse arrival-timing shows the times of maximum luminosities during outbursts of GRO J1008-57 to be close to periastron at orbital phase -0.03. This makes the source one of a few for which outburst dates can be predicted with very high precision. Spectra of the source in 2005, 2007, and 2011 can be well described by a simple power law with high-energy cutoff and an additional black body at lower energies. The photon index of the power law and the black-body flux only depend on the 15-50 keV source flux. No apparent hysteresis effects are seen. These correlations allow us to predict the evolution of the pulsar's X-ray spectral shape over all outbursts as a function of just one parameter, the source's flux. If modified by an additional soft component, this prediction even holds during GRO J1008-57's 2012 type II outburst.
Keywords: X-rays: binaries; pulsars: individual: GRO J1008-57; accretion; accretion disks; ephemerides

GRS 1739-278 Observed at Very Low Luminosity with XMM-Newton and NuSTAR - Furst, F.; Tomsick, J. A.; Yamaoka, K.; Dauser, Thomas; Miller, J. M.; Clavel, Maica; Corbel, S.; Fabian, A.; Garcia, Javier; Harrison, F. A.; Loh, A.; Kaaret, P.; et al. (Astrophysical Journal, 2016)
Keywords: accretion; accretion disks; stars: black holes; X-rays: binaries; X-rays: individual: GRS 1739-278

Hard X-ray properties of radio-selected blazars - Langejahn, M.; Kadler, M.; Wilms, Jörn; Litzinger, E.; Kreter, M.; Gehrels, N.; Baumgartner, W. H.; Markwardt, C. B.; Tueller, J. (Astronomy & Astrophysics, 2020)
Context. Hard X-ray properties of beamed active galactic nuclei have been published in the 105-month Swift/BAT catalog, but there have not been any studies carried out so far on a well-defined, radio-selected sample of low-peaked blazars in the hard X-ray band.
CRIS-Team WoS Importer:2020-06-16

High-energy neutrino follow-up search of gravitational wave event GW150914 with ANTARES and IceCube - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2016)
We present the high-energy-neutrino follow-up observations of the first gravitational wave transient GW150914 observed by the Advanced LIGO detectors on September 14, 2015. We search for coincident neutrino candidates within the data recorded by the IceCube and Antares neutrino detectors. A possible joint detection could be used in targeted electromagnetic follow-up observations, given the significantly better angular resolution of neutrino events compared to gravitational waves. We find no neutrino candidates in both temporal and spatial coincidence with the gravitational wave event. Within ±500 s of the gravitational wave event, the number of neutrino candidates detected by IceCube and Antares were three and zero, respectively. This is consistent with the expected atmospheric background, and none of the neutrino candidates were directionally coincident with GW150914. We use this nondetection to constrain neutrino emission from the gravitational-wave event.

Highly charged ions in a new era of high resolution X-ray astrophysics - Hell, Natalie; Beiersdorfer, Peter; Brown, Gregory V.; Eckart, Megan E.; Kelley, Richard L.; Kilbourne, Caroline A.; Leutenegger, Maurice A.; Lockard, Thomas E.; Porter, F. Scott; Wilms, Jörn (X-Ray Spectrometry, 2019)
X-ray astronomy and ground-based atomic physics have a long history of fruitful collaboration: Sound understanding of the underlying atomic physics is the key to reliable interpretation of the spectra from celestial sources; conversely, astronomical spectra have been used to benchmark and advance atomic physics. This interplay is about to become even more important as we enter a new era of high-resolution X-ray astrophysics with large effective collection area. Although high-resolution observations with the gratings on the Chandra and XMM-Newton observatories continue to drive new science, upcoming planned and proposed missions will open up new discovery space in the near future that is currently challenging to access: high-resolution spectroscopy on extended sources, in the Fe K band, and on short time scales. This review summarizes open questions in these areas and the design parameters for the Hitomi, XRISM, Athena, and Arcus observatories. The expected high quality of spectra taken with these observatories puts new constraints on the accuracy of atomic reference data required to take full advantage of the diagnostic potential of these spectra.
CRIS-Team Scopus Importer:2019-11-19

High-Precision Determination of Oxygen Kα Transition Energy Excludes Incongruent Motion of Interstellar Oxygen - Leutenegger, M. A.; Kühn, S.; Micke, P.; Steinbrügge, R.; Stierhof, Jakob; Shah, C.; Hell, N.; Bissinger, Matthias; Hirsch, Maria; Ballhausen, Ralf; Lang, Melanie; Gräfe, Christina; et al. (Physical Review Letters, 2020)
We demonstrate a widely applicable technique to absolutely calibrate the energy scale of x-ray spectra with experimentally well-known and accurately calculable transitions of highly charged ions, allowing us to measure the K-shell Rydberg spectrum of molecular O2 with 8 meV uncertainty. We reveal a systematic ∼450 meV shift from previous literature values, and settle an extraordinary discrepancy between astrophysical and laboratory measurements of neutral atomic oxygen, the latter being calibrated against the aforementioned O2 literature values. Because of the widespread use of such, now deprecated, references, our method impacts on many branches of x-ray absorption spectroscopy. Moreover, it potentially reduces absolute uncertainties there to below the meV level.
CRIS-Team Scopus Importer:2020-12-25

High Resolution Photoexcitation Measurements Exacerbate the Long-Standing Fe XVII Oscillator Strength Problem - Kuehn, Steffen; Shah, Chintan; Lopez-Urrutia, Jose R. Crespo; Fujii, Keisuke; Steinbruegge, Rene; Stierhof, Jakob; Togawa, Moto; Harman, Zoltan; Oreshkina, Natalia S.; Cheung, Charles; Kozlov, Mikhail G.; Porsev, Sergey G.; et al. (Physical Review Letters, 2020)
For more than 40 years, most astrophysical observations and laboratory studies of two key soft x-ray diagnostic 2p-3d transitions, 3C and 3D, in Fe XVII ions found oscillator strength ratios f(3C)/f(3D) disagreeing with theory, but uncertainties had precluded definitive statements on this much studied conundrum. Here, we resonantly excite these lines using synchrotron radiation at PETRA III, and reach, at a millionfold lower photon intensities, a 10 times higher spectral resolution, and 3 times smaller uncertainty than earlier work. Our final result of f(3C)/f(3D)=3.09(8)(6) supports many of the earlier clean astrophysical and laboratory observations, while departing by five sigmas from our own newest large-scale ab initio calculations, and excluding all proposed explanations, including those invoking nonlinear effects and population transfers.
CRIS-Team Scopus Importer:2021-04-19

High variability in Vela X-1: giant flares and off states - Kreykenbohm, Ingo; Wilms, Jörn; Kretschmar, Peter; Torrejon, J. M.; Pottschmidt, K.; Hanke, Manfred; Santangelo, A.; Ferrigno, Carlo; Staubert, R. (Astronomy & Astrophysics, 2008)
Aims. We investigate the spectral and temporal behavior of the high mass X-ray binary Vela X-1 during a phase of high activity, with special focus on the observed giant flares and off states.Methods. INTEGRAL observed Vela X-1 in a long almost uninterrupted observation for two weeks in 2003 Nov/Dec. The data were analyzed with OSA 7.0 and FTOOLS 6.2. We derive the pulse period, light curves, spectra, hardness ratios, and hardness intensity diagrams, and study the eclipse.Results. In addition to an already high activity level, Vela X-1 exhibited several intense flares, the brightest ones reaching a maximum intensity of more than 5 Crab in the 20-40 keV band and several off states where the source was no longer detected by INTEGRAL. We determine the pulse period to be 283.5320 +/- 0.0002 s, which is stable throughout the entire observation. Analyzing the eclipses provided an improvement in the ephemeris. Spectral analysis of the flares indicates that there appear to be two types of flares: relatively brief flares, which can be extremely intense and show spectral softening, in contrast to high intensity states, which are longer and show no softening.Conclusions. Both flares and off states are interpreted as being due to a strongly structured wind of the optical companion. When Vela X-1 encounters a cavity with strongly reduced density, the flux will drop triggering the onset of the propeller effect, which inhibits further accretion, giving rise to off states. The sudden decrease in the density of the material required to trigger the propeller effect in Vela X-1 is of the same order as predicted by theoretical papers about the densities in OB star winds. A similarly structured wind can produce giant flares when Vela X-1 encounters a dense blob in the wind.
Keywords: X-rays: stars; stars: flare; stars: pulsars: individual: Vela X-1; stars: magnetic fields

Hot subdwarf stars in close-up view: I. Rotational properties of subdwarf B stars in close binary systems and nature of their unseen companions - Geier, Stephan; Heber, Ulrich; Podsiadlowski, Ph.; Edelmann, Heinz; Napiwotzki, R.; Kupfer, Thomas; Müller, Sebastian (Astronomy & Astrophysics, 2010)
The origin of hot subdwarf B stars (sdBs) is still unclear. About half of the known sdBs are in close binary systems for which common envelope ejection is the most likely formation channel. Little is known about this dynamic phase of binary evolution. Since most of the known sdB systems are single-lined spectroscopic binaries, it is difficult to derive masses and unravel the companions' nature, which is the aim of this paper. Due to the tidal influence of the companion in close binary systems, the rotation of the primary becomes synchronised to its orbital motion. In this case it is possible to constrain the mass of the companion, if the primary mass, its projected rotational velocity as well as its surface gravity are known. For the first time we measured the projected rotational velocities of a large sdB binary sample from high resolution spectra. We analysed a sample of 51 sdB stars in close binaries, 40 of which have known orbital parameters comprising half of all such systems known today. Synchronisation in sdB binaries is discussed both from the theoretical and the observational point of view. The masses and the nature of the unseen companions could be constrained in 31 cases. We found orbital synchronisation most likely to be established in binaries with orbital periods shorter than 1.2 d. Only in five cases it was impossible to decide whether the sdB's companion is a white dwarf or an M dwarf. The companions to seven sdBs could be clearly identified as late M stars. One binary may have a brown dwarf companion. The unseen companions of nine sdBs are white dwarfs with typical masses. The mass of one white dwarf companion is very low. In eight cases (including the well known system KPD1930+2752) the companion mass exceeds 0.9∼M-, four of which even exceed the Chandrasekhar limit indicating that they may be neutron stars. Even stellar mass black holes are possible for the most massive companions. The distribution of the inclinations of the systems with low mass companions appears to be consistent with expectations, whereas a lack of high inclinations becomes obvious for the massive systems. We show that the formation of such systems can be explained with common envelope evolution and present an appropriate formation channel including two phases of unstable mass transfer and one supernova explosion. The sample also contains a candidate post-RGB star, which rotates fast despite its long orbital period. The post-RGB stars are expected to spin-up caused by their ongoing contraction. The age of the sdB is another important factor. If the EHB star is too young, the synchronisation process might not be finished yet. Estimating the ages of the target stars from their positions on the EHB band, we found PG 2345+318, which is known not to be synchronised, to lie near the zero-age extreme horizontal branch as are the massive candidates PG 1232-136, PG 1432+159 and PG 1101+249. These star may possibly be too young to have reached synchronisation. The derived large fraction of putative massive sdB binary systems in low inclination orbits is inconsistent with theoretical predictions. Even if we dismiss three candidates because they may be too young and assume that the other sdB primaries are of low mass, PG 1743+477 and, in particular, HE 0532-4503 remain as candidates whose companions may have masses close to or above the Chandrasekhar limit. X-ray observations and accurate photometry are suggested to clarify their nature. As high inclination systems must also exist, an appropriate survey has already been launched to find such binaries. © 2010 ESO.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; stars: rotation; subdwarfs

Implications of the Warm Corona and Relativistic Reflection Models for the Soft Excess in Mrk 509 - Garcia, Javier A.; Kara, Erin; Walton, Dominic; Beuchert, Tobias; Dauser, Thomas; Gatuzz, Efrain; Balokovic, Mislav; Steiner, James F.; Tombesi, Francesco; Connors, Riley M. T.; Kallman, Timothy R.; Harrison, Fiona A.; et al. (Astrophysical Journal, 2019)
We present the analysis of the first Nuclear Spectroscopic Telescope Array observations (similar to 220 ks), simultaneous with the last Suzaku observations (similar to 50 ks), of the active galactic nucleus of the bright Seyfert 1 galaxy Mrk 509. The time-averaged spectrum in the 1-79 keV X-ray band is dominated by a power-law continuum (Gamma similar to 1.8-1.9), a strong soft excess around 1 keV, and signatures of X-ray reflection in the form of Fe K emission (similar to 6.4 keV), an Fe K absorption edge (similar to 7.1 keV), and a Compton hump due to electron scattering (similar to 20-30 keV). We show that these data can be described by two very different prescriptions for the soft excess: a warm (kT similar to 0.5-1 keV) and optically thick (tau similar to 10-20) Comptonizing corona or a relativistically blurred ionized reflection spectrum from the inner regions of the accretion disk. While these two scenarios cannot be distinguished based on their fit statistics, we argue that the parameters required by the warm corona model are physically incompatible with the conditions of standard coronae. Detailed photoionization calculations show that even in the most favorable conditions, the warm corona should produce strong absorption in the observed spectrum. On the other hand, while the relativistic reflection model provides a satisfactory description of the data, it also requires extreme parameters, such as maximum black hole spin, a very low and compact hot corona, and a very high density for the inner accretion disk. Deeper observations of this source are thus necessary to confirm the presence of relativistic reflection and further understand the nature of its soft excess.
Keywords: accretion; accretion disks; black hole physics; galaxies: active; galaxies: individual (Mrk 509); galaxies: nuclei

IMPROVED REFLECTION MODELS OF BLACK HOLE ACCRETION DISKS: TREATING THE ANGULAR DISTRIBUTION OF X-RAYS - Garcia, Javier; Dauser, Thomas; Lohfink, Anne; Kallman, T. R.; Steiner, J. F.; Mcclintock, J. E.; Brenneman, L.; Wilms, Jörn; Eikmann, Wiebke; Reynolds, C. S.; Tombesi, F. (Astrophysical Journal, 2014)
X-ray reflection models are used to constrain the properties of the accretion disk, such as the degree of ionization of the gas and the elemental abundances. In combination with general relativistic ray tracing codes, additional parameters like the spin of the black hole and the inclination to the system can be determined. However, current reflection models used for such studies only provide angle-averaged solutions for the flux reflected at the surface of the disk. Moreover, the emission angle of the photons changes over the disk due to relativistic light bending. To overcome this simplification, we have constructed an angle-dependent reflection model with the xillver code and self-consistently connected it with the relativistic blurring code RELLINE. The new model, relxill, calculates the proper emission angle of the radiation at each point on the accretion disk and then takes the corresponding reflection spectrum into account. We show that the reflected spectra from illuminated disks follow a limb-brightening law highly dependent on the ionization of disk and yet different from the commonly assumed form I alpha ln(1 + 1/mu). A detailed comparison with the angle-averaged model is carried out in order to determine the bias in the parameters obtained by fitting a typical relativistic reflection spectrum. These simulations reveal that although the spin and inclination are mildly affected, the Fe abundance can be overestimated by up to a factor of two when derived from angle-averaged models. The fit of the new model to the Suzaku observation of the Seyfert galaxy Ark 120 clearly shows a significant improvement in the constraint of the physical parameters, in particular by enhancing the accuracy in the inclination angle and the spin determinations.
Keywords: accretion; accretion disks; black hole physics; galaxies: individual (Ark 120); line: formation; radiative transfer; X-rays: general

INTEGRAL and Swift observations of EXO 2030+375 during a giant outburst - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Aims. We investigate the X- ray spectral and timing properties of the high mass X- ray binary EXO 2030+ 375 observed during its June - September 2006 giant ( type II) outburst.Methods. The data analyzed in this work are from partly simultaneous observations with INTEGRAL and Swift. The pulse period P and its temporal derivative. P are measured. X- ray pulse profiles in different energy ranges and time intervals are constructed. Pulse averaged X- ray spectra for different time intervals are studied.Results. We report a strong spin-up of the source during the outburst, comparable to that observed in 1985 during the previous giant outburst when the source was discovered. The value of. P is found to be linearly related to the X- ray luminosity of the source during the outburst. For the first time the hard X- ray (> 25 keV) characteristics of the source during a type II outburst are studied. The X- ray pulse profiles apparently change with luminosity. The X- ray spectral continuum in the 3 - 120 keV energy range is modeled with an absorbed power law with an exponential cutoff around E similar to 26 keV. An iron emission line at similar to 6 - 7 keV is observed. The spectrum reveals some features between 10 and 20 keV which can be modeled either by a broad emission line at similar to 13 - 15 keV ( a " bump") or by two absorption lines at similar to 10 and similar to 20 keV.
Keywords: X-ray binaries; stars : neutron; accretion; accretion disks

INTEGRAL deep observations of the Small Magellanic Cloud - Coe, M. J.; Bird, A. J.; Buckley, D. A. H.; Corbet, R. H. D.; Dean, A. J.; Finger, M.; Galache, J. L.; Haberl, Frank; Mcbride, V. A.; Negueruela, Ignacio; Schurch, Matthew; Townsend, L. J.; et al. (Monthly Notices of the Royal Astronomical Society, 2010)
Deep observations of the Small Magellanic Cloud (SMC) and region were carried out in the hard X-ray band by the INTEGRAL observatory in 2008-2009. The field of view of the instrument permitted simultaneous coverage of the entire SMC and the eastern end of the Magellanic Bridge. In total, INTEGRAL detected seven sources in the SMC and five in the Magellanic Bridge; the majority of the sources were previously unknown systems. Several of the new sources were detected undergoing bright X-ray outbursts and all the sources exhibited transient behaviour except the supergiant system SMC X-1. They are all thought to be high-mass X-ray binary systems in which the compact object is a neutron star.
Keywords: stars: neutron; X-rays: binaries

INTEGRAL discovery of a high-energy tail in the microquasar Cygnus X-3 - Cangemi, F.; Rodriguez, J.; Grinberg, V.; Belmont, R.; Laurent, P.; Wilms, Jörn (Astronomy & Astrophysics, 2021)
Context. The X-ray spectra of X-ray binaries are dominated by emission of either soft or hard X-rays which defines their soft and hard spectral states. While the generic picture is relatively well understood, little is known about the interplay of the various media at work, or about the reasons why some sources do not follow common behavior. Cygnus X-3 is amongst the list of X-ray binaries that show quite complex behavior, with various distinct spectral states not seen in other sources. These states have been characterized in many studies. Because of its softness and intrinsic low flux above typically 50 keV, very little is known about the hard X/soft gamma-ray (100-1000 keV) emission in Cygnus X-3.Aims. Using the whole INTEGRAL data base, we aim to explore the 3-1000 keV spectra of Cygnus X-3. This allows to probe this region with the highest sensitivity ever, and search for the potential signature of a high-energy non-thermal component as sometimes seen in other sources.Methods. Our work is based on state classification carried out in previous studies with data from the Rossi X-Ray Timing Explorer. We extend this classification to the whole INTEGRAL data set in order to perform a long-term state-resolved spectral analysis. Six stacked spectra were obtained using 16 years of data from JEM-X (3-25 keV), ISGRI (25-300 keV), and SPI (20-400 keV).Results. We extract stacked images in three different energy bands, and detect the source up to 200 keV. In the hardest states, our purely phenomenological approach clearly reveals the presence of an additonnal component > 50 keV in addition to the component usually interpreted as thermal Comptonization. We apply a more physical model of hybrid thermal/nonthermal corona (EQPAIR) to characterize this nonthermal component and compare our results with those of previous studies and analyses. Our modeling indicates a more efficient acceleration of electrons in states where major ejections are observed. We also evaluate and find a dependence of the photon index of the power law as a function of the strong orbital modulation of the source in the Flaring InterMediate state. This dependence could be due to a higher absorption when Cygnus X-3 is behind its companion. However, the uncertainties on the density column prevent us from drawing any firm conclusions.
CRIS-Team WoS Importer:2021-02-12

INTEGRAL observation of the accreting pulsar GX 1+4 - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Aims: We present the results of the INTEGRAL monitoring campaign on the accreting low mass X-ray binary pulsar GX1+4 performed during the Galactic plane scan of the INTEGRAL Core Programme.Methods. The source was observed in different luminosity states ranging from L20-40 keV = 1.7 x 10(-10) erg cm(-2) s(-1), to L20-40 keV = 10.5 x 10(-10) erg cm(-2) s(-1) for about 779 ks from March 2003 until October 2004.Results. Our observations confirm the secular spin down of GX 1+4 with the spin period (P-s) varying from 139.63 s to 141.56 s. In the highest luminosity state, a spin-up phase is observed. The phase-averaged spectrum of the source was modelled either with an absorbed cut-off power law or with a Comptonization model with significantly different parameters in the two brightest luminosity states. No evidence of any absorption-like feature is observed in the phase averaged spectrum up to 110 keV. At highest luminosity, the source is found to pulsate up to 130 keV. Phase resolved spectroscopy reveals a phase-dependent continuum and marginal evidence for an absorption feature at 34 +/- 2 keV in the descending part of the pulse. If interpreted as due to electron resonant cyclotron scattering, the magnetic field in the emitting region would be (2.9 +/- 0.2) x 10(12) (1+z) G where z is the gravitational red shift of the emitting region. We also observed a very low luminosity state, typical of this source, which lasted for about two days during which the source spectrum was modelled by a simple power law, and a pulsed signal was still detectable in the 15-100 keV energy range.
Keywords: X-rays : stars; stars : pulsars : individual : GX 1+4

INTEGRAL observations of Hercules X-1 - Klochkov, D.; Staubert, R.; Postnov, Konstantin; Shakura, N.; Santangelo, A.; Tsygankov, S.; Lutovinov, A.; Kreykenbohm, Ingo; Wilms, Jörn (Astronomy & Astrophysics, 2008)
Aims. We investigate the X-ray spectral and timing properties of the accreting X-ray pulsar Her X-1 observed with the INTEGRAL satellite in July-August 2005.Methods. The data analyzed in this work cover a substantial part of one main-on state of the source. The short time scale pulse period development is measured. X-ray pulse profiles for different energy ranges and time intervals are constructed. Pulse-averaged and pulse-phase resolved broad band X-ray spectra are studied. Spectral changes during X-ray dips are explored.Results. The X-ray pulse profiles are found to change significantly during the period of observations. For the first time a strong spin-up is measured within one 35 d cycle. Spectral characteristics observed during the X-ray dips are consistent with their interpretation as being due to partial covering as has been reported by several authors. The fundamental cyclotron absorption line is firmly observed in both pulse-averaged and pulse-phase resolved X-ray spectra. The energy, width, and the depth of the line are found to vary significantly with pulse phase.
Keywords: X-rays : binaries; accretion; accretion disks; stars : neutron

INTEGRAL observations of the variability of OAO1657-415 - Barnstedt, J.; Staubert, R.; Santangelo, A.; Ferrigno, Carlo; Horns, Dieter; Klochkov, D.; Kretschmar, Peter; Kreykenbohm, Ingo; Segreto, Alberto; Wilms, Jörn (Astronomy & Astrophysics, 2008)
Context. The Galactic Plane Scan (GPS) was one of the core observation programmes of the INTEGRAL satellite. The highly variable accreting pulsar OAO1657-415 was frequently observed within the GPS.Aims. We investigate the spectral and timing properties of OAO1657-415 and their variability on short and long time scales in the energy range 6-160 keV.Methods. Using standard extraction tools and custom software for extracting INTEGRAL data we analysed energy-resolved light curves with a time resolution of one second-mainly data of the ISGRI instrument. We also analysed phase-averaged broad band spectra -including JEM-X spectra -and pulse-phase resolved spectra of ISGRI.Results. During the time covered by the INTEGRAL observations, the pulse period evolution shows an initial spin-down, which is followed by an equally strong spin-up. In combining our results with historical pulse period measurements (correcting them for orbital variation) and with stretches of continuous observations by BATSE, we find that the long-term period evolution is characterised by a long-term spin-up overlayed by sets of relative spin-down/spin-up episodes, which appear to repeat quasi-periodically on a 4.8 yr time scale. We measure an updated local ephemeris and confirm the previously determined orbital period with an improved accuracy. The spectra clearly change with pulse phase. The spectrum measured during the main peak of the pulse profile is particularly hard. We do not find any evidence of a cyclotron line, wether in the phase-averaged spectrum or in phase-resolved spectra.
Keywords: x-rays : binaries; pulsars : individual : OAO1657-415

Intrinsic limits on resolutions in muon- and electron-neutrino charged-current events in the KM3NeT/ORCA detector - Adrian-Martinez, S.; Ageron, M.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Andre, Michel; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Avgitas, T.; et al. (Journal of High Energy Physics, 2017)
Studying atmospheric neutrino oscillations in the few-GeV range with a multimegaton detector promises to determine the neutrino mass hierarchy. This is the main science goal pursued by the future KM3NeT/ORCA water Cherenkov detector in the Mediterranean Sea. In this paper, the processes that limit the obtainable resolution in both energy and direction in charged-current neutrino events in the ORCA detector are investigated. These processes include the composition of the hadronic fragmentation products, the subsequent particle propagation and the photon-sampling fraction of the detector. GEANT simulations of neutrino interactions in seawater produced by GENIE are used to study the effects in the 1-20 GeV range. It is found that fluctuations in the hadronic cascade in conjunction with the variation of the inelasticity y are most detrimental to the resolutions. The effect of limited photon sampling in the detector is of significantly less importance. These results will therefore also be applicable to similar detectors/media, such as those in ic
Keywords: Neutrino Detectors and Telescopes (experiments)

Inversion of the decay of the cyclotron line energy in Hercules X-1 - Staubert, R.; Klochkov, D.; Fuerst, F.; Wilms, Jörn; Rothschild, R. E.; Harrison, F. (Astronomy & Astrophysics, 2017)
Recent observations of Her X-1 with NuSTAR and INTEGRAL in 2016 have provided evidence that the 20-year decay of the cyclotron line energy found between 1996 and 2015 has ended and that an inversion with a new increase, possibly similar to the one observed around 1990-1993, has started. We consider this a strong motivation for further observations and for enhanced efforts to significantly improve our theoretical understanding of the accretion process in binary X-ray pulsars. We speculate about the physics behind the long-term decay and its inversion, a possible cyclic behavior, and correlations with other variable observables.
Keywords: magnetic fields; binaries: eclipsing; stars: neutron; radiation mechanisms: non-thermal; line: formation; X-rays: general

Investigating source confusion in PMN J1603-4904 - Krauss, F.; Kreter, M.; Mueller, C.; Markowitz, A.; Böck, Moritz; Burnett, T.; Dauser, Thomas; Kadler, M.; Kreikenbohm, A.; Ojha, R.; Wilms, Jörn (Astronomy & Astrophysics, 2018)
PMN J1603-4904 is a likely member of the rare class of gamma-ray emitting young radio galaxies. Only one other source, PKS 1718-649, has been confirmed so far. These objects, which may transition into larger radio galaxies, are a stepping stone to understanding AGN evolution. It is not completely clear how these young galaxies, seen edge-on, can produce high-energy gamma rays. PMN J1603-4904 has been detected by TANAMI Very Long Baseline Interferometry (VLBI) observations and has been followed-up with multiwavelength observations. A Fermi Gamma-ray Space Telescope Large Area Telescope (Fermi-LAT) gamma-ray source has been associated with this young galaxy in the LAT catalogs. We have obtained Chandra observations of the source to consider the possibility of source confusion due to the relatively large positional uncertainty of Fermi-LAT. The goal was to investigate the possibility of other X-ray bright sources in the vicinity of PMN J1603-4904 that could be counterparts to the gamma-ray emission. With Chandra/ACIS, we find no other sources in the uncertainty ellipse of Fermi-LAT data, which includes an improved localization analysis of eight years of data. We further study the X-ray fluxes and spectra. We conclude that PMN J1603-4904 is indeed the second confirmed gamma-ray bright young radio galaxy.
Keywords: galaxies: active; galaxies: jets; Galaxy: abundances; galaxies: individual: PMN J1603-4904

Investigating the effect of source contamination on eXTP/SFA - Zhang, Juan; Li, Gang; Ge, Mingyu; Kirsch, Christian; Lorenz, Maximilian; Wilms, Jörn; Qi, Liqiang; Sheng, Lizhi; Yang, Yi Jung; Dauser, Thomas; Xu, Yupeng; Lu, Fangju; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2020)
The Spectroscopy Focusing Array (SFA) onboard the enhanced X-ray Timing and Polarimetry (eXTP) observatory consists of 9 modules, each comprising a Wolter type I telescope with a field of view (FOV) around 16 arcminutes and a focal plane silicon drift detector (SDD) with 19 hexagonal pixels. Due to the large size of each individual SDD pixel (each pixel corresponds to an area of ∼ 3.6 arcminutes in diameter) and the limited pixel number, SFA can not obtain a real image of the observed region like many other X-ray imaging telescopes. Thus, contamination from nearby bright sources needs to be considered when we study the properties of the target source. We simulate such contaminations using the SIXTE simulator. In this paper we present the results by taking observations of the millisecond pulsar PSR J0437-4715 as an example, and discuss the cases for contamination on background or target source respectively.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Contamination; EXTP/SFA; Nearby source

Investigating the Mini and Giant Radio Flare Episodes of Cygnus X-3 - Egron, Elise; Pellizzoni, Alberto; Righini, Simona; Giroletti, Marcello; Koljonen, Karri; Pottschmidt, Katja; Trushkin, Sergei; Lobina, Jessica; Pilia, Maura; Wilms, Jörn; Corbel, Stephane; Grinberg, Victoria; et al. (Astrophysical Journal, 2021)
The microquasar Cygnus X-3 underwent a giant radio flare in 2017 April, reaching a maximum flux of similar to 16.5 Jy at 8.5 GHz. We present results from a long monitoring campaign carried out with Medicina at 8.5, 18.6, and 24.1 GHz, parallel to the Metsahovi radio telescope at 37 GHz, from 2017 April 4 to 11. We observe a spectral steepening from alpha = 0.2 to 0.5 (with S-nu proportional to nu(-alpha)) within 6 hr of the epoch of the flare's peak maximum, and rapid changes in the spectral slope in the following days during brief enhanced emission episodes while the general trend of the radio flux density indicated the decay of the giant flare. We further study the radio orbital modulation of Cyg X-3 emission associated with the 2017 giant flare and with six mini-flares observed in 1983, 1985, 1994, 1995, 2002, and 2016. The enhanced emission episodes observed during the decline of the giant flare at 8.5 GHz coincide with the orbital phase phi similar to 0.5 (orbital inferior conjunction). On the other hand, the light curves of the mini-flares observed at 15-22 GHz peak at phi similar to 0, except for the 2016 light curve, which is shifted 0.5 w.r.t. the other ones. We attribute the apparent phase shift to the variable location of the emitting region along the bent jet. This might be explained by the different accretion states of the flaring episodes (the 2016 mini-flare occurred in the hypersoft X-ray state).
CRIS-Team WoS Importer:2021-01-15

Irradiation of an accretion disc by a jet: general properties and implications for spin measurements of black holes - Dauser, Thomas; Garcia, Javier; Wilms, Jörn; Böck, Moritz; Brenneman, L. W.; Falanga, M.; Fukumura, K.; Reynolds, C. S. (Monthly Notices of the Royal Astronomical Society, 2013)
X-ray irradiation of the accretion disc leads to strong reflection features, which are then broadened and distorted by relativistic effects. We present a detailed, general relativistic approach to model this irradiation for different geometries of the primary X-ray source. These geometries include the standard point source on the rotational axis as well as more jet-like sources, which are radially elongated and accelerating. Incorporating this code in the RELLINE model for relativistic line emission, the line shape for any configuration can be predicted. We study how different irradiation geometries affect the determination of the spin of the black hole. Broad emission lines are produced only for compact irradiating sources situated close to the black hole. This is the only case where the black hole spin can be unambiguously determined. In all other cases the line shape is narrower, which could either be explained by a low spin or an elongated source. We conclude that in those cases and independent of the quality of the data no unique solution for the spin exists and therefore only a lower limit of the spin value can be given.
Keywords: accretion; accretion discs; black hole physics; lines: profiles; galaxies: active; galaxies: nuclei

Is the plateau state in GRS 1915+105 equivalent to canonical hard states? - Van Oers, Pieter; Markoff, Sera; Rahoui, Farid; Maitra, Dipankar; Nowak, Michael; Wilms, Jörn; Castro-Tirado, Alberto J.; Rodriguez, Jerome; Dhawan, Vivek; Harlaftis, Emilios (Monthly Notices of the Royal Astronomical Society, 2010)
GRS 1915+105 is a very peculiar black hole binary that exhibits accretion-related states that are not observed in any other stellar-mass black hole system. One of these states, however referred to as the plateau state - may be related to the canonical hard state of black hole X-ray binaries. Both the plateau and hard state are associated with steady, relatively lower X-ray emission and flat/inverted radio emission, that is sometimes resolved into compact, self-absorbed jets. However, while generally black hole binaries quench their jets when the luminosity becomes too high, GRS 1915+105 seems to sustain them despite the fact that it accretes at near- or super-Eddington rates. In order to investigate the relationship between the plateau and the hard state, we fit two multiwavelength observations using a steady-state outflow-dominated model, developed for hard-state black hole binaries. The data sets consist of quasi-simultaneous observations in radio, near- infrared and X-ray bands. Interestingly, we find both significant differences between the two plateau states, as well as between the best-fitting model parameters and those representative of the hard state. We discuss our interpretation of these results, and the possible implications for GRS 1915+105's relationship to canonical black hole candidates.
Keywords: accretion; accretion discs; black hole physics; radiation mechanisms: general; galaxies: active; galaxies: jets; X-rays: binaries

Joint Constraints on Galactic Diffuse Neutrino Emission from the ANTARES and IceCube Neutrino Telescopes - Albert, A.; Grasso, D.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The existence of diffuse Galactic neutrino production is expected from cosmic-ray interactions with Galactic gas and radiation fields. Thus, neutrinos are a unique messenger offering the opportunity to test the products of Galactic cosmic-ray interactions up to energies of hundreds of TeV. Here we present a search for this production using ten years of Astronomy with a Neutrino Telescope and Abyss environmental RESearch (ANTARES) track and shower data, as well as seven years of IceCube track data. The data are combined into a joint likelihood test for neutrino emission according to the KRA(gamma) model assuming a 5 PeV per nucleon Galactic cosmic-ray cutoff. No significant excess is found. As a consequence, the limits presented in this Letter start constraining the model parameter space for Galactic cosmic-ray production and transport.
Keywords: cosmic rays; diffusion; Galaxy: disk; gamma rays: diffuse background; neutrinos

Joint spectral-timing modelling of the hard lags in GX 339-4: constraints on reflection models - Cassatella, P.; Uttley, P.; Wilms, Jörn; Poutanen, Juri (Monthly Notices of the Royal Astronomical Society, 2012)
The X-ray variations of hard state black hole X-ray binaries above 2 keV show hard lags, in that the variations at harder energies follow variations at softer energies, with a time lag t depending on frequency ? approximately as t??-0.7. Several models have so far been proposed to explain this time delay, including fluctuations propagating through an accretion flow, spectral variations during coronal flares, Comptonization in the extended hot corona or a jet, or time delays due to large-scale reflection from the accretion disc. In principle, these models can be used to predict the shape of the energy spectrum as well as the frequency dependence of the time lags, through the construction of energy-dependent response functions which map the emission as a function of time delay in the system. Here we use this approach to test a simple reflection model for the frequency-dependent lags seen in the hard state of GX 339-4, by simultaneously fitting the model to the frequency-dependent lags and energy spectrum measured by XMMNewton in 2004 and 2009. Our model cannot simultaneously fit both the lag and spectral data, since the relatively large lags require an extremely flared disc which subtends a large solid angle to the continuum at large radii, in disagreement with the observed Fe Ka emission. Therefore, we consider it more likely that the lags >2 keV are caused by propagation effects in the accretion flow, possibly related to the accretion disc fluctuations which have been observed previously.
Keywords: accretion; accretion discs; black hole physics; stars: individual: GX 339-4; X-rays: binaries

KM3NeT front-end and readout electronics system: hardware, firmware, and software - Aiello, Sebastiano; Amllei, Fabrizio; Andre, Michel; Androulakis, Giorgos; Anghinolfi, Marco; Anton, Gisela; Ardid, Miquel; Aublin, Julien; Bagatelas, Christos; Barbarino, Giancarlo; Baret, Bruny; Du Pree, Suzan Basegmez; et al. (Journal of Astronomical Telescopes, Instruments, and Systems, 2019)
The KM3NeT research infrastructure being built at the bottom of the Mediterranean Sea will host water-Cherenkov telescopes for the detection of cosmic neutrinos. The neutrino telescopes will consist of large volume three-dimensional grids of optical modules to detect the Cherenkov light from charged particles produced by neutrino-induced interactions. Each optical module houses 31 3-in. photomultiplier tubes, instrumentation for calibration of the photomultiplier signal and positioning of the optical module, and all associated electronics boards. By design, the total electrical power consumption of an optical module has been capped at seven Watts. We present an overview of the front-end and readout electronics system inside the optical module, which has been designed for a 1-ns synchronization between the clocks of all optical modules in the grid during a life time of at least 20 years. (C) 2019 Society of Photo-Optical Instrumentation Engineers (SPIE)
CRIS-Team WoS Importer:2020-02-28

LABORATORY MEASUREMENTS of the K-SHELL TRANSITION ENERGIES in L-SHELL IONS of SI and S - Hell, Natalie; Brown, G. V.; Wilms, Jörn; Grinberg, Victoria; Clementson, J.; Liedahl, D.; Porter, F. S.; Kelley, R. L.; Kilbourne, C. A.; Beiersdorfer, P. (Astrophysical Journal, 2016)
We have measured the energies of the strongest 1s-2 ℓ (ℓ = s, p) transitions in He- through Ne-like silicon and sulfur ions to an accuracy of <1 eV using the Lawrence Livermore National Laboratorys electron beam ion traps, EBIT-I and SuperEBIT, and the NASA/GSFC EBIT Calorimeter Spectrometer (ECS). We identify and measure the energies of 18 and 21 X-ray features from silicon and sulfur, respectively. The results are compared to new Flexible Atomic Code calculations and to semi-relativistic Hartree-Fock calculations by Palmeri et al. (2008). These results will be especially useful for wind diagnostics in high-mass X-ray binaries, such as Vela X-1 and Cygnus X-1, where high-resolution spectral measurements using Chandras high-energy transmission grating has made it possible to measure Doppler shifts of 100 km s. The accuracy of our measurements is consistent with that needed to analyze Chandra observations, exceeding Chandras 100 km s limit. Hence, the results presented here not only provide benchmarks for theory, but also accurate rest energies that can be used to determine the bulk motion of material in astrophysical sources. We show the usefulness of our results by applying them to redetermine Doppler shifts from Chandra observations of Vela X-1.
Keywords: atomic data; methods: laboratory: atomic; X-rays: binaries; X-rays: general

Letter of intent for KM3NeT 2.0 - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E.; Andre, Michel; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; et al. (Journal of Physics G: Nuclear and Particle Physics, 2016)
The main objectives of the KM3NeT Collaboration are (i) the discovery and subsequent observation of high-energy neutrino sources in the Universe and (ii) the determination of the mass hierarchy of neutrinos. These objectives are strongly motivated by two recent important discoveries, namely: (1) the high-energy astrophysical neutrino signal reported by IceCube and (2) the sizable contribution of electron neutrinos to the third neutrino mass eigenstate as reported by Daya Bay, Reno and others. To meet these objectives, the KM3NeT Collaboration plans to build a new Research Infrastructure consisting of a network of deep-sea neutrino telescopes in the Mediterranean Sea. A phased and distributed implementation is pursued which maximises the access to regional funds, the availability of human resources and the synergistic opportunities for the Earth and sea sciences community. Three suitable deep-sea sites are selected, namely off-shore Toulon (France), Capo Passero (Sicily, Italy) and Pylos (Peloponnese, Greece). The infrastructure will consist of three so-called building blocks. A building block comprises 115 strings, each string comprises 18 optical modules and each optical module comprises 31 photo-multiplier tubes. Each building block thus constitutes a three-dimensional array of photo sensors that can be used to detect the Cherenkov light produced by relativistic particles emerging from neutrino interactions. Two building blocks will be sparsely configured to fully explore the IceCube signal with similar instrumented volume, different methodology, improved resolution and complementary field of view, including the galactic plane. One building block will be densely configured to precisely measure atmospheric neutrino oscillations.
Keywords: deep sea neutrino telescope; neutrino astronomy; neutrino mass hierarchy; neutrino physics

Limits on dark matter annihilation in the sun using the ANTARES neutrino telescope - Adrian-Martineza, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics Letters B, 2016)
A search for muon neutrinos originating from dark matter annihilations in the Sun is performed using the data recorded by the ANTARES neutrino telescope from 2007 to 2012. In order to obtain the best possible sensitivities to dark matter signals, an optimisation of the event selection criteria is performed taking into account the background of atmospheric muons, atmospheric neutrinos and the energy spectra of the expected neutrino signals. No significant excess over the background is observed and 90% C.L. upper limits on the neutrino flux, the spin-dependent and spin-independent WIMP-nucleon cross-sections are derived for WIMP masses ranging from 50 GeV to 5 TeV for the annihilation channels WIMP+WIMP→bb-,WW and ττ.
Keywords: Dark matter; Indirect detection; Neutralino; Neutrino telescope; Sun; WIMP

Long-term change in the cyclotron line energy in Hercules X-1 - Staubert, R.; Klochkov, D.; Wilms, Jörn; Postnov, Konstantin; Shakura, N. I.; Rothschild, R. E.; Fuerst, F.; Harrison, F. A. (Astronomy & Astrophysics, 2014)
Aims. We investigate the long-term evolution of the cyclotron resonance scattering feature (CRSF) in the spectrum of the binary X-ray pulsar Her X-1 and present evidence of a true long-term decrease in the centroid energy E-cyc of the cyclotron line in the pulse phase averaged spectra from 1996 to 2012.Methods. Our results are based on repeated observations of Her X-1 by those X-ray observatories capable of measuring clearly beyond the cyclotron line energy of similar to 40 keV; these are RXTE, INTEGRAL, Suzaku, and NuSTAR. We consider results based on our own successful observing proposals as well as results from the literature.Results. The historical evolution of the pulse phase averaged CRSF centroid energy Ecyc since its discovery in 1976 is characterized by an initial value around 35 keV, an abrupt jump upwards to beyond similar to 40 keV between 1990 and 1994, and an apparent decay thereafter. Much of this decay, however, was found to be due to an artifact, namely a correlation between Ecyc and the X-ray luminosity L-x discovered in 2007. In observations after 2006, however, we now find a statistically significant true decrease in the cyclotron line energy. At the same time, the dependence of Ecyc on X-ray luminosity is still valid with an increase of similar to 5% in energy for a factor of two increase in luminosity. We also report on the first evidence of a weak dependence of Ecyc on phase of the 35 d precessional period, which manifests itself not only in the modulation of the X-ray flux, but also in the systematic variation in the shape of the 1.24 s pulse profile. One of our motivations for repeatedly observing Her X-1, namely the suspicion that the cyclotron line energy may be gradually decreasing after its strong upward jump in the early 1990s, is finally confirmed. A decrease in Ecyc by 4.2 keV over the 16 years from 1996 to 2012 can either be modeled by a linear decay, or by a slow decay until 2006 followed by a more abrupt decrease thereafter.Conclusions. The observed timescale for the decrease in Ecyc of a few decades is too short for a decay of the global magnetic field. We speculate that the physical reason could be connected to a geometric displacement of the cyclotron resonant scattering region in the polar field or to a true physical change in the magnetic field configuration at the polar cap by the continued accretion. In the second scenario, the upward jump in Ecyc observed around 1991 may have been due to a relatively fast event in which the polar magnetic field rearranged itself after releasing part of the accumulated material to larger areas of the neutron star surface.
Keywords: radiation mechanisms: non-thermal; binaries: eclipsing; pulsars: individual: Her X-1; accretion; accretion disks; magnetic fields; X-rays: binaries

Long-term monitoring of the ANTARES optical module efficiencies using K-40 decays in sea water - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (European Physical Journal C, 2018)
Cherenkov light induced by radioactive decay products is one of the major sources of background light for deep-sea neutrino telescopes such as ANTARES. These decays are at the same time a powerful calibration source. Using data collected by the ANTARES neutrino telescope from mid 2008 to 2017, the time evolution of the photon detection efficiency of optical modules is studied. A modest loss of only 20% in 9 years is observed. The relative time calibration between adjacent modules is derived as well.

Long term variability of Cygnus X-1 VI. Energy-resolved X-ray variability 1999-2011 - Grinberg, Victoria; Pottschmidt, K.; Boeck, M.; Schmid, Christian; Nowak, M. A.; Uttley, P.; Tomsick, J. A.; Rodriguez, Jerome; Hell, Natalie; Markowitz, Alex; Bodaghee, A.; Bel, M. Cadolle; et al. (Astronomy & Astrophysics, 2014)
We present the most extensive analysis of Fourier-based X-ray timing properties of the black hole binary Cygnus X-1 to date, based on 12 years of bi-weekly monitoring with RXTE from 1999 to 2011. Our aim is a comprehensive study of timing behavior across all spectral states, including the elusive transitions and extreme hard and soft states. We discuss the dependence of the timing properties on spectral shape and photon energy, and study correlations between Fourier-frequency dependent coherence and time lags with features in the power spectra. Our main results are: (a) The fractional rms in the 0.125-256 Hz range in different spectral states shows complex behavior that depends on the energy range considered. It reaches its maximum not in the hard state, but in the soft state in the Comptonized tail above 10 keV. (b) The shape of power spectra in hard and intermediate states and the normalization in the soft state are strongly energy dependent in the 2.1-15 keV range. This emphasizes the need for an energy-dependent treatment of power spectra and a careful consideration of energy- and mass-scaling when comparing the variability of different source types, e.g., black hole binaries and AGN. PSDs during extremely hard and extremely soft states can be easily confused for energies above similar to 5 keV in the 0.125-256 Hz range. (c) The coherence between energy bands drops during transitions from the intermediate into the soft state but recovers in the soft state. (d) The time lag spectra in soft and intermediate states show distinct features at frequencies related to the frequencies of the main variability components seen in the power spectra and show the same shift to higher frequencies as the source softens. Our results constitute a template for other sources and for physical models for the origin of the X-ray variability. In particular, we discuss how the timing properties of Cyg X-1 can be used to assess the evolution of variability with spectral shape in other black hole binaries. Our results suggest that none of the available theoretical models can explain the full complexity of X-ray timing behavior of Cyg X-1, although several ansatzes with different physical assumptions are promising.
Keywords: X-rays: binaries; stars: individual: Cygnus X-1; binaries: close

Long term variability of Cygnus X-1 VII. Orbital variability of the focussed wind in Cyg X-1/HDE 226868 system - Grinberg, V.; Leutenegger, M. A.; Hell, Natalie; Pottschmidt, K.; Böck, Moritz; Garcia, J. A.; Hanke, Manfred; Nowak, M. A.; Sundqvist, J. O.; Townsend, R. H. D.; Wilms, Jörn (Astronomy & Astrophysics, 2015)
Binary systems with an accreting compact object off er a unique opportunity to investigate the strong, clumpy, line-driven winds of early-type supergiants by using the compact object's X-rays to probe the wind structure. We analyze the two-component wind of HDE 226868, the O9.7Iab giant companion of the black hole Cyg X-1, using 4.77 Ms Rossi X-ray Timing Explorer (RXTE) observations of the system taken over the course of 16 years. Absorption changes strongly over the 5.6 d binary orbit, but also shows a large scatter at a given orbital phase, especially at superior conjunction. The orbital variability is most prominent when the black hole is in the hard X-ray state. Our data are poorer for the intermediate and soft state, but show signs for orbital variability of the absorption column in the intermediate state. We quantitatively compare the data in the hard state to a toy model of a focussed Castor-Abbott-Klein wind: as it does not incorporate clumping, the model does not describe the observations well. A qualitative comparison to a simplified simulation of clumpy winds with spherical clumps shows good agreement in the distribution of the equivalent hydrogen column density for models with a porosity length on the order of the stellar radius at inferior conjunction; we conjecture that the deviations between data and model at superior conjunction could either be due to lack of a focussed wind component in the model or to a more complicated clump structure.
Keywords: stars: individual: Cyg X-1; X-rays: binaries; binaries : close; stars: winds; outflows

Long term variability of Cygnus X-1 V. State definitions with all sky monitors - Grinberg, Victoria; Hell, Natalie; Pottschmidt, K.; Boeck, M.; Nowak, M. A.; Rodriguez, Jerome; Bodaghee, A.; Bel, M. Cadolle; Case, G. L.; Hanke, Manfred; Kühnel, Matthias; Markoff, S. B.; et al. (Astronomy & Astrophysics, 2013)
We present a scheme for determining the spectral state of the canonical black hole Cyg X-1 using data from previous and current X-ray all sky monitors (RXTE-ASM, Swift-BAT, MAXI, and Fermi-GBM). Determinations of the hard/intermediate and soft state agree to better than 10% between different monitors, facilitating the determination of the state and its context for any observation of the source, potentially over the lifetimes of different individual monitors. A separation of the hard and the intermediate states, which strongly differ in their spectral shape and short-term timing behavior, is only possible when data in the soft X-rays (<5 keV) are available. A statistical analysis of the states confirms the different activity patterns of the source (e.g., month- to year-long hard-state periods or phases during which numerous transitions occur). It also shows that the hard and soft states are stable, with the probability of Cyg X-1 remaining in a given state for at least one week to be larger than 85% in the hard state and larger than 75% in the soft state. Intermediate states are short lived, with a 50% probability that the source leaves the intermediate state within three days. Reliable detection of these potentially short-lived events is only possible with monitor data that have a time resolution better than 1 d.
Keywords: X-rays: binaries; stars: individual: Cygnus X-1; binaries: close

Long-term variability of Vela X-1 - Kretschmar, Peter; Keating, J.; Kreykenbohm, Ingo; Wilms, Jörn; Staubert, R. (2010)
The archetypical wind-accreting X-ray pulsar Vela X-1 is known to be variable on a large range of timescales. Relatively tranquil phases exist as well as extended phases of high variability and flaring. We present results from a systematic study of variations with orbital phase and other timescales based on RXTE/ASM and Swift/BAT data.
Keywords: X-rays: binaries; Stars: neutron; Stars: winds; outflows

Looking at A 0535+26 at low luminosities with NuSTAR - Ballhausen, Ralf; Pottschmidt, Katja; Furst, Felix; Wilms, Jörn; Tomsick, John A.; Schwarm, Fritz-Walter; Stern, Daniel; Kretschmar, Peter; Caballero, Isabel; Harrison, Fiona A.; Boggs, Steven E.; Christensen, Finn E.; et al. (Astronomy & Astrophysics, 2017)
We report on two NuSTAR observations of the high-mass X-ray binary A 0535 + 26 taken toward the end of its normal 2015 outburst at very low 3-50 keV luminosities of similar to 1.4 x 10(36) erg s(-1) and similar to 5 x 10(35) erg s(-1), which are complemented by nine Swift observations. The data clearly confirm indications seen in earlier data that the source's spectral shape softens as it becomes fainter. The smooth exponential rollover at high energies seen in the first observation evolves to a much more abrupt steepening of the spectrum at 20-30 keV. The continuum evolution can be nicely described with emission from a magnetized accretion column, modeled using the compmag model modified by an additional Gaussian emission component for the fainter observation. Between the two observations, the optical depth changes from 0.75 +/- 0.04 to 0.56(-0.04)(+0.01), the electron temperature remains constant, and there is an indication that the column decreases in radius. Since the energy-resolved pulse profiles remain virtually unchanged in shape between the two observations, the emission properties of the accretion column reflect the same accretion regime. This conclusion is also confirmed by our result that the energy of the cyclotron resonant scattering feature (CRSF) at similar to 45 keV is independent of the luminosity, implying that the magnetic field in the region in which the observed radiation is produced is the same in both observations. Finally, we also constrain the evolution of the continuum parameters with the rotational phase of the neutron star. The width of the CRSF could only be constrained for the brighter observation. Based on Monte Carlo simulations of CRSF formation in single accretion columns, its pulse phase dependence supports a simplified fan beam emission pattern. The evolution of the CRSF width is very similar to that of the CRSF depth, which is, however, in disagreement with expectations.
Keywords: X-rays: binaries; pulsars: individual: A 0535+26; stars: neutron; accretion; accretion disks; stars: magnetic field

Low charge states of Si and S in Cygnus X-1 - Hell, Natalie; Miskovicova, I.; Brown, G. V.; Wilms, Jörn; Clementson, J.; Hanke, Manfred; Beiersdorfer, P.; Liedahl, D.; Pottschmidt, K.; Porter, F. S.; Kilbourne, C. A.; Kelley, R. L.; et al. (IOP PUBLISHING LTD, 2013)
Strong, relatively short, absorption dips have been observed in the x-ray light curves measured from the high mass x-ray binary system Cygnus X-1. With increasing strength of the dips, which are believed to be caused by 'clumps' of cold material present in the stellar wind of Cyg X-1's companion star, K-shell absorption lines in L-shell ions of Si and S develop. To determine the bulk motion of the clumps via the Doppler shifts of these lines with high accuracy, we measured their reference energies using the Lawrence Livermore National Laboratory electron beam ion trap EBIT-I and EBIT Calorimeter Spectrometer. Our findings-shifts consistent with zero velocity of the absorber throughout all ionization states at orbital phase zero-provide evidence for an onion-like ion structure of the clumps.

Luminosity dependent accretion state change in GRO J1008-57 - Kühnel, Matthias; Müller, Sebastian; Kreykenbohm, Ingo; Fuerst, Felix; Pottschmidt, Katja; Rothschild, Richard E.; Caballero, Isabel; Grinberg, Victoria; Schoenherr, Gabriele; Shrader, Chris; Klochkov, Dmitry; Staubert, Ruediger; et al. (2014)
In a former publication, we have analyzed the transient neutron star X-ray binary GRO J1008-57 using all available RXTE-, Swift-, and Suzaku-data. As we have found, the source's spectral components, i.e., a power-law with high exponential cutoff and a black-body, are strongly correlated with the hard X-ray flux (15-50 keV). We update the analytical description of these dependence, including a change in the photon index behaviour from a flat to a logarithmic function. The flux, where the change occurs, is consistent with the onset of the black-body emission. Thus, a change of the accretion state always occurs in GRO J1008-57 at a particular flux level.

Measurement of atmospheric neutrino oscillations with the ANTARES neutrino telescope ANTARES Collaboration - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Basa, S.; et al. (Physics Letters B, 2012)
The data taken with the ANTARES neutrino telescope from 2007 to 2010, a total live time of 863 days, are used to measure the oscillation parameters of atmospheric neutrinos. Muon tracks are reconstructed with energies as low as 20 GeV. Neutrino oscillations will cause a suppression of vertical upgoing muon neutrinos of such energies crossing the Earth. The parameters determining the oscillation of atmospheric neutrinos are extracted by fitting the event rate as a function of the ratio of the estimated neutrino energy and reconstructed flight path through the Earth. Measurement contours of the oscillation parameters in a two-flavour approximation are derived. Assuming maximal mixing, a mass difference of Delta m(32)(2) = (3.1 +/- 0.9) . 10(-3) eV(2) is obtained, in good agreement with the world average value. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Neutrino oscillations; Neutrino telescope; ANTARES

Measurement of the atmospheric nu (mu) energy spectrum from 100 GeV to 200 TeV with the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; et al. (European Physical Journal C, 2013)
Atmospheric neutrinos are produced during cascades initiated by the interaction of primary cosmic rays with air nuclei. In this paper, a measurement of the atmospheric energy spectrum in the energy range 0.1-200 TeV is presented, using data collected by the ANTARES underwater neutrino telescope from 2008 to 2011. Overall, the measured flux is similar to 25 % higher than predicted by the conventional neutrino flux, and compatible with the measurements reported in ice. The flux is compatible with a single power-law dependence with spectral index gamma (meas)=3.58 +/- 0.12. With the present statistics the contribution of prompt neutrinos cannot be established.

Measurement of the atmospheric νe and νμ energy spectra with the ANTARES neutrino telescope - Albert, A.; Alves, S.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bendahman, M.; et al. (Physics Letters B, 2021)
This letter presents a combined measurement of the energy spectra of atmospheric νe and νμ in the energy range between ∼100 GeV and ∼50 TeV with the ANTARES neutrino telescope. The analysis uses 3012 days of detector livetime in the period 2007–2017, and selects 1016 neutrinos interacting in (or close to) the instrumented volume of the detector, yielding shower-like events (mainly from νe+ν‾e charged current plus all neutrino neutral current interactions) and starting track events (mainly from νμ+ν‾μ charged current interactions). The contamination by atmospheric muons in the final sample is suppressed at the level of a few per mill by different steps in the selection analysis, including a Boosted Decision Tree classifier. The distribution of reconstructed events is unfolded in terms of electron and muon neutrino fluxes. The derived energy spectra are compared with previous measurements that, above 100 GeV, are limited to experiments in polar ice and, for νμ, to Super-Kamiokande.
CRIS-Team Scopus Importer:2021-04-02
Keywords: ANTARES; Atmospheric neutrinos; Neutrino telescope

Measurement of the group velocity of light in sea water at the ANTARES site - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; Baret, B.; et al. (Astroparticle Physics, 2012)
The group velocity of light has been measured at eight different wavelengths between 385 nm and 532 nm in the Mediterranean Sea at a depth of about 2.2 km with the ANTARES optical beacon systems. A parametrisation of the dependence of the refractive index on wavelength based on the salinity, pressure and temperature of the sea water at the ANTARES site is in good agreement with these measurements. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino telescope; Optical beacon system; Velocity of light; Refractive index

MEASUREMENTS OF CYCLOTRON FEATURES AND PULSE PERIODS IN THE HIGH-MASS X-RAY BINARIES 4U 1538-522 AND 4U 1907+09 WITH THE INTERNATIONAL GAMMA-RAY ASTROPHYSICS LABORATORY - Hemphill, Paul B.; Rothschild, Richard E.; Caballero, Isabel; Pottschmidt, Katja; Kühnel, Matthias; Fuerst, Felix; Wilms, Jörn (Astrophysical Journal, 2013)
We present a spectral and timing analysis of International Gamma-Ray Astrophysics Laboratory (INTEGRAL) observations of two high-mass X-ray binaries, 4U 1538-522 and 4U 1907+09. Our timing measurements for 4U 1538-522 find the pulse period to have exhibited a spin-up trend until approximately 2009, after which there is evidence for a torque reversal, with the source beginning to spin down to the most recently measured period of 525.407 +/- 0.001 s. The most recent INTEGRAL observations of 4U 1907+09 are not found to yield statistically significant pulse periods due to the significantly lower flux from the source compared with 4U 1538-522. A spectral model consisting of a power-law continuum with an exponential cutoff and modified by two cyclotron resonance scattering features is found to fit both sources well, with the cyclotron scattering features detected at similar to 22 and similar to 49 keV for 4U 1538-522 and at similar to 18 and similar to 36 keV for 4U 1907+09. The spectral parameters of 4U 1538-522 are generally not found to vary significantly with flux and there is little to no variation across the torque reversal. Examining our results in conjunction with previous work, we find no evidence for a correlation between cyclotron line energy and luminosity for 4U 1538-522. 4U 1907+09 shows evidence for a positive correlation between cyclotron line energy and luminosity, which would make it the fourth, and lowest luminosity, cyclotron line source to exhibit this relationship.
Keywords: pulsars: individual (4U 1538-522; 4U 1907+09); stars: magnetic field; stars: oscillations; X-rays: binaries; X-rays: stars

Measuring the atmospheric neutrino oscillation parameters and constraining the 3+1 neutrino model with ten years of ANTARES data - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Belhorma, B.; et al. (Journal of High Energy Physics, 2019)
The ANTARES neutrino telescope has an energy threshold of a few tens of GeV. This allows to study the phenomenon of atmospheric muon neutrino disappearance due to neutrino oscillations. In a similar way, constraints on the 3+1 neutrino model, which foresees the existence of one sterile neutrino, can be inferred. Using data collected by the ANTARES neutrino telescope from 2007 to 2016, a new measurement of Δm322 and θ23 has been performed — which is consistent with world best-fit values — and constraints on the 3+1 neutrino model have been derived.[Figure not available: see fulltext.].
CRIS-Team Scopus Importer:2019-07-02
Keywords: Neutrino Detectors and Telescopes (experiments); Oscillation

Meteor studies in the framework of the JEM-EUSO program - Abdellaoui, Ghouti; Abe, S.; Acheli, A.; Adams, J. H. J. H.; Ahmad, S.; Ahriche, A.; Albert, J. -N.; Allard, D.; Alonso, Gustavo; Anchordoqui, L.; Andreev, V.; Anzalone, A.; et al. (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
We summarize the state of the art of a program of UV observations from space of meteor phenomena, a secondary objective of the JEM-EUSO international collaboration. Our preliminary analysis indicates that JEM-EUSO, taking advantage of its large FOV and good sensitivity, should be able to detect meteors down to absolute magnitude close to 7. This means that JEM-EUSO should be able to record a statistically significant flux of meteors, including both sporadic ones, and events produced by different meteor streams. Being unaffected by adverse weather conditions, JEM-EUSO can also be a very important facility for the detection of bright meteors and fireballs, as these events can be detected even in conditions of very high sky background. In the case of bright events, moreover, exhibiting some persistence of the meteor train, preliminary simulations show that it should be possible to exploit the motion of the ISS itself and derive at least a rough 3D reconstruction of the meteor trajectory. Moreover, the observing strategy developed to detect meteors may also be applied to the detection of nuclearites, exotic particles whose existence has been suggested by some theoretical investigations. Nuclearites are expected to move at higher velocities than meteoroids, and to exhibit a wider range of possible trajectories, including particles moving upward after crossing the Earth. Some pilot studies, including the approved Mini-EUSO mission, a precursor of JEM-EUSO, are currently operational or in preparation. We are doing simulations to assess the performance of Mini-EUSO for meteor studies, while a few meteor events have been already detected using the ground-based facility EUSO-TA.
Keywords: Meteors; Nuclearites; JEM-EUSO; Mini-EUSO; EUSO-TA

Millimeter VLBI of NGC 1052: Dynamics - Baczko, Anne-Kathrin; Schulz, Robert; Ros, Eduardo; Kadler, Matthias; Perucho, Manel; Wilms, Jörn (Galaxies, 2016)

Model-independent search for neutrino sources with the ANTARES neutrino telescope - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Martí, J.; Basa, S.; Bertin, V.; Biagi, S.; et al. (Astroparticle Physics, 2020)
A novel method to analyse the spatial distribution of neutrino candidates recorded with the ANTARES neutrino telescope is introduced, searching for an excess of neutrinos in a region of arbitrary size and shape from any direction in the sky. Techniques originating from the domains of machine learning, pattern recognition and image processing are used to purify the sample of neutrino candidates and for the analysis of the obtained skymap. In contrast to a dedicated search for a specific neutrino emission model, this approach is sensitive to a wide range of possible morphologies of potential sources of high-energy neutrino emission. The application of these methods to ANTARES data yields a large-scale excess with a post-trial significance of 2.5σ. Applied to public data from IceCube in its IC40 configuration, an excess consistent with the results from ANTARES is observed with a post-trial significance of 2.1σ.
CRIS-Team Scopus Importer:2019-07-02
Keywords: Anisotropy; Astroparticle physics; Neutrino astronomy; Pattern recognition

Modelling of 35-d superorbital cycle of B and V light curves of IMXB HZ Her/Her X-1 - Kolesnikov, D. A.; Shakura, N.; Postnov, K. A.; Volkov, I. M.; Bikmaev, I. F.; Irsmambetova, T. R.; Staubert, R.; Wilms, Jörn; Irtuganov, E.; Golysheva, P. Yu; Shugarov, S. Yu; Nikolenko, I.; et al. (Monthly Notices of the Royal Astronomical Society, 2020)
The X-ray binary Her X-1 consists of an accreting neutron star and the optical component HZ Her. The 35-d X-ray superorbital variability of this system is known, since its discovery in 1972 by the Uhuru satellite and is believed to be caused by forced precession of a warped accretion disc tilted to the orbital plane. We argue that the observed features of the 35-d optical variability of HZ Her can be explained by free precession of the neutron star with a period close to that of the forced disc. The model parameters include (a) the X-ray luminosity of the neutron star; (b) the optical flux from the accretion disc; and (c) the tilt of the inner and outer edges of the accretion disc. A possible synchronization mechanism based on the coupling between the neutron star free precession and the dynamical action of non-stationary gas streams is discussed.
CRIS-Team WoS Importer:2020-12-04

Modelling the light curves of ultraluminous X-ray sources as precession - Dauser, Thomas; Middleton, M.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2017)
We present a freely available XSPEC model for the modulations seen in the long-term light curves of multiple ultraluminous X-ray sources (ULXs). By incorporating the physics of multiple electron scatterings (ray traced with a Monte Carlo routine), we go beyond analytical predictions and show that the geometrical beaming of radiation in the conical outflow can be more than a factor of 100 for opening angles smaller than 10 degrees. We apply our new model to the long-term, well-sampled Swift light curve of the recently confirmed ULX pulsar NGC 5907 X-1 with an established period of 78 d. Our results suggest that geometrical beaming together with a slight precession of the conical wind can describe the light curve with a consistent set of parameters for the wind. The small opening angle of roughly 10 degrees-13 degrees implies a highly supercritical flow and boosting factors of the order of B = 60-90 that would yield a fairly low surface magnetic field strength of 2 x 10(10) G.
Keywords: accretion; accretion discs; black hole physics; pulsars: individual: NGC 5907 ULX-1; X-rays: binaries

Modulated High-Energy Gamma-Ray Emission from the Microquasar Cygnus X-3 - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Axelsson, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, B.; et al. (Science, 2009)
Microquasars are accreting black holes or neutron stars in binary systems with associated relativistic jets. Despite their frequent outburst activity, they have never been unambiguously detected emitting high-energy gamma rays. The Fermi Large Area Telescope (LAT) has detected a variable high-energy source coinciding with the position of the x-ray binary and microquasar Cygnus X-3. Its identification with Cygnus X-3 is secured by the detection of its orbital period in gamma rays, as well as the correlation of the LAT flux with radio emission from the relativistic jets of Cygnus X-3. The gamma-ray emission probably originates from within the binary system, opening new areas in which to study the formation of relativistic jets.

Monte Carlo simulations for the ANTARES underwater neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Journal of Cosmology and Astroparticle Physics, 2021)
Monte Carlo simulations are a unique tool to check the response of a detector and to monitor its performance. For a deep-sea neutrino telescope, the variability of the environmental conditions that can affect the behaviour of the data acquisition system must be considered, in addition to a reliable description of the active parts of the detector and of the features of physics events, in order to produce a realistic set of simulated events. In this paper, the software tools used to produce neutrino and cosmic ray signatures in the telescope and the strategy developed to represent the time evolution of the natural environment and of the detector efficiency are described.
CRIS-Team Scopus Importer:2021-02-12
Keywords: Cosmic ray experiments; Neutrino astronomy; Neutrino detectors; Neutrino experiments

MUCHFUSS - Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS - Geier, Stephan; Schaffenroth, Veronika; Hirsch, H.; Tillich, A.; Heber, Ulrich; Maxted, P. F. L.; Ostensen, R. H.; Barlow, B. N.; O'Toole, S. J.; Kupfer, Thomas; Marsh, T.; Gaensicke, Boris T; et al. (Astronomische Nachrichten, 2012)
The project Massive Unseen Companions to Hot Faint Underluminous Stars from SDSS (MUCHFUSS) aims at finding hot subdwarf stars with massive compact companions (white dwarfs with masses M > 1.0 M ⊙, neutron stars or black holes). The existence of such systems is predicted by binary evolution calculations and some candidate systems have been found. We identified ≃1100 hot subdwarf stars from the Sloan Digital Sky Survey (SDSS). Stars with high velocities have been reobserved and individual SDSS spectra have been analysed. About 70 radial velocity variable subdwarfs have been selected as good candidates for follow-up time resolved spectroscopy to derive orbital parameters and photometric follow-up to search for features like eclipses in the light curves. Up to now we found nine close binary sdBs with short orbital periods ranging from ≃0.07 d to 1.5 d. Two of them are eclipsing binaries with companions that are most likely of substellar nature © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
CRIS-Team Scopus Importer:2020-12-21
Keywords: Binaries: spectroscopic; Subdwarfs

Multi-messenger Observations of a Binary Neutron Star Merger - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, Paolo; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; Afrough, M.; et al. (Astrophysical Journal Letters, 2017)
On 2017 August 17 a binary neutron star coalescence candidate (later designated GW170817) with merger time 12:41:04 UTC was observed through gravitational waves by the Advanced LIGO and Advanced Virgo detectors. The Fermi Gamma-ray Burst Monitor independently detected a gamma-ray burst (GRB 170817A) with a time delay of similar to 1.7 s with respect to the merger time. From the gravitational-wave signal, the source was initially localized to a sky region of 31 deg(2) at a luminosity distance of 40(-8)(+8) Mpc and with component masses consistent with neutron stars. The component masses were later measured to be in the range 0.86 to 2.26 M-circle dot. An extensive observing campaign was launched across the electromagnetic spectrum leading to the discovery of a bright optical transient (SSS17a, now with the IAU identification of AT 2017gfo) in NGC 4993 (at similar to 40 Mpc) less than 11 hours after the merger by the One-Meter, Two Hemisphere (1M2H) team using the 1 m Swope Telescope. The optical transient was independently detected by multiple teams within an hour. Subsequent observations targeted the object and its environment. Early ultraviolet observations revealed a blue transient that faded within 48 hours. Optical and infrared observations showed a redward evolution over similar to 10 days. Following early non-detections, X-ray and radio emission were discovered at the transient's position similar to 9 and similar to 16 days, respectively, after the merger. Both the X-ray and radio emission likely arise from a physical process that is distinct from the one that generates the UV/optical/near-infrared emission. No ultra-high-energy gamma-rays and no neutrino candidates consistent with the source were found in follow-up searches. These observations support the hypothesis that GW170817 was produced by the merger of two neutron stars in NGC4993 followed by a short gamma-ray burst (GRB 170817A) and a kilonova/macronova powered by the radioactive decay of r-process nuclei synthesized in the ejecta.
Keywords: gravitational waves; stars: neutron

Multiwavelength observations of the black hole transient Swift J1745-26 during the outburst decay - Kalemci, E.; Arabaci, M. Ozbey; Guver, Tolga; Russell, D. M.; Tomsick, J. A.; Wilms, Jörn; Weidenspointner, G.; Kuulkers, E.; Falanga, M.; Dincer, Tolga; Drave, S.; Belloni, T.; et al. (Monthly Notices of the Royal Astronomical Society, 2014)
We characterized the broad-band X-ray spectra of Swift J1745-26 during the decay of the 2013 outburst using INTEGRAL ISGRI, JEM-X and Swift XRT. The X-ray evolution is compared to the evolution in optical and radio. We fit the X-ray spectra with phenomenological and Comptonization models. We discuss possible scenarios for the physical origin of an similar to 50 d flare observed both in optical and X-rays similar to 170 d after the peak of the outburst. We conclude that it is a result of enhanced mass accretion in response to an earlier heating event. We characterized the evolution in the hard-X-ray band and showed that for the joint ISGRI-XRT fits, the e-folding energy decreased from 350 to 130 keV, while the energy where the exponential cut-off starts increased from 75 to 112 keV as the decay progressed. We investigated the claim that high-energy cut-offs disappear with the compact jet turning on during outburst decays, and showed that spectra taken with HEXTE on RXTE provide insufficient quality to characterize cut-offs during the decay for typical hard-X-ray fluxes. Long INTEGRAL monitoring observations are required to understand the relation between the compact jet formation and hard-X-ray behaviour. We found that for the entire decay (including the flare), the X-ray spectra are consistent with thermal Comptonization, but a jet synchrotron origin cannot be ruled out.
Keywords: stars: black holes; stars: individual: Swift J174510.8-2624; X-rays: binaries

MURCHISON WIDEFIELD ARRAY LIMITS on RADIO EMISSION from ANTARES NEUTRINO EVENTS - Croft, Steve; Kaplan, D. L.; Tingay, S. J.; Murphy, Tara; Bell, M. E.; Rowlinson, Antonia; Adrian-Martinez, S.; Ageron, M.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; et al. (Astrophysical Journal Letters, 2016)
We present a search, using the Murchison Widefield Array (MWA), for electromagnetic (EM) counterparts to two candidate high-energy neutrino events detected by the ANTARES neutrino telescope in 2013 November and 2014 March. These events were selected by ANTARES because they are consistent, within 0°.4, with the locations of galaxies within 20 Mpc of Earth. Using MWA archival data at frequencies between 118 and 182 MHz, taken ∼20 days prior to, at the same time as, and up to a year after the neutrino triggers, we look for transient or strongly variable radio sources that are consistent with the neutrino positions. No such counterparts are detected, and we set a 5σ upper limit for low-frequency radio emission of ∼10 erg s for progenitors at 20 Mpc. If the neutrino sources are instead not in nearby galaxies, but originate in binary neutron star coalescences, our limits place the progenitors at z 0.2. While it is possible, due to the high background from atmospheric neutrinos, that neither event is astrophysical, the MWA observations are nevertheless among the first to follow up neutrino candidates in the radio, and illustrate the promise of wide-field instruments like MWA for detecting EM counterparts to such events.
Keywords: neutrinos; radio continuum: general

New constraints on all flavor Galactic diffuse neutrino emission with the ANTARES telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
The flux of very high-energy neutrinos produced in our Galaxy by the interaction of accelerated cosmic rays with the interstellar medium is not yet determined. The characterization of this flux will shed light on Galactic accelerator features, gas distribution morphology and Galactic cosmic ray transport. The central Galactic plane can be the site of an enhanced neutrino production, thus leading to anisotropies in the extraterrestrial neutrino signal as measured by the IceCube Collaboration. The ANTARES neutrino telescope, located in the Mediterranean Sea, offers a favorable view of this part of the sky, thereby allowing for a contribution to the determination of this flux. The expected diffuse Galactic neutrino emission can be obtained, linking a model of generation and propagation of cosmic rays with the morphology of the gas distribution in the Milky Way. In this paper, the so-called "gamma model" introduced recently to explain the high-energy gamma-ray diffuse Galactic emission is assumed as reference. The neutrino flux predicted by the "gamma model" depends on the assumed primary cosmic ray spectrum cutoff. Considering a radially dependent diffusion coefficient, this proposed scenario is able to account for the local cosmic ray measurements, as well as for the Galactic gamma-ray observations. Nine years of ANTARES data are used in this work to search for a possible Galactic contribution according to this scenario. All flavor neutrino interactions are considered. No excess of events is observed, and an upper limit is set on the neutrino flux of 1.1 (1.2) times the prediction of the "gamma model," assuming the primary cosmic ray spectrum cutoff at 5 (50) PeV. This limit excludes the diffuse Galactic neutrino emission as the major cause of the "spectral anomaly" between the two hemispheres measured by IceCube.

No anticorrelation between cyclotron line energy and X-ray flux in 4U 0115+634 - Müller, Sebastian; Ferrigno, C.; Kühnel, Matthias; Schoenherr, G.; Becker, P. A.; Wolff, M. T.; Hertel, Dominik; Schwarm, Fritz-Walter; Grinberg, Victoria; Obst, M.; Caballero, I.; Pottschmidt, K.; et al. (Astronomy & Astrophysics, 2013)
We report on an outburst of the high mass X-ray binary 4U 0115+634 with a pulse period of 3.6 s in 2008 March/April as observed with RXTE and INTEGRAL. During the outburst the neutron star's luminosity varied by a factor of 10 in the 3-50 keV band. In agreement with earlier work we find evidence of five cyclotron resonance scattering features at similar to 10.7, 21.8, 35.5, 46.7, and 59.7 keV. Previous work had found an anticorrelation between the fundamental cyclotron line energy and the X-ray flux. We show that this apparent anticorrelation is probably due to the unphysical interplay of parameters of the cyclotron line with the continuum models used previously, e. g., the negative and positive exponent power law (NPEX). For this model, we show that cyclotron line modeling erroneously leads to describing part of the exponential cutoff and the continuum variability, and not the cyclotron lines. When the X-ray continuum is modeled with a simple exponentially cutoff power law modified by a Gaussian emission feature around 10 keV, the correlation between the line energy and the flux vanishes, and the line parameters remain virtually constant over the outburst. We therefore conclude that the previously reported anticorrelation is an artifact of the assumptions adopted in the modeling of the continuum.
Keywords: X-rays: binaries; pulsars: individual 4U 0115+634; magnetic fields

NON-LOCAL THERMAL EQUILIBRIUM MODEL ATMOSPHERES FOR THE HOTTEST WHITE DWARFS: SPECTRAL ANALYSIS OF THE COMPACT COMPONENT IN NOVA V4743 Sgr - Rauch, T.; Orio, M.; Gonzales-Riestra, R.; Nelson, T.; Still, M.; Werner, Klaus; Wilms, Jörn (Astrophysical Journal, 2010)
Half a year after its outburst in 2002 September, nova V4743 Sgr evolved into the brightest supersoft X-ray source in the sky with a flux maximum around 30 angstrom. We calculated grids of synthetic energy distributions based on non-local thermal equilibrium model atmospheres for the analysis of the hottest white dwarfs (WDs) and present the result of fits to Chandra and XMM-Newton grating X-ray spectra of V4743 Sgr of outstanding quality, exhibiting prominent resonance lines of C v, C VI, N VI, N VII, and O VII in absorption. The nova reached its highest effective temperature (T(eff) = 740 +/- 70 kK) around 2003 April and remained at that temperature at least until 2003 September. We conclude that the WD is massive, approximate to 1.1-1.2M(circle dot). The nuclear-burning phase lasted for 2-2.5 years after the outburst, probably the average duration for a classical nova. The photosphere of V4743 Sgr was strongly carbon deficient (approximate to 0.01 times solar) and enriched in nitrogen and oxygen (>5 times solar). Especially the very low C/N ratio indicates that the material at the WD's surface underwent thermonuclear burning. Thus, this nova retained some of the accreted material and did not eject all of it in outburst. From 2003 March to September, the nitrogen abundance is strongly decreasing; new material is probably already being accreted at this stage.
Keywords: novae; cataclysmic variables; stars: abundances; stars: AGB and post-AGB; stars: atmospheres; stars: individual (V4743 Sgr); white dwarfs

Normalizing a relativistic model of X-ray reflection. Definition of the reflection fraction and its implementation in relxill - Dauser, Thomas; Garcia, J.; Walton, D. J.; Eikmann, Wiebke; Kallman, T.; Mcclintock, J.; Wilms, Jörn (Astronomy & Astrophysics, 2016)
The only relativistic reflection model that implements a parameter relating the intensity incident on an accretion disk to the observed intensity is relxill. The parameter used in earlier versions of this model, referred to as the reflection strength, is unsatisfactory; it has been superseded by a parameter that provides insight into the accretion geometry, namely the reflection fraction. The reflection fraction is defined as the ratio of the coronal intensity illuminating the disk to the coronal intensity that reaches the observer. Methods. The relxill model combines a general relativistic ray-tracing code and a photoionization code to compute the component of radiation reflected from an accretion that is illuminated by an external source. The reflection fraction is a particularly important parameter for relativistic models with well-defined geometry, such as the lamp post model, which is a focus of this paper. Results. Relativistic spectra are compared for three inclinations and for four values of the key parameter of the lamp post model, namely the height above the black hole of the illuminating, on-axis point source. In all cases, the strongest reflection is produced for low source heights and high spin. A low-spin black hole is shown to be incapable of producing enhanced relativistic reflection. Results for the relxill model are compared to those obtained with other models and a Monte Carlo simulation. Conclusions. Fitting data by using the relxill model and the recently implemented reflection fraction, the geometry of a system can be constrained. The reflection fraction is independent of system parameters such as inclination and black hole spin. The reflection-fraction parameter was implemented with the name refl-frac in all flavours of the relxill model, and the non-relativistic reflection model xillver, in v0.4a (18 January 2016).
Keywords: accretion; accretion disks; galaxies: active; line: profiles; X-rays: galaxies

NO TIME FOR DEAD TIME: TIMING ANALYSIS OF BRIGHT BLACK HOLE BINARIES WITH NuSTAR - Bachetti, Matteo; Harrison, Fiona A.; Cook, Rick; Tomsick, John; Schmid, Christian; Grefenstette, Brian W.; Barret, Didier; Boggs, Steven E.; Christensen, Finn E.; Craig, William W.; Fabian, Andrew C.; Fuerst, Felix; et al. (Astrophysical Journal, 2015)
Timing of high-count-rate sources with the NuSTAR Small Explorer Mission requires specialized analysis techniques. NuSTAR was primarily designed for spectroscopic observations of sources with relatively low count rates rather than for timing analysis of bright objects. The instrumental dead time per event is relatively long (similar to 2.5msec) and varies event-to-event by a few percent. The most obvious effect is a distortion of the white noise level in the power density spectrum (PDS) that cannot be easily modeled with standard techniques due to the variable nature of the dead time. In this paper, we show that it is possible to exploit the presence of two completely independent focal planes and use the cospectrum, the real part of the cross PDS, to obtain a good proxy of the white-noise-subtracted PDS. Thereafter, one can use a Monte Carlo approach to estimate the remaining effects of dead time, namely, a frequency-dependent modulation of the variance and a frequency-independent drop of the sensitivity to variability. In this way, most of the standard timing analysis can be performed, albeit with a sacrifice in signal-to-noise ratio relative to what would be achieved using more standard techniques. We apply this technique to NuSTAR observations of the black hole binaries GX 339-4, Cyg X-1, and GRS 1915+105.
Keywords: accretion; accretion disks; black hole physics; methods: data analysis; methods: statistical; X-rays: stars

NuSTAR AND SUZAKU OBSERVATIONS OF THE HARD STATE IN CYGNUS X-1: LOCATING THE INNER ACCRETION DISK - Parker, M. L.; Tomsick, J. A.; Miller, J. M.; Yamaoka, K.; Lohfink, A.; Nowak, M.; Fabian, A. C.; Alston, W. N.; Boggs, S. E.; Christensen, F. E.; Craig, W. W.; Fuerst, F.; et al. (Astrophysical Journal, 2015)
We present simultaneous Nuclear Spectroscopic Telescope Array (NuSTAR) and Suzaku. observations of the X-ray binary Cygnus X-1 in the hard state. This is the first time this state has been observed in Cyg X-1 with NuSTAR, which enables us to study the reflection and broadband spectra in unprecedented detail. We confirm that the iron line cannot be fit with a combination of narrow lines and absorption features, instead requiring. a relativistically blurred profile in combination with a narrow line and absorption from the companion wind. We use the reflection models of Garcia et al. to simultaneously measure the black hole spin, disk inner radius, and coronal height in a self-consistent manner. Detailed fits to the iron line profile indicate a high level of relativistic blurring, indicative of reflection from the inner accretion disk. We find a high spin, a small inner disk radius, and a low source height. and rule out truncation to greater than three gravitational radii at the 3 sigma confidence level. In addition, we find that the line profile has not changed greatly in the switch from soft to hard states, and that the differences are consistent with changes in the underlying reflection spectrum rather than the relativistic blurring. We find that the blurring parameters are consistent when fitting either just the iron line or the entire broadband spectrum, which is well modeled with a Comptonized continuum plus reflection model.
Keywords: accretion; accretion disks; black hole physics; X-rays: binaries; X-rays: individual (Cygnus X-1)

NuSTAR and XMM-Newton Observations of the Hard X-Ray Spectrum of Centaurus A - Fuerst, F.; Mueller, C.; Madsen, K. K.; Lanz, L.; Rivers, E.; Brightman, M.; Arevalo, P.; Balokovic, M.; Beuchert, T.; Boggs, S. E.; Christensen, F. E.; Craig, W. W.; et al. (Astrophysical Journal, 2016)
Keywords: galaxies: active; galaxies: individual: Centaurus A; X-rays: galaxies

Observation of strong two-electron-one-photon transitions in few-electron ions - Togawa, Moto; Kuehn, S.; Shah, Chintan; Amaro, Pedro; Steinbruegge, R.; Stierhof, Jakob; Hell, N.; Rosner, M.; Fujii, Keisuke; Bissinger, Matthias; Ballhausen, Ralf; Hoesch, M.; et al. (Physical Review A, 2020)
We resonantly excite the K series of O5+ and O6+ up to principal quantum number n=11 with monochromatic x rays, producing K-shell holes, and observe their relaxation by soft-x-ray emission. Some photoabsorption resonances of O5+ reveal strong two-electron-one-photon (TEOP) transitions. We find that for the [(1s2s)15p3/2]3/2;1/2 states, TEOP relaxation is by far stronger than the radiative decay and competes with the usually much faster Auger decay path. This enhanced TEOP decay arises from a strong correlation with the near-degenerate upper states [(1s2p3/2)14s]3/2;1/2 of a Li-like satellite blend of the He-like Kα transition. Even in three-electron systems, TEOP transitions can play a dominant role, and the present results should guide further research on the ubiquitous and abundant many-electron ions where electronic energy degeneracies are far more common and configuration mixing is stronger.
CRIS-Team Scopus Importer:2021-04-19

Observation of the cosmic ray shadow of the Sun with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin,; Biagi, S.; et al. (Physical Review D, 2020)
The ANTARES detector is an undersea neutrino telescope in the Mediterranean Sea. The search for pointlike neutrino sources is one of the main goals of the ANTARES telescope, requiring a reliable method to evaluate the detector angular resolution and pointing accuracy. This work describes the study of the Sun "shadow" effect with the ANTARES detector. The shadow is the deficit in the atmospheric muon flux in the direction of the Sun caused by the absorption of the primary cosmic rays. This analysis is based on the data collected between 2008 and 2017 by the ANTARES telescope. The observed statistical significance of the Sun shadow detection is 3.7 sigma, with an estimated angular resolution of 0.59 degrees +/- 0.10 degrees for downward-going muons. The pointing accuracy is found to be consistent with the expectations and no evidence of systematic pointing shifts is observed.
CRIS-Team WoS Importer:2021-01-15

Observatory science with eXTP - In'T Zand, Jean J. M.; Bozzo, Enrico; Qu, Jinlu; Li, Xiang-Dong; Amati, Lorenzo; Chen, Yang; Donnarumma, Immacolata; Doroshenko, Victor; Drake, Stephen A.; Hernanz, Margarita; Jenke, Peter A.; Maccarone, Thomas J.; et al. (Science China-Physics Mechanics & Astronomy, 2019)
In this White Paper we present the potential of the enhanced X-ray Timing and Polarimetry (eXTP) mission for studies related to Observatory Science targets. These include flaring stars, supernova remnants, accreting white dwarfs, low and high mass X-ray binaries, radio quiet and radio loud active galactic nuclei, tidal disruption events, and gamma-ray bursts. eXTP will be excellently suited to study one common aspect of these objects: their often transient nature. Developed by an international Consortium led by the Institute of High Energy Physics of the Chinese Academy of Science, the eXTP mission is expected to be launched in the mid 2020s.
Keywords: space research instruments; nuclear astrophysics; flare stars; accretion and accretion disks; mass loss and stellar winds; cataclysmic binaries; X-ray binaries; supernova remnants; active galactic nuclei; X-ray bursts; gamma-ray bursts; gravitational waves

Observing the Transient Pulsations of SMC X-1 with NuSTAR - Pike, Sean N.; Harrison, Fiona A.; Bachetti, Matteo; Brumback, Mckinley C.; Furst, Felix S.; Madsen, Kristin K.; Pottschmidt, Katja; Tomsick, John A.; Wilms, Jörn (Astrophysical Journal, 2019)
We report on Nuclear Spectroscopic Telescope Array observations of transient pulsations in the neutron star X-ray binary SMC X-1. The transition from nonpulsing to pulsing states was not accompanied by a large change in flux. Instead, both pulsing and nonpulsing states were observed in a single observation during the low-flux super-orbital state. During the high state, we measure a pulse period of P = 0.70117(9) s at T-ref = 56145 MJD. Spectral analysis during nonpulsing and pulsing states reveals that the observations can be consistently modeled by an absorbed power law with a phenomenological cutoff resembling a Fermi-Dirac distribution, or by a partially obscured cutoff power law. The shapes of the underlying continua show little variability between epochs, while the covering fraction and column density vary between super-orbital states. The strength of pulsations also varies, leading us to infer that the absence and reemergence of pulsations are related to changing obscuration, such as by a warped accretion disk. SMC X-1 is accreting near or above its Eddington limit, reaching an unabsorbed X-ray luminosity of L-x (2-10 keV) approximate to 5 x 10(38) erg s(-1). This suggests that SMC X-1 may be a useful local analog to ultraluminous X-ray pulsars (ULXPs), which likewise exhibit strong variability in their pulsed fractions, as well as flux variability on similar timescales. In particular, the gradual pulse turn-on, which has been observed in M82 X-2, is similar to the behavior we observe in SMC X-1. Thus we propose that pulse fraction variability of ULXPs may also be due to variable obscuration.
Keywords: accretion; accretion disks; stars: neutron; X-rays: binaries; X-rays: individual (SMC X-1)

Observing the WHIM with Athena - Brand, Thorsten; Wilms, Jörn; Dauser, Thomas; Peille, P.; Cobo, B.; Ceballos, M.; Den Hartog, R. A.; Kaastra, J. S.; O'Brien, P.; Barcons, X.; Piro, L.; Den Herder, J. W A; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
We present simulations of the detection probability for absorption lines from ions in the warm and hot ionized medium (WHIM) with Athena in the spectra of Gamma-ray burst afterglows. The simulations are based on Swift XRT lightcurves of these afterglows and are performed using the end-to-end simulation framework SIXTE. We simulate both the case of single and multiple absorption lines, as well as results for line searches in absorption structures from a more complex medium. We show that the Athena X-IFU can detect WHIM lines with strong Ovii lines (equivalent widths larger than 0.14 eV) in spectra containing 3 x 10 counts.
Keywords: Athena; GRB; Simulation; SIXTE; WHIM; X-IFU

ON ESTIMATING THE HIGH-ENERGY CUTOFF IN THE X-RAY SPECTRA OF BLACK HOLES VIA REFLECTION SPECTROSCOPY - Garcia, Javier A.; Dauser, Thomas; Steiner, James F.; McClintock, Jeffrey E.; Keck, Mason L.; Wilms, Jörn (Astrophysical Journal Letters, 2015)
The fundamental parameters describing the coronal spectrum of an accreting black hole are the slope Gamma of the power-law continuum and the energy E-cut at which it rolls over. Remarkably, this latter parameter can be accurately measured for values as high as 1 MeV by modeling the spectrum of X-rays reflected from a black hole accretion disk at energies below 100 keV. This is possible because the details in the reflection spectrum, rich in fluorescent lines and other atomic features, are very sensitive to the spectral shape of the hardest coronal radiation illuminating the disk. We show that by fitting simultaneous NuSTAR (3-79 keV) and low-energy (e.g., Suzaku) data with the most recent version of our reflection model relxill one can obtain reasonable constraints on E-cut at energies from tens of keV up to 1 MeV, for a source as faint as 1 mCrab in a 100 ks observation.
Keywords: accretion; accretion disks; atomic processes; black hole physics

On the cyclotron line in cepheus X-4 - Wilms, Jörn; et al. (Astronomy & Astrophysics, 2007)
Context. Accreting X-ray pulsars provide us with laboratories for the study of extreme gravitational and magnetic fields, hence accurate descriptions of their observational properties contribute to our understanding of this group of objects.Aims. We aim to detect a cyclotron resonance scattering feature in the Be Be/X-ray binary Cep X-4 and to investigate pulse profile and spectral changes through the outburst.Methods. Spectral fitting and timing analysis are employed to probe th the properties of Cep X-4 during during an outburst in 2002 June.Results. A previously announced cyclotron feature at 30.7 keV is confirmed, while the source shows spectral behaviour and luminosity related changes similar to those observed in previous outbursts. The long-term X-ray lightcurve shows a periodicity at 20.85 d, which could be attributed to the orbit in this Be system.
Keywords: X-rays; binaries - stars; magnetic fields - stars; pulsars; individual; Cep X-4-stars; pulsars; individual; GS 2138+56

On the Detection Potential of Blazar Flares for Current Neutrino Telescopes - Kreter, M.; Kadler, M.; Krauss, F.; Mannheim, K.; Buson, S.; Ojha, R.; Wilms, Jörn; Bottcher, M. (Astrophysical Journal, 2020)
Blazar jets are extreme environments, in which relativistic proton interactions with an ultraviolet photon field could give rise to photopion production. High-confidence associations of individual high-energy neutrinos with blazar flares could be achieved via spatially and temporally coincident detections. In 2017, the track-like, extremely high-energy neutrino event IC 170922A was found to coincide with increased gamma-ray emission from the blazar TXS 0506+056, leading to the identification of the most promising neutrino point-source candidate so far. We calculate the expected number of neutrino events that can be detected with IceCube, based on a broadband parameterization of bright short-term blazar flares that were observed in the first 6.5 yr of Fermi/Large Area Telescope observations. We find that the integrated keV-to-GeV fluence of most individual blazar flares is far too small to yield a substantial Poisson probability for the detection of one or more neutrinos with IceCube. We show that the sample of potentially detectable high-energy neutrinos from individual blazar flares is rather small. We further show that the blazars 3C 279 and PKS 1510-089 dominate the all-sky neutrino prediction from bright and short-term blazar flares. In the end, we discuss strategies to search for more significant associations in future data unblindings of IceCube and KM3NeT.
CRIS-Team WoS Importer:2020-11-06

On the determination of the spin of the black hole in Cyg X-1 from X-ray reflection spectra - Fabian, A. C.; Wilkins, D. R.; Miller, J. M.; Reis, R. C.; Reynolds, C. S.; Cackett, E. M.; Nowak, M. A.; Pooley, G. G.; Pottschmidt, K.; Sanders, J. S.; Ross, R. R.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2012)
The spin of Cygnus X-1 is measured by fitting reflection models to Suzaku data covering the energy band 0.9400 keV. The inner radius of the accretion disc is found to lie within 2 gravitational radii (rg=GM/c2), and a value of is obtained for the dimensionless black hole spin. This agrees with recent measurements using the continuum fitting method by Gou et al. and of the broad iron line by Duro et al. The disc inclination is measured at , which is consistent with the recent optical measurement of the binary system inclination by Orosz et al. of 27 degrees +/- 08. We pay special attention to the emissivity profile caused by irradiation of the inner disc by the hard power-law source. The X-ray observations and simulations show that the index q of that profile deviates from the commonly used, Newtonian, value of 3 within 3rg, steepening considerably within 2rg, as expected in the strong gravity regime.
Keywords: accretion; accretion discs; black hole physics; line: profiles; X-rays: general

On the nature of the 35-day cycle in the X-ray binary Her X-1/HZ Her - Shakura, N.; Kolesnikov, D.; Postnov, K.; Volkov, I.; Bikmaev, I.; Irsmambetova, T.; Staubert, R.; Wilms, Jörn; Irtuganov, E.; Shurygin, P.; Golysheva, P.; Shugarov, S.; et al. (High-mass X-ray Binaries: Illuminating the Passagefrom Massive Binaries to Merging Compact Objects, 2019)
The X-ray binary Her X-1 consists of an accreting neutron star and the optical companion HZ Her. The 35-day X-ray variability of this system is known since its discovery in 1972 by the UHURU satellite and is believed to be caused by forced precession of the warped accretion disk tilted to the orbital plane. We argue that the observed features of the optical variability of HZ Her can be explained by free precession of the neutron star with a period close to that of the forced disk precession. The model parameters include a) the intensity (power) of the stream of matter flowing out of the optical star; b) the X-ray luminosity of the neutron star; c) the optical flux of the accretion disk; d) the X-ray irradiation pattern on the donor star; e) the tilt of the inner and outer edge of the accretion disk. A possible synchronization mechanism based on the coupling between the neutron star free precession and the dynamical action of non-stationary gas streams is discussed shortly.
CRIS-Team Scopus Importer:2020-02-21
Keywords: stars: binaries: close; stars: neutron; X-rays: binaries

ON THE RADIAL ONSET OF CLUMPING IN THE WIND OF THE B0I MASSIVE STAR QV NOR - Torrejon, J. M.; Schulz, N. S.; Nowak, M. A.; Oskinova, L.; Rodes-Roca, J. J.; Shenar, T.; Wilms, Jörn (Astrophysical Journal, 2015)
We present an analysis of a 78 ks Chandra high-energy transmission gratings observation of the B0I star QV Nor, the massive donor of the wind-accreting pulsar 4U1538-52. The neutron star (NS) orbits its companion in a very close orbit (r < 1.4R(*), in units of the stellar radii), thereby allowing probing of the innermost wind regions. The flux of the Fe K alpha line during eclipse reduces to only similar to 30% of the flux measured out of eclipse. This indicates that the majority of Fe fluorescence must be produced in regions close to the NS, at distances smaller than 1R(*) from its surface. The fact that the flux of the continuum decreases to only similar to 3% during eclipse allows for a high contrast of the Fe Ka line fluorescence during eclipse. The line is not resolved and centered at lambda = 1.9368(-0.0018)(+0.0032) angstrom. From the inferred plasma speed limit of v < c Delta lambda/lambda < 800 km s(-1) and range of ionization parameters of log xi =[-1, 2], together with the stellar density profile, we constrain the location of the cold, dense material in the stellar wind of QV Nor using simple geometrical considerations. We then use the Fe K alpha line fluorescence as a tracer of wind clumps and determine that these clumps in the stellar wind of QV Nor (B0I) must already be present at radii r < 1.25R(*), close to the photosphere of the star.
Keywords: stars: individual (QV Nor; 4U1538+52); stars: winds; outflows; X-rays: binaries

ON THE ROLE OF THE ACCRETION DISK IN BLACK HOLE DISK-JET CONNECTIONS - Miller, J. M.; Pooley, G. G.; Fabian, A. C.; Nowak, M. A.; Reis, R. C.; Cackett, E. M.; Pottschmidt, K.; Wilms, Jörn (Astrophysical Journal, 2012)
Models of jet production in black hole systems suggest that the properties of the accretion disk-such as its mass accretion rate, inner radius, and emergent magnetic field-should drive and modulate the production of relativistic jets. Stellar-mass black holes in the "low/hard" state are an excellent laboratory in which to study disk-jet connections, but few coordinated observations are made using spectrometers that can incisively probe the inner disk. We report on a series of 20 Suzaku observations of Cygnus X-1 made in the jet-producing low/hard state. Contemporaneous radio monitoring was done using the Arcminute MicroKelvin Array radio telescope. Two important and simple results are obtained: (1) the jet (as traced by radio flux) does not appear to be modulated by changes in the inner radius of the accretion disk and (2) the jet is sensitive to disk properties, including its flux, temperature, and ionization. Some more complex results may reveal aspects of a coupled disk-corona-jet system. A positive correlation between the reflected X-ray flux and radio flux may represent specific support for a plasma ejection model of the corona, wherein the base of a jet produces hard X-ray emission. Within the framework of the plasma ejection model, the spectra suggest a jet base with v/c similar or equal to 0.3 or the escape velocity for a vertical height of z similar or equal to 20 GM/c(2) above the black hole. The detailed results of X-ray disk continuum and reflection modeling also suggest a height of z similar or equal to 20 GM/c(2) for hard X-ray production above a black hole, with a spin in the range 0.6 <= a <= 0.99. This height agrees with X-ray time lags recently found in Cygnus X-1. The overall picture that emerges from this study is broadly consistent with some jet-focused models for black hole spectral energy distributions in which a relativistic plasma is accelerated at z = 10-100 GM/c(2). We discuss these results in the context of disk-jet connections across the black hole mass scale.
Keywords: accretion; accretion disks; black hole physics; relativistic processes; X-rays: binaries

Optical and X-ray early follow-up of ANTARES neutrino alerts - Adrian-Martinez, S.; Ageron, M.; Albert, A.; Al Samarai, I.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; et al. (Journal of Cosmology and Astroparticle Physics, 2016)
High-energy neutrinos could be produced in the interaction of charged cosmic rays with matter or radiation surrounding astrophysical sources. Even with the recent detection of extraterrestrial high-energy neutrinos by the IceCube experiment, no astrophysical neutrino source has yet been discovered. Transient sources, such as gamma-ray bursts, core-collapse supernovae, or active galactic nuclei are promising candidates. Multi-messenger programs offer a unique opportunity to detect these transient sources. By combining the information provided by the ANTARES neutrino telescope with information coming from other observatories, the probability of detecting a source is enhanced, allowing the possibility of identifying a neutrino progenitor from a single detected event. A method based on optical and X-ray follow-ups of high-energy neutrino alerts has been developed within the ANTARES collaboration. This method does not require any assumptions on the relation between neutrino and photon spectra other than time-correlation. This program, denoted as TAToO, triggers a network of robotic optical telescopes (TAROT and ROTSE) and the Swift-XRT with a delay of only a few seconds after a neutrino detection, and is therefore well-suited to search for fast transient sources. To identify an optical or X-ray counterpart to a neutrino signal, the images provided by the follow-up observations are analysed with dedicated pipelines. A total of 42 alerts with optical and 7 alerts with X-ray images taken with a maximum delay of 24 hours after the neutrino trigger have been analysed. No optical or X-ray counterparts associated to the neutrino triggers have been found, and upper limits on transient source magnitudes have been derived. The probability to reject the gamma-ray burst origin hypothesis has been computed for each alert.

Outburst of GX 304-1 monitored with INTEGRAL: positive correlation between the cyclotron line energy and flux - Klochkov, D.; Doroshenko, Victor; Santangelo, A.; Staubert, R.; Ferrigno, Carlo; Kretschmar, Peter; Caballero, I.; Wilms, Jörn; Kreykenbohm, Ingo; Pottschmidt, K.; Rothschild, R. E.; Wilson-Hodge, C. A.; et al. (Astronomy & Astrophysics, 2012)
Context. X-ray spectra of many accreting pulsars exhibit significant variations as a function of flux and thus of mass accretion rate. In some of these pulsars, the centroid energy of the cyclotron line(s), which characterizes the magnetic field strength at the site of the X-ray emission, has been found to vary systematically with flux.Aims. GX304-1 is a recently established cyclotron line source with a line energy around 50 keV. Since 2009, the pulsar shows regular outbursts with the peak flux exceeding one Crab. We analyze the INTEGRAL observations of the source during its outburst in January-February 2012.Methods. The observations covered almost the entire outburst, allowing us to measure the source's broad-band X-ray spectrum at different flux levels. We report on the variations in the spectral parameters with luminosity and focus on the variations in the cyclotron line.Results. The centroid energy of the line is found to be positively correlated with the luminosity. We interpret this result as a manifestation of the local sub-Eddington (sub-critical) accretion regime operating in the source.
Keywords: X-rays: binaries; stars: neutron; accretion; accretion disks

Overview of the Advanced X-ray Imaging Satellite (AXIS) - Reynolds, Christopher S.; Kara, Erin A.; Mushotzky, Richard F.; Ptak, Andrew; Koss, Michael J.; Williams, Brian J.; Allen, Steven W.; Bauer, Franz E.; Bautz, Marshall; Bodaghee, Arash; Burdge, Kevin B.; Cappelluti, Nico; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2023)
The Advanced X-ray Imaging Satellite (AXIS) is a Probe-class concept that will build on the legacy of the Chandra X-ray Observatory by providing low-background, arcsecond-resolution imaging in the 0.3-10 keV band across a 450 arcminute2 field of view, with an order of magnitude improvement in sensitivity. AXIS utilizes breakthroughs in the construction of lightweight segmented X-ray optics using single-crystal silicon, and developments in the fabrication of large-format, small-pixel, high readout rate CCD detectors with good spectral resolution, allowing a robust and cost-effective design. Further, AXIS will be responsive to target-of-opportunity alerts and, with onboard transient detection, will be a powerful facility for studying the time-varying X-ray universe, following on from the legacy of the Neil Gehrels (Swift) X-ray observatory that revolutionized studies of the transient X-ray Universe. In this paper, we present an overview of AXIS, highlighting the prime science objectives driving the AXIS concept and how the observatory design will achieve these objectives.
CRIS-Team Scopus Importer:2023-11-24
Keywords: APEX Probe missions; X-ray astronomy; X-ray detectors; X-ray optics

Performance assessment of different pulse reconstruction algorithms for the ATHENA X-ray Integral Field Unit - Peille, Philippe; Ceballos, Maria Teresa; Cobo, Beatriz; Wilms, Jörn; Bandler, Simon; Smith, Stephen J.; Dauser, Thomas; Brand, Thorsten; Den Hartog, Roland; De Plaa, Jelle; Barret, Didier; Den Herder, Jan Willem; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
The X-ray Integral Field Unit (X-IFU) microcalorimeter, on-board Athena, with its focal plane comprising 3840 Transition Edge Sensors (TESs) operating at 90 mK, will provide unprecedented spectral-imaging capability in the 0.2-12 keV energy range. It will rely on the on-board digital processing of current pulses induced by the heat deposited in the TES absorber, as to recover the energy of each individual events. Assessing the capabilities of the pulse reconstruction is required to understand the overall scientific performance of the X-IFU, notably in terms of energy resolution degradation with both increasing energies and count rates. Using synthetic data streams generated by the X-IFU End-to-End simulator, we present here a comprehensive benchmark of various pulse reconstruction techniques, ranging from standard optimal filtering to more advanced algorithms based on noise covariance matrices. Beside deriving the spectral resolution achieved by the different algorithms, a first assessment of the computing power and ground calibration needs is presented. Overall, all methods show similar performances, with the reconstruction based on noise covariance matrices showing the best improvement with respect to the standard optimal filtering technique. Due to prohibitive calibration needs, this method might however not be applicable to the X-IFU and the best compromise currently appears to be the so-called resistance space analysis which also features very promising high count rate capabilities.
Keywords: Athena; microcalorimeters; performance analysis; pulse reconstruction; X-IFU; X-rays

Performances of JEM-EUSO: angular reconstruction (vol 30, pg 153, 2015) - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)

Performances of JEM-EUSO: energy and X (max) reconstruction - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The Extreme Universe Space Observatory (EUSO) on-board the Japanese Experimental Module (JEM) of the International Space Station aims at the detection of ultra high energy cosmic rays from space. The mission consists of a UV telescope which will detect the fluorescence light emitted by cosmic ray showers in the atmosphere. The mission, currently developed by a large international collaboration, is designed to be launched within this decade. In this article, we present the reconstruction of the energy of the observed events and we also address the X (max) reconstruction. After discussing the algorithms developed for the energy and X (max) reconstruction, we present several estimates of the energy resolution, as a function of the incident angle, and energy of the event. Similarly, estimates of the X (max) resolution for various conditions are presented.
Keywords: JEM-EUSO; Energy reconstruction; X-max reconstruction

PheniX: a new vision for the hard X-ray sky - Roques, Jean-Pierre; Jourdain, Elisabeth; Bassani, Loredana; Bazzano, Angela; Belmont, Renaud; Bird, A. J.; Caroli, Ezio; Chauvin, Maxime; Clark, D.; Gehrels, N.; Goerlach, U.; Harrisson, F.; et al. (Experimental Astronomy, 2012)
We are proposing a mission devoted to high energy X-ray astronomy that is based on a focusing telescope operating in the 1-200 keV energy range but optimized for the hard X-ray range. The main scientific topics concern: Physics of compact objects: The proximity of compact objects provides a unique laboratory to study matter and radiation in extreme conditions of temperature and density in strong gravitational environment. The emission of high energy photons from these objects is far from being understood. The unprecedented sensitivity in the high energy domain will allow a precise determination of the non-thermal processes at work in the vicinity of compact objects. The full 1-200 keV energy coverage will be ideal to disentangle the emission processes produced in the spacetime regions most affected by strong-gravity, as well as the physical links: disk-thermal emission-iron line-comptonisation-reflection-non-thermal emission-jets. Neutron stars-magnetic field-cyclotron lines: Time resolved spectroscopy (and polarimetry) at ultra-high sensitivity of AXP, milliseconds pulsars and magnetars will give new tools to study the role of the synchrotron processes at work in these objects. Cyclotron lines-direct measurement of magnetic filed-equation of state constraints-short bursts-giant flares could all be studied with great details. AGN: The large sensitivity improvement will provide detailed spectral properties of the high energy emission of AGN's. This will give a fresh look to the connection between accretion and jet emission and will provide a new understanding of the physical processes at work. Detection of high-redshift active nuclei in this energy range will allow to introduce an evolutionary aspect to high-energy studies of AGN, probing directly the origin of the Cosmic X-ray Background also in the non-thermal range (> 20 keV). Element formation-Supernovae: The energy resolution achievable for this mission (< 0.5 keV) and a large high energy effective area are ideally suited for the 44Ti line study (68 and 78 keV). This radioactive nuclei emission will give an estimate of their quantities and speed in their environment. In addition the study of the spatial structure and spectral emission of SNR will advance our knowledge of the dynamics of supernovae explosions, of particles acceleration mechanisms and how the elements are released in the interstellar medium. Instrumental design: The progress of X-ray focusing optics techniques allows a major step in the instrumental design: the collecting area becomes independent of the detection area. This drastically reduces the instrumental background and will open a new era. The optics will be based on depth-graded multi-layer mirrors in a Wolter I configuration. To obtain a significant effective area in the hundred of keV range a focal length in the 40-50 meters range (attainable with a deployable mast) is needed. In addition such a mission could benefit from recent progress made on mirror coating. We propose to cover the 1-200 keV energy range with a single detector, a double-sided Germanium strip detector operating at 80 K. The main features will be: (a) good energy resolution (.150 keV at 5 keV and <.5 keV at 100 keV), (b) 3 dimensional event localization with a low number of electronic chains, (c) background rejection by the 3D localization, (d) polarisation capabilities in the Compton regime.
Keywords: Hard X-rays; Germanium; Grazing incidence optics; Space instrument

Polarized Gamma-Ray Emission from the Galactic Black Hole Cygnus X-1 - Laurent, P.; Rodriguez, Jerome; Wilms, Jörn; Bel, M. Cadolle; Pottschmidt, K.; Grinberg, Victoria (Science, 2011)
Because of their inherently high flux allowing the detection of clear signals, black hole x-ray binaries are interesting candidates for polarization studies, even if no polarization signals have been observed from them before. Such measurements would provide further detailed insight into these sources' emission mechanisms. We measured the polarization of the gamma-ray emission from the black hole binary system Cygnus X-1 with the International Gamma-Ray Astrophysics Laboratory Imager on Board the Integral Satellite (INTEGRAL/IBIS) telescope. Spectral modeling of the data reveals two emission mechanisms: The 250- to 400-keV ( kilo-electron volt) data are consistent with emission dominated by Compton scattering on thermal electrons and are weakly polarized. The second spectral component seen in the 400-keV to 2-MeV band is by contrast strongly polarized, revealing that the MeV emission is probably related to the jet first detected in the radio band.

Potential origin of the state-dependent high-energy tail in the black hole microquasar Cygnus X-1 as seen with INTEGRAL - Cangemi, F.; Beuchert, T.; Siegert, T.; Rodriguez, J.; Grinberg, V.; Belmont, R.; Gouiffès, C.; Kreykenbohm, Ingo; Laurent, P.; Pottschmidt, K.; Wilms, Jörn (Astronomy & Astrophysics, 2021)
Context. 0.1-10 MeV observations of the black hole microquasar Cygnus X-1 have shown the presence of a spectral feature in the form of a power law in addition to the standard black body (0.1-10 keV) and Comptonization (10-200 keV) components observed by INTEGRAL in several black-hole X-ray binaries. This so-called "high-energy tail"was recently shown to be strong in the hard spectral state of Cygnus X-1, and, in this system, has been interpreted as the high-energy part of the emission from a compact jet. Aims. This result was nevertheless obtained from a data set largely dominated by hard state observations. In the soft state, only upper limits on the presence and hence the potential parameters of a high-energy tail could be derived. Using an extended data set, we aim to obtain better constraints on the properties of this spectral component in both states. Methods. We make use of data obtained from about 15 years of observations with the INTEGRAL satellite. The data set is separated into the different states and we analyze stacked state-resolved spectra obtained from the X-ray monitors, the gamma-ray imager, and the gamma-ray spectrometer (SPI) onboard. Results. A high-energy component is detected in both states, confirming its earlier detection in the hard state and its suspected presence in the soft state with INTEGRAL, as seen in a much smaller SPI data set. We first characterize the high-energy tail components in the two states through a model-independent, phenomenological analysis. We then apply physical models based on hybrid Comptonization (eqpair and belm). The spectra are well modeled in all cases, with a similar goodness of the fits. While in the semi-phenomenological approach the high-energy tail has similar indices in both states, the fits with the physical models seem to indicate slightly different properties. Based on this approach, we discuss the potential origins of the high-energy components in both the soft and hard states, and favor an interpretation where the high-energy component is due to a compact jet in the hard state and hybrid Comptonization in either a magnetized or nonmagnetized corona in the soft state.
CRIS-Team Scopus Importer:2021-06-25
Keywords: Accretion; accretion disks; Black hole physics; Radiation mechanisms: non-thermal; X-rays: binaries; X-rays: individuals: Cyg X-1

Probing cosmic inflation with the LiteBIRD cosmic microwave background polarization survey - Allys, E.; Arnold, K.; Aumont, J.; Aurlien, R.; Azzoni, S.; Baccigalupi, C.; Banday, A. J.; Banerji, R.; Barreiro, R. B.; Bartolo, N.; Bautista, L.; Beck, D.; et al. (Progress of Theoretical and Experimental Physics, 2023)
LiteBIRD, the Lite (Light) satellite for the study of B-mode polarization and Inflation from cosmic background Radiation Detection, is a space mission for primordial cosmology and fundamental physics. The Japan Aerospace Exploration Agency (JAXA) selected LiteBIRD in May 2019 as a strategic large-class (L-class) mission, with an expected launch in the late 2020s using JAXA’s H3 rocket. LiteBIRD is planned to orbit the Sun–Earth Lagrangian point L2, where it will map the cosmic microwave background polarization over the entire sky for three years, with three telescopes in 15 frequency bands between 34 and 448 GHz, to achieve an unprecedented total sensitivity of 2.2 μK-arcmin, with a typical angular resolution of 0.5◦ at 100 GHz. The primary scientific objective of LiteBIRD is to search for the signal from cosmic inflation, either making a discovery or ruling out well-motivated inflationary models. The measurements of LiteBIRD will also provide us with insight into the quantum nature of gravity and other new physics beyond the standard models of particle physics and cosmology. We provide an overview of the LiteBIRD project, including scientific objectives, mission and system requirements, operation concept, spacecraft and payload module design, expected scientific outcomes, potential design extensions, and synergies with other projects.
CRIS-Team Scopus Importer:2023-06-09

PROBING THE ACCRETION DISK AND CENTRAL ENGINE STRUCTURE OF NGC 4258 WITH SUZAKU AND XMM-NEWTON OBSERVATIONS - Reynolds, Christopher S.; Nowak, Michael A.; Markoff, Sera; Tueller, Jack; Wilms, Jörn; Young, Andrew J. (Astrophysical Journal, 2009)
We present an X-ray study of the low-luminosity active galactic nucleus (AGN) in NGC 4258 using data from Suzaku, XMM-Newton, and the Swift/Burst Alert Telescope survey. We find that signatures of X-ray reprocessing by cold gas are very weak in the spectrum of this Seyfert-2 galaxy; a weak, narrow fluorescent K alpha emission line of cold iron is robustly detected in both the Suzaku and XMM-Newton spectra but at a level much below that of most other Seyfert-2 galaxies. We conclude that the circumnuclear environment of this AGN is very "clean" and lacks the Compton-thick obscuring torus of unified Seyfert schemes. From the narrowness of the iron line, together with evidence of line flux variability between the Suzaku and XMM-Newton observations, we constrain the line emitting region to be between 3 x 10(3)r(g) and 4 x 10(4)r(g) from the black hole. We show that the observed properties of the iron line can be explained if the line originates from the surface layers of a warped accretion disk. In particular, we present explicit calculations of the expected iron line from a disk warped by Lens-Thirring precession from a misaligned central black hole. Finally, the Suzaku data reveal clear evidence of large amplitude 2-10 keV variability on timescales of 50 ksec and smaller amplitude flares on timescales as short as 5-10 ksec. If associated with accretion disk processes, such rapid variability requires an origin in the innermost regions of the disk (r approximate to 10r(g) or less). Analysis of the difference spectrum between a high-and low-flux states suggests that the variable component of the X-ray emission is steeper and more absorbed than the average AGN emission, suggesting that the primary X-ray source and absorbing screen have a spatial structure on comparable scales. We note the remarkable similarity between the circumnuclear environment of NGC 4258 and another well studied low-luminosity AGN, M81*.
Keywords: black hole physics; galaxies: individual (NGC 4258); galaxies: Seyfert; X-rays: galaxies

Probing the physical properties of the intergalactic medium using SRG/eROSITA spectra from blazars - Gatuzz, E.; Wilms, Jörn; Hämmerich, Steven; Arcodia, R. (Astronomy & Astrophysics, 2024)
Most baryonic matter resides in the intergalactic medium (IGM). This diffuse gas is primarily composed of ionized hydrogen and helium and fills the space between galaxies. Observations of this environment are crucial for better understanding the physical processes in it. We present an analysis of the IGM absorption using blazar spectra from the first eROSITA all-sky survey (eRASS1) performed onboard of the Spectrum-Roentgen-Gamma mission (SRG) and XMM-Newton X-ray observations. First, we fit the continuum spectra using a log-parabolic spectrum model and fixed the Galactic absorption. Then, we included a collisional ionization equilibrium model, namely IONeq, to account for the IGM absorption. The column density N(H) and metallicity (Z) were set as free parameters. At the same time, the redshift of the absorber was fixed to half the blazar redshift as an approximation of the full line-of-sight absorber. We measured IGM-N(H) for 147 sources for SRG and 10 sources for XMM-Newton. We found a clear trend between IGM-N(H) and the blazar redshifts that scales as (1 + z)1.63 ± 0.12. The mean hydrogen density at z = 0 is n0 = (2.75 ± 0.63)×10-7 cm-3. The mean temperature over the redshift range is log(T/K) = 5.6 ± 0.6, and the mean metallicity is Z = 0.16 ± 0.09. We found no acceptable fit using a power-law model for the temperatures or metallicities as a function of the redshift. These results indicate that the IGM contributes substantially to the total absorption seen in the blazar spectra.
CRIS-Team Scopus Importer:2024-03-29
Keywords: Galaxies: high-redshift; Intergalactic medium; X-rays: galaxies; X-rays: general

Quantifying the Effect of Cosmic Ray Showers on the X-IFU Energy Resolution - Peille, P.; Den Hartog, R.; Miniussi, A.; Stever, S.; Bandler, S.; Kirsch, Christian; Lorenz, Maximilian; Dauser, Thomas; Wilms, Jörn; Lotti, S.; Gatti, F.; Macculi, C.; et al. (Journal of Low Temperature Physics, 2020)
The X-ray Integral Field Unit (X-IFU) will operate an array of more than 3000 Transition Edge Sensor pixels at 90 mK with an unprecedented energy resolution of 2.5 eV at 7 keV. In space, primary cosmic rays and secondary particles produced in the instrument structure will continuously deposit energy on the detector wafer and induce fluctuations on the pixels’ thermal bath. We have investigated through simulations of the X-IFU readout chain how these fluctuations eventually influence the energy measurement of X-ray photons. Realistic timelines of thermal bath fluctuations at different positions in the array are generated as a function of a thermal model and the expected distribution of the deposited energy of the charged particles. These are then used to model the TES response to these thermal perturbations and their influence on the onboard energy reconstruction process. Overall, we show that with adequate heatsinking, the main energy resolution degradation effect remains minimal and within the associated resolution allocation of 0.2 eV. We further study how a dedicated triggering algorithm could be put in place to flag the rarer large thermal events.
CRIS-Team Scopus Importer:2020-02-14
Keywords: Cosmic rays; Energy resolution; TES; X-IFU; X-ray microcalorimeters

Radio and gamma-ray properties of extragalactic jets from the TANAMI sample - Boeck, M.; Kadler, Matthias; Müller, Cornelia; Tosti, G.; Ojha, R.; Wilms, Jörn; Bastieri, D.; Burnett, T.; Carpenter, B.; Cavazzuti, E.; Dutka, M.; Blanchard, J.; et al. (Astronomy & Astrophysics, 2016)
The TANAMI program has been observing parsec-scale radio jets of southern (declination south of - 30°) γ-ray bright AGN, simultaneously with Fermi/LAT monitoring of their γ-ray emission, via high-resolution radio imaging with Very Long Baseline Interferometry techniques. We present the radio and γ-rayproperties of the TANAMI sources based on one year of contemporaneous TANAMI and Fermi/LAT data. A large fraction (72%) of the TANAMI sample can be associated with bright γ-ray sources for this time range. Association rates differ for different optical classes with all BL Lacs, 76% of quasars, and just 17% of galaxies detected by the LAT. Upper limits were established on the γ-ray flux from TANAMI sources not detected by LAT. This analysis led to the identification of three new Fermi sources whose detection was later confirmed. The γ-ray and radio luminosities are related by L ∞ L . The brightness temperatures of the radio cores increase with the average γ-ray luminosity and the presence of brightness temperatures above the inverse Compton limit implies strong Doppler boosting in those sources. The undetected sources have lower γ/radio luminosity ratios and lower contemporaneous brightness temperatures. Unless the Fermi/LAT-undetected blazars are much γ-ray-fainter than the Fermi/LAT-detected sources, their γ-ray luminosity should not be significantly lower than the upper limits calculated here.
Keywords: Galaxies: active; Galaxies: jets; Galaxies: nuclei; Gamma rays: galaxies; Radio continuum: galaxies

Radio and X-ray observations of jet ejection in Cygnus X-2 - Spencer, R. E.; Rushton, A. P.; Balucinska-Church, M.; Paragi, Zsolt; Schulz, N. S.; Wilms, Jörn; Pooley, G. G.; Church, M. J. (Monthly Notices of the Royal Astronomical Society, 2013)
The ejection of a relativistic jet has been observed in the luminous Galactic low-mass X-ray binary Cygnus X-2. Using high-resolution radio observations, a directly resolved ejection event has been discovered while the source was on the horizontal branch of the Z-track. Contemporaneous radio and X-ray observations were made with the European VLBI Network at 6 cm and the Swift X-ray observatory in the 0.3-10 keV band. This has been difficult to achieve because of the previous inability to predict jet formation. Two sets of similar to 10 h observations were spaced 12 h apart, the jet apparently switching on during Day 1. The radio results show an unresolved core evolving into an extended jet. A preliminary value of jet velocity v/c of 0.33 +/- 0.12 was obtained, consistent with previous determinations in Galactic sources. Simultaneous radio and X-ray lightcurves are presented and the X-ray hardness ratio shows the source to be on the horizontal branch where jets are expected. The observations support our proposal that jet formation can in future be predicted based on X-ray intensity increases beyond a critical value.
Keywords: acceleration of particles; accretion: accretion discs; stars: neutron; X-rays: binaries; X-rays: individual: Cygnus X-2

Rapid and multiband variability of the TeV bright active nucleus of the galaxy IC 310 - Aleksie, J.; Antonelli, L. A.; Antoranz, Pedro; Babic, Ana; De Almeida, U. Barres; Barrio, J. A.; Becerra Gonzalez, Josefa; Bednarek, Wlodek; Berger, K.; Bernardini, E.; Biland, A.; Blanch, O.; et al. (Astronomy & Astrophysics, 2014)
Context. The radio galaxy IC 310 has recently been identified as a gamma-ray emitter based on observations at GeV energies with Fermi-LAT and at very high energies (VHE, E > 100 GeV) with the MAGIC telescopes. Originally classified as a head-tail radio galaxy, the nature of this object is subject of controversy since its nucleus shows blazar-like behavior.Aims. To understand the nature of IC310 and the origin of the VHE emission, we studied the spectral and flux variability of IC 310 from the X-ray band to the VHE gamma-ray regime.Methods. The light curve of IC310 above 300GeV has been measured with the MAGIC telescopes from 2009 October to 2010 February. Contemporaneous Fermi-LAT data (2008-2011) in the 10-500 GeV energy range were also analyzed. In the X-ray regime, archival observations from 2003 to 2007 with XMM-Newton, Chandra, and Swift-XRT in the 0.5-10 keV band were studied.Results. The VHE light curve reveals several high-amplitude and short-duration flares. Day-to-day flux variability is clearly present (>5 sigma). The photon index between 120 GeV and 8 TeV remains at the value Gamma similar to 2.0 during both low and high flux states. The VHE spectral shape does not show significant variability, whereas the flux at 1 TeV changes by a factor of similar to 7. Fermi-LAT detected only eight gamma-ray events in the energy range 10 GeV-500 GeV in three years of observation. The measured photon index of Gamma = 1.3 +/- 0.5 in the Fermi-LAT range is very hard. The X-ray measurements show strong variability in both flux and photon index. The latter varied from 1.76 +/- 0.07 to 2.55 +/- 0.07.Conclusions. The rapid variability measured in gamma-rays and X-rays confirms the blazar-like behavior of IC310. The multi-TeV gamma-ray emission seems to originate from scales of less than 80 Schwarzschild radii (for a black hole mass of 2 x 10(8) M-circle dot) within the compact core of its FR I radio jet with orientation angle 10 degrees-38 degrees. The spectral energy distribution resembles that of an extreme blazar, albeit the luminosity is more than two orders of magnitude lower.
Keywords: galaxies: active; galaxies: individual: IC 310; gamma rays: galaxies; X-rays: galaxies

Rapid variability of Markarian 421 during extreme flaring as seen through the eyes of XMM-Newton - Gokus, A.; Wilms, Jörn; Kadler, M.; Dorner, D.; Nowak, M. A.; Kreikenbohm, A.; Leiter, K.; Bretz, T.; Schleicher, B.; Markowitz, A. G.; Pottschmidt, K.; Mannheim, K.; et al. (Monthly Notices of the Royal Astronomical Society, 2024)
By studying the variability of blazars across the electromagnetic spectrum, it is possible to resolve the underlying processes responsible for rapid flux increases, so-called flares. We report on an extremely bright X-ray flare in the high-peaked BL Lacertae object Markarian 421 (Mrk 421) that occurred simultaneously with enhanced γ-ray activity detected at very high energies by First G-APD Cherenkov Telescope on 2019 June 9. We triggered an observation with XMM-Newton, which observed the source quasi-continuously for 25 h. We find that the source was in the brightest state ever observed using XMM-Newton, reaching a flux of 2.8 × 10-9 over an energy range of 0.3-10 keV. We perform a spectral and timing analysis to reveal the mechanisms of particle acceleration and to search for the shortest source-intrinsic time-scales. Mrk 421 exhibits the typical harder-when-brighter behaviour throughout the observation and shows a clock-wise hysteresis pattern, which indicates that the cooling dominates over the acceleration process. While the X-ray emission in different sub-bands is highly correlated, we can exclude large time lags as the computed z-transformed discrete correlation functions are consistent with a zero lag. We find rapid variability on time-scales of 1 ks for the 0.3-10 keV band and down to 300 s in the hard X-ray band (4-10 keV). Taking these time-scales into account, we discuss different models to explain the observed X-ray flare, and find that a plasmoid-dominated magnetic reconnection process is able to describe our observation best.
CRIS-Team Scopus Importer:2024-03-29
Keywords: acceleration of particles; BL Lacertae objects: individual: Markarian 421; galaxies: active; relativistic processes; X-rays: galaxies

Ray-tracing Arcus in Phase A - Günther, Hans Moritz; DeRoo, Casey; Heilmann, Ralf K.; Hertz, Edward N.; Smith, Randall; Wilms, Jörn (2018)
Spectroscopy of soft X-rays is an extremely powerful tool to understand the physics of hot plasmas in the universe, but in many cases, such as kinematic properties of stellar emission lines or weak absorption features, we have reached the limits of current instrumentation. Critical-angle transmission (CAT) gratings blaze the dispersed spectra into high orders and also offer high throughput.We present detailed ray-traces for the Arcus mission, which promises an effective area > 300 cm(2) in the soft X-ray band. It uses four petals of Athena-like silicon pore optics. Each petal spans an azimuth of about 30 degrees and thus offers a point-spread function that is significantly narrower in one dimension than a full mirror would provide. Each of these channels has its own optical axis. For each channel, CAT gratings are arranged on a tilted Rowland torus, and the four separate tori are positioned to overlap in such a way that the dispersed spectra from both pairs can be imaged onto a common set of CCD detectors, while at the same time keeping the requirement of the spectroscopic focus.Our ray-traces show that a set of 16 CCDs is sufficient to cover both zeroth orders and most of the dispersed signal. We study the impact of misalignment, finite size of components, and spacecraft jitter on the spectral resolution and effective area and prove that the design achieves R > 3000 even in the presence of these non-ideal effects.In 2017, we presented the ray-traces for the initial Arcus proposal. Since then, Arcus was accepted for a phase A study and we have spent a lot of additional effort to tweak the optical design (for example, we originally intended to have two petals each share an optical axis, but decided against it to avoid alignment constraints) and to link it back to practical mechanical engineering tolerances. In the process, parameters that were only roughly known in the initial proposal have been set to much better than a millimeter, and effects that seemed not important initially have now been studied in much more detail. This contribution presents those detailed studies and tells the story how we used ray-traces to make a better instrument with a more robust design.
Keywords: ray-tracing; X-ray optics; critical angle transmission grating; ARCUS; Rowland design

Redshifted Fe K alpha line from the unusual gamma-ray source PMN J1603-4904 - Mueller, C.; Krauss, F.; Dauser, Thomas; Kreikenbohm, A.; Beuchert, T.; Kadler, M.; Ojha, R.; Wilms, Jörn; Boeck, M.; Carpenter, B.; Dutka, M.; Markowitz, Alex; et al. (Astronomy & Astrophysics, 2015)
Conclusions. The detection of a redshiftecl X-ray emission line further challenges the original BL Lac classification of PMN J1603-4904. This result suggests that the source is observed at a larger angle to the line of sight than expected for blazars. and thus the source would add to the elusive class of gamma-ray loud misaligned jet objects, possibly a gamma-ray bright young radio galaxy.
Keywords: galaxies: active; galaxies: jets; galaxies: individual: PMN J1603-4904; X-rays: galaxies; gamma rays: galaxies

Reflection Spectroscopy of the Black Hole Binary XTE J1752-223 in Its Long-stable Hard State - Garcia, Javier A.; Steiner, James F.; Grinberg, Victoria; Dauser, Thomas; Connors, Riley M. T.; Mcclintock, Jeffrey E.; Remillard, Ronald A.; Wilms, Jörn; Harrison, Fiona A.; Tomsick, John A. (Astrophysical Journal, 2018)
We present a detailed spectral analysis of the black hole binary XTE J1752-223. in the hard state of its 2009 outburst. Regular monitoring of this source by the Rossi X-ray Timing Explorer mission provided high signal-to-noise spectra along the outburst rise and decay. During one full month this source stalled at similar to 30% of its peak count rate at a constant hardness and intensity. By combining all the data in this exceptionally stable hard state, we obtained an aggregate proportional counter array spectrum (3-45 keV) with 100. million counts, and a corresponding high energy X-ray timing experiment spectrum (20-140 keV) with 5.8. million counts. Implementing a version of our reflection code with a physical model for Comptonization, we obtain tight constraints on important physical parameters for this system. In particular, the inner accretion disk is measured very close in, at R-in =1.7 +/- 0.4 R-g. Assuming R-in = R-ISCO, we find a relatively high black hole spin (a* = 0.92 +/- 0.06). Imposing a lamppost geometry, we obtain a low inclination (i = 35 degrees +/- 4 degrees), which agrees with the upper limit found in the radio (i < 49 degrees). However, we note that this model cannot be statistically distinguished from a non-lamppost model with a free emissivity index, for which the inclination is markedly higher. Additionally, we find a relatively cool corona (57-70 keV) and large iron abundance (3.3-3.7 solar). We further find that properly accounting for Comptonization of the reflection emission improves the fit significantly and causes an otherwise low reflection fraction (similar to 0.2-0.3) to increase by an order of magnitude, in line with geometrical expectations for a lamppost corona. We compare these results with similar investigations reported for GX 339-4. in its bright hard state.
Keywords: accretion; accretion disks; atomic processes; black hole physics; line: formation; X-rays: individual (XTE J1752-223)

Relativistic reflection: Review and recent developments in modeling - Dauser, Thomas; Garcia, Javier; Wilms, Jörn (Astronomische Nachrichten, 2016)
Measuring relativistic reflection is an important tool to study the innermost regions of the an accreting black hole system. In the following we present a brief review on the different aspects contributing to the relativistic reflection. The combined approach is for the first time incorporated in the new "relxill" model. The advantages of this more self-consistent approach are briefly summarized. A special focus is put on the new definition of the intrinsic reflection fraction in the lamp post geometry, which allows to draw conclusions about the primary source of radiation in these system. Additionally the influence of the high energy cutoff of the primary source on the reflection spectrum is motivated, revealing the remarkable capabilities of constraining E by measuring relativistic reflection spectra from NuSTAR, preferably with lower energy coverage.
Keywords: Accretion; accretion disks; Black hole physics; Line: profiles; X-rays: galaxies

Results from DROXO: IV. EXTraS discovery of an X-ray flare from the Class i protostar candidate ISO-Oph 85 - Pizzocaro, D.; Stelzer, B.; Paladini, R.; Tiengo, A.; Lisini, G.; Novara, G.; Vianello, G.; Belfiore, A.; Marelli, M.; Salvetti, D.; Pillitteri, Ignazio; Sciortino, S.; et al. (Astronomy & Astrophysics, 2016)
X-ray emission from young stellar objects (YSOs) is a key ingredient in understanding star formation. For the early, protostellar (Class I) phase, a very limited (and controversial) quantity of X-ray results is available to date. Within the EXTraS (Exploring the X-ray Transient and variable Sky) project, we have discovered transient X-ray emission from a source whose counterpart is ISO-Oph 85, a strongly embedded YSO in the ρ Ophiuchi star-forming region. We extract an X-ray light curve for the flaring state, and determine the spectral parameters for the flare from XMM-Newton/EPIC data with a method based upon quantile analysis. We combine photometry from infrared to millimeter wavelengths from the literature with mid-IR Spitzer and unpublished submm Herschel photometry that we analysed for this work, and we describe the resulting spectral energy distribution (SED) with a set of precomputed models. The X-ray flare of ISO-Oph 85 lasted 2500 s and is consistent with a highly-absorbed one-component thermal model (N = 1.0 × 10 cm NH=1.0-0.5+1.2×1023cm-2 and kT= 1.15 keVkT=1.15-0.65+2.35 keV). The X-ray luminosity during the flare is log L [erg/s] = 31.1logLX [erg/s]=31.1-1.2+2.0; during quiescence we set an upper limit of log L [erg/s] < 29.5. We do not detect other flares from this source. The submillimeter fluxes suggest that the object is a Class I protostar. We caution, however, that the offset between the Herschel and optical/infrared position is larger than that for other YSOs in the region, leaving some doubt on this association. To the best of our knowledge, this is the first X-ray flare from a YSO that has been recognised as a candidate Class I protostar via the analysis of its complete SED, including the submm bands that are crucial for detecting the protostellar envelope. This work shows how the analysis of the whole SED is fundamental to the classification of YSOs, and how the X-ray source detection techniques we have developed can open a new era in time-resolved analysis of the X-ray emission from stars.
Keywords: Stars: activity; Stars: coronae; Stars: flare; Stars: protostars; X-rays: stars

Results from the search for dark matter in the Milky Way with 9 years of data of the ANTARES neutrino telescope - Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics Letters B, 2017)
Using data recorded with the ANTARES telescope from 2007 to 2015, a new search for dark matter annihilation in the Milky Way has been performed. Three halo models and five annihilation channels, WIMP + WIMP -> b (b) over bar, W+W-, tau(+)tau(-), mu(+)mu(-) and v (v) over bar, with WIMP masses ranging from 50 2 GeV/C-2 to 100 Tev/C-2, were considered. No excess over the expected background was found, and limits on the thermally averaged annihilation cross-section were set. (C) 2017 The Authors. Published by Elsevier B.V. This is an open access article under the CC BY license.
Keywords: Dark matter; WIMP; Indirect detection; Neutrino telescope; Galactic Centre; ANTARES

Revealing the broad iron Kα line in Cygnus X-1 through simultaneous XMM-Newton, RXTE, and INTEGRAL observations - Duro, Refiz; Dauser, Thomas; Grinberg, Victoria; Miskovicova, Ivica; Rodriguez, Jerome; Tomsick, John; Hanke, Manfred; Pottschmidt, Katja; Nowak, Michael A.; Kreykenbohm, Sonja Sophie; Bel, Marion Cadolle; Bodaghee, Arash; et al. (Astronomy & Astrophysics, 2016)
We report on the analysis of the broad Fe Kα line feature of Cyg X-1 in the spectra of four simultaneous hard intermediate state observations made with the X-ray Multiple Mirror mission (XMM-Newton), the Rossi X-ray Timing Explorer (RXTE), and the International Gamma-Ray Astrophysics Laboratory (INTEGRAL). The high quality of the XMM-Newton data taken in the Modified Timing Mode of the EPIC-pn camera provides a great opportunity to investigate the broadened Fe Kα reflection line at 6.4 keV with a very high signal to noise ratio. The 4-500 keV energy range is used to constrain the underlying continuum and the reflection at higher energies. We first investigate the data by applying a phenomenological model that consists of the sum of an exponentially cutoff power law and relativistically smeared reflection. Additionally, we apply a more physical approach and model the irradiation of the accretion disk directly from the lamp post geometry. All four observations show consistent values for the black hole parameters with a spin of a 0.9, in agreement with recent measurements from reflection and disk continuum fitting. The inclination is found to be i 30°, consistent with the orbital inclination and different from inclination measurements made during the soft state, which show a higher inclination. We speculate that the difference between the inclination measurements is due to changes in the inner region of the accretion disk.
Keywords: black hole physics; gravitation; X-rays: binaries

RXTE observations of the 1A 1118-61 in an outburst, and the discovery of a cyclotron line - Doroshenko, Victor; Suchy, S.; Santangelo, A.; Staubert, R.; Kreykenbohm, Ingo; Rothschild, R.; Pottschmidt, K.; Wilms, Jörn (Astronomy & Astrophysics, 2010)
We present the analysis of RXTE monitoring data obtained during the 2009 January outburst of the hard X-ray transient 1A 1118-61. Using these observations the broadband (3.5-120 keV) spectrum of the source was measured for the first time ever. We have found that the broadband continuum spectrum of the source is similar to other accreting pulsars and is well described by several conventionally used phenomenological models. We have discovered that regardless of the applied continuum model, a prominent broad absorption feature at similar to 55 keV is observed. We interpret this feature as a cyclotron resonance scattering feature (CRSF). The observed CRSF energy is one of the highest known and corresponds to a magnetic field of B similar to 4.8 x 10(12) G in the scattering region. Our data also indicate the presence of an iron emission line presence that has not been previously reported for 1A 1118-61. Timing properties of the source, including a strong spin-up, were found to be similar to those observed by CGRO/BATSE during the previous outburst, but the broadband capabilities of RXTE reveal a more complicated energy dependency of the pulse-profile.
Keywords: stars: neutron; pulsars: individual: 1A 1118-61; binaries: general

Science of atmospheric phenomena with JEM-EUSO - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, Anna; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The main goal of the JEM-EUSO experiment is the study of Ultra High Energy Cosmic Rays (UHECR, 10(19)-10(21) e V), but the method which will be used (detection of the secondary light emissions induced by cosmic rays in the atmosphere) allows to study other luminous phenomena. The UHECRs will be detected through the measurement of the emission in the range between 290 and 430 m, where some part of Transient Luminous Events (TLEs) emission also appears. This work discusses the possibility of using the JEM-EUSO Telescope to get new scientific results on TLEs. The high time resolution of this instrument allows to observe the evolution of TLEs with great precision just at the moment of their origin. The paper consists of four parts: review of the present knowledge on the TLE, presentation of the results of the simulations of the TLE images in the JEM-EUSO telescope, results of the Russian experiment Tatiana-2 and discussion of the possible progress achievable in this field with JEM-EUSO as well as possible cooperation with other space projects devoted to the study of TLE - TARANIS and ASIM. In atmospheric physics, the study of TLEs became one of the main physical subjects of interest after their discovery in 1989. In the years 1992 - 1994 detection was performed from satellite, aircraft and space shuttle and recently from the International Space Station. These events have short duration (milliseconds) and small scales (km to tens of km) and appear at altitudes 50 - 100 km. Their nature is still not clear and each new experimental data can be useful for a better understanding of these mysterious phenomena.
Keywords: Transient Luminous Events; Elves; Sprites; Jets - Atmospheric phenomena

Science with the EXTraS Project: Exploring the X-Ray Transient and Variable Sky - De Luca, A.; Salvaterra, R.; Tiengo, A.; D'Agostino, D.; Watson, M. G.; Haberl, F.; Wilms, Jörn (The Universe of Digital Sky Surveys, 2016)
Keywords: Physics

Science with the XEUS High Time Resolution Spectrometer - Barret, D.; Belloni, T.; Bhattacharyya, S.; Gilfanov, Marat; Gogus, E.; Homan, J.; Mendez, M.; Miller, J. M.; Miller, M. C.; Mereghetti, Sandro; Paltani, S.; Poutanen, Juri; et al. (2008)
XEUS has been recently selected by ESA for an assessment study. XEUS is a large mission candidate for the Cosmic Vision program, aiming for a launch date as early as 2018. XEUS is a follow-on to ESA's Cornerstone X-Ray Spectroscopy Mission (XMM-Newton). It will be placed in a halo orbit at L2, by a single Ariane 5 ECA, and comprises two spacecrafts. The Silicon pore optics assembly of XEUS is contained in the mirror spacecraft while the focal plane instruments are contained in the detector spacecraft, which is maintained at the focus of the mirror by formation flying. The main requirements for XEUS are to provide a focused beam of X-rays with ail effective aperture of 5 m(2) at 1 keV, 2 m(2) at 7 keV, a spatial resolution better than 5 aresec, a spectral resolution ranging from 2 to 6 eV in the 0.1-8 keV energy band, a total energy bandpass of 0.1-40 keV, ultra-fast timing, and finally polarimetric capabilities. The High Time Resolution Spectrometer (HTRS) is one of the five focal plane instruments, which comprises also a wide field imager, a, hard X-ray imager, a cryogenic spectrometer, and a polarmeter. The HTRS is unique in its ability to cope with extremely high count rates (up to 2 Mcts/s), while providing sub-millisecond time resolution and good (CCD like) energy resolution. In this paper, we focus on the specific scientific objectives to be pursued with the HTRS: they are all centered around the key theme "Matter under extreme conditions" of the Cosmic Vision science program. We demonstrate the potential of the HTRS observations to probe strong gravity and matter at supra-nuclear densities. We conclude this paper by describing the current implementation of the HTRS in the XEUS focal plane.
Keywords: strong gravity; dense matter; X-ray instrumentation; black holes; neutron stars; accretion

Searches for clustering in the time integrated skymap of the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2014)
This paper reports a search for spatial clustering of the arrival directions of high energy muon neutrinos detected by the ANTARES neutrino telescope. An improved two-point correlation method is used to study the autocorrelation of 3058 neutrino candidate events as well as cross-correlations with other classes of astrophysical objects: sources of high energy gamma rays, massive black holes and nearby galaxies. No significant deviations from the isotropic distribution of arrival directions expected from atmospheric backgrounds are observed.
Keywords: neutrino astronomy; neutrino detectors

SEARCHES FOR POINT-LIKE AND EXTENDED NEUTRINO SOURCES CLOSE TO THE GALACTIC CENTER USING THE ANTARES NEUTRINO TELESCOPE - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J-J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Astrophysical Journal Letters, 2014)
A search for cosmic neutrino sources using six years of data collected by the ANTARES neutrino telescope has been performed. Clusters of muon neutrinos over the expected atmospheric background have been looked for. No clear signal has been found. The most signal-like accumulation of events is located at equatorial coordinates R.A. = -46 degrees.8 and decl. = -64 degrees.9 and corresponds to a 2.2 sigma background fluctuation. In addition, upper limits on the flux normalization of an E-2 muon neutrino energy spectrum have been set for 50 pre-selected astrophysical objects. Finally, motivated by an accumulation of seven events relatively close to the Galactic Center in the recently reported neutrino sample of the IceCube telescope, a search for point sources in a broad region around this accumulation has been carried out. No indication of a neutrino signal has been found in the ANTARES data and upper limits on the flux normalization of an E-2 energy spectrum of neutrinos from point sources in that region have been set. The 90% confidence level upper limits on the muon neutrino flux normalization vary between 3.5 and 5.1 x 10(-8) GeV cm(-2) s(-1), depending on the exact location of the source.
Keywords: astroparticle physics; Galaxy: center; neutrinos

SEARCH FOR A CORRELATION BETWEEN ANTARES NEUTRINOS AND PIERRE AUGER OBSERVATORY UHECRs ARRIVAL DIRECTIONS - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Astrophysical Journal, 2013)
A multimessenger analysis optimized for a correlation of arrival directions of ultra-high energy cosmic rays (UHECRs) and neutrinos is presented and applied to 2190 neutrino candidate events detected in 2007-2008 by the ANTARES telescope and 69 UHECRs observed by the Pierre Auger Observatory between 2004 January 1 and 2009 December 31. No significant correlation is observed. Assuming an equal neutrino flux (E-2 energy spectrum) from all UHECR directions, a 90% CL upper limit on the neutrino flux of 5.0 x 10(-8) GeV cm(-2) s(-1) per source is derived.
Keywords: astroparticle physics; cosmic rays; neutrinos

SEARCH FOR COSMIC NEUTRINO POINT SOURCES WITH FOUR YEARS OF DATA FROM THE ANTARES TELESCOPE - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J; Baret, B.; Basa, S.; et al. (Astrophysical Journal, 2012)
In this paper, a time-integrated search for point sources of cosmic neutrinos is presented using the data collected from 2007 to 2010 by the ANTARES neutrino telescope. No statistically significant signal has been found and upper limits on the neutrino flux have been obtained. Assuming an E-nu(-2). spectrum, these flux limits are at 1-10x10(-8) GeV cm(-2) s(-1) for declinations ranging from -90 degrees to 40 degrees. Limits for specific models of RX J1713.7-3946 and Vela X, which include information on the source morphology and spectrum, are also given.
Keywords: astroparticle physics; cosmic rays; neutrinos

Search for dark matter annihilation in the earth using the ANTARES neutrino telescope - Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physics of the Dark Universe, 2017)
A search for a neutrino signal from WIMP pair annihilations in the centre of the Earth has been performed with the data collected with the ANTARES neutrino telescope from 2007 to 2012. The event selection criteria have been developed and tuned to maximise the sensitivity of the experiment to such a neutrino signal. No significant excess of neutrinos over the expected background has been observed. Upper limits at 90% C.L. on the WIMP annihilation rate in the Earth and the spin independent scattering cross-section of WIMPs to nucleons sigma(SI)(p) were calculated for WIMP pair annihilations into either iota(+) iota(-), W+W-, b (b) over bar or the non-SUSY v mu(v) over bar as a function of the WIMP mass (between 25 GeV/c(2) and 1000 GeV/c(2)) and as a function of the thermally averaged annihilation cross section times velocity (Earth) of the WIMPs in the centre of the Earth. For masses of the WIMP close to the mass of iron nuclei (50 GeV/c(2)), the obtained limits on sigma(SI)(p) are more stringent than those obtained by other indirect searches. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Dark matter; Neutrino telescope; ANTARES; Indirect detection; WIMP

Search for dark matter towards the Galactic Centre with 11 years of ANTARES data - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (Physics Letters B, 2020)
Neutrino detectors participate in the indirect search for the fundamental constituents of dark matter (DM) in form of weakly interacting massive particles (WIMPs). In WIMP scenarios, candidate DM particles can pair-annihilate into Standard Model products, yielding considerable fluxes of high-energy neutrinos. A detector like ANTARES, located in the Northern Hemisphere, is able to perform a complementary search looking towards the Galactic Centre, where a high density of dark matter is thought to accumulate. Both this directional information and the spectral features of annihilating DM pairs are entered into an unbinned likelihood method to scan the data set in search for DM-like signals in ANTARES data. Results obtained upon unblinding 3170 days of data reconstructed with updated methods are presented, which provides a larger, and more accurate, data set than a previously published result using 2101 days. A non-observation of dark matter is converted into limits on the velocity-averaged cross section for WIMP pair annihilation.
CRIS-Team Scopus Importer:2020-05-12
Keywords: ANTARES; Dark matter indirect detection; Galactic Centre; Neutrino telescope

Search for High-energy Neutrinos from Binary Neutron Star Merger GW170817 with ANTARES, IceCube, and the Pierre Auger Observatory - Albert, A.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin, V.; et al. (Astrophysical Journal Letters, 2017)
The Advanced LIGO and Advanced Virgo observatories recently discovered gravitational waves from a binary neutron star inspiral. A short gamma-ray burst (GRB) that followed the merger of this binary was also recorded by the Fermi Gamma-ray Burst Monitor (Fermi-GBM), and the Anti-Coincidence Shield for the Spectrometer for the International Gamma-Ray Astrophysics Laboratory (INTEGRAL), indicating particle acceleration by the source. The precise location of the event was determined by optical detections of emission following the merger. We searched for high-energy neutrinos from the merger in the GeV-EeV energy range using the ANTARES, IceCube, and Pierre Auger Observatories. No neutrinos directionally coincident with the source were detected within +/- 500 s around the merger time. Additionally, no MeV neutrino burst signal was detected coincident with the merger. We further carried out an extended search in the direction of the source for high-energy neutrinos within the 14 day period following the merger, but found no evidence of emission. We used these results to probe dissipation mechanisms in relativistic outflows driven by the binary neutron star merger. The non-detection is consistent with model predictions of short GRBs observed at a large off-axis angle.
Keywords: gamma-ray burst: general; gravitational waves; neutrinos

Search for high-energy neutrinos from bright GRBs with ANTARES - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
Gamma-ray bursts are thought to be sites of hadronic acceleration, thus neutrinos are expected from the decay of charged particles, produced in p gamma interactions. The methods and results of a search for muon neutrinos in the data of the ANTARES neutrino telescope from four bright GRBs (GRB 080916C, GRB 110918A, GRB 130427A and GRB 130505A) observed between 2008 and 2013 are presented. Two scenarios of the fireball model have been investigated: the internal shock scenario, leading to the production of neutrinos with energies mainly above 100 TeV, and the photospheric scenario, characterized by a low-energy component in neutrino spectra due to the assumption of neutrino production closer to the central engine. Since no neutrino events have been detected in temporal and spatial coincidence with these bursts, upper limits at 90 per cent confidence level on the expected neutrino fluxes are derived. The non-detection allows for directly constraining the bulk Lorentz factor of the jet Gamma and the baryon loading f(p).
Keywords: acceleration of particles; neutrinos; gamma-ray burst: individual: GRB 080916C; gamma-ray burst: individual: GRB 110918A; gamma-ray burst: individual: GRB 130427A; gamma-ray burst: individual: GRB 130505A

Search for high-energy neutrinos from gravitational wave event GW151226 and candidate LVT151012 with ANTARES and IceCube - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2017)
The Advanced LIGO observatories detected gravitational waves from two binary black hole mergers during their first observation run (O1). We present a high-energy neutrino follow-up search for the second gravitational wave event, GW151226, as well as for gravitational wave candidate LVT151012. We find two and four neutrino candidates detected by IceCube, and one and zero detected by ANTARES, within +/- 500 s around the respective gravitational wave signals, consistent with the expected background rate. None of these neutrino candidates are found to be directionally coincident with GW151226 or LVT151012. We use nondetection to constrain isotropic-equivalent high-energy neutrino emission from GW151226, adopting the GW event's 3D localization, to less than 2 x 10(51)-2 x 10(54) erg.

Search for high-redshift blazars with Fermi/LAT - Kreter, Michael; Gokus, Andrea; Kadler, Matthias; Krauß, Felicia; Buson, Sara; Ojha, Roopesh; Wilms, Jörn; Böttcher, Markus (Proceedings of Science, 2019)
High-redshift blazars (z ≥ 2.5) are the most powerful class of persistent γ-ray sources in the Universe. These objects possess the highest jet powers and luminosities and have black hole masses often in excess of 109 solar masses. In addition, high-z blazars are important cosmological probes and serve as test objects for blazar evolution models. Due to their large distance and the resulting electron/positron cascading on the extragalactic background light, their high-energy emission typically peaks below the GeV range. This makes these blazars difficult to study with Fermi/LAT and only the very brightest objects are detectable. Hence, only a small number of high-z blazars could be detected with Fermi/LAT so far. In this work, we present a strategy to increase the detection statistics at redshift z ≥ 2.5 via a search for flaring events in high-z γ-ray blazars whose long-term averaged flux is just below the sensitivity limit of Fermi/LAT. Seven previously GeV undetected high-z blazars have been identified with a test statistic of TS ≥ 25 from their bright monthly outburst periods, while more detections are expected in the future.
CRIS-Team Scopus Importer:2021-04-19

Search for High-redshift Blazars with Fermi/LAT - Kreter, M.; Gokus, A.; Krauss, F.; Kadler, M.; Ojha, R.; Buson, S.; Wilms, Jörn; Bottcher, M. (Astrophysical Journal, 2020)
High-z blazars (z 2.5) are the most powerful class of persistent γ-ray sources in the universe. These objects possess the highest jet powers and luminosities and have black hole masses often in excess of 109 solar masses. In addition, high-z blazars are important cosmological probes and serve as test objects for blazar evolution models. Due to their large distance, their high-energy emission typically peaks below the GeV range, which makes them difficult to study with Fermi/Large Area Telescope (LAT). Therefore, only the very brightest objects are detectable and, to date, only a small number of high-z blazars have been detected with Fermi/LAT. In this work, we studied the monthly binned long-term γ-ray emission of a sample of 176 radio and optically detected blazars that have not been reported as known γ-ray sources in the 3FGL catalog. To account for false-positive detections, we calculated monthly Fermi/LAT light curves for a large sample of blank sky positions and derived the number of random fluctuations that we expect at various test statistic (TS) levels. For a given blazar, a detection of TS > 9 in at least one month is expected ∼15% of the time. Although this rate is too high to secure detection of an individual source, half of our sample shows such single-month γ-ray activity, indicating a population of high-energy blazars at distances of up to z = 5.2. Multiple TS > 9 monthly detections are unlikely to happen by chance, and we have detected several individual new sources in this way, including the most distant γ-ray blazar, BZQ J1430+4204 (z = 4.72). Finally, two new γ-ray blazars at redshifts of z = 3.63 and z = 3.11 are unambiguously detected via very significant (TS > 25) flares in individual monthly time bins.
CRIS-Team Scopus Importer:2020-11-27
Keywords: Blazars (164); Gamma-ray astronomy (628); High-redshift galaxies (734)

Search for Multimessenger Sources of Gravitational Waves and High-energy Neutrinos with Advanced LIGO during Its First Observing Run, ANTARES, and IceCube - Albert, A.; Andre, M.; Anghinolfi, M.; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; Bertin,; et al. (Astrophysical Journal, 2019)
Astrophysical sources of gravitational waves, such as binary neutron star and black hole mergers or core-collapse supernovae, can drive relativistic outflows, giving rise to non-thermal high-energy emission. High-energy neutrinos are signatures of such outflows. The detection of gravitational waves and high-energy neutrinos from common sources could help establish the connection between the dynamics of the progenitor and the properties of the outflow. We searched for associated emission of gravitational waves and high-energy neutrinos from astrophysical transients with minimal assumptions using data from Advanced LIGO from its first observing run O1, and data from the ANTARES and IceCube neutrino observatories from the same time period. We focused on candidate events whose astrophysical origins could not be determined from a single messenger. We found no significant coincident candidate, which we used to constrain the rate density of astrophysical sources dependent on their gravitational-wave and neutrino emission processes.
Keywords: gravitational waves; neutrinos

Search for muon-neutrino emission from GeV and TeV gamma-ray flaring blazars using five years of data of the ANTARES telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2015)
The ANTARES telescope is well-suited for detecting astrophysical transient neutrino sources as it can observe a full hemisphere of the sky at all times with a high duty cycle. The background due to atmospheric particles can be drastically reduced, and the point-source sensitivity improved, by selecting a narrow time window around possible neutrino production periods. Blazars, being radio-loud active galactic nuclei with their jets pointing almost directly towards the observer, are particularly attractive potential neutrino point sources, since they are among the most likely sources of the very high-energy cosmic rays. Neutrinos and gamma rays may be produced in hadronic interactions with the surrounding medium. Moreover, blazars generally show high time variability in their light curves at different wavelengths and on various time scales. This paper presents a time-dependent analysis applied to a selection of flaring gamma-ray blazars observed by the FERMI/LAT experiment and by TeV Cherenkov telescopes using five years of ANTARES data taken from 2008 to 2012. The results are compatible with fluctuations of the background. Upper limits on the neutrino fluence have been produced and compared to the measured gamma-ray spectral energy distribution.
Keywords: X-ray binaries; neutrino astronomy

Search for muon neutrinos from gamma-ray bursts with the ANTARES neutrino telescope using 2008 to 2011 data - Adrian-Martinez, S.; Albert, A.; Al Samarai, I.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; et al. (Astronomy & Astrophysics, 2013)
Aims. We search for muon neutrinos in coincidence with GRBs with the ANTARES neutrino detector using data from the end of 2007 to 2011.Methods. Expected neutrino fluxes were calculated for each burst individually. The most recent numerical calculations of the spectra using the NeuCosmA code were employed, which include Monte Carlo simulations of the full underlying photohadronic interaction processes. The discovery probability for a selection of 296 GRBs in the given period was optimised using an extended maximum-likelihood strategy.Results. No significant excess over background is found in the data, and 90% confidence level upper limits are placed on the total expected flux according to the model.
Keywords: neutrinos; gamma-ray burst: general; methods: numerical

Search for neutrino counterparts of gravitational-wave events detected by LIGO and Virgo during run O2 with the ANTARES telescope - Albert, A.; André, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. J.; Aublin, J.; Baret, B.; Basa, S.; Belhorma, B.; Bertin, V.; Biagi, S.; et al. (European Physical Journal C: Particles and Fields, 2020)
An offline search for a neutrino counterpart to gravitational-wave (GW) events detected during the second observation run (O2) of Advanced-LIGO and Advanced-Virgo performed with ANTARES data is presented. In addition to the search for long tracks induced by νμ (ν¯ μ) charged current interactions, a search for showering events induced by interactions of neutrinos of any flavour is conducted. The severe spatial and time coincidence provided by the gravitational-wave alert allows regions above the detector horizon to be probed, extending the ANTARES sensitivity over the entire sky. The results of this all-neutrino-flavour and all-sky time dependent analysis are presented. The search for prompt neutrino emission within ±500 s around the time of six GW events yields no neutrino counterparts. Upper limits on the neutrino spectral fluence and constraints on the isotropic energy radiated via high-energy neutrinos (from a few TeV to a few tens of PeV) are set for each GW event analysed.
CRIS-Team Scopus Importer:2020-06-16

Search for neutrino emission from gamma-ray flaring blazars with the ANTARES telescope - Adrian-Martinez, S.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Astraatmadja, T.; Aubert, J-J.; Baret, B.; Basa, S.; et al. (Astroparticle Physics, 2012)
The ANTARES telescope is well-suited to detect neutrinos produced in astrophysical transient sources as it can observe a full hemisphere of the sky at all times with a high duty cycle. Radio-loud active galactic nuclei with jets pointing almost directly towards the observer, the so-called blazars, are particularly attractive potential neutrino point sources. The all-sky monitor LAT on board the Fermi satellite probes the variability of any given gamma-ray bright blazar in the sky on time scales of hours to months. Assuming hadronic models, a strong correlation between the gamma-ray and the neutrino fluxes is expected. Selecting a narrow time window on the assumed neutrino production period can significantly reduce the background.An unbinned method based on the minimization of a likelihood ratio was applied to a subsample of data collected in 2008 (61 days live time). By searching for neutrinos during the high state periods of the AGN light curve, the sensitivity to these sources was improved by about a factor of two with respect to a standard time-integrated point source search. First results on the search for neutrinos associated with ten bright and variable Fermi sources are presented. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino astronomy; Fermi LAT transient sources; Time-dependent search; Blazars

Search for relativistic magnetic monopoles with five years of the ANTARES detector data - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; et al. (Journal of High Energy Physics, 2017)
A search for magnetic monopoles using five years of data recorded with the ANTARES neutrino telescope from January 2008 to December 2012 with a total live time of 1121 days is presented. The analysis is carried out in the range beta > 0.6 of magnetic monopole velocities using a strategy based on run-by-run Monte Carlo simulations. No signal above the background expectation from atmospheric muons and atmospheric neutrinos is observed, and upper limits are set on the magnetic monopole flux ranging from 5.7 x 10(-16) to 1.5 x 10(-18) cm(-2).s(-1).sr(-1).
Keywords: Exotics; Neutrino Detectors and Telescopes (experiments)

Search for relativistic magnetic monopoles with the ANTARES neutrino telescope - Adrian-Martinez, S.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J-J.; et al. (Astroparticle Physics, 2012)
Magnetic monopoles are predicted in various unified gauge models and could be produced at intermediate mass scales. Their detection in a neutrino telescope is facilitated by the large amount of light emitted compared to that from muons. This paper reports on a search for upgoing relativistic magnetic monopoles with the ANTARES neutrino telescope using a data set of 116 days of live time taken from December 2007 to December 2008. The one observed event is consistent with the expected atmospheric neutrino and muon background, leading to a 90% C.L. upper limit on the monopole flux between 1.3 x 10-(17) and 8.9 x 10(-17) CM-2 s(-1) sr(-1) for monopoles with velocity beta >= 0.625. (c) 2012 Elsevier B.V. All rights reserved.
Keywords: Magnetic monopole; Neutrino telescopes; ANTARES

Search of dark matter annihilation in the galactic centre using the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Journal of Cosmology and Astroparticle Physics, 2015)
A search for high-energy neutrinos coming from the direction of the Galactic Centre is performed using the data recorded by the ANTARES neutrino telescope from 2007 to 2012. The event selection criteria are chosen to maximise the sensitivity to possible signals produced by the self-annihilation of weakly interacting massive particles accumulated around the centre of the Milky Way with respect to the atmospheric background. After data unblinding, the number of neutrinos observed in the line of sight of the Galactic Centre is found to be compatible with background expectations. The 90% C.L. upper limits in terms of the neutrino+anti-neutrino flux, Phi(nu mu + (nu) over bar mu), and the velocity averaged annihilation cross-section, , are derived for the WIMP self-annihilation channels into b (b) over bar; W+W-; tau(+)tau(-); mu(+)mu(-); nu(nu) over bar. The ANTARES limits for are shown to be the most stringent for a neutrino telescope over the WIMP masses 25 GeV < M-WIMP < 10TeV.
Keywords: neutrino experiments; dark matter experiments; neutrino astronomy

Sensitivity of the KM3NeT/ARCA neutrino telescope to point-like neutrino sources - Aiello, S.; Akrame, S. E.; Ameli, F.; G. Anassontzis, E.; Andre, M.; Androulakis, G.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aublin, J.; Avgitas, T.; Bagatelas, C.; et al. (Astroparticle Physics, 2019)
KM3NeT will be a network of deep-sea neutrino telescopes in the Mediterranean Sea. The KM3NeT/ARCA detector, to be installed at the Capo Passero site (Italy), is optimised for the detection of high-energy neutrinos of cosmic origin. Thanks to its geographical location on the Northern hemisphere, KM3NeT/ARCA can observe upgoing neutrinos from most of the Galactic Plane, including the Galactic Centre. Given its effective area and excellent pointing resolution, KM3NeT/ARCA will measure or significantly constrain the neutrino flux from potential astrophysical neutrino sources. At the same time, it will test flux predictions based on gamma-ray measurements and the assumption that the gamma-ray flux is of hadronic origin. Assuming this scenario, discovery potentials and sensitivities for a selected list of Galactic sources and to generic point sources with an E −2 spectrum are presented. These spectra are assumed to be time independent. The results indicate that an observation with 3σ significance is possible in about six years of operation for the most intense sources, such as Supernovae Remnants RX J1713.7-3946 and Vela Jr. If no signal will be found during this time, the fraction of the gamma-ray flux coming from hadronic processes can be constrained to be below 50% for these two objects.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Astrophysical neutrino sources; Cherenkov underwater neutrino telescope; KM3NeT

Short-period X-ray oscillations in super-soft novae and persistent super-soft sources - Ness, J-U; Beardmore, A. P.; Osborne, J. P.; Kuulkers, E.; Henze, M.; Piro, A. L.; Drake, J. J.; Dobrotka, A.; Schwarz, G.; Starrfield, S.; Kretschmar, P.; Hirsch, Maria; et al. (Astronomy & Astrophysics, 2015)
Conclusions. Since fast rotation periods of the white dwarfs as origin of these transient oscillations are speculative, we concentrate on pulsation mechanisms. We present initial considerations predicting the oscillation period to scale linearly with the white dwarf radius (and thus mass), weakly with the pressure at the base, and luminosity. Estimates of the size of the white dwarf could be useful for determining whether these systems are more massive than typical white dwarfs, and thus whether they are growing from accretion over time. Signs of such mass growth may have implications for whether some of these systems are attractive as Type Ia supernova progenitors.
Keywords: novae; cataclysmic variables; stars: oscillations; white dwarfs; X-rays: stars

Short term and multi-band variability of the active nucleus of IC 310 - Eisenacher, Dorit; Colin, Pierre; Lombardi, Saverio; Sitarek, Julian; Zandanel, Fabio; Paneque, David; Dauser, Thomas; Krauß, Felicia; Wilbert, Sven; Kadler, Matthias; Schulz, Robert; Wilms, Jörn; et al. (2012)
The MAGIC Telescopes detected the active galaxy IC 310 at very high energies (VHE, > 100 GeV) during observations of the Perseus cluster in 2009 and 2010. This source had originally been classified as a head-tail radio galaxy. By contrast, recent high-resolution radio images obtained with the VLBA reveal the blazar-like structure of IC 310 on parsec scales. This object is also investigated in terms of its variability at X-ray and gamma-ray energies. Studies of the multi-band flux variability at different time periods are presented. The spectral evolution seems to be different in the VHE gamma-ray and X-ray bands.
Keywords: Active Galactic Nuclei: individual (IC 310); gamma-rays: observations; gamma-ray telescopes; Radio galaxies

Simulating X-ray observations of galaxy clusters with the X-ray Integral Field Unit onboard the Athena mission - Cucchetti, Edoardo; Pointecouteau, Etienne; Peille, Philippe; Clerc, Nicolas; Rasia, Elena; Biffi, Veronica; Borgani, Stefano; Dolag, Klaus; Wilms, Jörn; Pajot, Francois; Barret, Didier (2018)
The X-ray Integral Field Unit (X-IFU) is the cryogenic imaging spectrometer onboard the ESA L2 mission Athena. With its array of almost 3840 superconducting Transition Edge Sensors micro-calorimeters, the X-IFU will provide spatially resolved (5" over the field of view) high-resolution spectroscopy (2.5 eV FWHM up to 7 keV) in the 0.2-12 keV energy band. These transformational capabilities will allow the X-IFU to probe the Hot and Energetic Universe, and notably measure the physical properties of large-scale structures with unprecedented accuracy. Starting from numerically-simulated massive (1014 Mo) galaxy clusters at different steps of their evolution, we investigate the capabilities of the X-IFU in recovering chemical abundances, redshift and gas temperature spatial distributions across time, making use of full field-of-view End-To-End simulations of X-IFU observations. This work serve as feasibility study for the Chemical Enrichment of the Universe science objective. We show that using 100 ks observations, the X-IFU will provide an unprecedented spatially-accurate knowledge of the physics of the ICM (abundances, temperature, bulk-motion). We also demonstrate that challenges related to the data analysis of extended sources with very high-resolution spectrometers (e.g. binning, line of sight mixing, particle background) need to be thoroughly addressed to maximise the science of the instrument.
Keywords: Athena; X-IFU; End-To-End simulations; galaxy clusters; chemical enrichment

Simulation of cyclotron resonant scattering features The effect of bulk velocity - Schwarm, Fritz-Walter; Schoenherr, G.; Kühnel, Matthias; Wilms, Jörn (2014)
X-ray binary systems consisting of a mass donating optical star and a highly magnetized neutron star, under the right circumstances, show quantum mechanical absorption features in the observed spectra called cyclotron resonant scattering features (CRSFs). We have developed a simulation to model CRSFs using Monte Carlo methods. We calculate Green's tables which can be used to imprint CRSFs to arbitrary X-ray continua. Our simulation keeps track of scattering parameters of individual photons, extends the number of variable parameters of previous works, and allows for more flexible geometries. Here we focus on the influence of bulk velocity of the accreted matter on the CRSF line shapes and positions.

Single-dish and VLBI observations of Cygnus X-3 during the 2016 giant flare episode - Egron, Elise; Pellizzoni, A.; Giroletti, M.; Righini, Simona; Stagni, M.; Orlati, Andrea; Migoni, C.; Melis, A.; Concu, R.; Barbas, L.; Buttaccio, S.; Cassaro, Pietro; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
In 2016 September, the microquasar Cygnus X-3 underwent a giant radio flare, which was monitored for 6 d with the Medicina Radio Astronomical Station and the Sardinia Radio Telescope. Long observations were performed in order to follow the evolution of the flare on an hourly scale, covering six frequency ranges from 1.5 to 25.6 GHz. The radio emission reached a maximum of 13.2 +/- 0.7 Jy at 7.2 GHz and 10 +/- 1 Jy at 18.6 GHz. Rapid flux variations were observed at high radio frequencies at the peak of the flare, together with rapid evolution of the spectral index: a steepened from 0.3 to 0.6 (with S-nu alpha nu(-alpha)) within 5 h. This is the first time that such fast variations are observed, giving support to the evolution from optically thick to optically thin plasmons in expansion moving outward from the core. Based on the Italian network (Noto, Medicina and SRT) and extended to the European antennas (Torun, Yebes, Onsala), very long baseline interferometry (VLBI) observations were triggered at 22 GHz on five different occasions, four times prior to the giant flare, and once during its decay phase. Flux variations of 2 h duration were recorded during the first session. They correspond to a mini-flare that occurred close to the core 10 d before the onset of the giant flare. From the latest VLBI observation we infer that 4 d after the flare peak the jet emission was extended over 30 mas.
Keywords: stars: flare; stars: individual: Cyg X-3; radio continuum: stars; X-rays: binaries

SIRENA: Software for Athena X-IFU Event Reconstruction - Ceballos, M. T.; Cobo, B.; Peille, P.; Wilms, Jörn; Brand, Thorsten; Dauser, Thomas; Bandler, S.; Smith, S. (ASTRONOMICAL DATA ANALYSIS SOFTWARE AND SYSTEMS XXVI, 2019)
CRIS-Team WoS Importer:2019-11-29

SIXTE: a generic X-ray instrument simulation toolkit - Dauser, Thomas; Falkner, Sebastian; Lorenz, Maximilian; Kirsch, Christian; Peille, Philippe; Cucchetti, Edoardo; Schmid, Christian; Brand, Thorsten; Oertel, Mirjam; Smith, Randall; Wilms, Jörn (Astronomy & Astrophysics, 2019)
We give an overview of the SImulation of X-ray TElescopes (SIXTE) software package, a generic, mission-independent Monte Carlo simulation toolkit for X-ray astronomical instrumentation. The package is based on a modular approach for the source definition, the description of the optics, and the detector type such that new missions can be easily implemented. The targets to be simulated are stored in a flexible input format called SIMPUT. Based on this source definition, a sample of photons is produced and then propagated through the optics. In order to model the detection process, the software toolkit contains modules for various detector types, ranging from proportional counter and Si-based detectors, to more complex descriptions like transition edge sensor (TES) devices. The implementation of characteristic detector effects and a detailed modeling of the read-out process allow for representative simulations and therefore enable the analysis of characteristic features, such as for example pile-up, and their impact on observations. We present an overview of the implementation of SIXTE from the input source, the imaging, and the detection process, highlighting the modular approach taken by the SIXTE software package. In order to demonstrate the capabilities of the simulation software, we present a selection of representative applications, including the all-sky survey of eROSITA and a study of pile-up effects comparing the currently operating XMM-Newton with the planned Athena-WFI instrument. A simulation of a galaxy cluster with the AthenaX-IFU shows the capability of SIXTE to predict the expected performance of an observation for a complex source with a spatially varying spectrum and our current knowledge of the future instrument.
CRIS-Team WoS Importer:2019-10-11

Space experiment TUS on board the Lomonosov satellite as pathfinder of JEM-EUSO - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
Space-based detectors for the study of extreme energy cosmic rays (EECR) are being prepared as a promising new method for detecting highest energy cosmic rays. A pioneering space device - the "tracking ultraviolet set-up" (TUS) - is in the last stage of its construction and testing. The TUS detector will collect preliminary data on EECR in the conditions of a space environment, which will be extremely useful for planning the major JEM-EUSO detector operation.
Keywords: Air-shower fluorescence telescope; JEM-EUSO; Pathfinder

Spectral analysis of 1H 0707-495 with XMM-Newton - Dauser, Thomas; Svoboda, Jiri; Schartel, N.; Wilms, Jörn; Dovciak, Michal; Ehle, Matthias; Karas, Vladimir; Santos-Lleo, Maria; Marshall, H. L. (Monthly Notices of the Royal Astronomical Society, 2012)
We present the results of a 500 ks long XMMNewton observation and a 120 ks long quasi-simultaneous Chandra observation of the Narrow-Line Seyfert 1 galaxy 1H 0707-495 performed in 2010 September. Consistent with earlier results by Fabian et al. and Zoghbi et al., the spectrum is found to be dominated by relativistically broadened reflection features from an ionized accretion disc around a maximally rotating black hole. Even though the spectra changed between this observation and earlier XMMNewton observations, the physical parameters of the black hole and accretion disc (i.e. spin and inclination) are consistent between both observations. We show that this reflection spectrum is slightly modified by absorption in a mildly relativistic, highly ionized outflow which changed velocity from around 0.11 c to 0.18 c between 2008 January and 2010 September. Alternative models, in which the spectral shape is dominated by absorption, lead to spectral fits of similar quality, however, the parameters inferred for the putative absorber are unphysical.
Keywords: galaxies: active; galaxies: individual: 1H 0707-495; galaxies: nuclei; X-rays: galaxies

Spectral and timing evolution of the bright failed outburst of the transient black hole Swift J174510.8-262411 - Del Santo, Melania; Belloni, T. M.; Tomsick, J. A.; Sbarufatti, Boris; Bel, M. Cadolle; Casella, Piergiorgio; Castro-Tirado, A.; Corbel, S.; Grinberg, Victoria; Homan, J.; Kalemci, E.; Motta, Sara Elisa; et al. (Monthly Notices of the Royal Astronomical Society, 2016)
We studied time variability and spectral evolution of the Galactic black hole transient Swift J174510.8-262411 during the first phase of its outburst. INTEGRAL and Swift observations collected from 2012 September 16 until October 30 have been used. The total squared fractional rms values did not drop below 5 per cent and quasi-periodic oscillations (QPOs), when present, were type-C, indicating that the source never made the transition to the soft-intermediate state. Even though the source was very bright (up to 1 Crab in hard X-rays), it showed a so called failed outburst as it never reached the soft state. XRT and IBIS broad-band spectra, well represented by a hybrid thermal/non-thermal Comptonization model, showed physical parameters characteristic of the hard and intermediate states. In particular, the derived temperature of the geometrically thin disc blackbody was about 0.6 keV at maximum. We found a clear decline of the optical depth of the corona electrons (close to values of 0.1), as well as of the total compactness ratio l/l. The hard-to-hard/intermediate state spectral transition is mainly driven by the increase in the soft photon flux in the corona, rather than small variations of the electron heating. This, associated with the increasing of the disc temperature, is consistent with a disc moving towards the compact object scenario, i.e. the truncated-disc model. Moreover, this scenario is consistent with the decreasing fractional squared rms and increasing of the noise and QPO frequency. In our final group of observations, we found that the contribution from the non-thermal Comptonization to the total power supplied to the plasma is 0.59 and that the thermal electrons cool to kT < 26 keV.
Keywords: Accretion; accretion discs; Black hole physics; Gamma-rays: general; Radiation mechanisms: non-thermalI; Stars: individual: Swift J174510.8-262411; X-rays: binaries

SPECTRAL AND TIMING NATURE OF THE SYMBIOTIC X-RAY BINARY 4U 1954+319: THE SLOWEST ROTATING NEUTRON STAR IN AN X-RAY BINARY SYSTEM - Enoto, Teruaki; Sasano, Makoto; Yamada, Shin'Ya; Tamagawa, Toru; Makishima, Kazuo; Pottschmidt, Katja; Marcu, Diana; Corbet, Robin H. D.; Fuerst, Felix; Wilms, Jörn (Astrophysical Journal, 2014)
The symbiotic X-ray binary (SyXB) 4U 1954+ 319 is a rare system hosting a peculiar neutron star (NS) and an M-type optical companion. Its similar to 5.4 hr NS spin period is the longest among all known accretion-powered pulsars and exhibited large (similar to 7%) fluctuations over 8 yr. A spin trend transition was detected with Swift/BAT around an X-ray brightening in 2012. The source was in quiescent and bright states before and after this outburst based on 60 ks Suzaku observations in 2011 and 2012. The observed continuum is well described by a Comptonized model with the addition of a narrow 6.4 keV Fe-K alpha line during the outburst. Spectral similarities to slowly rotating pulsars in high-mass X-ray binaries, its high pulsed fraction (similar to 60%-80%), and the location in the Corbet diagram favor high B-field (greater than or similar to 10(12) G) over a weak field as in low-mass X-ray binaries. The observed low X-ray luminosity (10(33)-10(35) erg s(-1)), probable wide orbit, and a slow stellar wind of this SyXB make quasi-spherical accretion in the subsonic settling regime a plausible model. Assuming a similar to 10(13) G NS, this scheme can explain the similar to 5.4 hr equilibrium rotation without employing the magnetar-like field (similar to 10(16) G) required in the disk accretion case. The timescales of multiple irregular flares (similar to 50 s) can also be attributed to the free-fall time from the Alfven shell for a similar to 10(13) G field. A physical interpretation of SyXBs beyond the canonical binary classifications is discussed.
Keywords: accretion; accretion disks; binaries: symbiotic; magnetic fields; stars: individual (3A 1954+319; 4U 1954+319); stars: neutron; X-rays : binaries

Spectral formation in accreting X-ray pulsars: bimodal variation of the cyclotron energy with luminosity - Becker, P. A.; Klochkov, D.; Schoenherr, G.; Nishimura, O.; Ferrigno, C.; Caballero, I.; Kretschmar, Peter; Wolff, M. T.; Wilms, Jörn; Staubert, R. (Astronomy & Astrophysics, 2012)
Context. Accretion-powered X-ray pulsars exhibit significant variability of the cyclotron resonance scattering feature (CRSF) centroid energy on pulse-to-pulse timescales, and also on much longer timescales. Two types of spectral variability are observed. For sources in group 1, the CRSF energy is negatively correlated with the variable source luminosity, and for sources in group 2, the opposite behavior is observed. The physical basis for this bimodal behavior is currently not well understood.Aims. We explore the hypothesis that the accretion dynamics in the group 1 sources is dominated by radiation pressure near the stellar surface, and that Coulomb interactions decelerate the gas to rest in the group 2 sources.Methods. We derive a new expression for the critical luminosity, L-crit, such that radiation pressure decelerates the matter to rest in sources with X-ray luminosity L-X > L-crit. The formula for L-crit is based on a simple physical model for the structure of the accretion column in luminous X-ray pulsars that takes into account radiative deceleration, the energy dependence of the cyclotron cross section, the thermodynamics of the accreting gas, the dipole structure of the pulsar magnetosphere, and the diffusive escape of radiation through the column walls. We show that for typical neutron star parameters, L-crit = 1.5 x 10(37)B(12)(16/15) erg s(-1), where B-12 is the surface magnetic field strength in units of 10(12) G.Results. The formula for the critical luminosity is evaluated for five sources, using the maximum value of the CRSF centroid energy to estimate the surface magnetic field strength B-12. The results confirm that the group 1 sources are supercritical (L-X > L-crit) and the group 2 sources are subcritical (L-X < L-crit), although the situation is less clear for those highly variable sources that cross over the line L-X = L-crit. We also explain the variation of the CRSF energy with luminosity as a consequence of the variation of the characteristic emission height. The sign of this dependence is opposite in the supercritical and subcritical cases, hence creating the observed bimodal behavior.Conclusions. We have developed a new model for the critical luminosity in accretion-powered X-ray pulsars that explains the bimodal dependence of the CRSF centroid energy on the X-ray luminosity L-X. Our model provides a physical basis for the observed variation of the CRSF energy as a function of L-X for both the group 1 (supercritical) and the group 2 (subcritical) sources as a result of the variation of the emission height in the column.
Keywords: stars: neutron; pulsars: general; radiative transfer; accretion; accretion disks

SPECTRAL STATE DEPENDENCE OF THE 0.4-2 MEV POLARIZED EMISSION IN CYGNUS X-1 SEEN WITH INTEGRAL/IBIS, AND LINKS WITH THE AMI RADIO DATA - Rodriguez, Jerome; Grinberg, Victoria; Laurent, Philippe; Bel, Marion Cadolle; Pottschmidt, Katja; Pooley, Guy; Bodaghee, Arash; Wilms, Jörn; Gouiffes, Christian (Astrophysical Journal, 2015)
Polarization of the greater than or similar to 400 keV hard tail of the microquasar Cygnus X-1 has been independently reported by INTEGRAL/Imager on Board the INTEGRAL Satellite (IBIS), and INTEGRAL/SPectrometer on INTEGRAL and interpreted as emission from a compact jet. These conclusions were, however, based on the accumulation of all INTEGRAL data regardless of the spectral state. We utilize additional INTEGRAL exposure accumulated until 2012 December, and include the AMI/Ryle (15 GHz) radio data in our study. We separate the observations into hard, soft, and intermediate/transitional states and detect radio emission from a compact jet in hard and intermediate states (IS), but not in the soft. The 10-400 keV INTEGRAL (JEM-X and IBIS) state resolved spectra are well modeled with thermal Comptonization and reflection components. We detect a hard tail in the 0.4-2 MeV range for the hard state only. We extract the state dependent polarigrams of Cyg X-1, which are all compatible with no or an undetectable level of polarization except in the 400-2000 keV range in the hard state where the polarization fraction is 75% +/- 32% and the polarization angle 40.degrees 0 +/- 14.degrees 3. An upper limit on the 0.4-2 MeV soft state polarization fraction is 70%. Due to the short exposure, we obtain no meaningful constraint for the IS. The likely detection of a >400 keV polarized tail in the hard state, together with the simultaneous presence of a radio jet, reinforce the notion of a compact jet origin of the >400 keV emission.
Keywords: accretion; accretion disks; black hole physics; stars: individual (Cyg X-1); X-rays: stars

Spectro-timing analysis of Cygnus X-1 during a fast state transition - Böck, Moritz; Grinberg, Victoria; Pottschmidt, K.; Hanke, Manfred; Nowak, M. A.; Markoff, S. B.; Uttley, P.; Rodriguez, Jerome; Pooley, G. G.; Suchy, S.; Rothschild, R. E.; Wilms, Jörn (Astronomy & Astrophysics, 2011)
We present the analysis of two long, quasi-uninterrupted RXTE observations of Cygnus X-1 that span several days within a 10 d interval. The spectral characteristics during this observation cover the region where previous observations have shown the source to be most dynamic. Despite that the source behavior on time scales of hours and days is remarkably similar to that on year time scales. This includes a variety of spectral/temporal correlations that previously had only been observed over CygX-1's long-term evolution. Furthermore, we observe a full transition from a hard to a soft spectral state that occurs within less than 2.5 h - shorter than previously reported for any other similar CygX-1 transition. We describe the spectra with a phenomenological model dominated by a broken power law, and we fit the X-ray variability power spectra with a combination of a cutoff power law and Lorentzian components. The spectral and timing properties are correlated: the power spectrum Lorentzian components have an energy-dependent amplitude, and their peak frequencies increase with photon spectral index. Averaged over 3.2-10 Hz, the time lag between the variability in the 4.5-5.7 keV and 9.5-15 keV bands increases with decreasing hardness when the variability is dominated by the Lorentzian components during the hard state. The lag is small when there is a large power law noise contribution, shortly after the transition to the soft state. Interestingly, the soft state not only shows the shortest lags, but also the longest lags when the spectrum is at its softest and faintest. We discuss our results in terms of emission models for black hole binaries.
Keywords: X-rays: binaries; X-rays: individuals: CygX-1

SPECTRO-TIMING STUDY of GX 339-4 in A HARD INTERMEDIATE STATE - Furst, F.; Grinberg, Victoria; Tomsick, J. A.; Bachetti, Matteo; Boggs, S. E.; Brightman, M.; Christensen, F. E.; Craig, W. W.; Gandhi, P.; Grefenstette, B.; Hailey, C. J.; Harrison, F. A.; et al. (Astrophysical Journal, 2016)
We present an analysis of Nuclear Spectroscopic Telescope Array observations of a hard intermediate state of the transient black hole GX 339-4 taken in 2015 January. With the source softening significantly over the course of the 1.3 day long observation we split the data into 21 sub-sets and find that the spectrum of all of them can be well described by a power-law continuum with an additional relativistically blurred reflection component. The photon index increases from ∼1.69 to ∼1.77 over the course of the observation. The accretion disk is truncated at around nine gravitational radii in all spectra. We also perform timing analysis on the same 21 individual data sets, and find a strong type-C quasi-periodic oscillation (QPO), which increases in frequency from ∼0.68 to ∼1.05 Hz with time. The frequency change is well correlated with the softening of the spectrum. We discuss possible scenarios for the production of the QPO and calculate predicted inner radii in the relativistic precession model as well as the global disk mode oscillations model. We find discrepancies with respect to the observed values in both models unless we allow for a black hole mass of ∼100 , which is highly unlikely. We discuss possible systematic uncertainties, in particular with the measurement of the inner accretion disk radius in the relativistic reflection model. We conclude that the combination of observed QPO frequencies and inner accretion disk radii, as obtained from spectral fitting, is difficult to reconcile with current models.

Spectrum-RG astrophysical project - Pavlinsky, M.; Sunyaev, R.; Churazov, Eugene; Vikhlinin, A.; Sazonov, Sergey; Revnivtsev, M.; Arefiev, V.; Lapshov, I.; Akimov, V.; Levin, V.; Buntov, M.; Semena, N.; et al. (2009)
The Spectrum-Roentgen-Gamma mission will be launched in the 2012 year into a L2 orbit with Soyuz launcher and Fregat buster from Baikonur. The mission will conduct all-sky survey with X-ray mirror telescopes eROSITA and ART-XC up to 11 keV. It will allow detection of about 100 thousand clusters of galaxies and discovery large scale Universe structure. It will also discover all obscured accreting Black Holes in nearby galaxies and many (about 3 millions) new distant AGN. Then it is planned to observe dedicated sky regions with high sensitivity and thereafter to perform follow-up pointed observations of selected sources.
Keywords: X-ray astrophysical mission; X-ray telescope; all-sky X-ray survey

Sperm whale long-range echolocation sounds revealed by ANTARES, a deep-sea neutrino telescope - Andre, Michel; Caballe, A.; Van Der Schaar, M.; Solsona, A.; Houegnigan, L.; Zaugg, S.; Sanchez, A. M.; Castell, J. V.; Sole, Marta; Vila, F.; Djokic, D.; Adrian-Martinez, S.; et al. (Scientific Reports, 2017)
Despite dedicated research has been carried out to adequately map the distribution of the sperm whale in the Mediterranean Sea, unlike other regions of the world, the species population status is still presently uncertain. The analysis of two years of continuous acoustic data provided by the ANTARES neutrino telescope revealed the year-round presence of sperm whales in the Ligurian Sea, probably associated with the availability of cephalopods in the region. The presence of the Ligurian Sea sperm whales was demonstrated through the real-time analysis of audio data streamed from a cabled-to-shore deep-sea observatory that allowed the hourly tracking of their long-range echolocation behaviour on the Internet. Interestingly, the same acoustic analysis indicated that the occurrence of surface shipping noise would apparently not condition the foraging behaviour of the sperm whale in the area, since shipping noise was almost always present when sperm whales were acoustically detected. The continuous presence of the sperm whale in the region confirms the ecological value of the Ligurian sea and the importance of ANTARES to help monitoring its ecosystems.

Staring at 4U 1909+07 with Suzaku - Fürst, Felix; Pottschmidt, K.; Kreykenbohm, Ingo; Müller, Sebastian; Kühnel, Matthias; Wilms, Jörn; Rothschild, R. E. (Astronomy & Astrophysics, 2012)
We present an analysis of the neutron star high mass X-ray binary (HMXB) 4U 1909+07 mainly based on Suzaku data. We extend the pulse period evolution, which behaves in a random-walk like manner, indicative of direct wind accretion. Studying the spectral properties of 4U 1909+07 between 0.5 to 90 keV we find that a power-law with an exponential cutoff can describe the data well, when additionally allowing for a blackbody or a partially covering absorber at low energies.We find no evidence for a cyclotron resonant scattering feature (CRSF), a feature seen in many other neutron star HMXBs sources. By performing pulse phase resolved spectroscopy we investigate the origin of the strong energy dependence of the pulse profile, which evolves from a broad two-peak profile at low energies to a profile with a single, narrow peak at energies above 20 keV. Our data show that it is very likely that a higher folding energy in the high energy peak is responsible for this behavior. This in turn leads to the assumption that we observe the two magnetic poles and their respective accretion columns at different phases, and that these accretion columns have slightly different physical conditions.
Keywords: accretion; accretion disks; X-rays: binaries; stars: neutron

Statistical properties of flux variations in blazar light curves at GeV and TeV energies - Wagner, Sarah M.; Burd, P. R.; Dorner, D.; Mannheim, K.; Buson, S.; Gokus, Andrea; Madejski, G.; Scargle, J. D.; Arbet-Engels, A.; Baack, D.; Balbo, M.; Biederbeck, N.; et al. (Proceedings of Science, 2022)
Despite numerous detections of individual flares, the physical origin of the rapid variability observed from blazars remains uncertain. Using Bayesian blocks and the Eisenstein-Hut HOP algorithm, we characterize flux variations of high significance in the γ-ray light curves of two samples of blazars. Daily binned long-term light curves of TeV-bright blazars observed with the First G-APD Cherenkov Telescope (FACT) are compared to those of GeV-bright blazars observed with the Large Area Telescope on board the Fermi Gamma-ray Space Telescope (Fermi-LAT). We find no evidence for systematic asymmetry of the flux variations based on the derived rise and decay time scales. Additionally, we show that the daily-binned blazar light curves can be described by an exponential stochastic Ornstein-Uhlenbeck process with parameters depending on energy. Our analysis suggests that the flux variability in both samples is a superposition of faster fluctuations. This is, for instance, challenging to explain by shock-acceleration but expected for magnetic reconnection.
CRIS-Team Scopus Importer:2022-12-23

Study of the many fluorescent lines and the absorption variability in GX 301-2 with XMM-Newton - Fürst, Felix; Suchy, S.; Kreykenbohm, Ingo; Barragan, L.; Wilms, Jörn; Pottschmidt, K.; Caballero, I.; Kretschmar, Peter; Ferrigno, Carlo; Rothschild, R. E. (Astronomy & Astrophysics, 2011)
We present an in-depth study of the high mass X-ray binary (HMXB) GX 301-2 during its pre-periastron flare using data from the XMM-Newton satellite. The energy spectrum shows a power law continuum absorbed by a large equivalent hydrogen column on the order of 10(24) cm(-2) and a prominent Fe K alpha fluorescent emission line. Besides the Fe K alpha line, evidence for Fe K beta, Ni K alpha, Ni K beta, S K alpha, Ar K alpha, Ca K alpha, and Cr K alpha fluorescent lines is found. The observed line strengths are consistent with fluorescence in a cold absorber. This is the first time that Cr K alpha is seen in emission in the X-ray spectrum of a HMXB. In addition to the modulation by the strong pulse period of similar to 685 s the source is highly variable and shows different states of activity. We perform time-resolved as well as pulse-to-pulse resolved spectroscopy to investigate differences between these states of activity. We find that fluorescent line fluxes are strongly variable and generally follow the overall flux. The N-H value is variable by a factor of 2, but not correlated to continuum normalization. We find an interval of low flux in the light curve in which the pulsations cease almost completely, without any indication of an increasing absorption column. We investigate this dip in detail and argue that it is most likely that during the dip the accretion ceased and the afterglow of the fluorescent iron accounted for the main portion of the X-ray flux. A similar dip was found earlier in RXTE data, and we compare our findings to these results.
Keywords: stars: neutron; accretion; accretion disks; X-rays: binaries; X-rays: individuals: GX 301-2

Sub-milliarcsecond imaging of a bright flare and ejection event in the extragalactic jet 3C 111 - Schulz, R.; Kadler, M.; Ros, E.; Perucho, M.; Krichbaum, T. P.; Agudo, I.; Beuchert, T.; Lindqvist, M.; Mannheim, K.; Wilms, Jörn; Zensus, J. A. (Astronomy & Astrophysics, 2020)
Context. Flares in radio-loud active galactic nuclei are thought to be associated with the injection of fresh plasma into the compact jet base. Such flares are usually strongest and appear earlier at shorter radio wavelengths. Hence, very long baseline interferometry (VLBI) at millimeter(mm)-wavelengths is the best-suited technique for studying the earliest structural changes of compact jets associated with emission flares. Aims. We study the morphological changes of the parsec-scale jet in the nearby (z = 0.049) γ-ray bright radio galaxy 3C 111 following a flare that developed into a major radio outburst in 2007. Methods. We analyse three successive observations of 3C 111 at 86 GHz with the Global mm-VLBI Array (GMVA) between 2007 and 2008 which yield a very high angular resolution of ∼45 μas. In addition, we make use of single-dish radio flux density measurements from the F-GAMMA and POLAMI programmes, archival single-dish and VLBI data. Results. We resolve the flare into multiple plasma components with a distinct morphology resembling a bend in an otherwise remarkably straight jet. The flare-associated features move with apparent velocities of ∼4.0c to ∼4.5c and can be traced also at lower frequencies in later epochs. Near the base of the jet, we find two bright features with high brightness temperatures up to ∼1011 K, which we associate with the core and a stationary feature in the jet. Conclusions. The flare led to multiple new jet components indicative of a dynamic modulation during the ejection. We interpret the bend-like feature as a direct result of the outburst which makes it possible to trace the transverse structure of the jet. In this scenario, the components follow different paths in the jet stream consistent with expectations for a spine-sheath structure, which is not seen during intermediate levels of activity. The possibility of coordinated multiwavelength observations during a future bright radio flare in 3C 111 makes this source an excellent target for probing the radio-γ-ray connection.
CRIS-Team Scopus Importer:2020-12-25
Keywords: Galaxies: active; Galaxies: individual: 3C 111; Galaxies: jets; Techniques: high angular resolution

Suzaku observation of IGR J16318-4848 - Barragan, L.; Wilms, Jörn; Pottschmidt, K.; Nowak, M. A.; Kreykenbohm, Ingo; Walter, R.; Tomsick, J. A. (Astronomy & Astrophysics, 2009)
We report on the first Suzaku observation of IGR J16318-4848, the most extreme example of a new group of highly absorbed X-ray binaries that have recently been discovered by the International Gamma-Ray Astrophysics Laboratory (INTEGRAL). The Suzaku observation was carried out between 2006 August 14 and 17, with a net exposure time of 97 ks.The average X-ray spectrum of the source can be well described (chi(2)(red) = 0.99) with a continuum model typical for neutron stars i.e., a strongly absorbed power law continuum with a photon index of 0.676(42) and an exponential cutoff at 20.5(6) keV. The absorbing column is N-H = 1.95(3) x 10(24) cm(-2). Consistent with earlier work, strong fluorescent emission lines of Fe K alpha, Fe K beta, and Ni K alpha are observed. Despite the large N-H, no Compton shoulder is seen in the lines, arguing for a non-spherical and inhomogeneous absorber. Seen at an average 5-60 keV absorbed flux of 3.4x10(-10) erg cm(-2) s(-1), the source exhibits significant variability on timescales of hours.
Keywords: stars: individual IGR J16318-4848; binaries: general; X-rays: binaries

SUZAKU OBSERVATIONS OF 4U 1957+11: POTENTIALLY THE MOST RAPIDLY SPINNING BLACK HOLE IN (THE HALO OF) THE GALAXY - Nowak, Michael A.; Wilms, Jörn; Pottschmidt, Katja; Schulz, Norbert; Maitra, Dipankar; Miller, Jon (Astrophysical Journal, 2012)
We present three Suzaku observations of the black hole candidate 4U 1957+11 (V1408 Aql)-a source that exhibits some of the simplest and cleanest examples of soft, disk-dominated spectra. 4U 1957+11 also presents among the highest peak temperatures found from disk-dominated spectra. Such temperatures may be associated with rapid black hole spin. The 4U 1957+11 spectra also require a very low normalization, which can be explained by a combination of small inner disk radius and a large distance (>10 kpc) which places 4U 1957+11 well into the Galactic halo. We perform joint fits to the Suzaku spectra with both relativistic and Comptonized disk models. Assuming a low-mass black hole and the nearest distance (3 M-circle dot, 10 kpc), the dimensionless spin parameter a* equivalent to Jc/GM(2) greater than or similar to 0.9. Higher masses and farther distances yield a* approximate to 1. Similar conclusions are reached with Comptonization models; they imply a combination of small inner disk radii (or, equivalently, rapid spin) and large distance. Low spin cannot be recovered unless 4U 1957+11 is a low-mass black hole that is at the unusually large distance of greater than or similar to 40 kpc. We speculate whether the suggested maximal spin is related to how the system came to reside in the halo.
Keywords: accretion; accretion disks; black hole physics; radiation mechanisms: thermal; X-rays: binaries

Suzaku Observations of 4U 1957+11: The Most Rapidly Spinning Black Hole in the Galaxy? - Nowak, Michael A.; Wilms, Jörn; Pottschmidt, Katja; Schulz, Norbert; Miller, Jon; Maitra, Dipankar (2012)
We present three Suzaku observations of the black hole candidate 4U 1957+11-a source that exhibits some of the simplest and cleanest examples of soft, disk-dominated spectra. 4U 1957+11 also presents among the highest peak temperatures found from disk-dominated spectra. Such temperatures may be associated with rapid black hole spin. The 4U 1957+11 spectra also require a very low normalization, which can be explained by a combination of small inner disk radius and a large distance (> 10 kpc) which places 4U 1957+11 well into the Galactic halo. We perform joint fits to the Suzaku spectra with relativistic disk models. Assuming a low mass black hole and the nearest distance (3M(circle dot), 10 kpc), the dimensionless spin parameter a* = Jc/GM(2) greater than or similar to 0.9. Higher masses and farther distances yield a* approximate to 1. Low spin cannot be recovered unless 4U 1957+11 is a low mass black hole that is at the unusually large distance of greater than or similar to 40 kpc.
Keywords: accretion; accretion disks; black hole physics; X-rays: binaries

Suzaku observations of the 2013 outburst of KS 1947+300 - Ballhausen, Ralf; Kühnel, Matthias; Pottschmidt, Katja; Furst, Felix; Hemphill, Paul B.; Falkner, Sebastian; Gottlieb, Amy M.; Grinberg, Victoria; Kretschmar, Peter; Kreykenbohm, Ingo; Rothschild, Richard E.; Wilms, Jörn (Astronomy & Astrophysics, 2016)
We report on the timing and spectral analysis of two Suzaku observations with different flux levels of the high-mass X-ray binary KS 1947+300 during its 2013 outburst. In agreement with simultaneous NuSTAR observations, the continuum is well described by an absorbed power law with a cutoff and an additional blackbody component. In addition, we find fluorescent emission from neutral, He-like, and even H-like iron. We determine a pulse period of 18.8 s with the source showing a spin-up between the two observations. Both Suzaku observations show very similar behavior of the pulse profile, which is strongly energy dependent. This profile has an evolution from a profile with one peak at low energies to a profile with two peaks of different widths toward higher energies seen in both the Suzaku and NuSTAR data. Such an evolution to a more complex profile at higher energies is rarely seen in X-ray pulsars, most cases show the opposite behavior. Pulse phase-resolved spectral analysis shows a variation in the absorbing column density, N, over pulse phase. Spectra taken during the pulse profile minima are intrinsically softer compared to the pulse phase-averaged spectrum.
Keywords: Accretion; accretion disks; Pulsars: individual: KS 1947+300; X-rays: binaries

SUZAKU OBSERVATIONS OF THE HMXB 1A 1118-61 - Suchy, Slawomir; Pottschmidt, Katja; Rothschild, Richard E.; Wilms, Jörn; Fürst, Felix; Barragan, Laura; Caballero, Isabel; Grinberg, Victoria; Kreykenbohm, Ingo; Doroshenko, Victor; Santangelo, Andrea; Staubert, Ruediger; et al. (Astrophysical Journal, 2011)
We present broadband analysis of the Be/X-ray transient 1A 1118-61 by Suzaku at the peak of its third observed outburst in 2009 January and two weeks later when the source flux had decayed by an order of magnitude. The continuum was modeled with a cutoffpl model as well as a compTT model, with both cases requiring an additional blackbody component at lower energies. We confirm the detection of a cyclotron line at similar to 55 keV and discuss the possibility of a first harmonic at similar to 110 keV. Pulse profile comparisons show a change in the profile structure at lower energies, an indication for possible changes in the accretion geometry. Phase-resolved spectroscopy in the outburst data shows a change in the continuum throughout the pulse period. The decrease in the cyclotron resonance scattering feature centroid energy also indicates that the viewing angle on the accretion column is changing throughout the pulse period.
Keywords: pulsars: individual (1A 1118-61); stars: magnetic field; X-rays: binaries; X-rays: stars

Swift/BAT measurements of the cyclotron line energy decay in the accreting neutron star Hercules X-1: indication of an evolution of the magnetic field? - Klochkov, D.; Staubert, R.; Postnov, K.; Wilms, Jörn; Rothschild, R. E.; Santangelo, A. (Astronomy & Astrophysics, 2015)
Conclusions. The decay of E-cyc either indicates a local evolution of the magnetic field structure in the polar regions of the neutron star or a geometrical displacement of the line-forming region due to long-term changes in the structure of the X-ray emitting region. The shortness of the observed timescale of the decay, E-cyc/(E) over dot(cyc) similar to 100 yr, suggests that trend reversals and/or jumps of the line energy might be observed in the future.
Keywords: accretion; accretion disks; stars: neutron; stars: magnetic field

Synthetic simulations of the extragalactic sky seen by eROSITA I. Pre-launch selection functions from Monte-Carlo simulations - Clerc, N.; Ramos-Ceja, M. E.; Ridl, J.; Lamer, G.; Brunner, H.; Hofmann, Florian; Comparat, J.; Pacaud, Florian; Kaefer, F.; Reiprich, T. H.; Merloni, A.; Schmid, Christian; et al. (Astronomy & Astrophysics, 2018)
Context. Studies of galaxy clusters provide stringent constraints on models of structure formation. Provided that selection effects are under control, large X-ray surveys are well suited to derive cosmological parameters, in particular those governing the dark energy equation of state.Aims. We forecast the capabilities of the all-sky eROSITA (extended ROentgen Survey with an Imaging Telescope Array) survey to be achieved by the early 2020s. We bring special attention to modelling the entire chain from photon emission to source detection and cataloguing.Methods. The selection function of galaxy clusters for the upcoming eROSITA mission is investigated by means of extensive and dedicated Monte-Carlo simulations. Employing a combination of accurate instrument characterisation and a state-of-the-art source detection technique, we determine a cluster detection efficiency based on the cluster fluxes and sizes.Results. Using this eROSITA cluster selection function, we find that eROSITA will detect a total of approximately 10(5) clusters in the extra-galactic sky. This number of clusters will allow eROSITA to put stringent constraints on cosmological models. We show that incomplete assumptions on selection effects, such as neglecting the distribution of cluster sizes, induce a bias in the derived value of cosmological parameters.Conclusions. Synthetic simulations of the eROSITA sky capture the essential characteristics impacting the next-generation galaxy cluster surveys and they highlight parameters requiring tight monitoring in order to avoid biases in cosmological analyses.
Keywords: cosmological parameters; surveys; large-scale structure of Universe; X-rays: galaxies: clusters; cosmology: observations; methods: data analysis

TANAMI blazars in the IceCube PeV-neutrino fields - Krauß, Felicia; Kadler, Matthias; Mannheim, K.; Schulz, Robert; Truestedt, J.; Wilms, Jörn; Ojha, R.; Ros, Eduardo; Anton, Gisela; Baumgartner, W.; Beuchert, Tobias; Blanchard, J.; et al. (Astronomy & Astrophysics, 2014)
The IceCube Collaboration has announced the discovery of a neutrino flux in excess of the atmospheric background. Owing to the steeply falling atmospheric background spectrum, events at PeV energies most likely have an extraterrestrial origin. We present the multiwavelength properties of the six radio-brightest blazars that are positionally coincident with these events using contemporaneous data of the TANAMI blazar sample, including high-resolution images and spectral energy distributions. Assuming the X-ray to gamma-ray emission originates in the photoproduction of pions by accelerated protons, the integrated predicted neutrino luminosity of these sources is high enough to explain the two detected PeV events.
Keywords: neutrinos; galaxies: active; quasars: general

TANAMI monitoring of Centaurus A: The complex dynamics in the inner parsec of an extragalactic jet - Mueller, C.; Kadler, Matthias; Ojha, R.; Perucho, Manel; Großberger, Christoph; Ros, Eduardo; Wilms, Jörn; Blanchard, J.; Boeck, M.; Carpenter, B.; Dutka, M.; Edwards, P. G.; et al. (Astronomy & Astrophysics, 2014)
Context. Centaurus A (Cen A) is the closest radio-loud active galactic nucleus. Very Long Baseline Interferometry (VLBI) enables us to study the spectral and kinematic behavior of the radio jet-counterjet system on milliarcsecond scales, providing essential information for jet emission and propagation models.Aims. In the framework of the TANAMI monitoring, we investigate the kinematics and complex structure of Cen A on subparsec scales. We have been studying the evolution of the central parsec jet structure of CenA for over 3.5 years. The proper motion analysis of individual jet components allows us to constrain jet formation and propagation and to test the proposed correlation of increased high-energy flux with jet ejection events. Cen A is an exceptional laboratory for such a detailed study because its proximity translates to unrivaled linear resolution, where one milliarcsecond corresponds to 0.018 pc.Methods. As a target of the southern-hemisphere VLBI monitoring program TANAMI, observations of CenA are done approximately every six months at 8.4 GHz with the Australian Long Baseline Array (LBA) and associated telescopes in Antarctica, Chile, New Zealand, and South Africa, complemented by quasi-simultaneous 22.3 GHz observations.Results. The first seven epochs of high-resolution TANAMI VLBI observations at 8.4 GHz of CenA are presented, resolving the jet on (sub-) milliarcsecond scales. They show a differential motion of the subparsec scale jet with significantly higher component speeds farther downstream where the jet becomes optically thin. We determined apparent component speeds within a range of 0 : 1 c to 0 : 3 c and identified long-term stable features. In combination with the jet-to-counterjet ratio, we can constrain the angle to the line of sight to theta similar to 12 degrees-45 degrees.Conclusions. The high-resolution kinematics are best explained by a spine-sheath structure supported by the downstream acceleration occurring where the jet becomes optically thin. On top of the underlying, continuous flow, TANAMI observations clearly resolve individual jet features. The flow appears to be interrupted by an obstacle causing a local decrease in surface brightness and circumfluent jet behavior. We propose a jet-star interaction scenario to explain this appearance. The comparison of jet ejection times to high X-ray flux phases yields a partial overlap of the onset of the X-ray emission and increasing jet activity, but the limited data do not support a robust correlation.
Keywords: galaxies: active; galaxies: individual: Centaurus A; galaxies: individual: NGC 5128; techniques: high angular resolution; galaxies: jets

TANAMI: Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry - Mueller, C.; Kadler, M.; Ojha, R.; Schulz, Robert; Truestedt, J.; Edwards, P. G.; Ros, E.; Carpenter, B.; Angioni, R.; Blanchard, J.; Böck, Moritz; Burd, P. R.; et al. (Astronomy & Astrophysics, 2018)
Context. TANAMI is a multiwavelength program monitoring active galactic nuclei (AGN) south of -30 degrees declination including high-resolution very long baseline interferometry (VLBI) imaging, radio, optical/UV, X-ray, and gamma-ray studies. We have previously published first-epoch 8.4 GHz VLBI images of the parsec-scale structure of the initial sample. In this paper, we present images of 39 additional sources. The full sample comprises most of the radio-and gamma-ray brightest AGN in the southern quarter of the sky, overlapping with the region from which high-energy (>100 TeV) neutrino events have been found.Aims. We characterize the parsec-scale radio properties of the jets and compare them with the quasi-simultaneous Fermi/LAT gamma-ray data. Furthermore, we study the jet properties of sources which are in positional coincidence with high-energy neutrino events compared to the full sample. We test the positional agreement of high-energy neutrino events with various AGN samples.Methods. TANAMI VLBI observations at 8.4 GHz are made with southern hemisphere radio telescopes located in Australia, Antarctica, Chile, New Zealand, and South Africa.Results. Our observations yield the first images of many jets below -30 degrees declination at milliarcsecond resolution. We find that gamma-ray loud TANAMI sources tend to be more compact on parsec-scales and have higher core brightness temperatures than gamma-ray faint jets, indicating higher Doppler factors. No significant structural difference is found between sources in positional coincidence with high-energy neutrino events and other TANAMI jets. The 22 gamma-ray brightest AGN in the TANAMI sky show only a weak positional agreement with high-energy neutrinos demonstrating that the >100 TeV IceCube signal is not simply dominated by a small number of the gamma-ray brightest blazars. Instead, a larger number of sources have to contribute to the signal with each individual source having only a small Poisson probability for producing an event in multi-year integrations of current neutrino detectors.
Keywords: galaxies: active; galaxies: jets; galaxies: nuclei; radio continuum: galaxies; techniques: high angular resolution; neutrinos

TANAMI: tracking active galactic nuclei with austral milliarcsecond interferometry I. First-epoch 8.4GHz images - Ojha, R.; Kadler, Matthias; Böck, Moritz; Booth, R.; Dutka, M. S.; Edwards, P. G.; Fey, A. L.; Fuhrmann, L.; Gaume, R. A.; Hase, H.; Horiuchi, S.; Jauncey, D. L.; et al. (Astronomy & Astrophysics, 2010)
Context. A number of theoretical models vie to explain the gamma-ray emission from active galactic nuclei (AGN). This was a key discovery of EGRET. With its broader energy coverage, higher resolution, wider field of view and greater sensitivity, the Large Area Telescope (LAT) of the Fermi Gamma-ray Space Telescope is dramatically increasing our knowledge of AGN gamma-ray emission. However, discriminating between competing theoretical models requires quasi-simultaneous observations across the electromagnetic spectrum. By resolving the powerful parsec-scale relativistic outflows in extragalactic jets and thereby allowing us to measure critical physical properties, Very Long Baseline Interferometry observations are crucial to understanding the physics of extragalactic gamma-ray objects.Aims. We introduce the TANAMI program (Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry) which is monitoring an initial sample of 43 extragalactic jets located south of -30 degrees declination at 8.4GHz and 22GHz since 2007. All aspects of the program are discussed. First epoch results at 8.4GHz are presented along with physical parameters derived therefrom.Methods. These observations were made during 2007/2008 using the telescopes of the Australian Long Baseline Array in conjunction with Hartebeesthoek in South Africa. These data were correlated at the Swinburne University correlator.Results. We present first epoch images for 43 sources, some observed for the first time at milliarcsecond resolution. Parameters of these images as well as physical parameters derived from them are also presented and discussed. These and subsequent images from the TANAMI survey are available at http://pulsar.sternwarte.uni-erlangen.de/tanami/.Conclusions. We obtain reliable, high dynamic range images of the southern hemisphere AGN. All the quasars and BL Lac objects in the sample have a single-sided radio morphology. Galaxies are either double-sided, single-sided or irregular. About 28% of the TANAMI sample has been detected by LAT during its first three months of operations. Initial analysis suggests that when galaxies are excluded, sources detected by LAT have larger opening angles than those not detected by LAT. Brightness temperatures of LAT detections and non-detections seem to have similar distributions. The redshift distributions of the TANAMI sample and sub-samples are similar to those seen for the bright gamma-ray AGN seen by LAT and EGRET but none of the sources with a redshift above 1.8 have been detected by LAT.
Keywords: galaxies: active; galaxies: jets; galaxies: nuclei; gamma rays: observations; quasars: general

Temporal variations of strength and location of the South Atlantic Anomaly as measured by RXTE - Fürst, Felix; Wilms, Jörn; Rothschild, Richard E.; Pottschmidt, Katja; Smith, David M.; Lingenfelter, Richard (Earth and Planetary Science Letters, 2009)
The evolution of the particle background at an altitude of similar to 540 km during the time interval between 1996 and 2007 is studied using the particle monitor of the High Energy X-ray Timing Experiment on board NASA's Rossi X-ray Timing Explorer. A special emphasis of this study is the location and strength of the South Atlantic Anomaly (SAA). The size and strength of the SAA are anti-correlated with the 10.7 cm radio flux of the Sun, which leads the SAA strength by similar to 1 year reflecting variations in solar heating of the upper atmosphere. The location of the SAA is also found to drift westwards with an average drift rate of about 0.3 degrees/yr following the drift of the geomagnetic-field configuration. Superimposed to this drift rate are irregularities, where the SAA suddenly moves eastwards and where furthermore the speed of the drift changes. The most prominent of these irregularities is found in the second quarter of 2003 and another event took place in 1999. We suggest that these events are previously unrecognized manifestations of the geomagnetic jerks of the Earth's magnetic field. (c) 2009 Elsevier B.V. All rights reserved.
Keywords: space radiation environment; South Atlantic Anomaly; radiation monitors; Rossi X-ray Timing Explorer

TESSIM: A simulator for the Athena-X-IFU - Wilms, Jörn; Smith, S. J.; Peille, P.; Ceballos, M. T.; Cobo, B.; Dauser, Thomas; Brand, Thorsten; Den Hartog, R. H.; Bandler, S. R.; De Plaa, J.; Den Herder, J. W.A. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
We present the design of tessim, a simulator for the physics of transition edge sensors developed in the framework of the Athena end to end simulation effort. Designed to represent the general behavior of transition edge sensors and to provide input for engineering and science studies for Athena, tessim implements a numerical solution of the linearized equations describing these devices. The simulation includes a model for the relevant noise sources and several implementations of possible trigger algorithms. Input and output of the software are standard FITS-files which can be visualized and processed using standard X-ray astronomical tool packages. Tessim is freely available as part of the SIXTE package (http://www.sternwarte.uni-erlangen.de/research/sixte/).
Keywords: Athena; simulation; transition edge detectors; X-ray detector

THE 2010 MAY FLARING EPISODE OF CYGNUS X-3 IN RADIO, X-RAYS, AND gamma-RAYS - Williams, Peter K. G.; Tomsick, John A.; Bodaghee, Arash; Bower, Geoffrey C.; Pooley, Guy G.; Pottschmidt, Katja; Rodriguez, Jerome; Wilms, Jörn; Migliari, Simone; Trushkin, Sergei A. (Astrophysical Journal Letters, 2011)
In 2009, Cygnus X-3 (Cyg X-3) became the first microquasar to be detected in the GeV gamma-ray regime, via the satellites Fermi and AGILE. The addition of this new band to the observational toolbox holds promise for building a more detailed understanding of the relativistic jets of this and other systems. We present a rich data set of radio, hard and soft X-ray, and gamma-ray observations of Cyg X-3 made during a flaring episode in 2010 May. We detect a similar to 3 day softening and recovery of the X-ray emission, followed almost immediately by a similar to 1 Jy radio flare at 15 GHz, followed by a 4.3 sigma gamma-ray flare (E > 100 MeV) similar to 1.5 days later. The radio sampling is sparse, but we use archival data to argue that it is unlikely the gamma-ray flare was followed by any significant unobserved radio flares. In this case, the sequencing of the observed events is difficult to explain in a model in which the gamma-ray emission is due to inverse Compton scattering of the companion star's radiation field. Our observations suggest that other mechanisms may also be responsible for gamma-ray emission from Cyg X-3.
Keywords: black hole physics; X-rays: binaries; X-rays: individual (Cygnus X-3)

The 35-day cycle in the X-ray binary HZ Her/Her X-1 - Kolesnikov, D.; Shakura, N.; Postnov, K.; Volkov, I.; Bikmaev, I.; Irsmambetova, T.; Staubert, R.; Wilms, Jörn; Irtuganov, E.; Shurygin, P.; Golysheva, P.; Shugarov, S.; et al. (Contributions of the Astronomical Observatory Skalnate Pleso, 2020)
We present the results of modelling the 35-day superorbital changes in the B and V lightcurves and X-ray flux of HZ Her/Her X-1. The model is implemented in a computer program written in the C programming language, with a module for parameter optimisation written in Python. The model includes a tilted precessing and warped accretion disc around a freely precessing neutron star. The disc is warped near its inner edge due to interaction with the rotating neutron star magnetosphere. The magnetic torque depends on the precessional phase of the neutron star. The neutron star X-ray emission flux also depends on the free precession phase, which modulates the X-ray illumination of the optical star's atmosphere and the intensity of gas streams. We demonstrate that this model is able to reproduce both the optical observations of HZ Her and the behaviour of the system's 35-day X-ray cycle.
CRIS-Team WoS Importer:2020-04-21

THE 5 hr PULSE PERIOD AND BROADBAND SPECTRUM OF THE SYMBIOTIC X-RAY BINARY 3A 1954+319 - Marcu, Diana M.; Fürst, Felix; Pottschmidt, Katja; Grinberg, Victoria; Müller, Sebastian; Wilms, Jörn; Postnov, Konstantin A.; Corbet, Robin H. D.; Markwardt, Craig B.; Cadolle Bel, Marion (Astrophysical Journal Letters, 2011)
We present an analysis of the highly variable accreting X-ray pulsar 3A 1954 + 319 using 2005-2009 monitoring data obtained with INTEGRAL and Swift. This considerably extends the pulse period history and covers flaring episodes in 2005 and 2008. In 2006 the source was identified as one of only a few known symbiotic X-ray binaries (SyXBs), i.e., systems composed of a neutron star accreting from the inhomogeneous medium around an M-giant star. The extremely long pulse period of similar to 5.3 hr is directly visible in the 2008 INTEGRAL-ISGRI outburst light curve. The pulse profile is double peaked and generally not significantly energy dependent although there is an indication of possible softening during the main pulse. During the outburst a strong spin-up of -1.8 x 10(-4) hr hr(-1) occurred. Between 2005 and 2008 a long-term spin-down trend of 2.1 x 10(-5) hr hr(-1) was observed for the first time for this source. The 3-80 keV pulse peak spectrum of 3A 1954 + 319 during the 2008 flare could be well described by a thermal Comptonization model. We interpret the results within the framework of a recently developed quasi-spherical accretion model for SyXBs.
Keywords: binaries: symbiotic; stars: individual (3A 1954+319); stars: neutron; X-rays: binaries

THE ACCRETION DISK CORONA AND DISK ATMOSPHERE OF 4U 1624-490 AS VIEWED BY THE CHANDRA-HIGH ENERGY TRANSMISSION GRATING SPECTROMETER - Xiang, Jingen; Lee, Julia C.; Nowak, Michael A.; Wilms, Jörn; Schulz, Norbert S. (Astrophysical Journal, 2009)
We present a detailed spectral study ( photoionization modeling and variability) of the "Big Dipper" 4U 1624-490 based on a Chandra-High Energy Transmission Grating Spectrometer ( HETGS) observation over the similar to 76 ks binary orbit of 4U 1624-490. While the continuum spectrum can be modeled using a blackbody plus power law, a slightly better fit is obtained using a single Gamma = 2.25 power-law partially ( 71%) covered by a local absorber of column density N-H, Local = 8.1(-0.6)(+0.7) x 10(22) cm(-2). The data show a possible quasi-sinusoidal modulation with period 43(-9)(+13) ks that might be due to changes in local obscuration. Photoionization modeling with the xstar code and variability studies of the observed strong Fe xxv and Fe XXVI absorption lines point to a two-temperature plasma for their origin: a highly ionized component of ionization parameter xi(hot) approximate to 10(4.3) erg cm s(-1) ( T similar to 3.0 x 10(6) K) associated with an extended accretion disk corona of radius R similar to 3 x 10(10) cm, and a less-ionized more variable component of xi approximate to 10(3.4) erg cm s(-1) ( T similar to 1.0 x 10(6) K) and xi approximate to 10(3.1) erg cm s(-1) ( T similar to 0.9 x 10(6) K) coincident with the accretion disk rim. We use this, with the observed Fe xxv and Fe XXVI absorption line variations ( in wavelength, strength, and width) to construct a viewing geometry that is mapped to changes in plasma conditions over the 4U 1624-490 orbital period.
Keywords: accretion; accretion disks; plasmas; X-rays: binaries; X-rays: individual (4U 1624-490)

The accretion environment in Vela X-1 during a flaring period using XMM-Newton - Martinez-Nunez, Silvia; Torrejon, J. M.; Kühnel, Matthias; Kretschmar, Peter; Stuhlinger, M.; Rodes-Roca, J. J.; Fuerst, F.; Kreykenbohm, Ingo; Martin-Carrillo, A.; Pollock, A. M. T.; Wilms, Jörn (Astronomy & Astrophysics, 2014)
We present analysis of 100 ks contiguous XMM-Newton data of the prototypical wind accretor Vela X-1. The observation covered eclipse egress between orbital phases 0.134 and 0.265, during which a giant flare took place, enabling us to study the spectral properties both outside and during the flare. This giant flare with a peak luminosity of 3.92(-0.09)(+0.42) x 10(37) erg s(-1) allows estimates of the physical parameters of the accreted structure with a mass of similar to 10(21) g. We have been able to model several contributions to the observed spectrum with a phenomenological model formed by three absorbed power laws plus three emission lines. After analysing the variations with orbital phase of the column density of each component, as well as those in the Fe and Ni fluorescence lines, we provide a physical interpretation for each spectral component. Meanwhile, the first two components are two aspects of the principal accretion component from the surface of the neutron star, the third component seems to be the X-ray light echo formed in the stellar wind of the companion.
Keywords: X-rays: binaries; pulsars: individual: Vela X-1

The ANTARES telescope neutrino alert system - Ageron, M.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; Aubert, J. -J.; et al. (Astroparticle Physics, 2012)
The ANTARES telescope has the capability to detect neutrinos produced in astrophysical transient sources. Potential sources include gamma-ray bursts, core collapse supernovae, and flaring active galactic nuclei. To enhance the sensitivity of ANTARES to such sources, a new detection method based on coincident observations of neutrinos and optical signals has been developed. A fast online muon track reconstruction is used to trigger a network of small automatic optical telescopes. Such alerts are generated for special events, such as two or more neutrinos, coincident in time and direction, or single neutrinos of very high energy. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: ANTARES; Neutrino astronomy; Transient sources; Optical follow-up

The Athena X-ray Integral Field Unit: a consolidated design for the system requirement review of the preliminary definition phase - Barret, Didier; Albouys, Vincent; Den Herder, Jan-Willem; Piro, Luigi; Cappi, Massimo; Huovelin, Juhani; Kelley, Richard; Miguel Mas-Hesse, J.; Paltani, Stephane; Rauw, Gregor; Rozanska, Agata; Svoboda, Jiri; et al. (Experimental Astronomy, 2023)
The Athena X-ray Integral Unit (X-IFU) is the high resolution X-ray spectrometer studied since 2015 for flying in the mid-30s on the Athena space X-ray Observatory. Athena is a versatile observatory designed to address the Hot and Energetic Universe science theme, as selected in November 2013 by the Survey Science Committee. Based on a large format array of Transition Edge Sensors (TES), X-IFU aims to provide spatially resolved X-ray spectroscopy, with a spectral resolution of 2.5 eV (up to 7 keV) over a hexagonal field of view of 5 arc minutes (equivalent diameter). The X-IFU entered its System Requirement Review (SRR) in June 2022, at about the same time when ESA called for an overall X-IFU redesign (including the X-IFU cryostat and the cooling chain), due to an unanticipated cost overrun of Athena. In this paper, after illustrating the breakthrough capabilities of the X-IFU, we describe the instrument as presented at its SRR (i.e. in the course of its preliminary definition phase, so-called B1), browsing through all the subsystems and associated requirements. We then show the instrument budgets, with a particular emphasis on the anticipated budgets of some of its key performance parameters, such as the instrument efficiency, spectral resolution, energy scale knowledge, count rate capability, non X-ray background and target of opportunity efficiency. Finally, we briefly discuss the ongoing key technology demonstration activities, the calibration and the activities foreseen in the X-IFU Instrument Science Center, touch on communication and outreach activities, the consortium organisation and the life cycle assessment of X-IFU aiming at minimising the environmental footprint, associated with the development of the instrument. Thanks to the studies conducted so far on X-IFU, it is expected that along the design-to-cost exercise requested by ESA, the X-IFU will maintain flagship capabilities in spatially resolved high resolution X-ray spectroscopy, enabling most of the original X-IFU related scientific objectives of the Athena mission to be retained. The X-IFU will be provided by an international consortium led by France, The Netherlands and Italy, with ESA member state contributions from Belgium, Czech Republic, Finland, Germany, Poland, Spain, Switzerland, with additional contributions from the United States and Japan.
CRIS-Team WoS Importer:2023-03-17

The Athena X-ray Integral Field Unit (X-IFU) - Barret, Didier; Lam Trong, Thien; Den Herder, Jan Willem; Piro, Luigi; Barcons, Xavier; Huovelin, Juhani; Kelley, Richard; Mas-Hesse, J. Miguel; Mitsuda, Kazuhisa; Paltani, Stéphane; Rauw, Gregor; Rozanska, Agata; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
The X-ray Integral Field Unit (X-IFU) on board the Advanced Telescope for High-ENergy Astrophysics (Athena) will provide spatially resolved high-resolution X-ray spectroscopy from 0.2 to 12 keV, with ∼ 5" pixels over a field of view of 5 arc minute equivalent diameter and a spectral resolution of 2.5 eV up to 7 keV. In this paper, we first review the core scientific objectives of Athena, driving the main performance parameters of the X-IFU, namely the spectral resolution, the field of view, the effective area, the count rate capabilities, the instrumental background. We also illustrate the breakthrough potential of the X-IFU for some observatory science goals. Then we brie y describe the X-IFU design as defined at the time of the mission consolidation review concluded in May 2016, and report on its predicted performance. Finally, we discuss some options to improve the instrument performance while not increasing its complexity and resource demands (e.g. count rate capability, spectral resolution).
Keywords: Athena; Instrumentation; Space telescopes; X-ray Integral Field Unit; X-ray spectroscopy

The Athena X-ray Integral Field Unit (X-IFU) - Pajot, F.; Barret, D.; Lam-Trong, T.; Den Herder, J. -W.; Piro, Luigi; Cappi, M.; Huovelin, Juhani; Kelley, R.; Mas-Hesse, J. M.; Mitsuda, K.; Paltani, S.; Rauw, G.; et al. (Journal of Low Temperature Physics, 2018)
The X-ray Integral Field Unit (X-IFU) of the Advanced Telescope for High-ENergy Astrophysics (Athena) large-scale mission of ESA will provide spatially resolved high-resolution X-ray spectroscopy from 0.2 to 12 keV, with 5 '' pixels over a field of view of 5 arc minute equivalent diameter and a spectral resolution of 2.5 eV (FWHM) up to 7 keV. The core scientific objectives of Athena drive the main performance parameters of the X-IFU. We present the current reference configuration of the X-IFU, and the key issues driving the design of the instrument.
Keywords: X-ray astronomy; Imaging spectroscopy; Microcalorimeter

The atmospheric monitoring system of the JEM-EUSO instrument - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The JEM-EUSO telescope will detect Ultra-High Energy Cosmic Rays (UHECRs) from space, detecting the UV Fluorescence Light produced by Extensive Air Showers (EAS) induced by the interaction of the cosmic rays with the earth's atmosphere. The capability to reconstruct the properties of the primary cosmic ray depends on the accurate measurement of the atmospheric conditions in the region of EAS development. The Atmospheric Monitoring (AM) system of JEM-EUSO will host a LIDAR, operating in the UV band, and an Infrared camera to monitor the cloud cover in the JEM-EUSO Field of View, in order to be sensitive to clouds with an optical depth tau a parts per thousand yen 0.15 and to measure the cloud top altitude with an accuracy of 500 m and an altitude resolution of 500 m.
Keywords: Ultra high energy cosmic rays; Atmospheric monitoring; IR camera; LIDAR

THE Be/X-RAY BINARY SWIFT J1626.6-5156 AS A VARIABLE CYCLOTRON LINE SOURCE - Decesar, Megan E.; Boyd, Patricia T.; Pottschmidt, Katja; Wilms, Jörn; Suchy, Slawomir; Miller, M. Coleman (Astrophysical Journal, 2013)
Swift J1626.6-5156 is a Be/X-ray binary that was in outburst from 2005 December until 2008 November. We have examined Rossi X-ray Timing Explorer/Proportional Counter Array (PCA) and High Energy X-ray Timing Explorer spectra of three long observations of this source taken early in its outburst, when the PCA 2-20 keV count rate was > 70 counts s(-1) PCU-1, as well as several combined observations from different stages of the outburst. The spectra are best fit with an absorbed cutoff power law with a similar to 6.4 keV iron emission line and a Gaussian optical depth absorption line at similar to 10 keV. We present strong evidence that this absorption-like feature is a cyclotron resonance scattering feature, making Swift J1626.6-5156 a new candidate cyclotron line source. The redshifted energy of similar to 10 keV implies a magnetic field strength of similar to 8.6(1 + z) x 10(11) G in the region of the accretion column close to the magnetic poles where the cyclotron line is produced. Analysis of phase-averaged spectra spanning the duration of the outburst suggests a possible positive correlation between the fundamental cyclotron energy and source luminosity. Phase-resolved spectroscopy from a long observation reveals a variable cyclotron line energy, with phase dependence similar to a variety of other pulsars, as well as the first harmonic of the fundamental cyclotron line.
Keywords: magnetic fields; stars: individual (Swift J1626.6-5156); stars: neutron; X-rays: binaries

The broadband spectrum of cygnus X-1 - Wilms, Jörn; et al. (2007)
The Black Hole (BH) binary Cygnus X-1 has been observed simultaneously by INTEGRAL, RXTE, and XMM-Newton for four times in November and December 2004, when Cyg X-1 became first observable with XMM-Newton. During these observations the source was found in one of its transitional states between the hard state and the soft state. We obtained a high signal to noise spectrum of Cyg X-1 from 3 keV to 1 MeV which allows us to put constraints on the nature of the Comptonizing plasma by modeling the continuum with Comptonization models as eqpair [3]. Using XMM-Newton we were also able to confirm the presence of a relativistically broadened Fe K alpha line.
Keywords: stars : individual (Cyg X-1); black hole physics

The broad iron K alpha line of Cygnus X-1 as seen by XMM-Newton in the EPIC-pn modified timing mode - Duro, Refiz; Dauser, Thomas; Wilms, Jörn; Pottschmidt, K.; Nowak, M. A.; Fritz, S.; Kendziorra, E.; Kirsch, M. G. F.; Reynolds, C. S.; Staubert, R. (Astronomy & Astrophysics, 2011)
We present the analysis of the broadened, flourescent iron K alpha line in simultaneous XMM-Newton and RXTE data from the black hole Cygnus X-1. The XMM-Newton data were taken in a modified version of the timing mode of the EPIC-pn camera. In this mode the lower energy threshold of the instrument is increased to 2.8 keV to avoid telemetry drop outs due to the brightness of the source, while at the same time preserving the signal-to-noise ratio in the FeK alpha band. We find that the best-fit spectrum consists of the sum of an exponentially cutoff power-law and relativistically smeared, ionized reflection. The shape of the broadened FeKa feature is due to strong Compton broadening combined with relativistic broadening. Assuming a standard, thin accretion disk, the black hole is close to rotating maximally.
Keywords: X-rays: binaries; black hole physics; gravitation

The causal connection between disc and power-law variability in hard state black hole X-ray binaries - Uttley, P.; Wilkinson, T.; Cassatella, P.; Wilms, Jörn; Pottschmidt, K.; Hanke, Manfred; Böck, Moritz (Monthly Notices of the Royal Astronomical Society, 2011)
We use the XMM-Newton EPIC-pn instrument in timing mode to extend spectral time-lag studies of hard state black hole X-ray binaries into the soft X-ray band. We show that variations of the disc blackbody emission substantially lead variations in the power-law emission, by tenths of a second on variability time-scales of seconds or longer. The large lags cannot be explained by Compton scattering but are consistent with time delays due to viscous propagation of mass accretion fluctuations in the disc. However, on time-scales less than a second the disc lags the power-law variations by a few milliseconds, consistent with the disc variations being dominated by X-ray heating by the power law, with the short lag corresponding to the light traveltime between the power-law emitting region and the disc. Our results indicate that instabilities in the accretion disc are responsible for continuum variability on time-scales of seconds or longer and probably also on shorter time-scales.
Keywords: accretion; accretion discs; X-rays: binaries; X-rays: individual: GX 339-4

The clumpy absorber in the high-mass X-ray binary Vela X-1 - Grinberg, Victoria; Hell, Natalie; El Mellah, I.; Neilsen, J.; Sander, A. A. C.; Leutenegger, M.; Furst, F.; Huenemoerder, D. P.; Kretschmar, Peter; Kühnel, Matthias; Martinez-Nunez, Silvia; Niu, Shu; et al. (Astronomy & Astrophysics, 2017)
Bright and eclipsing, the high-mass X-ray binary Vela X-1 offers a unique opportunity to study accretion onto a neutron star from clumpy winds of O/B stars and to disentangle the complex accretion geometry of these systems. In Chandra-HETGS spectroscopy at orbital phase similar to 0.25, when our line of sight towards the source does not pass through the large-scale accretion structure such as the accretion wake, we observe changes in overall spectral shape on timescales of a few kiloseconds. This spectral variability is, at least in part, caused by changes in overall absorption and we show that such strongly variable absorption cannot be caused by unperturbed clumpy winds of O/B stars. We detect line features from high and low ionization species of silicon, magnesium, and neon whose strengths and presence depend on the overall level of absorption. These features imply a co-existence of cool and hot gas phases in the system, which we interpret as a highly variable, structured accretion flow close to the compact object such as has been recently seen in simulations of wind accretion in high-mass X-ray binaries.
Keywords: X-rays: individuals: Vela X-1; X-rays: binaries; stars: winds; outflows; stars: massive

The column density towards LMC X-1 - Hanke, Manfred; Wilms, Jörn; Nowak, M. A.; Barragan, L.; Schulz, N. S. (Astronomy & Astrophysics, 2010)
We measure the neutral absorption towards the black hole X-ray binary system LMC X-1 from six archival soft X-ray spectra obtained with the gratings and/or CCD detectors on Chandra, XMM-Newton, and Swift. Four spectral models for the soft continuum are investigated. While the power law model may overestimate N-H considerably, the others give consistent results. Taking the lower metalicity of the Large Magellanic Cloud into account, we find equivalent hydrogen column densities of N-H = (1.0-1.3) x 10(22) cm(-2), with a systematic dependence on the orbital phase. This variation in the neutral absorption can nearly explain the orbital modulation of the soft X-ray flux recently detected with the All Sky Monitor (ASM) on the Rossi X-ray Timing Explorer (RXTE).
Keywords: X-rays: individuals: LMC X-1; X-rays: binaries; X-rays: ISM; galaxies: abundances

THE COMPLEX ACCRETION GEOMETRY OF GX 339-4 AS SEEN BY NuSTAR AND SWIFT - Fuerst, F.; Nowak, M. A.; Tomsick, J. A.; Miller, J. M.; Corbel, S.; Bachetti, Matteo; Boggs, S. E.; Christensen, F. E.; Craig, W. W.; Fabian, A. C.; Gandhi, P.; Grinberg, Victoria; et al. (Astrophysical Journal, 2015)
We present spectral analyses of five Nuclear Spectroscopic Telescope Array and Swift observations of GX 339-4 taken during a failed outburst during the summer of 2013. These observations cover Eddington luminosity fractions in the range approximate to 0.9%-6%. Throughout this outburst GX 339-4 stayed in the hard state and all five observations show similar X-ray spectra, with a hard power law with a photon index near 1.6, and significant contribution from reflection. Using simple reflection models we find unrealistically high iron abundances. Allowing for different photon indices for the continuum incident on the reflector relative to the underlying observed continuum results in a statistically better fit and reduced iron abundances. With a photon index around 1.3, the input power law on the reflector is significantly harder than that which is directly observed. We study the influence of different emissivity profiles and geometries and consistently find an improvement when using separate photon indices. The inferred inner accretion disk radius is strongly model dependent, but we do not find evidence for a truncation radius larger than 100 r(g) in any model. The data do not allow independent spin constraints, but the results are consistent with the literature (i.e., a > 0). Our best-fit models indicate an inclination angle in the range 40 degrees-60 degrees, consistent with limits on the orbital inclination but higher than reported in the literature using standard reflection models. The iron line around 6.4 keV is clearly broadened, and we detect a superimposed narrow core as well. This core originates from a fluorescent region outside the influence of the strong gravity of the black hole. Additionally, we discuss possible geometries.
Keywords: accretion; accretion disks; stars: black holes; X-rays: binaries; X-rays: individual (GX 339-4)

The cosmic ray shadow of the Moon observed with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Martit, J.; Basa, S.; Belhorma, B.; et al. (European Physical Journal C, 2018)
One of the main objectives of the ANTARES telescope is the search for point- like neutrino sources. Both the pointing accuracy and the angular resolution of the detector are important in this context and a reliableway to evaluate this performance is needed. In order to measure the pointing accuracy of the detector, one possibility is to study the shadow of the Moon, i. e. the deficit of the atmospheric muon flux from the direction of the Moon induced by the absorption of cosmic rays. Analysing the data taken between 2007 and 2016, theMoon shadow is observed with 3.5s statistical significance. The detector angular resolution for downwardgoing muons is 0.73. +/- 0.14.. The resulting pointing performance is consistent with the expectations. An independent check of the telescope pointing accuracy is realised with the data collected by a shower array detector onboard of a ship temporarily moving around the ANTARES location.

The design of the wide field monitor for LOFT - Brandt, Soren; Hernanz, Margarita; Alvarez, L.; Argan, A.; Artigues, B.; Azzarello, P.; Barret, D.; Bozzo, E.; Budtz-Jorgensen,; Campana, Riccardo; Cros, A.; Del Monte, E.; et al. (2014)
LOFT (Large Observatory For x-ray Timing) is one of the ESA M3 missions selected within the Cosmic Vision program in 2011 to carry out an assessment phase study and compete for a launch opportunity in 2022-2024. The phase-A studies of all M3 missions were completed at the end of 2013. LOFT is designed to carry on-board two instruments with sensitivity in the 2-50 keV range: a 10 m(2) class Large Area Detector (LAD) with a < 1 degrees collimated FoV and a wide field monitor (WFM) making use of coded masks and providing an instantaneous coverage of more than 1/3 of the sky. The prime goal of the WFM will be to detect transient sources to be observed by the LAD. However, thanks to its unique combination of a wide field of view (FoV) and energy resolution (better than 500 eV), the WFM will be also an excellent monitoring instrument to study the long term variability of many classes of X-ray sources. The WFM consists of 10 independent and identical coded mask cameras arranged in 5 pairs to provide the desired sky coverage. We provide here an overview of the instrument design, configuration, and capabilities of the LOFT WFM. The compact and modular design of the WFM could easily make the instrument concept adaptable for other missions.
Keywords: ESA Missions; LOFT Wide Field Monitor; Silicon Drift Detectors; Coded Mask Imaging; Compact Objects; Gamma Ray Bursts

THE DOUBLE-DEGENERATE NUCLEUS OF THE PLANETARY NEBULA TS 01: A CLOSE BINARY EVOLUTION SHOWCASE - Tovmassian, Gagik; Yungelson, Lev; Rauch, Thomas; Suleimanov, Valery; Napiwotzki, Ralf; Stasinska, Grazyna; Tomsick, John; Wilms, Jörn; Morisset, Christophe; Pena, Miriam; Richer, Michael G. (Astrophysical Journal, 2010)
We present a detailed investigation of SBS 1150+599A, a close binary star hosted by the planetary nebula PN G135.9+55.9 (TS 01). The nebula, located in the Galactic halo, is the most oxygen-poor known to date and is the only one known to harbor a double degenerate core. We present XMM-Newton observations of this object, which allowed the detection of the previously invisible component of the binary core, whose existence was inferred so far only from radial velocity (RV) and photometric variations. The parameters of the binary system were deduced from a wealth of information via three independent routes using the spectral energy distribution (from the infrared to X-rays), the light and RV curves, and a detailed model atmosphere fitting of the stellar absorption features of the optical/UV component. We find that the cool component must have a mass of 0.54 +/- 0.2 M(circle dot), an average effective temperature, T(eff), of 58,000 +/- 3000 K, a mean radius of 0.43 +/- 0.3 R(circle dot), a gravity, log g = 5.0 +/- 0.3, and that it nearly fills its Roche lobe. Its surface elemental abundances are found to be: 12 + log He/H = 10.95 +/- 0.04 dex, 12 + log C/H = 7.20 +/- 0.3 dex, 12 + log N/H < 6.92, and 12 + log O/H < 6.80, in overall agreement with the chemical composition of the planetary nebula. The hot component has T(eff) = 160-180 kK, a luminosity of about similar to 10(4) L(circle dot) and a radius slightly larger than that of a white dwarf. It is probably bloated and heated as a result of intense accretion and nuclear burning on its surface in the past. The total mass of the binary system is very close to the Chandrasekhar limit. This makes TS 01 one of the best Type Ia supernova progenitor candidates. We propose two possible scenarios for the evolution of the system up to its present stage.
Keywords: binaries: close; planetary nebulae: individual (PN G135.9+55.9; TS 01); stars: AGB and post-AGB; stars: atmospheres; stars: evolution; stars: individual (SBS1150+599A)

The dust-scattering component of X-ray extinction: Effects on continuum fitting and high-resolution absorption edge structure - Corrales, L. R.; Garcia, J.; Wilms, Jörn; Baganoff, F. (Monthly Notices of the Royal Astronomical Society, 2016)
Small angle scattering by dust grains causes a significant contribution to the total interstellar extinction for any X-ray instrument with sub-arcminute resolution (Chandra, Swift, XMM-Newton). However, the dust-scattering component is not included in the current absorption models: phabs, TBabs, and TBnew. We simulate a large number of Chandra spectra to explore the bias in the spectral fit and N measurements obtained without including extinction from dust scattering. We find that without incorporating dust scattering, the measured N will be too large by a baseline level of 25 per cent. This effect is modulated by the imaging resolution of the telescope, because some amount of unresolved scattered light will be captured within the aperture used to extract point source information. In high-resolution spectroscopy, dust scattering significantly enhances the total extinction optical depth and the shape of the photoelectric absorption edges. We focus in particular on the Fe-L edge at 0.7 keV, showing that the total extinction template fits well to the high-resolution spectrum of three X-ray binaries from the Chandra archive: GX 9+9, XTE J1817-330, and Cyg X-1. In cases where dust is intrinsic to the source, a covering factor based on the angular extent of the dusty material must be applied to the extinction curve, regardless of angular imaging resolution. This approach will be particularly relevant for dust in quasar absorption line systems and might constrain clump sizes in active galactic nuclei.
Keywords: Absorption lines; Extinction-quasars; Scattering-dust; X-rays: Binaries; X-rays: ISM

The effects of high density on the X-ray spectrum reflected from accretion discs around black holes - Garcia, Javier A.; Fabian, Andrew C.; Kallman, Timothy R.; Dauser, Thomas; Parker, Michael L.; Mcclintock, Jeffrey E.; Steiner, James F.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2016)
Current models of the spectrum of X-rays reflected from accretion discs around black holes and other compact objects are commonly calculated assuming that the density of the disc atmosphere is constant within several Thomson depths from the irradiated surface. An important simplifying assumption of these models is that the ionization structure of the gas is completely specified by a single, fixed value of the ionization parameter ξ, which is the ratio of the incident flux to the gas density. The density is typically fixed at ne = 10 cm. Motivated by observations, we consider higher densities in the calculation of the reflected spectrum. We show by computing model spectra for ne ≥ 10 cm that high-density effects significantly modify reflection spectra. The main effect is to boost the thermal continuum at energies ≥2 keV. We discuss the implications of these results for interpreting observations of both active galactic nuclei and black hole binaries. We also discuss the limitations of our models imposed by the quality of the atomic data currently available.
Keywords: Accretion; accretion discs; Atomic processes; Line: formation; Radiative transfer; Relativistic processes; X-rays: general

The enhanced X-ray Timing and Polarimetry mission-eXTP - Zhang, Shuangnan; Santangelo, Andrea; Feroci, Marco; Xu, Yupeng; Lu, Fangjun; Chen, Yong; Feng, Hua; Zhang, Shu; Brandt, Soren; Hernanz, Margarita; Baldini, Luca; Bozzo, Enrico; et al. (Science China-Physics Mechanics & Astronomy, 2019)
In this paper we present the enhanced X-ray Timing and Polarimetry mission-eXTP. eXTP is a space science mission designed to study fundamental physics under extreme conditions of density, gravity and magnetism. The mission aims at determining the equation of state of matter at supra-nuclear density, measuring effects of QED, and understanding the dynamics of matter in strong-field gravity. In addition to investigating fundamental physics, eXTP will be a very powerful observatory for astrophysics that will provide observations of unprecedented quality on a variety of galactic and extragalactic objects. In particular, its wide field monitoring capabilities will be highly instrumental to detect the electro-magnetic counterparts of gravitational wave sources. The paper provides a detailed description of: (1) the technological and technical aspects, and the expected performance of the instruments of the scientific payload; (2) the elements and functions of the mission, from the spacecraft to the ground segment.
CRIS-Team WoS Importer:2019-03-08

The eROSITA X-ray telescope on SRG - Predehl, P.; Andritschke, R.; Arefiev, V.; Babyshkin, V.; Batanov, O.; Becker, W.; Böhringer, H.; Bogomolov, A.; Boller, T.; Borm, K.; Bornemann, W.; Bräuninger, H.; et al. (Astronomy & Astrophysics, 2021)
eROSITA (extended ROentgen Survey with an Imaging Telescope Array) is the primary instrument on the Spectrum-Roentgen-Gamma (SRG) mission, which was successfully launched on July 13, 2019, from the Baikonour cosmodrome. After the commissioning of the instrument and a subsequent calibration and performance verification phase, eROSITA started a survey of the entire sky on December 13, 2019. By the end of 2023, eight complete scans of the celestial sphere will have been performed, each lasting six months. At the end of this program, the eROSITA all-sky survey in the soft X-ray band (0.2-2.3 keV) will be about 25 times more sensitive than the ROSAT All-Sky Survey, while in the hard band (2.3-8 keV) it will provide the first ever true imaging survey of the sky. The eROSITA design driving science is the detection of large samples of galaxy clusters up to redshifts z > 1 in order to study the large-scale structure of the universe and test cosmological models including Dark Energy. In addition, eROSITA is expected to yield a sample of a few million AGNs, including obscured objects, revolutionizing our view of the evolution of supermassive black holes. The survey will also provide new insights into a wide range of astrophysical phenomena, including X-ray binaries, active stars, and diffuse emission within the Galaxy. Results from early observations, some of which are presented here, confirm that the performance of the instrument is able to fulfil its scientific promise. With this paper, we aim to give a concise description of the instrument, its performance as measured on ground, its operation in space, and also the first results from in-orbit measurements.
CRIS-Team Scopus Importer:2021-03-19
Keywords: Dark energy; Space vehicles: instruments; Surveys; X-rays: general

The EUSO-Balloon pathfinder - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, Anna; Arai, Y.; Asano, K.; Ave Pernas, M.; Barrillon, P.; Batsch, T.; et al. (Experimental Astronomy, 2015)
EUSO-Balloon is a pathfinder for JEM-EUSO, the Extreme Universe Space Observatory which is to be hosted on-board the International Space Station. As JEM-EUSO is designed to observe Ultra-High Energy Cosmic Rays (UHECR)-induced Extensive Air Showers (EAS) by detecting their ultraviolet light tracks "from above", EUSO-Balloon is a nadir-pointing UV telescope too. With its Fresnel Optics and Photo-Detector Module, the instrument monitors a 50 km(2) ground surface area in a wavelength band of 290-430 nm, collecting series of images at a rate of 400,000 frames/sec. The objectives of the balloon demonstrator are threefold: a) perform a full end-to-end test of a JEM-EUSO prototype consisting of all the main subsystems of the space experiment, b) measure the effective terrestrial UV background, with a spatial and temporal resolution relevant for JEM-EUSO. c) detect tracks of ultraviolet light from near space for the first time. The latter is a milestone in the development of UHECR science, paving the way for any future space-based UHECR observatory. On August 25, 2014, EUSO-Balloon was launched from Timmins Stratospheric Balloon Base (Ontario, Canada) by the balloon division of the French Space Agency CNES. From a float altitude of 38 km, the instrument operated during the entire astronomical night, observing UV-light from a variety of ground-covers and from hundreds of simulated EASs, produced by flashers and a laser during a two-hour helicopter under-flight.
Keywords: UHECR; Air-fluorescence; JEM-EUSO; Balloon experiment

The evolution of structure and feedback with Arcus - Brenneman, Laura W.; Smith, Randall K.; Bregman, J.; Kaastra, J.; Brickhouse, N.; Allured, R.; Foster, A.; Wolk, S.; Wilms, Jörn; Valencic, L.; Willingale, R.; Grant, C.; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
Arcus is a NASA/MIDEX mission under development in response to the anticipated 2016 call for proposals. It is a freeflying, soft X-ray grating spectrometer with the highest-ever spectral resolution in the 8-51 Å (0.24 - 1.55 keV) energy range. The Arcus bandpass includes the most sensitive tracers of diffuse million-degree gas: spectral lines from O VII and O VIII, H- and He-like lines of C, N, Ne and Mg, and unique density- and temperature-sensitive lines from Si and Fe ions. These capabilities enable an advance in our understanding of the formation and evolution of baryons in the Universe that is unachievable with any other present or planned observatory. The mission will address multiple key questions posed in the Decadal Survey and NASA's 2013 Roadmap: How do baryons cycle in and out of galaxies? How do black holes and stars influence their surroundings and the cosmic web via feedback? How do stars, circumstellar disks and exoplanet atmospheres form and evolve? Arcus data will answer these questions by leveraging recent developments in off-plane gratings and silicon pore optics to measure X-ray spectra at high resolution from a wide range of sources within and beyond the Milky Way. CCDs with strong Suzaku heritage combined with electronics based on the Swift mission will detect the dispersed X-rays. Arcus will support a broad astrophysical research program, and its superior resolution and sensitivity in soft X-rays will complement the forthcoming Athena calorimeter, which will have comparably high resolution above 2 keV.
Keywords: Accretion; Active galaxies; Gratings; Large-scale structure; Outflows; Spectroscopy; Stars; X-rays

The EXTraS project: Exploring the X-ray transient and variable sky - De Luca, A.; Salvaterra, R.; Belfiore, A.; Carpano, S.; D'Agostino, D.; Haberl, F.; Israel, G. L.; Law-Green, D.; Lisini, G.; Marelli, M.; Novara, G.; Read, A. M.; et al. (Astronomy & Astrophysics, 2021)
Temporal variability in flux and spectral shape is ubiquitous in the X-ray sky and carries crucial information about the nature and emission physics of the sources. The EPIC instrument on board the XMM-Newton observatory is the most powerful tool for studying variability even in faint sources. Each day, it collects a large amount of information about hundreds of new serendipitous sources, but the resulting huge (and growing) dataset is largely unexplored in the time domain. The project called Exploring the X-ray transient and variable sky (EXTraS) systematically extracted all temporal domain information in the XMM-Newton archive. This included a search and characterisation of variability, both periodic and aperiodic, in hundreds of thousands of sources spanning more than eight orders of magnitude in timescale and six orders of magnitude in flux, and a search for fast transients that were missed by standard image analysis. All results, products, and software tools have been released to the community in a public archive. A science gateway has also been implemented to allow users to run the EXTraS analysis remotely on recent XMM datasets. We give details on the new algorithms that were designed and implemented to perform all steps of EPIC data analysis, including data preparation, source and background modelling, generation of time series and power spectra, and search for and characterisation of different types of variabilities. We describe our results and products and give information about their basic statistical properties and advice on their usage. We also describe available online resources. The EXTraS database of results and its ancillary products is a rich resource for any kind of investigation in almost all fields of astrophysics. Algorithms and lessons learnt from our project are also a very useful reference for any current and future experiment in the time domain.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Astronomical databases: miscellaneous; Catalogs; Methods: data analysis; X-rays: general

THE FIRST COMBINED SEARCH for NEUTRINO POINT-SOURCES in the SOUTHERN HEMISPHERE with the ANTARES and ICECUBE NEUTRINO TELESCOPES - Adrian-Martinez, S.; Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bormuth, R.; et al. (Astrophysical Journal, 2016)
We present the results of searches for point-like sources of neutrinos based on the first combined analysis of data from both the ANTARES and IceCube neutrino telescopes. The combination of both detectors, which differ in size and location, forms a window in the southern sky where the sensitivity to point sources improves by up to a factor of 2 compared with individual analyses. Using data recorded by ANTARES from 2007 to 2012, and by IceCube from 2008 to 2011, we search for sources of neutrino emission both across the southern sky and from a preselected list of candidate objects. No significant excess over background has been found in these searches, and flux upper limits for the candidate sources are presented for E and E power-law spectra with different energy cut-offs.
Keywords: astroparticle physics; neutrinos

The first GeV flare of the radio-loud narrow-line Seyfert 1 galaxy PKS 2004-447 - Gokus, Andrea; Paliya, V. S.; Wagner, S. M.; Buson, S.; D'Ammando, F.; Edwards, P. G.; Kadler, M.; Meyer, M.; Ojha, R.; Stevens, J.; Wilms, Jörn (Astronomy & Astrophysics, 2021)
Context. On 2019 October 25, the Fermi-Large Area Telescope observed the first ever γ-ray flare from the radio-loud narrow-line Seyfert 1 galaxy PKS 2004-447 (z = 0.24). Prior to this discovery, only four sources of this type had shown a flare at gigaelectronvolt energies. Aims. We report on follow-up observations in the radio, optical-UV, and X-ray bands that were performed by ATCA, the Neil Gehrels Swift Observatory, XMM-Newton, and NuSTAR, respectively, and analyse these multi-wavelength data with a one-zone leptonic model in order to understand the physical mechanisms that were responsible for the flare. Methods. We study the source's variability across all energy bands and additionally produce γ-ray light curves with different time binnings to study the variability in γ-rays on short timescales during the flare. We examine the combined X-ray spectrum from 0.5 to 50 keV by describing the spectral shape with an absorbed power law. We analyse multi-wavelength datasets before, during, and after the flare and compare these with a low activity state of the source by modelling the respective spectral energy distributions (SEDs) with a one-zone synchrotron inverse Compton radiative model. Finally, we compare the variability and the SEDs to γ-ray flares previously observed from other γ-loud narrow-line Seyfert 1 galaxies. Results. At γ-ray energies (0.1-300 GeV) the flare reached a maximum flux of (1.3 ± 0.2) × 10-6 ph cm-2 s-1 in daily binning and a total maximum flux of (2.7 ± 0.6) × 10-6 ph cm-2 s-1 when a 3 h binning was used. With a photon index of Γ0.1-300 GeV = 2.42 ± 0.09 during the flare, this corresponds to an isotropic γ-ray luminosity of (2.9 ± 0.8) × 1047 erg s-1. The γ-ray, X-ray, and optical-UV light curves that cover the end of September to the middle of November show significant variability, and we find indications for flux-doubling times of ∼2.2 h at γ-ray energies. The soft X-ray excess, which is observed for most narrow-line Seyfert 1 galaxies, is not visible in this source. During the flare, the SED exhibits large Compton dominance. While the increase in the optical-UV range can be explained by enhanced synchrotron emission, the elevated γ-ray flux can be accounted for by an increase in the bulk Lorentz factor of the jet, similar to that observed for other flaring γ-ray blazars.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Galaxies: active; Galaxies: jets; Gamma rays: galaxies; Quasars: individual: PKS 2004-447

The First NuSTAR Observation of 4U 1538-522: Updated Orbital Ephemeris and a Strengthened Case for an Evolving Cyclotron Line Energy - Hemphill, Paul B.; Rothschild, Richard E.; Cheatham, Diana M.; Furst, Felix; Kretschmar, Peter; Kühnel, Matthias; Pottschmidt, Katja; Staubert, Ruediger; Wilms, Jörn; Wolff, Michael T. (Astrophysical Journal, 2019)
We have performed a comprehensive spectral and timing analysis of the first NuSTAR observation of the high-mass X-ray binary 4U 1538-522. The observation covers the X-ray eclipse of the source, plus the eclipse ingress and egress. We use the new measurement of the mid-eclipse time to update the orbital parameters of the system and find marginally significant evolution in the orbital period, with (P) over dot(orb)/P-orb = (-0.95 +/- 0.37) x 10(-6) yr(-1). The cyclotron line energy is found to be approximately 1.2 keV higher than RXTE measurements from 1997 to 2003, in line with the increased energy observed by Suzaku in 2012 and strengthening the case for secular evolution of 4U 1538-522's CRSF. We additionally characterize the behavior of the iron fluorescence and emission lines and line-of-sight absorption as the source moves into and out of eclipse.
Keywords: accretion; accretion disks; binaries: eclipsing; stars: individual (QV Nor); stars: magnetic field; X-rays: binaries X-rays: individual (4U 1538-522)

The Galactic LMXB Population and the Galactic Centre Region - Sazonov, S.; Paizis, A.; Bazzano, A.; Chelovekov, I.; Khabibullin, I.; Postnov, K.; Mereminskiy, I.; Fiocchi, M.; Bélanger, G.; Bird, A. J.; Bozzo, E.; Chenevez, J.; et al. (New Astronomy Reviews, 2020)
Seventeen years of hard X-ray observations with the instruments of the INTEGRAL observatory, with a focus on the Milky Way and in particular on the Galactic Centre region, have provided a unique database for exploration of the Galactic population of low-mass X-ray binaries (LMXBs). Our understanding of the diverse energetic phenomena associated with accretion of matter onto neutron stars and black holes has greatly improved. We review the large variety of INTEGRAL based results related to LMXBs. In particular, we discuss the spatial distribution of LMXBs over the Galaxy and their X-ray luminosity function as well as various physical phenomena associated with Atoll and Z sources, bursters, symbiotic X-ray binaries, ultracompact X-ray binaries and persistent black hole LMXBs. We also present an up-to-date catalogue of confirmed LMXBs detected by INTEGRAL, which comprises 166 objects. Last but not least, the long-term monitoring of the Galactic Centre with INTEGRAL has shed light on the activity of Sgr A* in the recent past, confirming previous indications that our supermassive black hole experienced a major accretion episode just 100 years ago. This exciting topic is covered in this review too.
CRIS-Team Scopus Importer:2020-08-28
Keywords: Accretion; Black holes; INTEGRAL observatory; Neutron stars; Sgr A*; X-ray binaries

The gamma-ray emitting radio-loud narrow-line Seyfert 1 galaxy PKS 2004-447: II. the radio view - Schulz, R.; Kreikenbohm, A.; Kadler, M.; Ojha, R.; Ros, E.; Stevens, J.; Edwards, P. G.; Carpenter, B.; Elsaesser, D.; Gehrels, N.; Großberger, Christoph; Hase, H.; et al. (Astronomy & Astrophysics, 2016)
Context. Γ-ray-detected radio-loud narrow-line Seyfert 1 (γ-NLS1) galaxies constitute a small but interesting sample of the γ-ray-loud AGN. The radio-loudest γ-NLS1 known, PKS 2004-447, is located in the southern hemisphere and is monitored in the radio regime by the multiwavelength monitoring programme TANAMI. Aims. We aim for the first detailed study of the radio morphology and long-term radio spectral evolution of PKS 2004-447, which are essential for understanding the diversity of the radio properties of γ-NLS1s. Methods. The TANAMI VLBI monitoring program uses the Australian Long Baseline Array (LBA) and telescopes in Antarctica, Chile, New Zealand, and South Africa to monitor the jets of radio-loud active galaxies in the southern hemisphere. Lower resolution radio flux density measurements at multiple radio frequencies over four years of observations were obtained with the Australia Telescope Compact Array (ATCA). Results. The TANAMI VLBI image at 8.4 GHz shows an extended one-sided jet with a dominant compact VLBI core. Its brightness temperature is consistent with equipartition, but it is an order of magnitude below other γ-NLS1s with the sample value varying over two orders of magnitude. We find a compact morphology with a projected large-scale size < 11 kpc and a persistent steep radio spectrum with moderate flux-density variability. Conclusions. PKS 2004-447 appears to be a unique member of the γ-NLS1 sample. It exhibits blazar-like features, such as a flat featureless X-ray spectrum and a core-dominated, one-sided parsec-scale jet with indications for relativistic beaming. However, the data also reveal properties atypical for blazars, such as a radio spectrum and large-scale size consistent with compact-steep-spectrum (CSS) objects, which are usually associated with young radio sources. These characteristics are unique among all γ-NLS1s and extremely rare among γ-ray-loud AGN.
Keywords: Galaxies: active; Galaxies: individual: PKS 2004-447; Galaxies: jets; Radio continuum: galaxies; Techniques: interferometric

The gamma-ray emitting radio-loud narrow-line Seyfert 1 galaxy PKS 2004-447. I. The X-ray View - Kreikenbohm, A.; Schulz, R.; Kadler, Matthias; Wilms, Jörn; Markowitz, Alex; Chang, C. S.; Carpenter, B.; Elsaesser, D.; Gehrels, N.; Mannheim, K.; Mueller, C.; Ojha, R.; et al. (Astronomy & Astrophysics, 2016)
As part of the TANAMI multiwavelength progam, we discuss new X-ray observations of the γ-ray and radio-loud narrow line Seyfert 1 galaxy (γ-NLS1) PKS 2004-447. The active galaxy is a member of a small sample of radio-loud NLS1s detected in γ-rays by the Fermi Large Area Telescope. It st and s out for being the radio-loudest and the only southern-hemisphere source in this sample. We present results from our X-ray monitoring program comprised of Swift snapshot observations from 2012 through 2014 and two new X-ray observations with XMM-Newton in 2012. Supplemented by archival data from 2004 and 2011, our data set allows for a careful analysis of the X-ray spectrum and variability of this peculiar source. The (0.5-10) keV spectrum is described well by a power law (Γ ∼ 1.6), which can be interpreted as non-thermal emission from a relativistic jet. The source exhibits moderate flux variability on timescales of both months and years. Correlated brightness variations in the (0.5-2) keV and (2-10) keV b and s are explained by a single variable spectral component, such as the one from the jet. A possible soft excess seen in the data from 2004 cannot be confirmed by the new XMM-Newton observations taken during low-flux states. Any contribution to the total flux in 2004 is less than 20% of the power-law component. The (0.5-10) keV luminosities of PKS 2004-447 are in the range of (0.5-2.7) × 10 erg s. A comparison of the X-ray properties among the known γ-NLS1 galaxies shows that in four out of five cases the X-ray spectrum is dominated by a flat power law without intrinsic absorption. These objects are moderately variable in their brightness, while spectral variability is observed in at least two sources. The major difference across the X-ray spectra of γ-NLS1s is the luminosity, which spans a range of almost two orders of magnitude from 10 erg s to 10 erg s in the (0.5-10) keV b and .
Keywords: galaxies: active; galaxies: individual: PKS 2004-447; galaxies: jets; galaxies: Seyfert; quasars: general; X-rays: general

The giant outburst of 4U 0115+634 in 2011 with Suzaku and RXTE: Minimizing cyclotron line biases - Kühnel, Matthias; Kreykenbohm, Ingo; Ferrigno, Carlo; Pottschmidt, Katja; Marcu-Cheatham, Diana M.; Fuerst, Felix; Rothschild, Richard E.; Kretschmar, Peter; Klochkov, Dmitry; Hemphill, Paul; Hertel, Dominik; Müller, Sebastian; et al. (Astronomy & Astrophysics, 2020)
We present an analysis of X-ray spectra of the high-mass X-ray binary 4U 0115+634 as observed with Suzaku and RXTE in 2011 July, during the fading phase of a giant X-ray outburst. We used a continuum model consisting of an absorbed cutoff power law and an ad hoc Gaussian emission feature centered around 8.5 keV, which we attribute to cyclotron emission. Our results are consistent with a fundamental cyclotron absorption line centered at similar to 10.2 keV for all observed flux ranges. At the same time we rule out significant influence of the 8.5 kev Gaussian on the parameters of the cyclotron resonant scattering feature, which are not consistent with the cyclotron line energies or the depths of previously reported flux-dependent descriptions. We also show that some continuum models can lead to artificial line-like residuals in the analyzed spectra, which are then misinterpreted as unphysically strong cyclotron lines. Specifically, our results do not support the existence of a previously claimed additional cyclotron feature at similar to 15 keV. Apart from these features, we find for the first time evidence for a He-like FeXXV emission line at similar to 6.7 keV and weak H-like FeXXVI emission close to similar to 7.0 keV.
CRIS-Team WoS Importer:2020-03-13

The goodness of simultaneous fits in ISIS - Kühnel, Matthias; Falkner, Sebastian; Großberger, Christoph; Ballhausen, Ralf; Dauser, Thomas; Schwarm, Fritz-Walter; Kreykenbohm, Ingo; Nowak, Michael A.; Pottschmidt, Katja; Ferrigno, Carlo; Rothschild, Richard E.; Martínez-Núñez, Silvia; et al. (Acta Polytechnica, 2016)
In a previous work, we introduced a tool for analyzing multiple datasets simultaneously, which has been implemented into ISIS. This tool was used to fit many spectra of X-ray binaries. However, the large number of degrees of freedom and individual datasets raise an issue about a good measure for a simultaneous fit quality. We present three ways to check the goodness of these fits: we investigate the goodness of each fit in all datasets, we define a combined goodness exploiting the logical structure of a simultaneous fit, and we stack the fit residuals of all datasets to detect weak features. These tools are applied to all RXTE-spectra from GRO 1008−57, revealing calibration features that are not detected significantly in any single spectrum. Stacking the residuals from the best-fit model for the Vela X-1 and XTE J1859+083 data evidences fluorescent emission lines that would have gone undetected otherwise.
Keywords: Data analysis; Multiple datasets; X-rays binaries

The high energy Universe at ultra-high resolution: the power and promise of X-ray interferometry - Uttley, Phil; Hartog, Roland Den; Bambi, Cosimo; Barret, Didier; Bianchi, Stefano; Bursa, Michal; Cappi, Massimo; Casella, Piergiorgio; Cash, Webster; Costantini, Elisa; Dauser, Thomas; Trigo, Maria Diaz; et al. (Experimental Astronomy, 2021)
We propose the development of X-ray interferometry (XRI), to reveal the Universe at high energies with ultra-high spatial resolution. With baselines which can be accommodated on a single spacecraft, XRI can reach 100 μ as resolution at 10 Å (1.2 keV) and 20 μ as at 2 Å (6 keV), enabling imaging and imaging-spectroscopy of (for example) X-ray coronae of nearby accreting supermassive black holes (SMBH) and the SMBH ‘shadow’; SMBH accretion flows and outflows; X-ray binary winds and orbits; stellar coronae within ∼ 100 pc and many exoplanets which transit across them. For sufficiently luminous sources XRI will resolve sub-pc scales across the entire observable Universe, revealing accreting binary SMBHs and enabling trigonometric measurements of the Hubble constant with X-ray light echoes from quasars or explosive transients. A multi-spacecraft ‘constellation’ interferometer would resolve well below 1 μ as, enabling SMBH event horizons to be resolved in many active galaxies and the detailed study of the effects of strong field gravity on the dynamics and emission from accreting gas close to the black hole.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Instrumentation; Interferometry; X-ray astronomy

The high energy X-ray probe (HEX-P): instrument and mission profile - Madsen, Kristin K.; García, Javier A.; Stern, Daniel; Amini, Rashied; Basso, Stefano; Coutinho, Diogo; Grefenstette, Brian W.; Kenyon, Steven; Moretti, Alberto; Morrissey, Patrick; Nandra, Kirpal; Pareschi, Giovanni; et al. (Frontiers in Astronomy and Space Sciences, 2024)
The High Energy X-ray Probe (HEX-P) is a proposed NASA probe-class mission that combines the power of high angular resolution with a broad X-ray bandpass to provide the necessary leap in capabilities to address the important astrophysical questions of the next decade. HEX-P achieves breakthrough performance by combining technologies developed by experienced international partners. To meet the science goals, the payload consists of a suite of co-aligned X-ray telescopes designed to cover the 0.2–80 keV bandpass. The High Energy Telescope (HET) has an effective bandpass of 2–80 keV, and the Low Energy Telescope (LET) has an effective bandpass of 0.2–20 keV. HEX-P will be launched into L1 to enable high observing efficiency, and the combination of bandpass and high observing efficiency delivers a powerful platform for broad science to serve a wide community. The baseline mission is 5 years, with 30% of the observing time dedicated to the PI-led program and 70% to a General Observer (GO) program. The General Observer program will be executed along with the PI-led program.
CRIS-Team Scopus Importer:2024-03-29
Keywords: future concept; HEX-P; instrumentation; mission; X-ray

The impact of crosstalk in the X-IFU instrument on Athena science cases - Den Hartog, R.; Peille, P.; Dauser, Thomas; Jackson, B.; Bandler, S.; Barret, D.; Brand, Thorsten; Den Herder, J. W.; Kiviranta, M.; Van Der Kuur, J.; Smith, S.; Wilms, Jörn (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
In this paper we present a first assessment of the impact of various forms of instrumental crosstalk on the science performance of the X-ray Integral Field Unit (X-IFU) on the Athena X-ray mission. This assessment is made using the SIXTE end-to-end simulator in the context of one of the more technically challenging science cases for the XIFU instrument. Crosstalk considerations may influence or drive various aspects of the design of the array of high-countrate Transition Edge Sensor (TES) detectors and its Frequency Domain Multiplexed (FDM) readout architecture.
Keywords: Athena; crosstalk; energy resolution; FDM; SIXTE; TES detectors; X-IFU

The infrared camera onboard JEM-EUSO - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The Extreme Universe Space Observatory on the Japanese Experiment Module (JEM-EUSO) on board the International Space Station (ISS) is the first space-based mission worldwide in the field of Ultra High-Energy Cosmic Rays (UHECR). For UHECR experiments, the atmosphere is not only the showering calorimeter for the primary cosmic rays, it is an essential part of the readout system, as well. Moreover, the atmosphere must be calibrated and has to be considered as input for the analysis of the fluorescence signals. Therefore, the JEM-EUSO Space Observatory is implementing an Atmospheric Monitoring System (AMS) that will include an IR-Camera and a LIDAR. The AMS Infrared Camera is an infrared, wide FoV, imaging system designed to provide the cloud coverage along the JEM-EUSO track and the cloud top height to properly achieve the UHECR reconstruction in cloudy conditions. In this paper, an updated preliminary design status, the results from the calibration tests of the first prototype, the simulation of the instrument, and preliminary cloud top height retrieval algorithms are presented.
Keywords: JEM-EUSO; Space observatory; IR-camera; Ultra-High Energy Cosmic Rays (UHECR)

The INTEGRAL view on black hole X-ray binaries - Motta, S. E.; Rodriguez, J.; Jourdain, E.; Del Santo, M.; Belanger, G.; Cangemi, F.; Grinberg, V.; Kajava, J. J.E.; Kuulkers, E.; Malzac, J.; Pottschmidt, K.; Roques, J. P.; et al. (New Astronomy Reviews, 2021)
INTEGRAL is an ESA mission in fundamental astrophysics that was launched in October 2002. It has been in orbit for over 18 years, during which it has been observing the high-energy sky with a set of instruments specifically designed to probe the emission from hard X-ray and soft γ-ray sources. This paper is devoted to the subject of black hole binaries, which are among the most important sources that populate the high-energy sky. We present a review of the scientific literature based on INTEGRAL data, which has significantly advanced our knowledge in the field of relativistic astrophysics. We briefly summarise the state-of-the-art of the study of black hole binaries, with a particular focus on the topics closer to the INTEGRAL science. We then give an overview of the results obtained by INTEGRAL and by other observatories on a number of sources of importance in the field. Finally, we review the main results obtained over the past 18 years on all the black hole binaries that INTEGRAL has observed. We conclude with a summary of the main contributions of INTEGRAL to the field, and on the future perspectives.
CRIS-Team Scopus Importer:2021-07-30
Keywords: Accretion disc; Binary stars; Black hole physics; Gamma-rays: General; Jets; X-rays: General

The JEM-EUSO mission: An introduction - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Pernas, M. Ave; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The Extreme Universe Space Observatory on board the Japanese Experiment Module of the International Space Station, JEM-EUSO, is being designed to search from space ultra-high energy cosmic rays. These are charged particles with energies from a few 10(19) eV to beyond 10(20) eV, at the very end of the known cosmic ray energy spectrum. JEM-EUSO will also search for extreme energy neutrinos, photons, and exotic particles, providing a unique opportunity to explore largely unknown phenomena in our Universe. The mission, principally based on a wide field of view (60 degrees) near-UV telescope with a diameter of similar to 2.5 m, will monitor the earth's atmosphere at night, pioneering the observation from space of the ultraviolet tracks (290-430 nm) associated with giant extensive air showers produced by ultra-high energy primaries propagating in the earth's atmosphere. Observing from an orbital altitude of similar to 400 km, the mission is expected to reach an instantaneous geometrical aperture of A (g e o) a parts per thousand yen 2 x 10(5) km(2) sr with an estimated duty cycle of similar to 20 %. Such a geometrical aperture allows unprecedented exposures, significantly larger than can be obtained with ground-based experiments. In this paper we briefly review the history of space-based search for ultra-high energy cosmic rays. We then introduce the special issue of Experimental Astronomy devoted to the various aspects of such a challenging enterprise. We also summarise the activities of the on-going JEM-EUSO program.
Keywords: Ultra-high energy cosmic rays; Neutrinos

The JEM-EUSO observation in cloudy conditions - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)
The JEM-EUSO (Extreme Universe Space Observatory on-board the Japanese Experiment Module) mission will conduct extensive air shower (EAS) observations on the International Space Station (ISS). Following the ISS orbit, JEM-EUSO will experience continuous changes in the atmospheric conditions, including cloud presence. The influence of clouds on space-based observation is, therefore, an important topic to investigate from both EAS property and cloud climatology points of view. In the present work, the impact of clouds on the apparent profile of EAS is demonstrated through the simulation studies, taking into account the JEM-EUSO instrument and properties of the clouds. These results show a dependence on the cloud-top altitude and optical depth of the cloud. The analyses of satellite measurements on the cloud distribution indicate that more than 60 % of the cases allow for conventional EAS observation, and an additional similar to 20 % with reduced quality. The combination of the relevant factors results in an effective trigger aperture of EAS observation similar to 72 %, compared to the one in the clear atmosphere condition.
Keywords: JEM-EUSO; Ultra-high energy cosmic ray; Extensive air shower

The Large Area Detector of LOFT: the Large Observatory for X-ray Timing - Zane, S.; Walton, D.; Kennedy, T.; Feroci, Marco; Den Herder, J. -W.; Ahangarianabhari, M.; Argan, A.; Azzarello, P.; Baldazzi, Giuseppe; Barbera, Marco; Barret, D.; Bertuccio, G.; et al. (2014)
LOFT (Large Observatory for X-ray Timing) is one of the five candidates that were considered by ESA as an M3 mission (with launch in 2022-2024) and has been studied during an extensive assessment phase. It is specifically designed to perform fast X-ray timing and probe the status of the matter near black holes and neutron stars. Its pointed instrument is the Large Area Detector (LAD), a 10 m(2)-class instrument operating in the 2-30keV range, which holds the capability to revolutionise studies of variability from X-ray sources on the millisecond time scales.The LAD instrument has now completed the assessment phase but was not down-selected for launch. However, during the assessment, most of the trade-offs have been closed leading to a robust and well documented design that will be re-proposed in future ESA calls. In this talk, we will summarize the characteristics of the LAD design and give an overview of the expectations for the instrument capabilities.
Keywords: X-ray; Timing; Compact Objects

The Large Observatory For x-ray Timing - Feroci, Marco; Den Herder, J. W.; Bozzo, E.; Barret, D.; Brandt, Soren; Hernanz, Margarita; Van Der Klis, M.; Pohl, M.; Santangelo, A.; Stella, L.; Watts, A.; Wilms, Jörn; et al. (2014)
The Large Observatory For x-ray Timing (LOFT) was studied within ESA M3 Cosmic Vision framework and participated in the final downselection for a launch slot in 2022-2024. Thanks to the unprecedented combination of effective area and spectral resolution of its main instrument, LOFT will study the behaviour of matter under extreme conditions, such as the strong gravitational field in the innermost regions of accretion flows close to black holes and neutron stars, and the supranuclear densities in the interior of neutron stars. The science payload is based on a Large Area Detector (LAD, 10 m(2) effective area, 2-30 keV, 240 eV spectral resolution, 1 degrees collimated field of view) and a Wide Field Monitor (WFM, 2-50 keV, 4 steradian field of view, 1 arcmin source location accuracy, 300 eV spectral resolution). The WFM is equipped with an on-board system for bright events (e.g. GRB) localization. The trigger time and position of these events are broadcast to the ground within 30 s from discovery. In this paper we present the status of the mission at the end of its Phase A study.
Keywords: X-ray timing; X-ray spectroscopy; X-ray imaging; compact objects; X-ray detectors; microchannel plates

The Large Observatory for X-ray Timing (LOFT) - Feroci, Marco; Stella, L.; Van Der Klis, M.; Courvoisier, T. J. -L.; Hernanz, Margarita; Hudec, R.; Santangelo, A.; Walton, D.; Zdziarski, A.; Barret, D.; Belloni, T.; Braga, J.; et al. (Experimental Astronomy, 2012)
High-time-resolution X-ray observations of compact objects provide direct access to strong-field gravity, to the equation of state of ultradense matter and to black hole masses and spins. A 10 m(2)-class instrument in combination with good spectral resolution is required to exploit the relevant diagnostics and answer two of the fundamental questions of the European Space Agency (ESA) Cosmic Vision Theme "Matter under extreme conditions", namely: does matter orbiting close to the event horizon follow the predictions of general relativity? What is the equation of state of matter in neutron stars? The Large Observatory For X-ray Timing (LOFT), selected by ESA as one of the four Cosmic Vision M3 candidate missions to undergo an assessment phase, will revolutionise the study of collapsed objects in our galaxy and of the brightest supermassive black holes in active galactic nuclei. Thanks to an innovative design and the development of large-area monolithic silicon drift detectors, the Large Area Detector (LAD) on board LOFT will achieve an effective area of similar to 12 m(2) (more than an order of magnitude larger than any spaceborne predecessor) in the 2-30 keV range (up to 50 keV in expanded mode), yet still fits a conventional platform and small/medium-class launcher. With this large area and a spectral resolution of < 260 eV, LOFT will yield unprecedented information on strongly curved spacetimes and matter under extreme conditions of pressure and magnetic field strength.
Keywords: Missions; X-ray timing; compact objects; black holes; neutron stars

The LOFT Ground Segment - Bozzo, E.; Antonelli, A.; Argan, A.; Barret, D.; Binko, P.; Brandt, Soren; Cavazzuti, E.; Courvoisier, T.; Den Herder, J. W.; Feroci, Marco; Ferrigno, C.; Giommi, Paolo; et al. (2014)
LOFT, the Large Observatory For X-ray Timing, was one of the ESA M3 mission candidates that completed their assessment phase at the end of 2013. LOFT is equipped with two instruments, the Large Area Detector (LAD) and the Wide Field Monitor (WFM). The LAD performs pointed observations of several targets per orbit (similar to 90 minutes), providing roughly similar to 80 GB of proprietary data per day (the proprietary period will be 12 months). The WFM continuously monitors about 1/3 of the sky at a time and provides data for about similar to 100 sources a day, resulting in a total of similar to 20 GB of additional telemetry. The LOFT Burst alert System additionally identifies on-board bright impulsive events (e.g., Gamma-ray Bursts, GRBs) and broadcasts the corresponding position and trigger time to the ground using a dedicated system of similar to 15 VHF receivers. All WFM data are planned to be made public immediately. In this contribution we summarize the planned organization of the LOFT ground segment (GS), as established in the mission Yellow Book1. We describe the expected GS contributions from ESA and the LOFT consortium. A review is provided of the planned LOFT data products and the details of the data flow, archiving and distribution. Despite LOFT was not selected for launch within the M3 call, its long assessment phase (>2 years) led to a very solid mission design and an efficient planning of its ground operations.
Keywords: LOFT; X-rays; ground segment; space mission

The LOFT mission concept: A status update - Feroci, M.; Bozzo, E.; Brandt, S.; Hernanz, M.; Van Der Klis, M.; Liu, L. P.; Orleanski, P.; Pohl, M.; Santangelo, A.; Schanne, S.; Stella, L.; Takahashi, T.; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
The Large Observatory For x-ray Timing (LOFT) is a mission concept which was proposed to ESA as M3 and M4 candidate in the framework of the Cosmic Vision 2015-2025 program. Thanks to the unprecedented combination of effective area and spectral resolution of its main instrument and the uniquely large field of view of its wide field monitor, LOFT will be able to study the behaviour of matter in extreme conditions such as the strong gravitational field in the innermost regions close to black holes and neutron stars and the supra-nuclear densities in the interiors of neutron stars. The science payload is based on a Large Area Detector (LAD, >8m effective area, 2-30 keV, 240 eV spectral resolution, 1 degree collimated field of view) and a Wide Field Monitor (WFM, 2-50 keV, 4 steradian field of view, 1 arcmin source location accuracy, 300 eV spectral resolution). The WFM is equipped with an on-board system for bright events (e.g., GRB) localization. The trigger time and position of these events are broadcast to the ground within 30 s from discovery. In this paper we present the current technical and programmatic status of the mission.
Keywords: Silicon detectors; spectroscopy; timing; X-ray astronomy

The Magnetospheres of (Accreting) Neutron Stars - Wilms, Jörn (2014)
I give an overview of the most important observational tools to study the magnetospheres of accreting neutron stars, with a focus on accreting neutron stars in high mass X-ray binary systems. Topics covered are the different types of accretion onto neutron stars and the structure of the accretion column, and how models for these can be tested with observations.

The next-generation X-ray galaxy survey with eROSITA - Basu-Zych, Antara R.; Hornschemeier, Ann E.; Haberl, Frank; Vulic, Neven; Wilms, Jörn; Zezas, Andreas; Kovlakas, Konstantinos; Ptak, Andrew; Dauser, Thomas (Monthly Notices of the Royal Astronomical Society, 2020)
eROSITA, launched on 2019 July 13, will be completing the first all-sky survey in the soft and medium X-ray band in nearly three decades. This 4-yr survey, finishing in late 2023, will present a rich legacy for the entire astrophysics community and complement upcoming multiwavelength surveys (with, e.g. the Large Synoptic Survey Telescope and the Dark Energy Survey). Besides the major scientific aim to study active galactic nuclei (AGNs) and galaxy clusters, eROSITAwill contribute significantly to X-ray studies of normal (i.e. not AGN) galaxies. Starting from multiwavelength catalogues, we measure star formation rates and stellar masses for 60 212 galaxies constrained to distances of 50-200 Mpc. We chose this distance range to focus on the relatively unexplored volume outside the local Universe, where galaxies will be largely spatially unresolved and probe a range of X-ray luminosities that overlap with the low luminosity and/or highly obscured AGN population. We use the most recent X-ray scaling relations as well as the on-orbit eROSITA instrument performance to predict the X-ray emission from XRBs and diffuse hot gas and to perform both an analytic prediction and an end-to-end simulation using the mission simulation software, sixte. We consider potential contributions from hidden AGN and comment on the impact of normal galaxies on the measurement of the faint end of the AGN luminosity function. We predict that the eROSITA 4-yr survey, will detect ≳15 000 galaxies (3σ significance) at 50-200 Mpc, which is ∼100 × more normal galaxies than detected in any X-ray survey to date.
CRIS-Team Scopus Importer:2020-12-04
Keywords: galaxies: Statistics; surveys; X-rays: Galaxies

The NuSTAR X-Ray Spectrum of Hercules X-1: A Radiation-dominated Radiative Shock - Wolff, Michael T.; Becker, Peter A.; Gottlieb, Amy M.; Fuerst, Felix; Hemphill, Paul B.; Marcu-Cheatham, Diana M.; Pottschmidt, Katja; Schwarm, Fritz-Walter; Wilms, Jörn; Wood, Kent S. (Astrophysical Journal, 2016)
Keywords: methods: data analysis; radiative transfer; stars: individual: Her X-1; stars: neutron; X-rays: binaries

The Performance of the Athena X-ray Integral Field Unit at Very High Count Rates - Peille, Philippe; Dauser, Thomas; Kirsch, Christian; Den Hartog, R.; Cucchetti, E.; Wilms, Jörn; Barret, D.; Den Herder, J. -W.; Piro, Luigi (Journal of Low Temperature Physics, 2018)
The Athena X-ray Integral Field Unit (X-IFU) will operate at 90 mK a hexagonal matrix of 3840 Transition Edge Sensor pixels providing spatially resolved high-resolution spectroscopy (2.5 eV FWHM up to 7 keV) between 0.2 and 12 keV. During the observation of very bright X-ray sources, the X-IFU detectors will receive high photon rates going up to several tens of counts per second per pixel and hundreds per readout channel, well above the normal operating mode of the instrument. In this paper, we investigate through detailed end-to-end simulations the performance achieved by the X-IFU at the highest count rates. Special care is notably taken to model and characterize pulse processing limitations, readout-chain saturation effects, as well as the non-Gaussian degradation of the energy redistribution from crosstalk at the focal plane level (both thermal and electrical). Overall, we show that the instrument performance should safely exceed the scientific requirements, and in particular that more than 50% throughput at 1 Crab in the 5-8 keV band can be achieved with better than 10 eV average resolution with the use of a Beryllium filter, enabling breakthrough science in the field of bright sources.
Keywords: X-IFU; X-ray microcalorimeters; TES; Crosstalk; FDM

The positioning system of the ANTARES Neutrino Telescope - Adrian-Martinez, S.; Ageron, M.; Aguilar, J. A.; Al Samarai, I.; Albert, A.; Andre, Michel; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, Miguel; Jesus, A. C. Assis; Astraatmadja, T.; et al. (Journal of Instrumentation, 2012)
The ANTARES neutrino telescope, located 40km off the coast of Toulon in the Mediterranean Sea at a mooring depth of about 2475m, consists of twelve detection lines equipped typically with 25 storeys. Every storey carries three optical modules that detect Cherenkov light induced by charged secondary particles (typically muons) coming from neutrino interactions. As these lines are flexible structures fixed to the sea bed and held taut by a buoy, sea currents cause the lines to move and the storeys to rotate. The knowledge of the position of the optical modules with a precision better than 10cm is essential for a good reconstruction of particle tracks. In this paper the ANTARES positioning system is described. It consists of an acoustic positioning system, for distance triangulation, and a compass-tiltmeter system, for the measurement of the orientation and inclination of the storeys. Necessary corrections are discussed and the results of the detector alignment procedure are described.
Keywords: Timing detectors; Detector modelling and simulations II (electric fields; charge transport; multiplication and induction; pulse formation; electron emission; etc); Detector alignment and calibration methods (lasers; sources; particle-beams); Detector control systems (detector and experiment monitoring and slow-control systems; architecture; hardware; algorithms; databases)

The pre-outburst flare of the A 0535+26 August/September 2005 outburst - Caballero, I.; Santangelo, A.; Kretschmar, Peter; Staubert, R.; Postnov, Konstantin; Klochkov, D.; Camero-Arranz, A.; Finger, M. H.; Kreykenbohm, Ingo; Pottschmidt, K.; Rothschild, R. E.; Suchy, S.; et al. (Astronomy & Astrophysics, 2008)
We study the spectral and temporal behavior of the High Mass X-ray Binary A 0535+26 during a "pre-outburst flare" which took place similar to 5d before the peak of a normal (type I) outburst in August/September 2005. We compare the studied behavior with that observed during the outburst.Methods. We analyse RXTE observations that monitored A 0535+26 during the outburst. We complete spectral and timing analyses of the data. We study the evolution of the pulse period, present energy-dependent pulse profiles both at the initial pre-outburst flare and close to outburst maximum, and measure how the cyclotron resonance-scattering feature (hereafter CRSF) evolves.Results. We present three main results: a constant period P = 103.3960(5) s is measured until periastron passage, followed by a spin-up with a decreasing period derivative of. P = (-1.69 +/- 0.04) x 10(-8) s s(-1) at MJD 53 618, and P remains constant again at the end of the main outburst. The spin-up provides evidence for the existence of an accretion disk during the normal outburst. We measure a CRSF energy of E-cyc similar to 50 keV during the pre-outburst flare, and E-cyc similar to 46 keV during the main outburst. The pulse shape, which varies significantly during both pre-outburst flare and main outburst, evolves strongly with photon energy.
Keywords: X-rays : binaries; stars : magnetic fields; stars : individual : A 0535+26

The prototype detection unit of the KM3NeT detector: KM3NeT Collaboration - Adrian-Martinez, S.; Ageron, M.; Aharonian, F.; Aiello, S.; Albert, A.; Ameli, F.; Anassontzis, E. G.; Androulakis, G. C.; Anghinolfi, M.; Anton, Gisela; Anvar, S.; Ardid, M.; et al. (European Physical Journal C: Particles and Fields, 2016)
A prototype detection unit of the KM3NeT deep-sea neutrino telescope has been installed at 3500m depth 80 km offshore the Italian coast. KM3NeT in its final configuration will contain several hundreds of detection units. Each detection unit is a mechanical structure anchored to the sea floor, held vertical by a submerged buoy and supporting optical modules for the detection of Cherenkov light emitted by charged secondary particles emerging from neutrino interactions. This prototype string implements three optical modules with 31 photomultiplier tubes each. These optical modules were developed by the KM3NeT Collaboration to enhance the detection capability of neutrino interactions. The prototype detection unit was operated since its deployment in May 2014 until its decommissioning in July 2015. Reconstruction of the particle trajectories from the data requires a nanosecond accuracy in the time calibration. A procedure for relative time calibration of the photomultiplier tubes contained in each optical module is described. This procedure is based on the measured coincidences produced in the sea by the ^4040K background light and can easily be expanded to a detector with several thousands of optical modules. The time offsets between the different optical modules are obtained using LED nanobeacons mounted inside them. A set of data corresponding to 600 h of livetime was analysed. The results show good agreement with Monte Carlo simulations of the expected optical background and the signal from atmospheric muons. An almost background-free sample of muons was selected by filtering the time correlated signals on all the three optical modules. The zenith angle of the selected muons was reconstructed with a precision of about 3^° ∘.

The reawakening of the sleeping X-ray pulsar XTE J1946+274 - Müller, Sebastian; Kühnel, Matthias; Caballero, I.; Pottschmidt, K.; Fürst, Felix; Kreykenbohm, Ingo; Sagredo, Macarena; Obst, M.; Wilms, Jörn; Ferrigno, C.; Rothschild, R. E.; Staubert, R. (Astronomy & Astrophysics, 2012)
We report on a series of outbursts of the high-mass X-ray binary XTE J1946+274 in 2010/2011 observed with INTEGRAL, RXTE, and Swift. We discuss possible mechanisms resulting in the extraordinary outburst behavior of this source. The X-ray spectra can be described by standard phenomenological models, enhanced by an absorption feature of unknown origin at about 10 keV and a narrow iron K alpha fluorescence line at 6.4 keV, which are variable in flux and pulse phase. We find possible evidence for a cyclotron resonance scattering feature at about 25 keV at the 93% level. The presence of a strong cyclotron line at 35 keV seen in data from the source's 1998 outburst that was confirmed by a reanalysis of these data can be excluded. This result indicates that the cyclotron line feature in XTE J1946+274 is variable between individual outbursts.
Keywords: X-rays: binaries; accretion; accretion disks

THE REFLECTION COMPONENT FROM CYGNUS X-1 IN THE SOFT STATE MEASURED BY NuSTAR AND SUZAKU - Tomsick, John A.; Nowak, Michael A.; Parker, Michael; Miller, Jon M.; Fabian, Andy C.; Harrison, Fiona A.; Bachetti, Matteo; Barret, Didier; Boggs, Steven E.; Christensen, Finn E.; Craig, William W.; Forster, Karl; et al. (Astrophysical Journal, 2014)
The black hole binary Cygnus X-1 was observed in late 2012 with the Nuclear Spectroscopic Telescope Array (NuSTAR) and Suzaku, providing spectral coverage over the similar to 1-300 keV range. The source was in the soft state with a multi-temperature blackbody, power law, and reflection components along with absorption from highly ionized material in the system. The high throughput of NuSTAR allows for a very high quality measurement of the complex iron line region as well as the rest of the reflection component. The iron line is clearly broadened and is well described by a relativistic blurring model, providing an opportunity to constrain the black hole spin. Although the spin constraint depends somewhat on which continuum model is used, we obtain a(*) > 0.83 for all models that provide a good description of the spectrum. However, none of our spectral fits give a disk inclination that is consistent with the most recently reported binary values for Cyg X-1. This may indicate that there is a > 13 degrees misalignment between the orbital plane and the inner accretion disk (i.e., a warped accretion disk) or that there is missing physics in the spectral models.
Keywords: accretion; accretion disks; black hole physics; stars: individual (Cygnus X-1); X-rays: general; X-rays: stars

The role of the reflection fraction in constraining black hole spin - Dauser, Thomas; Garcia, Javier; Parker, M. L.; Fabian, A. C.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2014)
In many active galaxies, the X-ray reflection features from the innermost regions of the accretion disc are relativistically distorted. This distortion allows us to measure parameters of the black hole such as its spin. The ratio in flux between the direct and the reflected radiation, the so-called reflection fraction, is determined directly from the geometry and location of primary source of radiation. We calculate the reflection fraction in the lamp post geometry in order to determine its maximal possible value for a given value of black hole spin. We show that high reflection fractions in excess of two are only possible for rapidly rotating black holes, suggesting that the high spin sources produce the strongest relativistic reflection features. Using simulations we show that taking this constraint into account does significantly improve the determination of the spin values. We make software routines for the most popular X-ray data analysis packages available that incorporate these additional constraints.
Keywords: accretion; accretion discs; black hole physics; line: profiles; galaxies: active; galaxies: nuclei

The search for high-energy neutrinos coincident with fast radio bursts with the ANTARES neutrino telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
In the past decade, a new class of bright transient radio sources with millisecond duration has been discovered. The origin of these so-called fast radio bursts (FRBs) is still a mystery, despite the growing observational efforts made by various multiwavelength and multimessenger facilities. To date, many models have been proposed to explain FRBs, but neither the progenitors nor the radiative and the particle acceleration processes at work have been clearly identified. In this paper, we assess whether hadronic processes may occur in the vicinity of the FRB source. If they do, FRBs may contribute to the high-energy cosmic-ray and neutrino fluxes. A search for these hadronic signatures was carried out using the ANTARES neutrino telescope. The analysis consists in looking for high-energy neutrinos, in the TeV-PeV regime, that are spatially and temporally coincident with the detected FRBs. Most of the FRBs discovered in the period 2013-2017 were in the field of view of the ANTARES detector, which is sensitive mostly to events originating from the Southern hemisphere. From this period, 12 FRBs were selected and no coincident neutrino candidate was observed. Upper limits on the per-burst neutrino fluence were derived using a power-law spectrum, dN/DE nu proportional to E-nu(-gamma), for the incoming neutrino flux, assuming spectral indexes gamma = 1.0, 2.0, 2.5. Finally, the neutrino energy was constrained by computing the total energy radiated in neutrinos, assuming different distances for the FRBs. Constraints on the neutrino fluence and on the energy released were derived from the associated null results.
Keywords: acceleration of particles; neutrinos; astroparticle physics; radio continuum: transients; methods: data analysis

The Search for Neutrinos from TXS 0506+056 with the ANTARES Telescope - Albert, A.; Andre, M.; Anghinolfi, M.; Anton, Gisela; Ardid, M.; Aubert, J-J; Aublin, J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Belhorma, B.; et al. (Astrophysical Journal Letters, 2018)
The results of three different searches for neutrino candidates, associated with the IceCube-170922A event or from the direction of TXS 0506+056, by the ANTARES neutrino telescope, are presented. The first search refers to the online follow-up of the IceCube alert; the second is based on the standard time-integrated method employed by the Collaboration to search for point-like neutrino sources; the third uses information from the IceCube time-dependent analysis that reported bursting activity centered on 2014 December 13, as input for an ANTARES time-dependent analysis. The online follow-up and the time-dependent analysis yield no events related to the source. The time-integrated study performed over a period from 2007 to 2017 fits 1.03 signal events, which corresponds to a p-value of 3.4% (not considering trial factors). Only for two other astrophysical objects in our candidate list has a smaller p-value been found. When considering that 107 sources have been investigated, the post-trial p-value for TXS 0506+056 corresponds to 87%.
Keywords: astroparticle physics; elementary particles; galaxies: active

The simultaneous low state spectral energy distribution of 1ES 2344+514 from radio to very high energies - Aleksic, J.; Antonelli, L. A.; Antoranz, Pedro; Asensio, M.; Backes, Michael; De Almeida, U. Barres; Barrio, J. A.; Bednarek, Wlodek; Berger, K.; Bernardini, E.; Biland, A.; Blanch, O.; et al. (Astronomy & Astrophysics, 2013)
Context. BL Lacertae objects are variable at all energy bands on time scales down to minutes. To construct and interpret their spectral energy distribution (SED), simultaneous broad-band observations are mandatory. Up to now, the number of objects studied during such campaigns is very limited and biased towards high flux states.Aims. We present the results of a dedicated multi-wavelength study of the high-frequency peaked BL Lacertae (HBL) object and known TeV emitter 1ES 2344+514 by means of a pre-organised campaign.Methods. The observations were conducted during simultaneous visibility windows of MAGIC and AGILE in late 2008. The measurements were complemented by Mets hovi, RATAN-600, KVA+Tuorla, Swift and VLBA pointings. Additional coverage was provided by the ongoing long-term F-GAMMA and MOJAVE programs, the OVRO 40-m and CrAO telescopes as well as the Fermi satellite. The obtained SEDs are modelled using a one-zone as well as a self-consistent two-zone synchrotron self-Compton model.Results. 1ES 2344+514 was found at very low flux states in both X-rays and very high energy gamma rays. Variability was detected in the low frequency radio and X-ray bands only, where for the latter a small flare was observed. The X-ray flare was possibly caused by shock acceleration characterised by similar cooling and acceleration time scales. MOJAVE VLBA monitoring reveals a static jet whose components are stable over time scales of eleven years, contrary to previous findings. There appears to be no significant correlation between the 15 GHz and R-band monitoring light curves. The observations presented here constitute the first multi-wavelength campaign on 1ES 2344+514 from radio to VHE energies and one of the few simultaneous SEDs during low activity states. The quasi-simultaneous Fermi-LAT data poses some challenges for SED modelling, but in general the SEDs are described well by both applied models. The resulting parameters are typical for TeV emitting HBLs. Consequently it remains unclear whether a so-called quiescent state was found in this campaign.
Keywords: galaxies: active; BL Lacertae objects: individual: 1ES 2344+514; gamma rays: galaxies; X-rays: individuals: 1ES 2344+514; radiation mechanisms: non-thermal

The soft state of Cygnus X-1 observed with nustar: A variable corona and a stable inner disk - Walton, D. J.; Tomsick, J. A.; Madsen, K. K.; Grinberg, V.; Barret, D.; Boggs, S. E.; Christensen, F. E.; Clavel, Maica; Craig, W. W.; Fabian, A. C.; Fuerst, F.; Hailey, C. J.; et al. (Astrophysical Journal, 2016)
We present a multi-epoch hard X-ray analysis of Cygnus X-1 in its soft state based on four observations with the Nuclear Spectroscopic Telescope Array (NuSTAR). Despite the basic similarity of the observed spectra, there is clear spectral variability between epochs. To investigate this variability, we construct a model incorporating both the standard disk-corona continuum and relativistic reflection from the accretion disk, based on prior work on Cygnus X-1, and apply this model to each epoch independently. We find excellent consistency for the black hole spin and the iron abundance of the accretion disk, which are expected to remain constant on observational timescales. In particular, we confirm that Cygnus X-1 hosts a rapidly rotating black hole, 0.93 a 0.96, in broad agreement with the majority of prior studies of the relativistic disk reflection and constraints on the spin obtained through studies of the thermal accretion disk continuum. Our work also confirms the apparent misalignment between the inner disk and the orbital plane of the binary system reported previously, finding the magnitude of this warp to be ∼10°-15°. This level of misalignment does not significantly change (and may even improve) the agreement between our reflection results and the thermal continuum results regarding the black hole spin. The spectral variability observed by NuSTAR is dominated by the primary continuum, implying variability in the temperature of the scattering electron plasma. Finally, we consistently observe absorption from ionized iron at ∼6.7 keV, which varies in strength as a function of orbital phase in a manner consistent with the absorbing material being an ionized phase of the focused stellar wind from the supergiant companion star.
Keywords: Black hole physics; X-rays: Binaries; X-rays: Individual (Cygnus X-1)

The SUrvey for Pulsars and Extragalactic Radio Bursts - II. New FRB discoveries and their follow-up - Bhandari, S.; Keane, E. F.; Barr, E. D.; Jameson, A.; Petroff, E.; Johnston, Simon; Bailes, Matthew; Bhat, N. D. R.; Burgay, M.; Burke-Spolaor, S.; Caleb, M.; Eatough, R. P.; et al. (Monthly Notices of the Royal Astronomical Society, 2018)
We report the discovery of four Fast Radio Bursts (FRBs) in the ongoing SUrvey for Pulsars and Extragalactic Radio Bursts at the Parkes Radio Telescope: FRBs 150610, 151206, 151230 and 160102. Our real-time discoveries have enabled us to conduct extensive, rapid multimessenger follow-up at 12 major facilities sensitive to radio, optical, X-ray, gamma-ray photons and neutrinos on time-scales ranging from an hour to a few months post-burst. No counterparts to the FRBs were found and we provide upper limits on afterglow luminosities. None of the FRBs were seen to repeat. Formal fits to all FRBs show hints of scattering while their intrinsic widths are unresolved in time. FRB 151206 is at low Galactic latitude, FRB 151230 shows a sharp spectral cut-off, and FRB 160102 has the highest dispersion measure (DM = 2596.1 +/- 0.3 pc cm(-3)) detected to date. Three of the FRBs have high dispersion measures (DM > 1500 pc cm(-3)), favouring a scenario where the DMis dominated by contributions from the intergalactic medium. The slope of the Parkes FRB source counts distribution with fluences > 2 Jy ms is alpha = - 2.2(-1.2)(+0.6) and still consistent with a Euclidean distribution (alpha = -3/2). We also find that the all-sky rate is 1.7(-0.9)(+1.5) x 10(3)FRBs/(4 pi sr)/day above similar to 2 Jy ms and there is currently no strong evidence for a latitude- dependent FRB sky rate.
Keywords: radiation mechanisms: general; methods: data analysis; methods: observational; surveys; intergalactic medium; radio continuum: general

The TANAMI Multiwavelength Program: Dynamic spectral energy distributions of southern blazars - Krauß, Felicia; Wilms, Jörn; Kadler, Matthias; Ojha, R.; Schulz, Robert; Truestedt, J.; Edwards, P. G.; Stevens, J.; Ros, Eduardo; Baumgartner, W.; Beuchert, Tobias; Blanchard, J.; et al. (Astronomy & Astrophysics, 2016)
Context. Simultaneous broadband spectral and temporal studies of blazars are an important tool for investigating active galactic nuclei (AGN) jet physics. Aims. We study the spectral evolution between quiescent and flaring periods of 22 radio-loud AGN through multiepoch, quasi-simultaneous broadband spectra. For many of these sources these are the first broadband studies. Methods. We use a Bayesian block analysis of Fermi/LAT light curves to determine time ranges of constant flux for constructing quasi-simultaneous spectral energy distributions (SEDs). The shapes of the resulting 81 SEDs are described by two logarithmic parabolas and a blackbody spectrum where needed. Results. The peak frequencies and luminosities agree well with the blazar sequence for low states with higher luminosity implying lower peak frequencies. This is not true for sources in high states. The γ-ray photon index in Fermi/LAT correlates with the synchrotron peak frequency in low and intermediate states. No correlation is present in high states. The black hole mass cannot be determined from the SEDs. Surprisingly, the thermal excess often found in FSRQs at optical/UV wavelengths can be described by blackbody emission and not an accretion disk spectrum. Conclusions. The so-called harder-when-brighter trend, typically seen in X-ray spectra of flaring blazars, is visible in the blazar sequence. Our results for low and intermediate states, as well as the Compton dominance, are in agreement with previous results. Black hole mass estimates using recently published parameters are in agreement with some of the more direct measurements. For two sources, estimates disagree by more than four orders of magnitude, possibly owing to boosting effects. The shapes of the thermal excess seen predominantly in flat spectrum radio quasars are inconsistent with a direct accretion disk origin.
Keywords: BL Lacertae objects: general; Galaxies: active; Quasars: general; Relativistic processes

THE TRANSIENT ACCRETING X-RAY PULSAR XTE J1946+274: STABILITY OF X-RAY PROPERTIES AT LOW FLUX AND UPDATED ORBITAL SOLUTION - Marcu-Cheatham, Diana M.; Pottschmidt, Katja; Kühnel, Matthias; Müller, Sebastian; Falkner, Sebastian; Caballero, Isabel; Finger, Mark H.; Jenke, Peter J.; Wilson-Hodge, Colleen A.; Fuerst, Felix; Grinberg, Victoria; Hemphill, Paul B.; et al. (Astrophysical Journal, 2015)
We present a timing and spectral analysis of the X-ray pulsar XTE J1946+274 observed with Suzaku during an outburst decline in 2010 October and compare with previous results. XTE J1946+274 is a transient X-ray binary consisting of a Be-type star and a neutron star with a 15.75 s pulse period in a 172 days orbit with 2-3 outbursts per orbit during phases of activity. We improve the orbital solution using data from multiple instruments. The X-ray spectrum can be described by an absorbed Fermi-Dirac cut-off power-law model along with a narrow Fe K alpha line at 6.4 keV and a weak Cyclotron Resonance Scattering Feature (CRSF) at similar to 35 keV. The Suzaku data are consistent with the previously observed continuum flux versus iron line flux correlation expected from fluorescence emission along the line of sight. However, the observed iron line flux is slightly higher, indicating the possibility of a higher iron abundance or the presence of non-uniform material. We argue that the source most likely has only been observed in the subcritical (non-radiation dominated) state since its pulse profile is stable over all observed luminosities and the energy of the CRSF is approximately the same at the highest (similar to 5 x 10(37) erg s(-1)) and lowest (similar to 5. x 10(36) erg s(-1)) observed 3-60 keV luminosities.
Keywords: accretion; accretion disks; pulsars: individual (XTE J1946+274); X-rays: binaries

The unusual multiwavelength properties of the gamma-ray source PMN J1603-4904 - Müller, Cornelia; Kadler, Matthias; Ojha, R.; Boeck, M.; Krauß, Felicia; Taylor, G. B.; Wilms, Jörn; Blanchard, J.; Carpenter, B.; Dauser, Thomas; Dutka, M.; Edwards, P. G.; et al. (Astronomy & Astrophysics, 2014)
Context. We investigate the nature and classification of PMN J1603-4904, a bright radio source close to the Galactic plane, which is associated with one of the brightest hard-spectrum gamma-ray sources detected by Fermi/LAT. It has previously been classified as a low-peaked BL Lac object based on its broadband emission and the absence of optical emission lines. Optical measurements, however, suffer strongly from extinction and the absence of pronounced short-time gamma-ray variability over years of monitoring is unusual for a blazar.Aims. In this paper, we are combining new and archival multiwavelength data of PMN J1603-4904 in order to reconsider the classification and nature of this unusual gamma-ray source.Methods. For the first time, we study the radio morphology of PMN J1603-4904 at 8.4 GHz and 22.3 GHz, and its spectral properties on milliarcsecond scales, based on VLBI observations from the TANAMI program. We combine the resulting images with multiwavelength data in the radio, IR, optical/UV, X-ray, and gamma-ray regimes.Results. PMN J1603-4904 shows a symmetric brightness distribution at 8.4 GHz on milliarcsecond scales, with the brightest, and most compact component in the center of the emission region. The morphology is reminiscent of a compact symmetric object (CSO). Such objects, thought to be young radio galaxies, have been predicted to produce gamma-ray emission but have not been detected as a class by the Fermi gamma-ray telescope so far. Sparse (u, v)-coverage at 22.3 GHz prevents an unambiguous modeling of the source morphology at this higher frequency. Moreover, infrared measurements reveal an excess in the spectral energy distribution (SED), which can be modeled with a blackbody with a temperature of about 1600 K, and which is usually not present in blazar SEDs.Conclusions. The TANAMI VLBI data and the shape of the broadband SED challenge the current blazar classification of one of the brightest gamma-ray sources in the sky. PMN J1603-4904 seems to be either a highly peculiar BL Lac object or a misaligned jet source. In the latter case, the intriguing VLBI structure opens room for a possible classification of PMN J1603-4904 as a gamma-ray bright CSO.
Keywords: galaxies: active; galaxies: individual: PMNJ1603-4904; radio continuum: general; gamma rays: galaxies; techniques: interferometric; X-rays: galaxies

The Wide-Field Imager for IXO: Status and future activities - Strueder, Lothar; Aschauer, Florian; Bautz, Mark; Bombelli, Luca; Burrows, David; Fiorini, Carlo; Fraser, George; Herrmann, Sven; Kendziorra, Eckhard; Kuster, Markus; Lauf, Thomas; Lechner, Peter; et al. (2010)
The Wide Field Imager (WFI) of the International X-ray Observatory (IXO) is an X-ray imaging spectrometer based on a large monolithic DePFET (Depleted P-channel Field Effect Transistor) Active Pixel Sensor. Filling an area of 10 x 10 cm(2) with a format of 1024 x 1024 pixels it will cover a field of view of 18 arcmin. The pixel size of 100 x 100 mu m(2) corresponds to a fivefold oversampling of the telescope's expected 5 arcsec point spread function. The WFI's basic DePFET structure combines the functionalities of sensor and integrated amplifier with nearly Fano-limited energy resolution and high efficiency from 100 eV to 15 keV. The development of dedicated control and amplifier ASICs allows for high frame rates up to 1 kHz and flexible readout modes. Results obtained with representative prototypes with a format of 256 x 256 pixels are presented.
Keywords: International X-ray Observatory; IXO; Wide Field Imager; WFI; X-ray Astronomy; X-ray Spectroscopy; X-ray Imaging; DePFET; Active Pixel Sensor

The Wide Field Imager Instrument for Athena - Meidinger, Norbert; Nandra, Kirpal; Plattner, Markus; Porro, Matteo; Rau, Arne; Santangelo, Andrea; Tenzer, Chris; Wilms, Jörn (2014)
The "Hot and Energetic Universe" has been selected as the science theme for ESA's L2 mission, scheduled for launch in 2028. The proposed Athena X-ray observatory provides the necessary capabilities to achieve the ambitious goals of the science theme. The X-ray mirrors are based on silicon pore optics technology and will have a 12 m focal length. Two complementary camera systems are foreseen which can be moved in and out of the focal plane by an interchange mechanism. These instruments are the actively shielded micro-calorimeter spectrometer X-IFU and the Wide Field Imager (WFI).The WFI will combine an unprecedented survey power through its large field of view of 40 arcmin with a high count-rate capability (approx. 1 Crab). It permits a state-of-the-art energy resolution in the energy band of 0.1 keV to 15 keV during the entire mission lifetime (e.g. FWHM <= 150 eV at 6 keV). This performance is accomplished by a set of DEPFET active pixel sensor matrices with a pixel size matching the angular resolution of 5 arcsec (on-axis) of the mirror system. Each DEPFET pixel is a combined detector-amplifier structure with a MOSFET integrated onto a fully depleted 450 micron thick silicon bulk. The signal electrons generated by an X-ray photon are collected in a so-called internal gate below the transistor channel. The resulting change of the conductivity of the transistor channel is proportional to the number of electrons and thus a measure for the photon energy. DEPFETs have already been developed for the "Mercury Imaging X-ray Spectrometer" on-board of ESA's BepiColombo mission. For Athena we develop enhanced sensors with integrated electronic shutter and an additional analog storage area in each pixel. These features improve the peak-to-background ratio of the spectra and minimize dead time. The sensor will be read out with a new, fast, low-noise multi-channel analog signal processor with integrated sequencer and serial analog output. The architecture of sensor and readout ASIC allows readout in full frame mode and window mode as well by addressing selectively arbitrary sub-areas of the sensor allowing time resolution in the order of 10 mu s. The further detector electronics has mainly the following tasks: digitization, pre-processing and telemetry of event data as well as supply and control of the detector system. Although the sensor will already be equipped with an on-chip light blocking filter, a filter wheel is necessary to provide an additional external filter, an on-board calibration source, an open position for outgassing, and a closed position for protection of the sensor. The sensor concept provides high quantum efficiency over the entire energy band and we intend to keep the instrumental background as low as possible by designing a graded Z-shield around the sensor.All these properties make the WFI a very powerful survey instrument, significantly surpassing currently existing observatories and in addition allow high-time resolution of the brightest X-ray sources with low pile-up and high efficiency. This manuscript will summarize the current instrument concept and design, the status of the technology development, and the envisaged baseline performance.
Keywords: Active pixel sensor; Athena; DEPFET; focal plane camera; hot and energetic universe; WFI; X-ray detector

The Wide Field Imager of the International X-ray Observatory - Stefanescu, A.; Bautz, M. W.; Burrows, D. N.; Bombelli, L.; Fiorini, C.; Fraser, G.; Heinzinger, K.; Herrmann, S.; Kuster, Markus; Lauf, T.; Lechner, P.; Lutz, G.; et al. (ELSEVIER SCIENCE BV, 2010)
The International X-ray Observatory (IXO) will be a Joint X-ray observatory mission by ESA NASA and JAXA It will have a large effective area (3 m(2) at 1 25 key) grazing incidence mirror system with good angular resolution (5 arcsec at 0 1-10 keV) and will feature a comprehensive suite of scientific instruments an X-ray Microcalorimeter Spectrometer a High Time Resolution Spectrometer an X-ray Polarimeter an X-ray Grating Spectrometer a Hard X-ray Imager and a Wide-Field ImagerThe Wide Field Imager (WFI) has a field-of-view of 18 ft x 18 ft It will be sensitive between 01 and 15 keV offer the full angular resolution of the mirrors and good energy resolution The WFI will be Implemented as a 6 in wafer-scale monolithical array of 1024 x 1024 pixels 01 100 x 100 mu m(2) size The DEpleted P-channel Field-Effect Transistors (DEPFET) forming the individual pixels are devices combining the functionalities of both detector and amplifier Signal electrons are collected in a potential well below the transistor s gate modulating the transistor current Even when the device is powered off the signal charge is collected and kept in the potential well below the gate until it is explicitly cleared This makes flexible and fast readout modes possible (C) 2010 Elsevier B V All rights reserved
Keywords: IXO; X ray astronomy; DEPFET; Active Pixel Sensor; Imaging; Spectroscopy

The XMM-Newton view of the crab - Kirsch, Marcus G F; Schönherr, Gabriele; Kendziorra, Eckhard; Freyberg, Michael; Martin, Michael; Wilms, Jörn; Mukerjee, K.; Breitfellner, Michael; Smith, M. J. S.; Staubert, Rüdiger (Astronomy & Astrophysics, 2006)
Aims. We discuss the current X-ray view of the Crab Nebula and Pulsar, summarising our analysis of observations of the source with the EPIC-pn camera on board the XMM-Newton observatory. Different modes of EPIC-pn were combined in order to yield a complete scenario of the spectral properties of the Crab resolved in space and time ( pulse phase). In addition we give a description of the special EPIC-pn Burst mode and guidance for data reduction in that mode.Methods. We analysed spectra for the nebula and pulsar separately in the 0.6-12.0 keV energy band. All data were processed with the SAS 6.0.0 XMM-Newton Scientific Analysis System package; models were fitted to the data with XSPEC 11. The high time resolution of EPIC-pn in its Burst mode (7 mu s) was used for a phase resolved analysis of the pulsar spectrum, after determination of the period with epoch folding techniques. Data from the Small Window mode were processed and corrected for pile-up allowing for spectroscopy simultaneously resolved in space and time.Results. The spatial variation of the spectrum over the entire region of the Crab shows a gradual spectral softening from the inner pulsar region to the outer nebula region with a variation in photon index, Gamma, from 2.0 to 2.4. Pulse phase resolved spectroscopy of the Crab Pulsar reveals a phase dependent modulation of the photon index in form of a significant hardening of the spectrum in the inter-peak phase from Gamma = 1.7 during the pulse peak to Gamma = 1.5.
Keywords: instrumentation : detectors; stars : neutron; stars : pulsars : individual : PSR 0531+21; X-rays : stars

The X-ray Integral Field Unit (X-IFU) for Athena - Ravera, Laurent; Barret, Didier; Den Herder, Jan Willem; Piro, Luigi; Cledassou, Rodolphe; Pointecouteau, Etienne; Peille, Philippe; Pajot, Francois; Arnaud, Monique; Pigot, Claude; Duband, Lionel; Cara, Christophe; et al. (2014)
Athena is designed to implement the Hot and Energetic Universe science theme selected by the European Space Agency for the second large mission of its Cosmic Vision program. The Athena science payload consists of a large aperture high angular resolution X-ray optics (2 m(2) at 1 keV) and twelve meters away, two interchangeable focal plane instruments: the X-ray Integral Field Unit (X-IFU) and the Wide Field Imager. The X-IFU is a cryogenic X-ray spectrometer, based on a large array of Transition Edge Sensors (TES), offering 2.5 eV spectral resolution, with similar to 5" pixels, over a field of view of 5' in diameter. In this paper, we present the X-IFU detector and readout electronics principles, some elements of the current design for the focal plane assembly and the cooling chain. We describe the current performance estimates, in terms of spectral resolution, effective area, particle background rejection and count rate capability. Finally, we emphasize on the technology developments necessary to meet the demanding requirements of the X-IFU, both for the sensor, readout electronics and cooling chain.
Keywords: X-ray; missions; micro-calorimeter; Athena

The X-Ray Pulsar XTE J1858+034 Observed with NuSTAR and Fermi/GBM: Spectral and Timing Characterization plus a Cyclotron Line - Malacaria, C.; Kretschmar, P.; Madsen, K. K.; Wilson-Hodge, C. A.; Coley, Joel B.; Jenke, P.; Lutovinov, Alexander A.; Pottschmidt, Katja; Tsygankov, Sergey S.; Wilms, Jörn (Astrophysical Journal, 2021)
Accreting X-ray pulsars (XRPs) undergo luminous X-ray outbursts during which the spectral and timing behavior of the neutron star can be studied in detail. We analyze a NuSTAR observation of the XRP XTE J1858+034 during its outburst in 2019. The spectrum is fit with a phenomenological, a semiempirical, and a physical spectral model. A candidate cyclotron line is found at 48 keV, implying a magnetic field of 5.4 x 10(12) G at the site of emission. This is also supported by the physical best-fit model. We propose an orbital period of about 81 days based on the visual inspection of the X-ray outburst recurrence time. Based on Fermi/GBM data, the standard disk accretion-torque theory allowed us to infer a distance of 10.9 1.0 kpc. Pulse profiles are single-peaked and show a pulsed fraction that is strongly energy-dependent at least up to 40 keV.
CRIS-Team WoS Importer:2021-03-26

Time calibration with atmospheric muon tracks in the ANTARES neutrino telescope - Adrian-Martinez, S.; Albert, A.; Andre, M.; Anton, Gisela; Ardid, M.; Aubert, J. -J.; Baret, B.; Barrios-Marti, Javier; Basa, S.; Bertin, V.; Biagi, Simone; Bogazzi, C.; et al. (Astroparticle Physics, 2016)
The ANTARES experiment consists of an array of photomultipliers distributed along 12 lines and located deep underwater in the Mediterranean Sea. It searches for astrophysical neutrinos collecting the Cherenkov light induced by the charged particles, mainly muons, produced in neutrino interactions around the detector. Since at energies of ∼10 TeV the muon and the incident neutrino are almost collinear, it is possible to use the ANTARES detector as a neutrino telescope and identify a source of neutrinos in the sky starting from a precise reconstruction of the muon trajectory. To get this result, the arrival times of the Cherenkov photons must be accurately measured. A to perform time calibrations with the precision required to have optimal performances of the instrument is described. The reconstructed tracks of the atmospheric muons in the ANTARES detector are used to determine the relative time offsets between photomultipliers. Currently, this method is used to obtain the time calibration constants for photomultipliers on different lines at a precision level of 0.5 ns. It has also been validated for calibrating photomultipliers on the same line, using a system of LEDs and laser light devices.
Keywords: ANTARES; Atmospheric muon tracks; Neutrino Telescopes; Time calibration

Time-dependent search for neutrino emission from X-ray binaries with the ANTARES telescope - Albert, A.; Andre, Michel; Anton, Gisela; Ardid, Miguel; Aubert, J. -J.; Avgitas, T.; Baret, B.; Barrios-Marti, J.; Basa, S.; Bertin, V.; Biagi, Simone; Bormuth, R.; et al. (Journal of Cosmology and Astroparticle Physics, 2017)
ANTARES is currently the largest neutrino telescope operating in the Northern Hemisphere, aiming at the detection of high-energy neutrinos from astrophysical sources. Neutrino telescopes constantly monitor at least one complete hemisphere of the sky, and are thus well-suited to detect neutrinos produced in transient astrophysical sources. A time-dependent search has been applied to a list of 33 X-ray binaries undergoing high flaring activities in satellite data (RXTE/ASM, MAXI and Swift/BAT) and during hardness transition states in the 2008-2012 period. The background originating from interactions of charged cosmic rays in the Earth's atmosphere is drastically reduced by requiring a directional and temporal coincidence with astrophysical phenomena. The results of this search are presented together with comparisons between the neutrino flux upper limits and the neutrino flux predictions from astrophysical models. The neutrino flux upper limits resulting from this search limit the jet parameter space for some astrophysical models.
Keywords: neutrino astronomy; X-ray binaries; X-ray telescopes

Towards a Unified View of Inhomogeneous Stellar Winds in Isolated Supergiant Stars and Supergiant High Mass X-Ray Binaries - Martinez-Nunez, Silvia; Kretschmar, Peter; Bozzo, Enrico; Oskinova, Lidia M.; Puls, Joachim; Sidoli, Lara; Sundqvist, Jon Olof; Blay, Pere; Falanga, Maurizio; Furst, Felix; Gimenez-Garcia, Angel; Kreykenbohm, Ingo; et al. (Space Science Reviews, 2017)
Massive stars, at least similar to 10 times more massive than the Sun, have two key properties that make them the main drivers of evolution of star clusters, galaxies, and the Universe as a whole. On the one hand, the outer layers of massive stars are so hot that they produce most of the ionizing ultraviolet radiation of galaxies; in fact, the first massive stars helped to re-ionize the Universe after its Dark Ages. Another important property of massive stars are the strong stellar winds and outflows they produce. This mass loss, and finally the explosion of a massive star as a supernova or a gamma-ray burst, provide a significant input of mechanical and radiative energy into the interstellar space. These two properties together make massive stars one of the most important cosmic engines: they trigger the star formation and enrich the interstellar medium with heavy elements, that ultimately leads to formation of Earth-like rocky planets and the development of complex life. The study of massive star winds is thus a truly multidisciplinary field and has a wide impact on different areas of astronomy.In recent years observational and theoretical evidences have been growing that these winds are not smooth and homogeneous as previously assumed, but rather populated by dense "clumps". The presence of these structures dramatically affects the mass loss rates derived from the study of stellar winds. Clump properties in isolated stars are nowadays inferred mostly through indirect methods (i.e., spectroscopic observations of line profiles in various wavelength regimes, and their analysis based on tailored, inhomogeneous wind models). The limited characterization of the clump physical properties (mass, size) obtained so far have led to large uncertainties in the mass loss rates from massive stars. Such uncertainties limit our understanding of the role of massive star winds in galactic and cosmic evolution.Supergiant high mass X-ray binaries (SgXBs) are among the brightest X-ray sources in the sky. A large number of them consist of a neutron star accreting from the wind of a massive companion and producing a powerful X-ray source. The characteristics of the stellar wind together with the complex interactions between the compact object and the donor star determine the observed X-ray output from all these systems. Consequently, the use of SgXBs for studies of massive stars is only possible when the physics of the stellar winds, the compact objects, and accretion mechanisms are combined together and confronted with observations.This detailed review summarises the current knowledge on the theory and observations of winds from massive stars, as well as on observations and accretion processes in wind-fed high mass X-ray binaries. The aim is to combine in the near future all available theoretical diagnostics and observational measurements to achieve a unified picture of massive star winds in isolated objects and in binary systems.
Keywords: Massive stars; Stellar outflows; X-ray binary; Wind-fed systems; Accretion processes; SgXBs; SFXTs

Tracking the orbital and superorbital periods of SMC X-1 - Wilms, Jörn; et al. (Astrophysical Journal, 2007)
The high-mass X-ray binary (HMXB) SMCX-1 demonstrates an orbital variation of similar to 3.89 days and a superorbital variation with an average length of similar to 55 days. As we show here, however, the length of the superorbital cycle varies by almost a factor of 2, even across adjacent cycles. To study both the orbital and superorbital variation, we utilize light curves from the Rossi X-Ray Timing Explorer All-Sky Monitor (RXTE ASM). We employ the orbital ephemeris from P. Wojdowski et al. to obtain the average orbital profile, and we show that this profile exhibits complex modulation during noneclipse phases. In addition, a very interesting "bounceback" in X-ray count rate is seen during mid-orbital eclipse phases, with a softening of the emission during these periods. This bounceback has not been previously identified in pointed observations. We then define a superorbital ephemeris ( the phase of the superorbital cycle as a function of date) based on the ASM light curve and analyze the trend and distribution of superorbital cycle lengths. SMC X-1 exhibits a bimodal distribution of these lengths, similar to what has been observed in other systems ( e. g., Her X-1), but with more dramatic changes in cycle length. There is some hint, but not conclusive evidence, for a dependence of the superorbital cycle length on the underlying orbital period, as has been observed previously for Her X-1 and Cyg X-2. Using our superorbital ephemeris, we are also able to create an average superorbital profile over the 71 observed cycles, for which we witness overall hardening of the spectrum during low count rate times. We combine the orbital and superorbital ephemerides to study the correlation between the orbital and superorbital variations in the system, but find that the ASM light curve provides insufficient statistics to draw any definitive conclusions on possible correlations.
Keywords: accretion; accretion disks; X-rays : binaries

Two giant outbursts of V0332+53 observed with INTEGRAL - Ferrigno, Carlo; Ducci, Lorenzo; Bozzo, Enrico; Kretschmar, Peter; Kühnel, Matthias; Malacaria, Christian; Pottschmidt, Katja; Santangelo, Andrea; Savchenko, Volodymyr; Wilms, Jörn (Astronomy & Astrophysics, 2016)
Context. In July 2015, the high-mass X-ray binary V0332+53 underwent a giant outburst, a decade after the previous one. V0332+53 hosts a strongly magnetized neutron star. During the 2004-2005 outburst, an anti-correlation between the centroid energy of its fundamental cyclotron resonance scattering features (CRSFs) and the X-ray luminosity was observed. Aims. The long (≈ 100 d) and bright (L ≈ 10 erg s) 2015 outburst provided the opportunity to study the unique properties of the fundamental CRSF during another outburst and to study its dependence on the X-ray luminosity. Methods. The source was observed by the INTEGRAL satellite for 330 ks. We exploit the spectral resolution at high energies of the SPectrometer on INTEGRAL (SPI) and the Joint European X-ray Monitors to characterize its spectral properties, focusing in particular on the CRSF-luminosity dependence. We complement the data of the 2015 outburst with those collected by SPI in 2004-2005, which have so far been left unpublished. Results. We find a highly significant anti-correlation of the centroid energy of the fundamental CRSF and the 3-100 keV luminosity of E α -0.095(8)L keV. This trend is observed for both outbursts. We confirm the correlation between the width of the fundamental CRSF and the X-ray luminosity previously found in the JEM-X and IBIS dataset of the 2004-2005 outburst. By exploiting the RXTE/ASM and Swift/BAT monitoring data, we also report on the detection of a 34 d modulation superimposed on the mean profiles and roughly consistent with the orbital period of the pulsar. We discuss possible interpretations of such variability.
Keywords: pulsars: individual: V0332+53; stars: neutron; X-rays: binaries

Two similar to 35 day clocks in Hercules X-1: evidence for neutron star free precession - Staubert, R.; Klochkov, D.; Postnov, Konstantin; Shakura, N.; Wilms, Jörn; Rothschild, R. E. (Astronomy & Astrophysics, 2009)
We present evidence for the existence of two similar to 35 day clocks in the Her X-1/HZ Her binary system. similar to 35 day modulations are observed 1) in the Turn-On cycles with two on-and two off-states and 2) in the changing shape of the pulse profiles which re-appears regularly. The two ways of counting the 35 day cycles are generally in synchronization. This synchronization did apparently break down temporarily during the long Anomalous Low (AL3), which Her X-1 experienced in 1999/2000, in the sense that there must have been one extra Turn-On cycle. Our working hypothesis is that there are two clocks in the system, both with a period of about similar to 35 days: precession of the accretion disk (the less stable "Turn-On clock") and free precession of the neutron star (the more stable "Pulse profile clock"). We suggest that free precession of the neutron star is the master clock and that the precession of the accretion disk is basically synchronized to that of the neutron star through a feedback mechanism in the binary system. However, the Turn-On clock can slip against its master when the accretion disk has a very low inclination, as is observed to be the case during AL3. We take the apparent correlation between the histories of the Turn-Ons, of the Anomalous Lows and of the pulse period evolution, with a 5 yr quasi-periodicity, as evidence for strong physical interaction and feedback between the major components in the system. We speculate that the 5 yr (10 yr) period is due either to a corresponding activity cycle of HZ Her or a natural ringing period of the physical system of coupled components. The question of whether free precession really exists in neutron stars is very important for understanding matter with supra-nuclear density.
Keywords: stars: binaries: general; accretion; accretion disks; stars: neutron; X-rays: general; X-rays: binaries; X-rays: individuals: Her X-1

Ultra high energy photons and neutrinos with JEM-EUSO (vol 40, pg 215, 2015) - Adams, J. H.; Ahmad, S.; Albert, J. -N.; Allard, D.; Anchordoqui, L.; Andreev, V.; Anzalone, A.; Arai, Y.; Asano, K.; Ave Pernas, M.; Baragatti, P.; Barrillon, P.; et al. (Experimental Astronomy, 2015)

Ultra-violet imaging of the night-time earth by EUSO-Balloon towards space-based ultra-high energy cosmic ray observations - Abdellaoui, G.; Abe, S.; Adams, J. H.; Ahriche, A.; Allard, D.; Allen, L.; Alonso, G.; Anchordoqui, L.; Anzalone, A.; Arai, Y.; Asano, K.; Attallah, R.; et al. (Astroparticle Physics, 2019)
The JEM-EUSO (Joint Experiment Missions for the Extreme Universe Space Observatory) program aims at developing Ultra-Violet (UV) fluorescence telescopes for efficient detections of Extensive Air Showers (EASs) induced by Ultra-High Energy Cosmic Rays (UHECRs) from satellite orbit. In order to demonstrate key technologies for JEM-EUSO, we constructed the EUSO-Balloon instrument that consists of a ∼1 m 2 refractive telescope with two Fresnel lenses and an array of multi-anode photo-multiplier tubes at the focus. Distinguishing it from the former balloon-borne experiments, EUSO-Balloon has the capabilities of single photon counting with a gate time of 2.3 µs and of imaging with a total of 2304 pixels. As a pathfinder mission, the instrument was launched for an 8 h stratospheric flight on a moonless night in August 2014 over Timmins, Canada. In this work, we analyze the count rates over ∼2.5 h intervals. The measurements are of diffuse light, e.g. of airglow emission, back-scattered from the Earth's atmosphere as well as artificial light sources. Count rates from such diffuse light are a background for EAS detections in future missions and relevant factor for the analysis of EAS events. We also obtain the geographical distribution of the count rates over a ∼780 km 2 area along the balloon trajectory. In developed areas, light sources such as the airport, mines, and factories are clearly identified. This demonstrates the correct location of signals that will be required for the EAS analysis in future missions. Although a precise determination of count rates is relevant for the existing instruments, the absolute intensity of diffuse light is deduced for the limited conditions by assuming spectra models and considering simulations of the instrument response. Based on the study of diffuse light by EUSO-Balloon, we also discuss the implications for coming pathfinders and future space-based UHECR observation missions.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Airglow; EUSO-Balloon; Extensive air shower; JEM-EUSO; Ultra-high energy cosmic ray

Unity among Black Holes: Observational Similarities between Galactic Black Holes and Active Galactic Nuclei - Wilms, Jörn (SCIENCE PRESS, 2008)
A brief overview of recent observational work on the similarities of Galactic and supermassive black holes is given. It is shown that Galactic black holes and Active Galactic Nuclei both show relativistically broadened iron lines, follow the same relationship between their X-ray and their radio luminosity (L-radio alpha L-X(0.7)), and show similar X-ray variability. These observations indicate that the accretion flows around black holes scale over many orders of magnitude in mass and luminosity.
Keywords: X-rays: binaries; galaxies: active; accretion; accretion physics; black hole physics

UNVEILING THE NATURE OF IGR J17177-3656 WITH X-RAY, NEAR-INFRARED, AND RADIO OBSERVATIONS - Paizis, Adamantia; Nowak, M. A.; Wilms, Jörn; Chaty, Sylvain; Corbel, S.; Rodriguez, Jerome; Del Santo, Melania; Ubertini, P.; Chini, R. (Astrophysical Journal, 2011)
We report on the first broadband (1-200 keV) simultaneous Chandra-INTEGRAL observations of the recently discovered hard X-ray transient IGR J17177-3656 that took place on 2011 March 22, about two weeks after the source discovery. The source had an average absorbed 1-200 keV flux of about 8 x 10(-10) erg cm(-2) s(-1). We extracted a precise X-ray position of IGR J17177-3656, alpha(J2000) = 17(h)17(m)42(s).62, delta(J2000) = -36 degrees 56'04 ''.5 (90% uncertainty of 0 ''.6). We also report Swift, near-infrared, and quasi-simultaneous radio follow-up observations. With the multi-wavelength information at hand, we propose IGR J17177-3656 is a low-mass X-ray binary, seen at high inclination, probably hosting a black hole.
Keywords: accretion; accretion disks; binaries: close; stars: individual (IGR J17177-3656); X-rays: binaries

Unveiling the nature of IGR J17497-2821 using X-ray and near-infrared observations - Wilms, Jörn; et al. (Astrophysical Journal, 2007)
We report on a Chandra grating observation of the recently discovered hard X-ray transient IGR J17497-2821. The observation took place about 2 weeks after the discovery of the source at a flux level of about 20 mcrab in the 0.8-8 keV range. We extracted the most precise X-ray position of IGR J17497-2821, i.e., alpha(J2000) = 17(h)49(m)38.037(s), delta(J2000) = -28 degrees 21'17.37" (with a 90% uncertainty of 0.6"). We also report on optical and near-infrared photometric follow-up observations based on this position. With the multiwavelength information at hand, we discuss the possible nature of the source, proposing that IGR J17497-2821 is a low-mass X-ray binary, most likely hosting a black hole, with a red giant K-type companion.
Keywords: binaries : close; stars : individual (IGR J17497-2821); X-rays : binaries

Updating the orbital ephemeris of Hercules X-1; rate of decay and eccentricity of the orbit - Staubert, R.; Klochkov, D.; Wilms, Jörn (Astronomy & Astrophysics, 2009)
We present an update of the orbital ephemeris of the binary X-ray pulsar Her X-1 and determine an improved value for the rate of orbital decay. In addition, we report the first measurement of the orbital eccentricity. We analyzed pulse timing data of Her X-1 from X-ray observations by RXTE (Rossi X-Ray Timing Explorer) and INTEGRAL over the period 1996-2007. Accurate pulse arrival times were determined from solar system bary-centered photon arrival times by generating pulse profiles averaged over appropriately short integration times. Applying pulse phase connection techniques, it was possible to determine sufficiently accurate local ephemeris data for seven observation periods distributed over 12 years. Combining the new local T(pi/2) values with historical values from the literature we update the orbital ephemeris of Her X-1 to T(pi/2) = MJD 46 359.871940(6) and P(orb) = 1.700167590(2) d and measure a continuous change of the orbital period of dP(orb/dt) = -(4.85 +/- 0.13) x 10(-11) s s(-1). For the first time, a value for the eccentricity of the orbit of Her X-1 has been measured: is an element of = (4.2 +/- 0.8) x 10(-4).
Keywords: stars: binaries: general; stars: neutron; X-rays: general; X-rays: binaries; X-rays: individuals: Her X-1; ephemerides

USING THE X-RAY DUST SCATTERING HALO OF CYGNUS X-1 TO DETERMINE DISTANCE AND DUST DISTRIBUTIONS - Xiang, Jingen; Lee, Julia C.; Nowak, Michael A.; Wilms, Jörn (Astrophysical Journal, 2011)
We present a detailed study of the X-ray dust scattering halo of the black hole candidate Cygnus X-1 based on two Chandra High Energy Transmission Gratings Spectrometer observations. Using 18 different dust models, including one modified by us (eponymously dubbed XLNW), we probe the interstellar medium between us and this source. A consistent description of the cloud properties along the line of sight (LOS) that describes at the same time the halo radial profile, the halo light curves, and the column density from source spectroscopy is best achieved with a small subset of these models. Combining the studies of the halo radial profile and the halo light curves, we favor a geometric distance to Cygnus X-1 of d = 1.81 +/- 0.09 kpc. Our study also shows that there is a dense cloud, which contributes similar to 50% of the dust grains along the LOS to Cygnus X-1, located at similar to 1.6 kpc from us. The remainder of the dust along the LOS is close to the black hole binary.
Keywords: dust; extinction; scattering; X-rays: binaries; X-rays: individual (Cyg X-1); X-rays: ISM

Vacuum polarization alters the spectra of accreting X-ray pulsars - Sokolova-Lapa, Ekaterina; Stierhof, Jakob; Dauser, Thomas; Wilms, Jörn (Astronomy & Astrophysics, 2023)
It is a common belief that for magnetic fields typical of accreting neutron stars in high-mass X-ray binaries vacuum polarization only affects the propagation of polarized emission in the neutron star magnetosphere. We show that vacuum resonances can significantly alter the emission from the poles of accreting neutron stars. The effect is similar to vacuum polarization in the atmospheres of isolated neutron stars and can result in suppression of the continuum and the cyclotron lines. It is enhanced by magnetic Comptonization in the hot plasma and proximity to the electron cyclotron resonance. We present several models to illustrate the vacuum polarization effect for various optically thick media and discuss how the choice of polarization modes affects the properties of the emergent radiation by simulating polarized energy- and angle-dependent radiative transfer. Polarization effects, including vacuum polarization, crucially alter the emission properties. Together with strongly angle- and energy-dependent magnetic Comptonization, they result in a complex spectral shape, which can be described by dips and humps on top of a power-law-like continuum with high-energy cutoff. These effects provide a possible explanation for the common necessity of additional broad Gaussian components and two-component Comptonization models that are used to describe spectra of accreting X-ray pulsars. We also demonstrate the character of depolarization introduced by the radiation fielda's propagation inside the inhomogeneous emission region.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Magnetic fields; Methods: numerical; Polarization; Radiative transfer; Stars: neutron; X-rays: binaries

Variable cyclotron line in her X-1 - Wilms, Jörn; et al. (2007)
We present new results on the cyclotron resonance scattering feature (CRSF) in the X-ray spectrum of the binary X-ray pulsar Her X-1 from repeated observations by RXTE between 2000 and 2005, together with earlier results from RXTE and historical data. The centroid line energy E, in pulse phase averaged spectra shows considerable variation, both in the long-term historical development as well as during the time of the RXTE observations. Using RXTE data only, we find that the cyclotron line energy correlates with the observed maximum flux of the corresponding 35 day Main-On state, as measured by the RXTE/ASM. Contrary to what is observed in some high luminosity transient pulsars, the correlation found here is positive, with a change of similar to 5% in E-c for a change of a factor of two in X-ray flux. We suggest that this behaviour is expected in the case of sub-Eddington accretion and present a calculation of a quantitative estimate.
Keywords: X-ray binaries; X-ray pulsars; neutron stars; cyclotron lines

Variable neutron star free precession in Hercules X-1 from evolution of RXTE X-ray pulse profiles with phase of the 35-d cycle - Postnov, Konstantin; Shakura, N.; Staubert, R.; Kochetkova, A.; Klochkov, D.; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2013)
Accretion of matter on to the surface of a freely precessing neutron star (NS) with a complex non-dipole magnetic field can explain the change of X-ray pulse profiles of Her X-1 observed by RXTE with the phase of the 35-d cycle. We demonstrate this using all available measurements of X-ray pulse profiles in the 9-13 keV energy range obtained with the RXTE/Proportional Counter Array (PCA). The measured profiles guided the elaboration of a geometrical model and the definition of locations of emitting poles, arcs and spots on the NS surface which satisfactorily reproduce the observed pulse profiles and their dependence on free precession phase. We have found that the observed trend of the times of the 35-d turn-ons on the O-C diagram, which can be approximated by a collection of consecutive linear segments around the mean value, can be described by our model by assuming a variable free precession period, with a fractional period change of about a few per cent. Under this assumption and using our model, we have found that the times of phase zero of the NS free precession (which we identify with the maximum separation of the brightest spot on the NS surface with the NS spin axis) occur about 1.6 d after the mean turn-on times inside each 'stable' epoch, producing a linear trend on the O-C diagram with the same slope as the observed times of turn-ons. We propose that the 2.5 per cent changes in the free precession period that occur on time scales of several to tens of 35-d cycles can be related to wandering of the principal inertia axis of the NS body due to variations in the patterns of accretion on to the NS surface. The closeness of periods of the disc precession and the NS free precession can be explained by the presence of a synchronization mechanism in the system, which modulates the dynamical interaction of the gas streams and the accretion disc with the NS free precession period.
Keywords: accretion; accretion discs; stars: neutron; X-rays: binaries

Variable precession of the NS in Her X-1 - Staubert, R.; Klochkov, D.; Postnov, Konstantin; Shakura, N.; Wilms, Jörn; Rothschild, R. E. (2010)
We present evidence for an identical behavior of the precession of the accretion disk and that of the neutron star (NS) in Her X-1, based on investigating the well established 35 day modulation in Her X-1 in two different ways: 1) following the turn-ons, thought to be due to the precession of the accretion disk, and 2) following the re-appearance of the shape of the pulse profiles, which we assume to be due to precession of the NS. The turn-on evolution and the evolution of the 'phase-zero' values of the precessing NS (as determined from the pulse profiles) track each other very closely. Since the turn-on evolution is strongly correlated with the pulse period evolution, this means that there is also a strong correlation between the spin and the precession of the NS. There is a very strong physical coupling between the NS and the accretion disk, we suggest through physical feedback in the binary system. The apparent long-term stability of the 35 d clock may be due to the 'interior' of the NS, the coupling of which to the observable surface effects is of general importance for the physics of super-dense, highly magnetized material.
Keywords: Neutron stars; free precession; X-ray binaries; strong magnetic field; Her X-1

Variable pulse profiles of Hercules X-1 repeating with the same irregular 35 d clock as the turn-ons - Staubert, R.; Klochkov, D.; Vasco, D.; Postnov, Konstantin; Shakura, N.; Wilms, Jörn; Rothschild, R. E. (Astronomy & Astrophysics, 2013)
The accreting X-ray pulsar Her X-1 shows two types of long-term variations, both with periods of similar to 35 days: 1) turn-on cycles, a modulation of the flux, with a ten-day long main-on and a five-day long short-on, separated by two off-states, and 2) a systematic variation in the shape of the 1.24 s pulse profile. While there is general consensus that the flux modulation is due to variable shading of the X-ray emitting regions on the surface of the neutron star by the precessing accretion disk, the physical reason for the variation in the pulse profiles has remained controversial. Following the suggestion that free precession of the neutron star may be responsible for the variation in the pulse profiles, we developed a physical model of strong feedback interaction between the neutron star and the accretion disk in order to explain the seemingly identical values for the periods of the two types of variations, which were found to be in basic synchronization. In a deep analysis of pulse profiles observed by several different satellites over the last three decades we now find that the clock behind the pulse profile variations shows exactly the same erratic behavior as the turn-on clock, even on short time scales (a few 35 d cycles), suggesting that there may in fact be only one 35 d clock in the system. If this is true, it raises serious questions with respect to the idea of free precession of the neutron star, namely how the neutron star can change its precessional period every few years by up to 2.5% and how the feedback can be so strong, such that these changes can be transmitted to the accretion disk on rather short time scales.
Keywords: binaries: general; stars: individual: Her-X-1; X-rays: binaries; X-rays: stars; pulsars: general

VLBA polarimetric monitoring of 3C 111 - Beuchert, Tobias; Kadler, M.; Perucho, M.; Grossberger, C.; Schulz, R.; Agudo, I.; Casadio, C.; Gomez, J. L.; Gurwell, Mark; Homan, D.; Kovalev, Y. Y.; Lister, M. L.; et al. (Astronomy & Astrophysics, 2018)
Context. While studies of large samples of jets of active galactic nuclei (AGN) are important in order to establish a global picture, dedicated single-source studies are an invaluable tool for probing crucial processes within jets on parsec scales. These processes involve in particular the formation and geometry of the jet magnetic held as well as the flow itself.Aims. We aim to better understand the dynamics within relativistic magneto-hydrodynamical flows in the extreme environment and close vicinity of supermassive black holes.Methods. We analyze the peculiar radio galaxy 3C 111, for which long-term polarimetric observations are available. We make use of the high spatial resolution of the VLBA network and the MOJAVE monitoring program, which provides high data quality also for single sources and allows us to study jet dynamics on parsec scales in full polarization with an evenly sampled time-domain. While electric vectors can probe the underlying magnetic field, other properties of the jet such as the variable (polarized) flux density, feature size, and brightness temperature, can give valuable insights into the flow itself. We complement the VLBA data with data from the IRAM 30-m Telescope as well as the SMA.Results. We observe a complex evolution of the polarized jet. The electric vector position angles (EVPAs) of features traveling down the jet perform a large rotation of greater than or similar to 180 degrees across a distance of about 20 pc. As opposed to this smooth swing, the EVPAs are strongly variable within the first parsecs of the jet. We find an overall tendency towards transverse EVPAs across the jet with a local anomaly of aligned vectors in between. The polarized flux density increases rapidly at that distance and eventually saturates towards the outermost observable regions. The transverse extent of the flow suddenly decreases simultaneously to a jump in brightness temperature around where we observe the EVPAs to turn into alignment with the jet flow. Also the gradient of the feature size and particle density with distance steepens significantly at that region.Conclusions. We interpret the propagating polarized features as shocks and the observed local anomalies as the interaction of these shocks with a localized recollimation shock of the underlying flow. Together with a sheared magnetic field, this shock-shock interaction can explain the large rotation of the EVPA. The superimposed variability of the EVPAs close to the core is likely related to a clumpy Faraday screen, which also contributes significantly to the observed EVPA rotation in that region.
Keywords: galaxies: active; galaxies: jets; galaxies: individual: 3C 111; galaxies: magnetic fields; radio continuum: galaxies; polarization

Wide field imager instrument for the Advanced Telescope for High Energy Astrophysics - Meidinger, Norbert; Nandra, Kirpal; Plattner, Markus; Porro, Matteo; Rau, Arne; Santangelo, Andrea; Tenzer, Chris; Wilms, Jörn (Journal of Astronomical Telescopes, Instruments, and Systems, 2015)
The Advanced Telescope for High Energy Astrophysics (Athena) has been selected for ESA's L2 mission, scheduled for launch in 2028. It will provide the necessary capabilities to achieve the ambitious goals of the science theme "The Hot and Energetic Universe." Athena's x-ray mirrors will be based on silicon pore optics technology with a 12-m focal length. Two complementary focal plane camera systems are foreseen, which can be moved interchangeably to the focus of the mirror system: the actively shielded micro-calorimeter spectrometer X-IFU and the wide field imager (WFI). The WFI camera will provide an unprecedented survey power through its large field of view of 40 arc min with a high count-rate capability (similar to 1 Crab). It permits a state-of-the-art energy resolution in the energy band of 0.1 to 15 keV during the entire mission lifetime (e.g., full width at half maximum <= 150 eV at 6 keV). This performance is accomplished by a set of depleted P-channel field effect transistor (DEPFET) active pixel sensor matrices with a pixel size well suited to the angular resolution of 5 arc sec (on-axis) of the mirror system. Each DEPFET pixel is a combined detector-amplifier structure with a MOSFET integrated onto a fully depleted 450-mu m-thick silicon bulk. This manuscript will summarize the current instrument concept and design, the status of the technology development, and the envisaged baseline performance. (C) The Authors. Published by SPIE under a Creative Commons Attribution 3.0 Unported License. Distribution or reproduction of this work in whole or in part requires full attribution of the original publication, including its DOI.
Keywords: camera; detector; imaging; silicon; spectroscopy; x-ray

XIPE: The X-ray imaging polarimetry explorer - Soffitta, P.; Bellazzini, R.; Bozzo, E.; Burwitz, V.; Castro-Tirado, A. J.; Costa, E.; Courvoisier, T.; Feng, H.; Gburek, S.; Goosmann, R.; Karas, V.; Matt, G.; et al. (Space Telescopes and Instrumentation 2016: Ultraviolet to Gamma Ray, 2016)
XIPE, the X-ray Imaging Polarimetry Explorer, is a mission dedicated to X-ray Astronomy. At the time of writing XIPE is in a competitive phase A as fourth medium size mission of ESA (M4). It promises to reopen the polarimetry window in high energy Astrophysics after more than 4 decades thanks to a detector that efficiently exploits the photoelectric effect and to X-ray optics with large effective area. XIPE uniqueness is time-spectrally-spatially-resolved X-ray polarimetry as a breakthrough in high energy astrophysics and fundamental physics. Indeed the payload consists of three Gas Pixel Detectors at the focus of three X-ray optics with a total effective area larger than one XMM mirror but with a low weight. The payload is compatible with the fairing of the Vega launcher. XIPE is designed as an observatory for X-ray astronomers with 75 % of the time dedicated to a Guest Observer competitive program and it is organized as a consortium across Europe with main contributions from Italy, Germany, Spain, United Kingdom, Poland, Sweden.
Keywords: Gas Pixel Detector; Polarimetry; X-ray Astronomy; X-ray optics

XMM-Newton observations of the brightest ultraluminous X-ray sources - Stobbarts, A.-M.; Roberts, Timothy; Wilms, Jörn (Monthly Notices of the Royal Astronomical Society, 2006)
We present an analysis of 13 of the best quality ultraluminous X-ray source (ULX) data sets available from XMM-Newton European Photon Imaging Camera (EPIC) observations. We utilize the high signal-to-noise in these ULX spectra to investigate the best descriptions of their spectral shape in the 0.3-10 keV range. Simple models of an absorbed power law or multicolour disc blackbody prove inadequate at describing the spectra. Better fits are found using a combination of these two components, with both variants of this model - a cool (similar to 0.2 keV) disc blackbody plus hard power-law continuum, and a soft power-law continuum, dominant at low energies, plus a warm (similar to 1.7 keV) disc blackbody - providing good fits to 8/13 ULX spectra. However, by examining the data above 2 keV, we find evidence for curvature in the majority of data sets (8/13 with at least marginal detections), inconsistent with the dominance of a power law in this regime. In fact, the most successful empirical description of the spectra proved to be a combination of a cool (similar to 0.2 keV) classic blackbody spectrum, plus a warm disc blackbody that fits acceptably to 10/13 ULXs. The best overall fits are provided by a physically self-consistent accretion disc plus Comptonized corona model (DISKPN + EQPAIR), which fits acceptably to 11/13 ULXs. This model provides a physical explanation for the spectral curvature, namely that it originates in an optically thick corona, though the accretion disc photons seeding this corona still originate in an apparently cool disc. We note similarities between this fit and models of Galactic black hole binaries at high accretion rates, most notably the model of Done & Kubota. In this scenario the inner disc and corona become energetically coupled at high accretion rates, resulting in a cooled accretion disc and optically thick corona. We conclude that this analysis of the best spectral data for ULXs shows it to be plausible that the majority of the population are high accretion rate stellar-mass (perhaps up to 80 M-circle dot) black holes, though we cannot categorically rule out the presence of larger, similar to 1000-M-circle dot intermediate-mass black holes (IMBHs) in individual sources with the current X-ray data.
Keywords: accretion; accretion discs; black hole physics; X-rays : binaries; X-rays : galaxies

X-RAY AND NEAR-INFRARED OBSERVATIONS OF THE OBSCURED ACCRETING PULSAR IGR J18179-1621 - Nowak, M. A.; Paizis, Adamantia; Rodriguez, Jerome; Chaty, Sylvain; Del Santo, Melania; Grinberg, Victoria; Wilms, Jörn; Ubertini, P.; Chini, R. (Astrophysical Journal, 2012)
IGR J18179-1621 is an obscured accreting X-ray pulsar discovered by INTEGRAL on 2012 February 29. We report on our 20 ks Chandra-High Energy Transmission Gratings Spectrometer observation of the source performed on 2012 March 17, on two short contemporaneous Swift observations, and on our two near-infrared (K-s, H-n, and J(n)) observations performed on 2012 March 13 and 26. We determine the most accurate X-ray position of IGR J18179-1621, alpha(J2000) = 18(h)17(m)52.(s)18, delta(J2000) = -16 degrees 21'31.'' 68 (90% uncertainty of 0.'' 6). A strong periodic variability at 11.82 s is clearly detected in the Chandra data, confirming the pulsating nature of the source, with the light-curve softening at the pulse peak. The quasi-simultaneous Chandra-Swift spectra of IGR J18179-1621 can be well fit by a heavily absorbed hard power law (N-H = 2.2 +/- 0.3 x 10(23) cm(-2) and photon index Gamma = 0.4 +/- 0.1) with an average absorbed 2-8 keV flux of 1.4x10(-11) erg cm(-2) s(-1). At the Chandra-based position, a source is detected in our near-infrared (NIR) maps with K-s = 13.14 +/- 0.04 mag, H-n = 16 +/- 0.1 mag, and no J(n)-band counterpart down to similar to 18 mag. The NIR source, compatible with 2MASS J18175218-1621316, shows no variability between 2012 March 13 and 26. Searches of the UKIDSS database show similar NIR flux levels at epochs six months prior to and after a 2007 February 11 archival Chandra observation where the source's X-ray flux was at least 87 times fainter. In many ways IGR J18179-1621 is unusual: its combination of a several week long outburst (without evidence of repeated outbursts in the historical record), high absorption column (a large fraction of which is likely local to the system), and 11.82 s period does not fit neatly into existing X-ray binary categories.
Keywords: accretion; accretion disks; binaries: close; stars: individual; X-rays: binaries

X-ray emission from magnetized neutron star atmospheres at low mass-accretion rates: I. Phase-averaged spectrum - Sokolova-Lapa, Ekaterina; Gornostaev, M.; Wilms, Jörn; Ballhausen, Ralf; Falkner, Sebastian; Postnov, K.; Thalhammer, Philipp; Fürst, F.; Garcia, Javier; Shakura, N.; Becker, P. A.; Wolff, M. T.; et al. (Astronomy & Astrophysics, 2021)
Recent observations of X-ray pulsars at low luminosities allow, for the first time, the comparison of theoretical models of the emission from highly magnetized neutron star atmospheres at low mass-accretion rates (M ≤ 1015 g s-1) with the broadband X-ray data. The purpose of this paper is to investigate spectral formation in the neutron star atmosphere at low á¹€ and to conduct a parameter study of the physical properties of the emitting region. We obtain the structure of the static atmosphere, assuming that Coulomb collisions are the dominant deceleration process. The upper part of the atmosphere is strongly heated by the braking plasma, reaching temperatures of 30-40 keV, while its denser isothermal interior is much cooler (∼2 keV). We numerically solve the polarized radiative transfer in the atmosphere with magnetic Compton scattering, free-free processes, and nonthermal cyclotron emission due to possible collisional excitations of electrons. The strongly polarized emitted spectrum has a double-hump shape that is observed in low-luminosity X-ray pulsars. A low-energy "thermal"component is dominated by extraordinary photons that can leave the atmosphere from deeper layers because of their long mean free path at soft energies. We find that a high-energy component is formed because of resonant Comptonization in the heated nonisothermal part of the atmosphere even in the absence of collisional excitations. However, these latter, if present, affect the ratio of the two components. A strong cyclotron line originates from the optically thin, uppermost zone. A fit of the model to NuSTAR and Swift/XRT observations of GX 304-1 provides an accurate description of the data with reasonable parameters. The model can thus reproduce the characteristic double-hump spectrum observed in low-luminosity X-ray pulsars and provides insights into spectral formation.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Magnetic fields; Methods: numerical; Polarization; Radiative transfer; Stars: neutron; X-rays: binaries

X-ray monitoring of the radio and gamma-ray loud Narrow-Line Seyfert 1 Galaxy PKS 2004-447 - Kreikenbohm, A.; Kadler, M.; Wilms, Jörn; Schulz, R.; Mueller, C.; Ojha, R.; Ros, E.; Mannheim, K.; Elsaesser, D. (2013)
We present preliminary results of the X-ray analysis of XMM-Newton and Swift observations as part of a multi-wavelength monitoring campaign in 2012 of the radio-loud narrow line Seyfert 1 galaxy PKS 2004-447. The source was recently detected in gamma-rays by Fermi/LAT among only four other galaxies of that type. The 0.5 - 10 keV X-ray spectrum is well-described by a simple absorbed powerlaw (Gamma similar to 1.6). The source brightness exhibits variability on timescales of months to years with indications for spectral variability, which follows a "bluer-when-brighter" behaviour, similar to blazars.

X-RAY REFLECTED SPECTRA FROM ACCRETION DISK MODELS. III. A COMPLETE GRID OF IONIZED REFLECTION CALCULATIONS - Garcia, Javier; Dauser, Thomas; Reynolds, C. S.; Kallman, T. R.; Mcclintock, J. E.; Wilms, Jörn; Eikmann, Wiebke (Astrophysical Journal, 2013)
We present a new and complete library of synthetic spectra for modeling the component of emission that is reflected from an illuminated accretion disk. The spectra were computed using an updated version of our code XILLVER that incorporates new routines and a richer atomic database. We offer in the form of a table model an extensive grid of reflection models that cover a wide range of parameters. Each individual model is characterized by the photon index G of the illuminating radiation, the ionization parameter xi at the surface of the disk (i.e., the ratio of the X-ray flux to the gas density), and the iron abundance A(Fe) relative to the solar value. The ranges of the parameters covered are 1.2 <= Gamma <= 3.4, 1 <= xi <= 10(4), and 0.5 <= A(Fe) <= 10. These ranges capture the physical conditions typically inferred from observations of active galactic nuclei, and also stellar-mass black holes in the hard state. This library is intended for use when the thermal disk flux is faint compared to the incident power-law flux. The models are expected to provide an accurate description of the Fe K emission line, which is the crucial spectral feature used to measure black hole spin. A total of 720 reflection spectra are provided in a single FITS file (http://hea-www.cfa.harvard.edu/similar to javier/xillver/) suitable for the analysis of X-ray observations via the atable model in XSPEC. Detailed comparisons with previous reflection models illustrate the improvements incorporated in this version of XILLVER.
Keywords: accretion; accretion disks; atomic processes; black hole physics; line: formation; radiative transfer; X-rays: general

X-ray spectral and flux variability of the microquasar GRS 1758-258 on timescales from weeks to years - Hirsch, Maria; Pottschmidt, Katja; Smith, David M.; Bodaghee, Arash; Cadolle Bel, Marion; Grinberg, Victoria; Hell, Natalie; Krauß, Felicia; Kreykenbohm, Ingo; Lohfink, Anne; Nowak, Michael A.; Rodrigues, Bárbara H.; et al. (Astronomy & Astrophysics, 2020)
We present the spectral and timing evolution of the persistent black hole X-ray binary GRS 1758-258 based on almost 12 years of observations using the Rossi X-ray Timing Explorer Proportional Counter Array. While the source was predominantly found in the hard state during this time, it entered the thermally dominated soft state seven times. In the soft state GRS 1758-258 shows a strong decline in flux above 3 keV rather than the pivoting flux around 10 keV more commonly shown by black hole transients. In its 3-20 keV hardness intensity diagram, GRS 1758-258 shows a hysteresis of hard and soft state fluxes typical for transient sources in outburst. The RXTE-PCA and RXTE-ASM long-term light curves do not show any orbital modulations in the range of 2-30 d. However, in the dynamic power spectra significant peaks drift between 18.47 and 18.04 d for the PCA data, while less significant signatures between 19 d and 20 d are seen for the ASM data as well as for the Swift/BAT data. We discuss different models for the hysteresis behavior during state transitions as well as possibilities for the origin of the long term variation in the context of a warped accretion disk.
CRIS-Team Scopus Importer:2020-05-02
Keywords: X-rays: binaries; X-rays: individuals: GRS 1758-258

X-ray spectroscopy of MXB 1728-34 with XMM-Newton - Egron, Elise; Di Salvo, Tiziana; Burderi, L.; Papitto, Alessandro; Barragan, L.; Dauser, Thomas; Wilms, Jörn; D'Ai, Antonino; Riggio, Alessandro; Iaria, Rosario; Robba, N. R. (Astronomy & Astrophysics, 2011)
We analyzed an XMM-Newton observation of the low-mass X-ray binary and atoll source MXB 1728-34. The source was in a low-luminosity state during the XMM-Newton observation, corresponding to a bolometric X-ray luminosity of 5 x 10(36) d(5.1kpc)(2) erg s(-1). The 1-11 keV X-ray spectrum of the source, obtained combining data from all the five instruments on-board XMM-Newton, is well fitted by a Comptonized continuum. Evident residuals are present at 6-7 keV, which are ascribed to the presence of a broad iron emission line. This feature can be equally well fitted by a relativistically smeared line or by a self-consistent, relativistically smeared reflection model. Under the hypothesis that the iron line is produced by reflection from the inner accretion disk, we can infer important information on the physical parameters of the system, such as the inner disk radius, R-in = 25-100 km, and the inclination of the system, 44 degrees < i < 60 degrees.
Keywords: line: formation; line: identification; stars: neutron; stars: individual: MXB 1728-34; X-rays: binaries; X-rays: general

X-ray variation statistics and wind clumping in Vela X-1 - Fürst, Felix; Kreykenbohm, Ingo; Pottschmidt, K.; Wilms, Jörn; Hanke, Manfred; Rothschild, R. E.; Kretschmar, Peter; Schulz, N. S.; Huenemoerder, D. P.; Klochkov, D.; Staubert, R. (Astronomy & Astrophysics, 2010)
We investigate the structure of the wind in the neutron star X-ray binary system Vela X-1 by analyzing its flaring behavior. Vela X-1 shows constant flaring, with some flares reaching fluxes of more than 3.0 Crab between 20-60 keV for several 100 s, while the average flux is around 250 mCrab. We analyzed all archival INTEGRAL data, calculating the brightness distribution in the 20-60 keV band, which, as we show, closely follows a log-normal distribution. Orbital resolved analysis shows that the structure is strongly variable, explainable by shocks and a fluctuating accretion wake. Analysis of RXTE ASM data suggests a strong orbital change of N(H). Accreted clump masses derived from the INTEGRAL data are on the order of 5x10(19) - 10(21) g. We show that the lightcurve can be described with a model of multiplicative random numbers. In the course of the simulation we calculate the power spectral density of the system in the 20-100 keV energy band and show that it follows a red-noise power law. We suggest that a mixture of a clumpy wind, shocks, and turbulence can explain the measured mass distribution. As the recently discovered class of supergiant fast X-ray transients (SFXT) seems to show the same parameters for the wind, the link between persistent HMXB like Vela X-1 and SFXT is further strengthened.
Keywords: accretion; accretion disks; X-rays: binaries; X-rays: individuals: Vela X-1; methods: statistical

γ-ray emission in radio galaxies under the VLBI scope: II. The relationship between γ-ray emission and parsec-scale jets in radio galaxies - Angioni, R.; Ros, E.; Kadler, M.; Ojha, R.; Mueller, C.; Edwards, P. G.; Burd, P. R.; Carpenter, B.; Dutka, M. S.; Gulyaev, S.; Hase, H.; Horiuchi, S.; et al. (Astronomy & Astrophysics, 2020)
Aims. This is the second paper in our series studying the evolution of parsec-scale radio emission in radio galaxies in the Southern Hemisphere. Following our study of the radio and high-energy properties of γ-ray-emitting sources, here we investigate the kinematic and spectral properties of the parsec-scale jets of radio galaxies that have not yet been detected by the Fermi Large Area Telescope (Fermi-LAT) instrument on board NASA's Fermi Gamma-ray Space Telescope. For many sources, these results represent the first milliarcsecond resolution information in the literature. These studies were conducted within the framework of the Tracking Active Nuclei with Austral Milliarcsecond Interferometry (TANAMI) monitoring program and in the context of high-energy γ-ray observations from Fermi-LAT. Methods. We took advantage of the regular 8.4 GHz and 22.3 GHz Very Long Baseline Interferometry (VLBI) observations provided by the TANAMI monitoring program, and explored the kinematic properties of six γ-ray-faint radio galaxies. We complemented this with ∼8.5 years of Fermi-LAT data, deriving updated upper limits on the γ-ray emission from this subsample of TANAMI radio galaxies. We included publicly available VLBI kinematics of γ-ray-quiet radio galaxies monitored by the MOJAVE program and performed a consistent Fermi-LAT analysis. We combined these results with those from our previous paper to construct the largest sample of radio galaxies with combined VLBI and γ-ray measurements to date. The connection between parsec-scale jet emission and high-energy properties in the misaligned jets of radio galaxies was explored. Results. For the first time, we report evidence of superluminal motion up to βappâ€., =â€., 3.6 in the jet of the γ-ray-faint radio galaxy PKS 2153-69. We find a clear trend of higher apparent speed as a function of distance from the jet core, which indicates that the jet is still being accelerated on scales of tens of parsecs, or ∼105â€† Rs, corresponding to the end of the collimation and acceleration zone in nearby radio galaxies. We find evidence of subluminal apparent motion in the jets of PKS 1258-321 and IC 4296, and no measurable apparent motion for PKS 1549-79, PKS 1733-565, and PKS 2027-308. For all these sources, TANAMI provides the first multi-epoch kinematic analysis on parsec scales. We then compare the VLBI properties of γ-ray-detected and undetected radio galaxies, and find that the two populations show a significantly different distribution of median core flux density, and, possibly, of median core brightness temperature. In terms of correlation between VLBI and γ-ray properties, we find a significant correlation between median core flux density and γ-ray flux, but no correlation with typical Doppler boosting indicators such as median core brightness temperature and core dominance. Conclusions. Our study suggests that high-energy emission from radio galaxies is related to parsec-scale radio emission from the inner jet, but is not driven by Doppler boosting effects, in contrast to the situation in their blazar counterparts. This implies that γ-ray loudness does not necessarily reflect a higher prevalence of boosting effects.
CRIS-Team Scopus Importer:2020-10-23
Keywords: Galaxies: active; Galaxies: jets; Galaxies: nuclei; Gamma rays: galaxies